Investigating the broad domains of intrinsic capacity, functional ability and environment: An exploratory graph analysis approach for improving analytical methodologies for measuring healthy aging - Golino, Hudson; Thiyagarajan, Jotheeswaran Amuthavalli; Sadana, Ritu; Teles, Mariana; Christensen, Alexander; Boker, Steven (PsyArXiv Preprint)
The current paper compared the empirical structure of 280 variables from the 2016 wave of the Health and Retirement Study (N = 16,327) estimated using exploratory graph analysis with a theoretical structure based on 20 broad domains of intrinsic capacity, functional ability and environment, identified in the International Classification of Functioning, Disability and Health compendium. The results showed that a structure with 21 first-order factors had the best fit to the data (i.e., lowest total entropy fit value) for both the training and validation sample. A second-order exploratory graph analysis was applied on the interfactor correlation matrix and identified five second-order factors. The five-factor structure presented a better fit than the theoretical three-factor structure (approximately) representing intrinsic capacity, functional ability and environment. A close inspection of the network structure generated by analyzing the rotated network loadings of the 21 first-order factors revealed an interplay between cognition, mobility, need for help with daily activities, walking capacity, physical capacity, liver functioning, positive affect and perceived mastery, low perceived control, and depression/negative mood. Combined, our results can help guide future research by providing a framework for estimating the structure of multi-domain aging research as well as generating questions that can be addressed in future research.
Keywords: health aging; Methodology

Methodology for Analysis of the U.S. Health and Retirement Study - The New York Times; KFF Health News (Dying Broke, 2023)
Keywords: cognitive function; Langa-Weir classification; Methodology

Representativeness of the oversamples of Blacks and Hispanics in the Health and Retirement Study: A geographic analysis of 2020 - Schroeder, Heather; David R Weir; Brady T. West (Survey Research Center, Institute for Social Research, University of Michigan, 2023)
Keywords: Methodology; minorities; oversampling; survey design

Health and Retirement Study Imputation of Cognitive Functioning Measures: 1992-2018 - Ryan J McCammon; Gwenith G Fisher; Hassan, Halimah; Jessica Faul; Rogers, Willard; David R Weir (Survey Research Center, University of Michigan, 2022)
Keywords: Health Conditions and Status; Methodology

Introduction to the Special Issue on New Longitudinal Data for Retirement Analysis and Policy - Marco Angrisani; Samek, Anya; Arie Kapteyn (Journal of Pension Economics and Finance, 2021)
The number of data sources available for academic research on retirement economics and policy has increased rapidly in the past two decades. Data quality and comparability across studies have also improved considerably, with survey questionnaires progressively converging towards common ways of eliciting the same measurable concepts. Probability-based Internet panels have become a more accepted and recognized tool to obtain research data, allowing for fast, flexible, and cost-effective data collection compared to more traditional modes such as in-person and phone interviews. In an era of big data, academic research has also increasingly been able to access administrative records (e.g., Kostøl and Mogstad, 2014; Cesarini et al., 2016), private-sector financial records (e.g., Gelman et al., 2014), and administrative data married with surveys (Ameriks et al., 2020), to answer questions that could not be successfully tackled otherwise.
Keywords: Longitudinal data; Methodology

A Novel Metric for Developing Easy-to-Use and Accurate Clinical Prediction Models: The Time-cost Information Criterion. - Lee, Sei J; Alexander K Smith; Ramirez-Diaz, Ledif G; Kenneth E Covinsky; Gan, Siqi; Chen, Catherine L; W John Boscardin (Medical Care, 2021)
BACKGROUND: Guidelines recommend that clinicians use clinical prediction models to estimate future risk to guide decisions. For example, predicted fracture risk is a major factor in the decision to initiate bisphosphonate medications. However, current methods for developing prediction models often lead to models that are accurate but difficult to use in clinical settings. OBJECTIVE: The objective of this study was to develop and test whether a new metric that explicitly balances model accuracy with clinical usability leads to accurate, easier-to-use prediction models. METHODS: We propose a new metric called the Time-cost Information Criterion (TCIC) that will penalize potential predictor variables that take a long time to obtain in clinical settings. To demonstrate how the TCIC can be used to develop models that are easier-to-use in clinical settings, we use data from the 2000 wave of the Health and Retirement Study (n=6311) to develop and compare time to mortality prediction models using a traditional metric (Bayesian Information Criterion or BIC) and the TCIC. RESULTS: We found that the TCIC models utilized predictors that could be obtained more quickly than BIC models while achieving similar discrimination. For example, the TCIC identified a 7-predictor model with a total time-cost of 44 seconds, while the BIC identified a 7-predictor model with a time-cost of 119 seconds. The Harrell C-statistic of the TCIC and BIC 7-predictor models did not differ (0.7065 vs. 0.7088, P=0.11). CONCLUSION: Accounting for the time-costs of potential predictor variables through the use of the TCIC led to the development of an easier-to-use mortality prediction model with similar discrimination.
Keywords: Bayesian Information Criterion; Methodology

Proof of concept example for use of simulation to allow data pooling despite privacy restrictions. - Teresa Filshtein; Li, Xiang; Zimmerman, Scott C; Ackley, Sarah F; M. Maria Glymour; Melinda C Power (Epidemiology, 2021)
BACKGROUND: Integrating results from multiple samples is often desirable, but privacy restrictions may preclude full data pooling, and most datasets do not include fully harmonized variable sets. We propose a simulation-based method leveraging partial information across datasets to guide creation of synthetic data, based on explicit assumptions about the underlying causal structure, that permits pooled analyses that adjust for all desired confounders in the context of privacy restrictions. METHODS: This proof-of-concept project uses data from the Health and Retirement Study (HRS) and Atherosclerosis Risk in Communities (ARIC) study. We specified an estimand of interest and a directed acyclic graph (DAG) summarizing the presumed causal structure for the effect of glycated hemoglobin (HbA1c) on cognitive change. We derived publicly reportable statistics to describe the joint distribution of each variable in our DAG. These summary estimates were used as data-generating rules to create synthetic datasets. After pooling, we imputed missing covariates in the synthetic datasets and used the synthetic data to estimate the pooled effect of HbA1c on cognitive change, adjusting for all desired covariates. RESULTS: Distributions of covariates, as well as model coefficients and associated standard errors for our model estimating the effect of HbA1c on cognitive change were similar across cohort-specific original and pre-imputation synthetic data. The estimate from the pooled synthetic incorporates control for confounders measured in either original dataset. DISCUSSION: Our approach has advantages over meta-analysis or individual-level pooling/data harmonization when privacy concerns preclude data sharing and key confounders are not uniformly measured across datasets.
Keywords: data pooling; Methodology; privacy restrictions

Tools for Selecting Working Correlation Structures When Using Weighted GEE to Model Longitudinal Survey Data - Westgate, Philip M; Brady T. West (Journal of Survey Statistics and Methodology, 2021)
Weighted generalized estimating equations (GEEs) are popular for the marginal analysis of longitudinal survey data. This popularity is due to the ability of these estimating equations to provide consistent regression parameter estimates and corresponding standard error estimates as long as the population mean and survey weights are correctly specified. Although the data analyst must incorporate a working correlation structure within the weighted GEEs, this structure need not be correctly specified. However, accurate modeling of this structure has the potential to improve regression parameter estimation (i.e., reduce standard errors) and therefore, the selection of a working correlation structure for use within GEEs has received considerable attention in standard longitudinal data analysis settings. In this article, we describe how correlation selection criteria can be extended for use with weighted GEE in the context of analyzing longitudinal survey data. Importantly, we provide and demonstrate an R function that we have created for such analyses. Furthermore, we discuss correlation selection in the context of using existing software that does not have this explicit capability. The methods are demonstrated via the use of data from a real survey in which we are interested in the mean number of falls that elderly individuals in a specific subpopulation experience over time.
Keywords: GEEs; Methodology

VC-BART: Bayesian trees for varying coefficients - Deshpande, Sameer K.; Bai, Ray; Balocchi, Cecilia; Starling, Jennifer E.; Weiss, Jordan (Cornell University, 2020)
Many studies have reported associations between later-life cognition and socioeconomic position in childhood, young adulthood, and mid-life. However, the vast majority of these studies are unable to quantify how these associations vary over time and with respect to several demographic factors. Varying coefficient (VC) models, which treat the covariate effects in a linear model as nonparametric functions of additional effect modifiers, offer an appealing way to overcome these limitations. Unfortunately, state-of-the-art VC modeling methods require computationally prohibitive parameter tuning or make restrictive assumptions about the functional form of the covariate effects. In response, we propose VCBART, which estimates the covariate effects in a VC model using Bayesian Additive Regression Trees. With simple default hyperparameter settings, VCBART outperforms existing methods in terms of covariate effect estimation and prediction. Using VCBART, we predict the cognitive trajectories of 4,167 subjects from the Health and Retirement Study using multiple measures of socioeconomic position and physical health. We find that socioeconomic position in childhood and young adulthood have small effects that do not vary with age. In contrast, the effects of measures of mid-life physical health tend to vary with respect to age, race, and marital status.
Keywords: Cognition; Methodology; socioeconomics

Novel Methods and Data Sources for Surveillance of State-Level Diabetes and Prediabetes Prevalence - Mardon, Russ; David A Marker; Nooney, Jennifer; Campione, Joanne; Jenkins, Frank; Johnson, Maurice; Merrill, Lori; Deborah B. Rolka; Saydah, Sharon; Geiss, Linda S.; Zhang, Xuanping; Shrestha, Sundar (Preventing Chronic Disease, 2017)
States bear substantial responsibility for addressing the rising rates of diabetes and prediabetes in the United States. However, accurate state-level estimates of diabetes and prediabetes prevalence that include undiagnosed cases have been impossible to produce with traditional sources of state-level data. Various new and nontraditional sources for estimating state-level prevalence are now available. These include surveys with expanded samples that can support state-level estimation in some states and administrative and clinical data from insurance claims and electronic health records. These sources pose methodologic challenges because they typically cover partial, sometimes nonrandom subpopulations; they do not always use the same measurements for all individuals; and they use different and limited sets of variables for case finding and adjustment. We present an approach for adjusting new and nontraditional data sources for diabetes surveillance that addresses these limitations, and we present the results of our proposed approach for 2 states (Alabama and California) as a proof of concept. The method reweights surveys and other data sources with population undercoverage to make them more representative of state populations, and it adjusts for nonrandom use of laboratory testing in clinically generated data sets. These enhanced diabetes and prediabetes prevalence estimates can be used to better understand the total burden of diabetes and prediabetes at the state level and to guide policies and programs designed to prevent and control these chronic diseases.
Keywords: Diabetes; Methodology; prediabetes

Epidemiology of Mixed, Stress, and Urgency Urinary Incontinence in Middle-Aged/Older Women: the Importance of Incontinence History - Yuko M Komesu; Ronald M Schrader; Loren H Ketai; Rebecca G Rogers; Gena C. Dunivan (International Urogynecology Journal, 2016)
Introduction and hypothesis Urinary incontinence (UI) is common and the relationship among its subtypes complex. Our objective was to describe the natural history and predictors of the incontinence subtypes stress, urgency, and mixed, in middle-aged and older US women. We tested our hypothesis that UI subtype history predicted future occurrence, evaluating subtype incidence/remission over multiple time points in a stable cohort of women. Methods We analyzed longitudinal urinary incontinence data in 10,572 community-dwelling women aged 50 in the 2004 2010 Health and Retirement Study. Mixed, stress, and urgency incontinence prevalence (2004, 2006, 2008, 2010) and 2-year cumulative incidence and remissions (2004 2006, 2006 2008, 2008 2010) were estimated. Patient characteristics and incontinence subtype status 2004 2008 were entered into a multivariable, transition model to determine predictors for incontinence subtype occurrence in 2010. Results The prevalence of each subtype in this population (median age 63 66) was 2.6 8.9 . Subtype incidence equaled 2.1 3.5 and remissions for each varied between 22.3 and 48.7 . Incontinence subtype incidence predictors included ethnicity/race, age, body mass index, and functional limitations. Compared with white women, black women had decreased odds of incident stress incontinence and Hispanic women had increased odds of stress incontinence remission. The age range 80 90 and severe obesity predicted incident mixed incontinence. Functional limitations predicted mixed and urgency incontinence. The strongest predictor of incontinence subtype was subtype history. The presence of the respective incontinence subtypes in 2004 and 2006 strongly predicted 2010 recurrence (odds ratio OR stress incontinence = 30.7, urgency OR = 47.4, mixed OR = 42.1). Conclusions Although the number of remissions was high, a previous history of incontinence subtypes predicted recurrence. Incontinence status is dynamic, but tends to recur over the longer term.
Keywords: Health Conditions and Status; Methodology

Financial Assistance Patterns from Midlife Parents to Adult Children: A Test of the Cumulative Advantage Hypothesis - Padgett, C. S.; R Corey Remle (Journal of Family and Economic Issues, 2016)
Young adults may receive financial assistance from midlife parents as they experience life course transitions often associated with establishing independent status, such as schooling, marriage or gaining full-time work. We used longitudinal data from the Health and Retirement Study (1992 2002) and hypothesized that adult children in the United States who received repeated financial transfers from midlife parents experienced cumulative advantages across time. We also examined the data using parental household characteristics to reinforce the importance of previous transfer behaviors. We found that the receipt of prior transfers, family structure and parental household income were the strongest determinants of the odds that parents gave financial assistance to adult children as both generations aged. The findings also supported the cumulative advantage theory due to the larger likelihood of continued transfers. 2015 Springer Science Business Media New York
Keywords: Adult children; Demographics; Methodology

Gender Differences in Trajectories of Physical Activity Among Older Americans With Diabetes - Sara J McLaughlin; Cathleen M. Connell; Mary R Janevic (Journal of Aging and Health, 2016)
Objective: The primary objective of this study was to examine gender differences in engagement in physical activity over time among older U.S. adults with diabetes. Method: Using data from the Health and Retirement Study, we investigated physical activity between 2004 and 2010 among 1,857 adults aged 65 years and above with diabetes. Results: Less than half of adults were physically active at baseline. The probability of physical activity declined over the 6-year period, with no significant gender variation in the effect of time. Because the odds of physical activity were lower for women at baseline and the effect of time did not vary by gender, the trajectory of physical activity was less favorable for women than men. Discussion: The women in this cohort of older Americans started and remained less active than their male counterparts. Investigations covering a larger portion of the life course and those examining the impact of life events and transitions on physical activity among adults with diabetes are needed.
Keywords: Demographics; Health Conditions and Status; Methodology

On the genetic bias of the quarter of birth instrument - Cornelius A Rietveld; Webbink, Dinand (Economics and Human Biology, 2016)
Many studies in economics use quarter of birth as an instrument for identifying the causal effect of schooling on outcomes such as earnings and health. The key assumption in these studies is that people born in different quarters of the year do not differ systematically in their unobserved abilities. This study uses genetic data from the US Health and Retirement Study to analyze the validity of the quarter of birth instrument. We find some evidence that genetic factors influencing education are not randomly distributed over the year. However, these factors only slightly change the effect of quarter of birth on schooling.
Keywords: Genetics; Methodology

Helping Respondents Provide Good Answers in Web Surveys - Mick P. Couper; Zhang, Chan (Survey Research Methods, 2016)
This paper reports on a series of experiments to explore ways to use the technology of Web surveys to help respondents provide well-formed answers to questions that may be difficult to answer. Specifically, we focus on the use of drop-down or select lists and JavaScript lookup tables as alternatives to open text fields for the collection of information on prescription drugs. The first two experiments were conducted among members of opt-in panels in the U.S. The third experiment was conducted in the 2013 Health and Retirement Study Internet Survey. Respondents in each of the studies were randomly assigned to one of three input methods: text field, drop box, or JavaScript lookup, and asked to provide the names of prescription drugs they were taking. We compare both the quality of answers obtained using the three methods, and the effort (time) taken to provide such answers. We examine differences in performance on the three input format types by key respondent demographics and Internet experience. We discuss some of the technical challenges of implementing complex question types and offer some recommendations for the use of such tools in Web surveys.
Keywords: Methodology

How Might Differences in Immigration Experiences for Men and Women Lead to Gender Disparities in Functional Limitations for Older Mexican Immigrants in the U.S.? - Stepler, Renee A. (The George Washington University, 2016)
A number of studies have shown that across all races and ethnicities women tend to have higher levels of functional limitations than men despite lower rates of mortality (Warner and Brown 2011; Solé-Auró et al. 2014). While several studies do incorporate Mexican-Americans and include nativity as a control, it is possible that Mexican-born immigrants' experiences differ from their U.S.-born counterparts in ways that may affect health later in life. Using longitudinal data from the Health and Retirement Study, this study investigates the factors that may account for differences in the strength and mobility limitations between older men and women who are Mexican immigrants living in the United States. These data indicate that socioeconomic status, chronic disease, and depressive symptoms serve as predictors for functional limitations later in life for Mexican-born men and women, and that each of these predictors serves as an explanation for differences in the functional status of these men and women. These findings extend research of gender disparities in morbidity by examining this subpopulation and highlight the importance of focusing on preventing comorbidities and depression, especially for women.
Keywords: Demographics; Health Conditions and Status; Healthcare; Methodology

Improved Wealth Measures in the Health and Retirement Study: Asset Reconciliation and Cross-Wave Imputation - Michael D Hurd; Erik Meijer; Moldoff, Michael; Susann Rohwedder (2016)
In this report, we present improved wealth measures for the Health and Retirement Study (HRS), which aim to reduce the effect of observation error on wealth levels and changes in wealth. The new wealth measures take account of the asset verification section in the HRS and use cross-wave information, most notably the value of the same asset in adjacent waves, in the imputation models, so imputed values better preserve serial correlation in the asset values. We document how we dealt with several methodological challenges in the implementation of these improvements. The corrections from the asset verification data reduce the standard deviations of wave-to-wave changes by substantial amounts (up to 57 percent for total wealth). The most important effect of the cross-wave imputations is a considerable reduction of the number of spikes and trenches (large changes in value followed by large changes back).
Keywords: Demographics; Methodology

Income dynamics and health: A test of competing hypotheses - Hui-Peng Liew (Health Policy and Technology, 2016)
Objective: This study aims to examine the temporal processes underlying the relationship between income and health among the elderly to demonstrate the extent to which income histories have an influence on health changes. Methods: The empirical work of this study will be based on the 1992 2010 Health and Retirement Study (HRS). This study will test the low income hypothesis, the permanent income hypothesis, and the transitory income hypothesis using the method of growth curve modeling. Results: Results from growth curve analyses suggest that distinguishing these three income hypotheses is useful on theoretical, empirical, and policy grounds. It shows that the impact of low income, anticipated fluctuations in household income over the long run, as well as unanticipated income change over the short term on the changes in health over time are shaped along both socioeconomic and racial/ethnic lines. Conclusion: Given the present U.S. circumstances, perhaps something like a national healthcare system like the Obamacare and tax incentives and other benefit systems can be implemented to reduce the existing health disparities.
Keywords: Demographics; Healthcare; Methodology; Public Policy

A Life-Cycle Model with Ambiguous Survival Beliefs - Groneck, Max; Ludwig, Alexander; Zimper, Alexander (Journal of Economic Theory, 2016)
Based on a cognitive notion of neo-additive capacities reflecting likelihood insensitivity with respect to survival chances, we construct a Choquet Bayesian learning model over the life-cycle that generates a motivational notion of neo-additive survival beliefs expressing ambiguity attitudes. We embed these neo-additive survival beliefs as decision weights in a Choquet expected utility life-cycle consumption model and calibrate it with data on subjective survival beliefs from the Health and Retirement Study. Our quantitative analysis shows that agents with calibrated neo-additive survival beliefs (i) save less than originally planned, (ii) exhibit undersaving at younger ages, and (iii) hold larger amounts of assets in old age than their rational expectations counterparts who correctly assess their survival chances. Our neo-additive life-cycle model can therefore simultaneously accommodate three important empirical findings on household saving behavior.
Keywords: Methodology; Other

Marital Quality and Health in Middle and Later Adulthood: Dyadic Associations - Choi, Heejeong; Yorgason, Jeremy B.; Johnson, David R. (The Journals of Gerontology Series B: Psychological Sciences and Social Sciences, 2016)
Objectives. We investigated associations between positive marital quality and health among married persons aged 50 or older and their spouses. Prior research using data from married individuals has yielded inconsistent findings regarding the association between positive marital quality and global health outcomes. The present study involved married couples to examine how spouses positive marital quality affect their own and each other s health, and whether these effects vary by age.Methods. Using data from 3 waves of the Health and Retirement Study (2006, 2008, 2010), we estimated a series of actor partner interdependence models using mixed linear models.Results. Analyses found that over the 4-year period (2006 2010) increases in positive marital quality of both spouses were independently associated with increases in their self-rated health in midlife and old age as well as with declines in disability in old age. Increases in positive marital quality were also linked with declines in functional limitations for middle-aged and older adults.Discussion. Being perceived as a supportive spouse, as well as perceiving one s partner as such, has significant health implications. Overall, positive marital quality of both spouses contributes to health protection for middle-aged and older spouses.
Keywords: Adult children; Health Conditions and Status; Methodology

Measures of aging with disability in U.S. secondary data sets: Results of a scoping review - Putnam, Michelle; Molton, Ivan R.; Truitt, Anjali R.; Smith, Amanda E.; Jensen, Mark P. (Disability and Health Journal, 2016)
AbstractBackground There remain significant knowledge gaps in our understanding of aging with long-term disability. It is possible that important advances in knowledge could be gained using existing secondary data sets. However, little is known regarding which of the data sets available to researchers contain the age-related measures needed for this purpose, specifically age of onset and/or duration of disability measures. Objective To better understand the capacity to investigate aging with long-term disability (e.g. mobility limitation) and aging with long-term chronic conditions (e.g. spinal cord injury, multiple sclerosis) using extant data. Methods Public use national and regional data sets were identified through existing reports, web-based searches, and expert nomination. The age- and disability-related variables, including age of onset and duration of disability, were tabulated for data sets meeting inclusion criteria. Analysis was descriptive. Results A total of N = 44 data sets were reviewed. Of these, 22 contained both age and disability variables. Within these 22 data sets, 9 contained an age of onset or duration of disability variable. Six of the nine data sets contained age of diagnosis for a single or set of health conditions. Onset of functional limitation is in two, and onset of self-reported and/or employment disability is in four, of the nine data sets respectively. Conclusions There is some, but limited opportunity to investigate aging with long-term disability in extant U.S. public use secondary data sets.
Keywords: Disabilities; Health Conditions and Status; Methodology

Moderate Alcohol Consumption Is Not Associated with Reduced All-cause Mortality - Goulden, Robert (The American Journal of Medicine, 2016)
Background A large body of research suggests that light or moderate alcohol consumption is associated with reduced all-cause mortality. However, concerns remain that the observed relationship is due to selection bias, misclassification of ex-drinkers, or residual confounding. Methods The association between alcohol consumption and all-cause mortality was analyzed using Cox regression. The analysis was performed using data from the Health and Retirement Study, a longitudinal cohort of 24,029 individuals from a nationally representative sample of US adults aged more than 50 years. Drinking level was based on alcohol consumption measured at 3 points over the 4 years before the start of follow-up. Occasional drinkers those who reported drinking on at least 1 occasion, but always less than once per week served as the reference category. There was extensive adjustment for sociodemographic variables, health status, and functional status. Results During 206,966 person-years of follow up, 7902 individuals died. No level of regular alcohol consumption was associated with reduced all-cause mortality. The hazard ratio and 95 confidence interval in fully adjusted analyses was 1.02 (0.94-1.11) for andlt;7 drinks/week, 1.14 (1.02-1.28) for 7 to andlt;14 drinks/week, 1.13 (0.96-1.35) for 14 to andlt;21 drinks/week, and 1.45 (1.16-1.81) for 21 drinks/week. Conclusions Moderate alcohol consumption is not associated with reduced all-cause mortality in older adults. The previously observed association may have been due to residual confounding.
Keywords: Health Conditions and Status; Methodology

A new model for interdependent durations with an application to joint retirement - Bo E. Honoré; Áureo de Paula (London, Centre for Microdata Methods and Practice, 2016)
This paper introduces a bivariate version of the generalized accelerated failure time model. It allows for simultaneity in the econometric sense that the two realized outcomes depend structurally on each other. Another feature of the proposed model is that it will generate equal durations with positive probability. The motivating example is retirement decisions by married couples. In that example it seems reasonable to allow for the possibility that each partner's optimal retirement time depends on the retirement time of the spouse. Moreover, the data suggest that the wife and the husband retire at the same time for a nonnegligible fraction of couples. Our approach takes as a starting point a stylized economic model that leads to a univariate generalized accelerated failure time model. The covariates of that generalized accelerated failure time model act as utility-flow shifters in the economic model. We introduce simultaneity by allowing the utility flow in retirement to depend on the retirement status of the spouse. The econometric model is then completed by assuming that the observed outcome is the Nash bargaining solution in that simple economic model. The advantage of this approach is that it includes independent realizations from the generalized accelerated failure time model as a special case, and deviations from this special case can be given an economic interpretation. We illustrate the model by studying the joint retirement decisions in married couples using the Health and Retirement Study. We provide a discussion of relevant identifying variation and estimate our model using indirect inference. The main empirical finding is that the simultaneity seems economically important. In our preferred specification the indirect utility associated with being retired increases by approximately 5 when one's spouse retires. The estimated model also predicts that the marginal effect of a change in the husbands' pension plan on wives' retirement dates is about 3.3 of the direct effect on the husbands'.
Keywords: Adult children; Methodology; Pensions; Retirement Planning and Satisfaction

Occupation and Industry Coding in HRS/AHEAD - Michael A. Nolte; Servais, Marita; Turf, Megan (Survey Research Center, Institute for Social Research, University of Michigan, 2016)
This document describes the codeframes that have been used to classify occupation and industry in each wave of the Health and Retirement Study. For AHEAD data collections in 1993 and 1995, occupation was coded using the SRC 2-Digit Occupation Code (adapted from the 1980 U. S. Census Occupation Code) which masked for public release.1 Unmasked codes for 1995 (but not 1993) have been released. Industry was not asked. For HRS data collections in 1992, 1994, 1996, 1998, 2000, and 2004, occupation was coded using the 3-digit 1980 U. S. Census Occupation Code and masked for public release. Industry was coded using the 3-digit 1980 U. S. Census Industry Code which was masked for public release. Except for 1994, unmasked codes have been released as restricted data. For the 2006 and 2008 interviewing periods, occupation was coded using the 3-digit 2000 U.S. Census Occupation Code; and industry was coded using the 3-digit 2002 U. S. Census Industry Code; occupation and industry were masked for public release. Unmasked versions of these codes have been released as restricted data. For HRS 2010 and beyond, occupation information was coded using the 2010 Census Occupational Classification System. Industry information reported by HRS respondents was coded using the 2007 Census Industrial Classification system. Unmasked versions of these codes have been released as restricted data.
Keywords: Methodology

Pension Estimation Program Users Guide - Fang, Chichun; Amy Butchart; Helena Stolyarova; Michael A. Nolte; Robert Peticolas (University of Michigan, 2016)
Periodically, the HRS obtains pension Summary Plan Descriptions (SPDs) from the employers of study respondents1. These SPDs are then analyzed and coded, and the plan description data, along with specific data from the respondents, are analyzed using a software product known as the Pension Estimation Program. This program is designed to estimate the pension entitlements held by respondents of the HRS, based on the plan formulas and benefit provisions obtained from the linked sample of pension providers. The Pension Estimation Program uses systems of equations to represent each of the pension plans, including all benefit formulas and payment provisions. These equations, in turn, use as input work and income histories of the respondents. For a given set of assumptions, the program calculates the appropriate pension entitlements, and generates output data files for subsequent analysis. This is the documentation for the current (April 2016) version of the pension estimation program which replaces all previous versions. Researchers may wish to examine the Pension Coding Program Users Guide for information on HRS coding procedures.
Keywords: Methodology; Pensions

Perceived discrimination and personality development in adulthood - Angelina R Sutin; Yannick Stephan; Antonio Terracciano (Developmental Psychology, 2016)
Perceived discrimination is common and a significant source of stress that may have implications for personality development across adulthood. In this study, we examined whether experiences with discrimination were associated with maladaptive changes in the 5 major dimensions of personality using 2 longitudinal samples that differed in age and follow-up interval. In the Health and Retirement Study, participants who perceived discrimination increased in their tendency to experience negative emotions (neuroticism), decreased in their tendency to be trusting (agreeableness), and decreased in their tendency to be organized and disciplined (conscientiousness). These associations replicated using participants from the Midlife in the United States study. The findings indicate that social pathways, in addition to biological and developmental tasks, are important for adult personality development. (PsycINFO Database Record
Keywords: Health Conditions and Status; Methodology

Preliminary Detection of Relations Among Dynamic Processes With Two-Occasion Data - Henk, Corinne M.; Castro-Schilo, L. (Structural Equation Modeling, 2016)
Most novel analytic methods for longitudinal data are applicable to studies spanning three time-points of data at a minimum, whereas methods for two-occasion data have garnered comparatively little attention. Here, we address this limitation by introducing the two-wave latent change score (2W-LCS) model, a technique appropriate for preliminary detection of relations among dynamic processes with two-occasion data. The 2W-LCS model is well suited for the investigation of hypotheses in which changes in a construct are posited as predictors of changes in another construct. In an empirical illustration using data of elderly Hispanics from the Health and Retirement Study, we demonstrate how the 2W-LCS model provides the best match to theories rooted in changes, and highlight the advantages of this approach over other modeling alternatives (i.e., Little, Preacher, Selig, and Card, 2007; Selig and Preacher, 2009). 2015, Routledge. All rights reserved.
Keywords: Methodology

Regression models for expected length of stay - Grand, Mia Klinten; Putter, Hein (Statistics in Medicine, 2016)
In multi-state models, the expected length of stay (ELOS) in a state is not a straightforward object to relate to covariates, and the traditional approach has instead been to construct regression models for the transition intensities and calculate ELOS from these. The disadvantage of this approach is that the effect of covariates on the intensities is not easily translated into the effect on ELOS, and it typically relies on the Markov assumption. We propose to use pseudo-observations to construct regression models for ELOS, thereby allowing a direct interpretation of covariate effects while at the same time avoiding the Markov assumption. For this approach, all we need is a non-parametric consistent estimator for ELOS. For every subject (and for every state of interest), a pseudo-observation is constructed, and they are then used as outcome variables in the regression model. We furthermore show how to construct longitudinal (pseudo-) data when combining the concept of pseudo-observations with landmarking. In doing so, covariates are allowed to be time-varying, and we can investigate potential time-varying effects of the covariates. The models can be fitted using generalized estimating equations, and dependence between observations on the same subject is handled by applying the sandwich estimator. The method is illustrated using data from the US Health and Retirement Study where the impact of socio-economic factors on ELOS in health and disability is explored. Finally, we investigate the performance of our approach under different degrees of left-truncation, non-Markovianity, and right-censoring by means of simulation.
Keywords: Methodology

Subjective cognitive impairment of older adults: a comparison between the US and China - Bei Wu (International Journal of Methods in Psychiatric Research, 2016)
Subjective assessment may be incomparable across countries due to differences in reporting styles. Based on two nationally representative surveys from the US and China, this study used data from three anchoring vignettes to estimate to what extent the US and Chinese older adults aged 50 and above differed in their reporting styles of subjective cognitive impairment. Cross country differences of subjective cognitive impairment were then estimated, both before and after adjusting for reporting heterogeneity. Directly assessed word recall test scores were analyzed to evaluate whether findings based on subjective cognitive impairment was consistent with objective performance. The results revealed a discrepancy between self-reported subjective cognitive impairment and directly assessed memory function among older adults: while Chinese respondents reported lower severity levels of subjective cognitive impairment, the US respondents demonstrated better performance in immediate word recall tests. By accounting for differences in reporting styles using anchoring vignettes data, Chinese older adults showed higher levels of subjective cognitive impairment than the US older adults, which was consistent with results from direct assessment of memory function. Non-negligible differences are present in reporting styles of subjective cognitive impairment. Cross country comparison needs to take into account such reporting heterogeneity.
Keywords: Cross-National; Health Conditions and Status; Methodology

Trends in Engagement in Advance Care Planning Behaviors and the Role of Socioeconomic Status - Khosla, Nidhi; Angela L Curl; Washington, Karla T. (American Journal of Hospice and Palliative Medicine, 2016)
We investigated the trends in advance care planning (ACP) between 2002 and 2010 and whether socioeconomic status explained such trends. We conducted a pooled regression analysis of Health and Retirement Study data from 6052 proxies of deceased individuals. We studied 3 ACP behaviors, discussing end-of-life (EOL) care preferences, providing written EOL care instructions, and appointing a durable power of attorney for health care (DPAHC). ACP increased by 12 to 23 every 2 years from 2002 to 2010. Higher household income increased the odds of having a DPAHC. Education was not associated with ACP. Socioeconomic status alone appears to play a very limited role in predicting ACP. Engagement in ACP likely depends on a constellation of many social and contextual factors.
Keywords: Demographics; End of life decisions; Methodology; Retirement Planning and Satisfaction

Why Researchers Now Rely on Surveys for Race Data on OASDI and SSI Programs: A Comparison of Four Major Surveys - Martin, Patricia P.; Office of Retirement and Disability Policy (Washington, DC, Social Security Administration, 2016)
In the absence of reliable administrative data for race categories, SSA researchers now primarily use data from four major surveys (1) the Current Population Survey (CPS); (2) the Survey of Income and Program Participation (SIPP); (3) the American Community Survey (ACS); and (4) the Health and Retirement Study (HRS) to examine OASDI and SSI program use by race and ethnicity. The race data collected in these surveys are self-reported, and although there are inherent technical issues with that process, those data are the primary source of national race data available (R os, Romero, and Ram rez 2014). However, each data set possesses a unique set of advantages and limitations for analyzing the OASDI and SSI programs. This note provides a historical background on SSA's race and ethnicity data collection. It compares the four alternative data sources most commonly used to estimate OASDI and SSI program statistics by beneficiary race and ethnicity. This overview is designed to help individuals better understand the race and ethnicity data available in existing SSA publications. It may be of use to researchers considering future OASDI and SSI analyses as well.
Keywords: Demographics; Health Insurance; Methodology; Social Security

Accounting for adaptation in the economics of happiness - Miles S Kimball; Ryan D. Nunn; Daniel S. Silverman (2015)
Reported happiness provides a potentially useful way to evaluate unpriced goods and events; but measures of subjective well-being (SWB) often revert to the mean after responding to events, and this hedonic adaptation creates challenges for interpretation. Previous work tends to estimate time-invariant effects of events on happiness. In the presence of hedonic adaptation, this restriction can lead to biases, especially when comparing events to which people adapt at different rates. Our paper provides a flexible, extensible econometric framework that accommodates adaptation and permits the comparison of happiness-relevant life events with dissimilar hedonic adaptation paths. We present a method that is robust to individual fixed effects, imprecisely-dated data, and permanent consequences. The method is used to analyze a variety of events in the Health and Retirement Study panel. Many of the variables studied have substantial consequences for subjective well-being--consequences that differ greatly in their time profiles.
Keywords: Expectations; Health Conditions and Status; Methodology

Adoption and maintenance of health behaviors among middle-aged and older adults: the role of chronic disease diagnosis and depression - Xiang, Xiaoling (University of Illinois at Urbana–Champaign, 2015)
This study is a secondary-data analysis of adoption and maintenance of health behavior changes among U.S. middle-aged and older adults. This investigation focused on the impact of a chronic disease diagnosis on the likelihood of a health behavior change and whether the magnitude of change is modified by major or persistent depression prior to the chronic disease diagnosis. Further analyses assessed whether depression and a new chronic disease diagnosis affected long-term maintenance of health behaviors changes, once made. The study sample came from 1996-2010 waves of the Health and Retirement Study and consisted of 11,439 community-dwelling adults aged 50-80 years who were free of diabetes, heart disease, stroke, cancer, and chronic lung disease in 1996. Depression was measured by the 8-item Center for Epidemiologic Studies Depression Scale and the short form of the World Health Organization's Composite International Diagnostic Interview. Chronic disease diagnosis was ascertained from self-reported physician diagnosis of a specific condition. Health behaviors included six dichotomous measures of current smoking status, drinking level (moderate or excessive), vigorous physical activity (≥ 3 times per week), receipt of influenza vaccination, blood test for cholesterol, prostate exam for men, and mammography for women. Matched case-control difference-in-differences estimator was used to estimate the effect of each chronic disease diagnosis on the likelihood of change in each health behavior. Mixed-effects logistic regression was applied to analyze the longitudinal impact of depression on health behaviors and to examine whether depression modified the impact of a chronic disease diagnosis on health behaviors. Kaplan-Meier estimator and the marginal risk set model were performed to assess the impact of a chronic disease diagnosis, depression, and their interaction on the likelihood of relapse after a health behavior change had been initiated. Middle-aged and older adults tended to reduce smoking and drinking, and increase utilization of preventive health services after a diagnosis of chronic disease. However, they reported a consistent decline in vigorous physical activity post diagnosis across disease conditions. Participants with major or persistent depression at baseline were more likely to remain smoking and less likely to engage in vigorous physical activity during the 14 years of follow-up. Depression also appeared to modify behavioral responses to a chronic disease diagnosis. Participants with depression experienced smaller increase in influenza vaccination utilization after a chronic disease diagnosis compared to their initially non-depressed counterparts. Depression did not seem to modify the impact of a new chronic disease on other health behaviors. The majority of middle-aged and older adults who initiated a health behavior change adhered to the change in the long-term. A new diagnosis of chronic disease did not appear to affect the likelihood of behavior maintenance. Chronic disease diagnosis may be an important teachable moment that can motivate individuals to spontaneously adopt risk-reducing health behaviors. More focused and intensive interventions are needed for those with chronic disease and comorbid depression to produce meaningful behavior change outcomes. Future research needs to elucidate the mechanisms through which chronic disease diagnosis affects health behaviors, develop and test the effectiveness of interventions utilizing the teachable moment effect of a chronic disease diagnosis, along with identifying population-based strategies to promote physical activity among adults with chronic disease.
Keywords: Demographics; Health Conditions and Status; Methodology; Other

Adult Child Caregiver Health Trajectories and the Impact of Multiple Roles Over Time - Barnett, Amanda E. (Research on Aging, 2015)
Guided by stress process and life course theory, the purpose of this study was to examine adult child caregivers psychological and physical health trajectories and how their multiple family (caregiving, marital, and parenting) and nonfamily (employment) roles contributed to these health outcomes over time. Seven waves of data from the Health and Retirement Study were analyzed for 1,300 adult child caregivers using latent growth curve models. Adult child caregivers have distinct psychological and physical health trajectories that are related to their roles over time. The importance of any given role varies by the type of health outcome and timing in the life course. Caregiving alone does not contribute to adult child caregivers psychological and physical health; marital and employment roles also contribute significantly to caregivers life courses.
Keywords: Adult children; Employment and Labor Force; Event History/Life Cycle; Health Conditions and Status; Healthcare; Methodology

Asymptotically exact inference in conditional moment inequality models - Armstrong, Timothy B. (Journal of Econometrics, 2015)
This paper derives the rate of convergence and asymptotic distribution for a class of Kolmogorov-Smirnov style test statistics for conditional moment inequality models for parameters on the boundary of the identified set under general conditions. Using these results, I propose tests that are more powerful than existing approaches for choosing critical values for this test statistic. I quantify the power improvement by showing that the new tests can detect alternatives that converge to points on the identified set at a faster rate than those detected by existing approaches. A Monte Carlo study confirms that the tests and the asymptotic approximations they use perform well in finite samples. In an application to a regression of prescription drug expenditures on income with interval data from the Health and Retirement Study, confidence regions based on the new tests are substantially tighter than those based on existing methods. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Healthcare; Methodology

The Changing Nature of the Retirement Transition for Dual Earning Couples (University of Maryland, College Park, 2015)
My dissertation examines how dual-earning couples navigate the retirement transition differently now that women's and men's work lives have become more similar. As the retirement transition has become more complex, understanding how and when people retire requires researchers and policymakers to be attuned to the family lives in which individuals are embedded. The decision to retire is an individual choice but one's family circumstances, particularly one's spouse, can influence the process. Couples must often factor in spouses' age, health, pension assets, and health insurance coverage, especially since the work lives of many women have become much more similar to men. Whereas men's retirement decisions were seen to depend on their employment situation and women's' on their husband's, women's rising attachment to the labor force means their work lives should be increasingly important in understanding the retirement transition of couples. This dissertation fills a gap in retirement research by utilizing a life course perspective to systematically study change across cohorts in how marital partners manage the retirement transition amidst rapid structural changes in the economy. Analyses use multiple waves of data from the Health and Retirement Study, applying a variety of modeling techniques to investigate the way that couples move from employment to retirement. Specifically, I focus on retirement expectations and timing, looking at whether dual earning couples influence and synchronize each other's retirement and how this may change across cohorts. Results suggest that coordination between couples may be declining, as both husbands and wives influence their respective partners' retirement expectations less in later cohorts. Analysis of the degree to which dual-earning couples synchronize their retirement expectations show that such couples expect to retire together when they both have the pension resources to do so. Results from event history models further indicate that the retirement trajectories have changed for the leading baby boom cohort, as evidence implies they are delaying retirement longer than previous cohorts. The findings provide mixed support for the notion that wives are influencing their husbands' retirement timing more in later cohorts or that the influence of husbands on wives' retirement timing has declined across cohorts.
Keywords: Adult children; Demographics; Employment and Labor Force; Event History/Life Cycle; Health Conditions and Status; Methodology; Pensions; Policy; Retirement Planning and Satisfaction

Competing demands: Dependent children and parental retirement - Motro, Joanna (University of Maryland, College Park, 2015)
The 1960s through the 1980s saw an expansion of generous pensions allowing workers to retire at younger ages. Since then, pensions have become less generous, and more people are working longer. Although previous research has often focused on financial and pension-related explanations for the postponement of retirement, little research has focused on how family demands shape retirement decisions. Changes in family formation in the second half of the 20th Century include delayed marriage, delayed childbearing, divorce, and remarriage. These trends, combined with the increasing time children are taking to transition to adulthood, means that parents are now more likely to be supporting children as they prepare to retire. This dissertation examines how demands from children affect older parents as they approach retirement. Using data from the Health and Retirement Study, I ask whether parents with adolescent or dependent adult children postpone retirement to later ages than other parents. I examine retirement both prospectively, by comparing parents' retirement expectations across cohorts, and then longitudinally, by modeling one cohort's transition from working to retirement. In both analyses, I focus on the impact of children who are either dependent-aged (<18), college-aged, coresident, or financially dependent. Results from this study show that needs of children do not appear to exert much influence over their parent's retirement plans. Net of parental characteristics, demands from children do not have an independent effect on retirement outcomes. It also does not appear that children in more recent cohorts exert a greater influence on parental retirement despite greater demands from children in recent years. For some subgroups (e.g. unmarried mothers and fathers, black and Hispanic parents) having certain types of demands from children is associated with greater expectations of working at older ages, while having other types of children is associated with a lower chance of expecting to work longer. For some subgroups (e.g. unmarried mothers), having certain types of dependent children are associated with retiring later. However, for the majority of adults, retirement plans and behaviors are driven more by parental retirement readiness (e.g. wealth, pension participation, and age) rather than the needs of children.
Keywords: Adult children; Methodology; Policy; Retirement Planning and Satisfaction

Covariance pattern mixture models for the analysis of multivariate heterogeneous longitudinal data - Anderlucci, Laura; Cinzia Viroli (Annals of Applied Statistics, 2015)
We propose a novel approach for modeling multivariate longitudinal data in the presence of unobserved heterogeneity for the analysis of the Health and Retirement Study (HRS) data. Our proposal can be cast within the framework of linear mixed models with discrete individual random intercepts; however, differently from the standard formulation, the proposed Covariance Pattern Mixture Model (CPMM) does not require the usual local independence assumption. The model is thus able to simultaneously model the heterogeneity, the association among the responses and the temporal dependence structure. We focus on the investigation of temporal patterns related to the cognitive functioning in retired American respondents. In particular, we aim to understand whether it can be affected by some individual socio-economical characteristics and whether it is possible to identify some homogenous groups of respondents that share a similar cognitive profile. An accurate description of the detected groups allows government policy interventions to be opportunely addressed. Results identify three homogenous clusters of individuals with specific cognitive functioning, consistent with the class conditional distribution of the covariates. The flexibility of CPMM allows for a different contribution of each regressor on the responses according to group membership. In so doing, the identified groups receive a global and accurate phenomenological characterization.
Keywords: Demographics; Health Conditions and Status; Methodology

Debt literacy, financial experiences, and overindebtedness - Annamaria Lusardi; Peter Tufano (Journal of Pension Economics and Finance, 2015)
We analyze a national sample of Americans with respect to their debt literacy, financial experiences, and their judgments about the extent of their indebtedness. Debt literacy is a component of broader financial understanding that measures knowledge about debt and self-assessed financial knowledge. Financial experiences are the participants' reported experiences with traditional borrowing, alternative borrowing, and investing. Overindebtedness is a self-reported measure. Debt literacy is low, with only about one-third of the population grasping the basics of interest compounding. Even after controlling for demographics, we find a relationship between debt literacy and both financial experiences and debt loads. Individuals with lower levels of debt literacy tend to transact in high-cost manners, incurring higher fees and using high-cost borrowing. We provide a rough estimate of the national implications of debt ignorance on credit card costs by consumers. Less knowledgeable individuals also report that their debt loads are excessive or that they are unable to judge their debt position.
Keywords: Healthcare; Methodology; Net Worth and Assets; Other

Demand for Long-Term Care and Long-Term Care Insurance -- A Human Capital Perspective - Dey, Sanjoy (State University of New York at Buffalo, 2015)
The dissertation examines several aspects of the demand for long-term care and long-term care insurance. It develops and applies a comprehensive "full insurance" model analytically in order to empirically estimate the pattern of relationship between private long-term care insurance and other non-marketable alternatives: self-insurance, self-protection, family insurance and safety-net insurance. It therefore allows us to estimate the degree to which demand for private long-term care insurance is substituted or complemented by its non-marketable alternatives. We explicitly explore the crowding out of private long-term care insurance by Medicaid. The role of education and health in the demand for long-term care and long-term care insurance is the primary focus of this study. Individuals with better education and health expect to live longer; they can purchase this insurance product in better health during their late middle age and get rewarded by insurance companies in the form of lower premiums. Medicaid turns out to be an expensive insurance option for them as it carries a high deductible for people with high income and wealth, and an educated person is aware of the potential financial risk associated with future utilization of long-term care services. While conventional wisdom would suggest that the primary effect of education on demand for long-term care insurance operates through an income effect, the paper carefully shows, both theoretically and empirically that it is the knowledge effect and an independent health effect that have the most influence. The spectrum of knowledge effect goes beyond its immediate relevance for the labor market. The paper tries to provide a complex analysis of interactions of different forms of insurances from a broader human capital perspective. The dissertation carefully explores the primary statistically significant determinants of demand for long-term care with the specific focus on the role of private LTCI coverage in determining the choice of mode of care. The dissertation also delves into an empirical investigation to understand the relationship between private insurance coverage and ultimate utilization of long-term care services in different specific caregiving institutional frameworks. The thesis pays explicit attention to different arguments of demand function of private LTCI and future utilization of long-term care. We explore the decision taken by an individual to purchase private long-term care insurance in different strata of wealth distribution. Our comprehensive analysis provides a useful instrument to develop business strategies regarding forecasting future demand for private long-term care insurance for the firms operating in long-term care insurance industry. Our analysis can also be utilized to evaluate implications of any changes in public policies.
Keywords: Healthcare; Insurance; Medicare/Medicaid/Health Insurance; Methodology; Net Worth and Assets

Determinants of labor market choices: age differentials and family circumstances - Kutyavina, Marina (University of California, San Diego, 2015)
My research explores the interactions between labor market choices, public programs, and family circumstances. In the following three chapters, I study the relationship between labor market conditions and job search behavior of workers of differing ages, the effect of children's events on parental retirement timing, as well as the impact of UI extensions on recipients' spouses.
Keywords: Employment and Labor Force; Methodology; Public Policy

Development and demonstration of a state model for the estimation of incidence of partly undetected chronic diseases - Ralph Brinks; Barbara H. Bardenheier; Annika Hoyer; Ji Lin; Sandra Landwehr; Edward W Gregg (BMC MEDICAL RESEARCH METHODOLOGY, 2015)
Background: Estimation of incidence of the state of undiagnosed chronic disease provides a crucial missing link for the monitoring of chronic disease epidemics and determining the degree to which changes in prevalence are affected or biased by detection. Methods: We developed a four-part compartment model for undiagnosed cases of irreversible chronic diseases with a preclinical state that precedes the diagnosis. Applicability of the model is tested in a simulation study of a hypothetical chronic disease and using diabetes data from the Health and Retirement Study (HRS). Results: A two dimensional system of partial differential equations forms the basis for estimating incidence of the undiagnosed and diagnosed disease states from the prevalence of the associated states. In the simulation study we reach very good agreement between the estimates and the true values. Application to the HRS data demonstrates practical relevance of the methods. Discussion: We have demonstrated the applicability of the modeling framework in a simulation study and in the analysis of the Health and Retirement Study. The model provides insight into the epidemiology of undiagnosed chronic diseases.
Keywords: Health Conditions and Status; Methodology

Disability-Free Life-Years Lost Among Adults Aged ≥50 Years, With and Without Diabetes - Barbara H. Bardenheier; Ji Lin; Zhuo, Xiaohui; Mohammed K. Ali; Theodore J Thompson; Yiling J. Cheng; Edward W Gregg (Diabetes Care, 2015)
OBJECTIVE Quantify the impact of diabetes status on healthy and disabled years of life for older adults in the U.S. and provide a baseline from which to evaluate ongoing national public health efforts to prevent and control diabetes and disability.RESEARCH DESIGN AND METHODS Adults (n = 20,008) aged 50 years and older were followed from 1998 to 2012 in the Health and Retirement Study, a prospective biannual survey of a nationally representative sample of adults. Diabetes and disability status (defined by mobility loss, difficulty with instrumental activities of daily living IADL , and/or difficulty with activities of daily living ADL ) were self-reported. We estimated incidence of disability, remission to nondisability, and mortality. We developed a discrete-time Markov simulation model with a 1-year transition cycle to predict and compare lifetime disability-related outcomes between people with and without diabetes. Data represent the U.S. population in 1998.RESULTS From age 50, adults with diabetes died 4.6 years earlier, developed disability 6 7 years earlier, and spent about 1 2 more years in a disabled state than adults without diabetes. With increasing baseline age, diabetes was associated with significant (P 0.05) reductions in the number of total and disability-free life-years, but the absolute difference in years between those with and without diabetes was less than at younger baseline age. Men with diabetes spent about twice as much of their remaining years disabled (20 24 of remaining life across the three disability definitions) as men without diabetes (12 16 of remaining life across the three disability definitions). Similar associations between diabetes status and disability-free and disabled years were observed among women.CONCLUSIONS Diabetes is associated with a substantial reduction in nondisabled years, to a greater extent than the reduction of longevity.
Keywords: Health Conditions and Status; Methodology

Divorce/Separation in Later-Life: A Fixed Effects Analysis of Economic Well-Being by Gender - Sharma, Andy (Journal of Family and Economic Issues, 2015)
With the on-going aging of the United States population and an increase in the number of older men and women living in a divorced/separated state, examining the economic security of this group is a worthwhile undertaking. Utilizing the 2004 and 2010 waves of the RAND Health and Retirement Study, this study employed fixed effects (FE) regression to examine the effects of divorce/separation on total wealth for older men and women. Results suggested older divorced/separated individuals endured a significant loss in total wealth due to a martial disruption and women fared worse than men. However, older adults can take proactive steps to ease this financial setback.
Keywords: Adult children; Methodology; Net Worth and Assets; Public Policy

Does Investors' Personality Influence Their Portfolios? - Alessandro Bucciol; Luca Zarri (Tilburg, Netherlands, Netspar, 2015)
Based on large-scale survey data from the 2006-2012 waves of the US Health and Retirement Study (HRS) we show that individual portfolio decisions are influenced by a variety of traits and facets traditionally investigated in the field of personality psychology. Two personality traits that taken together depict a self-centered personality profile have the most significant impact on financial risk taking: lower Agreeableness and higher Cynical Hostility predict higher willingness to take risks. The effects of Agreeableness seem to pass through the preferences rather than the beliefs channel. Our findings shed new light on the non-cognitive side of individuals risk taking.
Keywords: Health Conditions and Status; Methodology; Net Worth and Assets; Risk Taking

Does Mode of Contact with Different Types of Social Relationships Predict Depression in Older Adults? Evidence from a Nationally Representative Survey - Alan R Teo; Choi, Hwajung; Sarah B. Andrea; Marcia A. Valenstein; Jason T Newsom; Dobscha, Steven K.; Zivin, Kara (Journal of the American Geriatrics Society, 2015)
ObjectivesTo determine associations between use of three different modes of social contact (in person, telephone, written or e-mail), contact with different types of people, and risk of depressive symptoms in a nationally representative, longitudinal sample of older adults. DesignPopulation-based observational cohort. SettingUrban and suburban communities throughout the contiguous United States. ParticipantsIndividuals aged 50 and older who participated in the Health and Retirement Survey between 2004 and 2010 (N = 11,065). MeasurementsFrequency of participant use of the three modes of social contact with children, other family members, and friends at baseline were used to predict depressive symptoms (measured using the eight-item Center for Epidemiologic Studies Depression Scale) 2 years later using multivariable logistic regression models. ResultsProbability of having depressive symptoms steadily increased as frequency of in-personbut not telephone or written or e-mail contactdecreased. After controlling for demographic, clinical, and social variables, individuals with in-person social contact every few months or less with children, other family, and friends had a significantly higher probability of clinically significant depressive symptoms 2 years later (11.5 ) than those having in-person contact once or twice per month (8.1 ; P .001) or once or twice per week (7.3 ; P .001). Older age, interpersonal conflict, and depression at baseline moderated some of the effects of social contact on depressive symptoms. ConclusionFrequency of in-person social contact with friends and family independently predicts risk of subsequent depression in older adults. Clinicians should consider encouraging face-to-face social interactions as a preventive strategy for depression.
Keywords: Demographics; Health Conditions and Status; Healthcare; Methodology; Retirement Planning and Satisfaction

Dynamic models of health and labor supply in later life - Lindsay Jacobs (The University of Wisconsin - Madison, 2015)
In these essays, I develop and estimate life-cycle models aimed at explaining various patterns in labor supply behavior at older ages. The first study measures the extent to which later-life differences in health and disability risks across occupations affect retirement behavior and how these risks influence initial career choice. In the second essay, I look at the degree to which the changing composition of occupations over time--from more to less physically demanding--has contributed to the increase in labor force participation at older ages. The final study examines the effects of wage and health transition processes as well as the role of accrued work-related strain on the labor force participation decisions of older males, aimed particularly at accounting for the high rates of "reverse retirement" seen in the data.
Keywords: Disabilities; Employment and Labor Force; Methodology; Retirement Planning and Satisfaction

Education, glucose control, and mortality risks among US older adults with diabetes - Matthew E Dupre; Silberberg, Mina; Willis, Janese M.; Feinglos, Mark N. (Diabetes Research and Clinical Practice, 2015)
Aims: Studies have shown that diabetes mellitus disproportionately afflicts persons of low socioeconomic status and that the burden of disease is greatest among the disadvantaged. However, our understanding of educational differences in the control of diabetes and its impact on survival is limited. This study investigated the associations among education, hemoglobin A(1c) (HbA(1c)), and subsequent mortality in adults with diabetes. Methods: Prospective cohort data from the 2006, 2008, and 2010 Health and Retirement Study were linked with biomarker data for U.S. older adults with diabetes (n = 3312). Weighted distributions were estimated for all subjects at baseline and by the American Diabetes Association's general guidelines for HbA(1c) control ( 7.0 53 mmol/mol vs. = 7.0 53 mmol/mol ). Proportional hazard models were used to estimate educational differences in all-cause mortality by HbA(1c) level with sequential adjustments for contributing risk factors. Results: Mortality risks associated with HbA1c = 7.0 53 mmol/mol were significantly greater in lower-educated adults than higher-educated adults (P 0.001). We found that the hazard ratios (HR) associated with HbA(1c) = 7.0 53 mmol/mol were highest among low-educated adults (HR = 2.18, 95 CI: 1.62, 2.94) and that a combination of socioeconomic, psychosocial, and behavioral factors accounted for most, but not all, of the associations. Conclusions: Educational differences in HbA(1c) control have significant implications for mortality and efforts to reduce these disparities should involve more vigilant screening and monitoring of lower-educated adults with diabetes. (C) 2015 Elsevier Ireland Ltd. All rights reserved.
Keywords: Demographics; Health Conditions and Status; Methodology; Risk Taking

The Effect of Retirement Date Expectations on Pre-retirement Wealth Accumulation: The Role of Gender and Bargaining Power in Married US Households - Romm, A. T. (Journal of Family and Economic Issues, 2015)
This paper used seven waves of data from the US Health and Retirement Study to investigate the impact of expectations regarding the timing of retirement on pre-retirement wealth accumulation of married households. More specifically, the effect of married individuals' subjective beliefs of working full time after age 62 on household wealth was analyzed. Individuals' perceptions of the usual retirement age on the job was used as an instrument for their subjective beliefs of working full time after age 62. On a whole, the point estimates suggested that the responsiveness of married mens' saving behavior to retirement dates expectations was larger than that of married women. In particular, wealth of married households where men had the bargaining power in terms of being sole earners, exhibited the largest decrease in response to increases in subjective probabilities of working past age 62.
Keywords: Adult children; Consumption and Savings; Employment and Labor Force; Expectations; Methodology; Net Worth and Assets; Public Policy; Retirement Planning and Satisfaction; Women and Minorities

The Effect of Using Different Imputation Methods for Economic Variables in Aging Surveys - Jinkook Lee; Erik Meijer; Drystan F. Phillips (Los Angeles, University of Southern California, 2015)
We study the sensitivity of analyses on income and wealth to the methods of imputation for missing data. We do so by implementing a conditional hot-deck imputation, based on the method used by the English Longitudinal Study of Ageing, in the Health and Retirement Study. We compare marginal and joint distributions and regression models estimated from data using these imputations to the same statistics estimated from the RAND HRS data, which use a much more elaborate imputation method, and to estimates from data using an intermediate method. Although many results are qualitatively or quantitatively similar, there are also notable differences.
Keywords: Income; Methodology

The effects of housing wealth on education and other essays in empirical microeconomics - Ruddy, Ryan (University of Houston, 2015)
This dissertation is composed of three essays. The first essay, Family Resources and Secondary Education Investment: Evidence From the Housing Boom uses plausibly exogenous home price increases during the housing boom in the late 1990's and early 2000's to identify the effect of family resources on investment in secondary education. Exploiting the large spatial and timing variation of home price changes during this period, I find the average home price increase lowered the probability of dropping out of high school by age 19 by 1 percentage point, a 10% reduction. Consistent with an increased expectation of ability to pay for college, home price increases also raised the probability of completing a college preparatory curriculum and attending college. Students who reported low grades in eighth grade respond the strongest to home price increases suggesting that merit-based scholarship programs might be less beneficial than scholarship programs which are not contingent on ability. Black students of all ability levels are more likely to remain in high school in response to a home price increase. A mean change in home price decreased the probability of black students dropping out by 20%. The second chapter, The Effect of Housing Wealth on Labor Market Outcomes and Behavior , expands on the findings of Chapter 1 and previous literature that found a link between housing wealth and education by examining the impact of home wealth on adult labor market outcomes and behavior. Using the NLSY97, I measure the effect of a change in home price while in high school on income at age 26, job industry, criminal behavior, and community participation. I find evidence that home wealth shocks increase the probability of holding white collar jobs, increase wages, and positively impact behavior outcomes. These effects are likely manifesting through the increased education found in previous work. The final chapter examines the effect of the introduction of Sildenafil (Viagra) on marriage rates for elderly men in the United States. I exploit the sudden introduction and rise of Viagra use along with the difficulty in obtaining Viagra prescriptions for men with heart problems or history of stroke in a difference in difference framework to find the effect of Viagra on marriage rates. I find that men physically able to take Viagra which married prior to the introduction of Viagra were more likely to remain in their current marriage or enter a new marriage after Viagra's introduction. Furthermore, I find no evidence that the marital behavior of women was altered by health conditions at the time of Viagra's introduction.
Keywords: Demographics; Health Conditions and Status; Healthcare; Methodology; Other; Public Policy; Women and Minorities

The effects of individual-level income and contextual-level income inequality on health - Simmert, Beth (Sociology, 2015)
The relationship between income inequality and health is often studied at either the individual-level or contextual-level. The purpose of this research is to assess both of these levels, by simultaneously examining the individual and contextual contributions of income inequality on health. To address this research objective, I use data for 14,126 respondents from the 2006 wave of the Health and Retirement Study (HRS), a nationally representative sample of Americans over 50. For this analysis, I use multi-level modeling with fixed and random intercepts to assess the relationship between income inequality and three measures of health. This study has two main findings. First, an increase in individual income predicts better self-rated, physical, and mental health in middle and older aged adults, but that this protective effect varies profoundly by race and gender. The second main finding of this research is that contextual-level income inequality has no effect on the health of those over 50 in the US. The main contribution of this research is that it emphasizes the need for using multi-level modelling when studying this problem in order to more fully understand the simultaneous contribution of individual- and contextual-level income inequality.
Keywords: Methodology

Effects of social security policies on benefit claiming, retirement and saving - Alan L Gustman; Thomas L. Steinmeier (Journal of Public Economics, 2015)
An enhanced version of a structural model jointly explains benefit claiming, wealth and retirement, including reversals from states of lesser to greater work. The model is estimated with Health and Retirement Study data. Alternative beliefs about the future of Social Security affect claiming behavior. Effects of three potential policies are also examined: increasing the early entitlement age, increasing the full retirement age, and eliminating the payroll tax for seniors. Predicted responses to increasing the full entitlement age are sensitive to beliefs. 2015 Elsevier B.V.
Keywords: Consumption and Savings; Event History/Life Cycle; Health Conditions and Status; Methodology; Pensions; Retirement Planning and Satisfaction; Social Security

Engagement in activities and cognitive functioning among older adults in the health and retirement study - May, Pamela E. (Psychology, 2015)
The goal of this dissertation is to examine the effect of cognitive and social activities on cognitive performance and health conditions in a national sample of older adults from the Health and Retirement Study (HRS). This dissertation first aimed to identify longitudinal relations between activity frequency and cognitive functioning. Two hypotheses were tested, baseline activity frequency predicts change in cognitive functioning over time, and baseline cognitive performance predicts change in activity frequency over time. The dissertation's second aim was to identify links between activity frequency and cognitive trajectories. The third aim was to identify longitudinal relations between activity frequency and overall health. Changes in cognitive functioning and health were also compared simultaneously over three time points, to identify causal relations. The sample included 3,397 respondents aged ? 60 years old from the Health and Retirement Study's 2008, 2010, and 2012 waves. Respondents completed brief cognitive tests and items regarding their health during each wave, as well as items ranking frequency of engagement in cognitive and social activities in 2008 and 2012. A series of structural equation models were implemented to test the aforementioned aims. A paucity of significant findings precluded a comparison between the two hypothesized models on activity frequency and cognitive functioning, as well as between the two contrasting models for activity frequency and overall health. Activity frequency did not significantly predict rate of change in cognitive performance or health conditions over time. Activity frequency also did not significantly change over time. However, frequency of baseline cognitive activity was associated with initial level of episodic memory. Further, a lower frequency of cognitive activities was associated with a higher number of health conditions at baseline, when education was not included in the model. Relations between health and cognition were not consistently indicated over time, suggesting that health conditions may not have strong causal effects on age-related changes in cognitive functioning. Significant associations between baseline activity engagement and initial level of episodic memory and health conditions does not allow one to rule out the protective effect of activity engagement on cognition and overall health.
Keywords: Demographics; Event History/Life Cycle; Health Conditions and Status; Healthcare; Methodology

The English are healthier than the Americans: really? - Cieza, Alarcos; Oberhauser, Cornelia; Bickenbach, Jerome; Richard N Jones; Tevfik Bedirhan Üstün; Kostanjsek, Nenad; John N Morris; Chatterji, Somnath (International Journal of Epidemiology, 2015)
Background: When comparing the health of two populations, it is not enough to compare the prevalence of chronic diseases. The objective of this study is therefore to propose a metric of health based on domains of functioning to determine whether the English are healthier than the Americans.Methods: We analysed representative samples aged 50 to 80 years from the 2008 wave of the Health and Retirement Study (N = 10 349) for the US data, and wave 4 of the English Longitudinal Study of Ageing (N = 9405) for English counterpart data. We first calculated the age-standardized disease prevalence of diabetes, hypertension, all heart diseases, stroke, lung disease, cancer and obesity. Second, we developed a metric of health using Rasch analyses and the questions and measured tests common to both surveys addressing domains of human functioning. Finally, we used a linear additive model to test whether the differences in health were due to being English or American.Results: The English have better health than the Americans when population health is assessed only by prevalence of selected chronic health conditions. The English health advantage disappears almost completely, however, when health is assessed with a metric that integrates information about functioning domains.Conclusions: It is possible to construct a metric of health, based on data directly collected from individuals, in which health is operationalized as domains of functioning. Its application has the potential to tackle one of the most intractable problems in international research on health, namely the comparability of health across countries.
Keywords: Cross-National; Health Conditions and Status; Healthcare; Methodology

Essays in industrial organization - Bayot, Denrick Go (The University of Chicago, 2015)
Chapter 1 considers markets where there are gains to committing to a contract but the contract is not enforceable. Contracts in these markets typically contain some feature that locks the noncommittal agent, such as a penalty for defaulting on a contract. I argue that these lock-in mechanisms might lead to inefficient contract provisions when there is some uncertainty in the agent's valuation of the contract, and such uncertainty cannot be contracted. I then apply this argument when examining the extent to which life insurance contracts drafted today exhibit this form of ex-post inefficiency. There are a few reasons why one would suspect the existence of excessive insurance provisions in the life insurance industry. First, premiums in life insurance contracts are heavily front-loaded to subsidize subsequent premiums. The front-loading of premiums in these contracts and reduction of future premiums, as nicely pointed out by Hendel and Lizzeri (2003), allows firms to insure against rising premiums (insurance against reclassification risk) by reducing the policyholder's incentive to drop a contract and shop for a possibly less expensive policy. Indeed, I find that the level at which these contracts are front-loaded eliminates any future incentive for policyholders to repurchase a contract. I also provide evidence that a policyholder's preference for insuring against mortality risks changes stochastically over time. Despite heavy premium front-loading, almost 40% of policyholders allow their insurance to lapse within the first 10 years. Considering that premiums are lower than the cost of supplying mortality risk insurance and that preferences for such insurance changes over time, one would suspect excessive ex-post life insurance provisions. The core analysis of Chapter 1 discusses why the market for term life insurance contracts fail to fully protect policyholders from reclassification risk. Hendel and Lizzeri (2003) argue that such failure arises from the policyholder's limited-commitment and credit constraints. In particular, they surmise that a policyholder's credit constraint prevents the level of front-loading necessary to prevent all healthy policyholders from eventually walking out. The anticipated default of healthy policyholders then leads to a partial break-down in reclassification risk insurance. I investigate this premise and find that limited commitment alone fails to explain the break-down in full reclassification risk insurance observed in the life-insurance industry. I find that efforts to mitigate ex-post inefficient insurance provisions led to the breakdown of full reclassification risk insurance in this market. Chapter 2 is a joint work with Juliette Caminade and explains why prices of champagne fall during the holiday season. In this chapter, we document countercyclical prices in the sparkling wine market during the holiday season. While quantity demand doubles, prices uniformly decrease and decreases by 16% on average. We examine the role of changes in aggregate elasticity during high demand periods. Using Nielsen retail data, we find that price elasticity for sparkling wine increases by 50% during the holidays. We then use household-level data to document how the change in demand is driven by the entry of a large share of new consumers. These consumers are responsible for a quarter of sales during the holidays and are more price elastic. For instance, they spend less on other alcoholic beverages, and they are more likely to use coupons for their purchases or buy generic products. These suggestive facts are confirmed by the results of our household level demand estimation, where we find that changes to aggregate elasticity is driven by the entry of a more elastic segment.
Keywords: Consumption and Savings; Employment and Labor Force; Healthcare; Methodology; Net Worth and Assets; Other; Risk Taking

Essays on applied economics - Yavuzoglu, Berk (The University of Wisconsin - Madison, 2015)
The first chapter uses a dynamic programming model and restricted data from Health and Retirement Survey to analyze the joint determination of labor supply, consumption and the decision to apply for Social Security (SS) benefits of single males beyond normal retirement age in the U.S., currently 66. Undertaking a counterfactual analysis, I find that the year 2000 SS amendment abolishing the "earnings test" for the age group 66 - 69 explains one-fourth of the recent increase in the elderly labor force participation rate (LFPR). I further find via counterfactual analyses that the labor supply decision is sensitive to changes in SS benefit and payroll tax amounts on the extensive margin, but the effects on the intensive margin are not substantial. I also estimate labor supply elasticities for the elderly and find that the elasticities are around unit elasticity. The second chapter augments the Additively Non-ignorable (AN) model of Hirano et. al. (2001) so that it is suitable for data collection efforts that have a short panel component. Our modification yields a convenient semi-parametric bias correction framework for handling selective non-response that can emerge when multiple visits to the same unit are planned. In such surveys, selective non-response can be due to attrition, when initial response followed by nonresponse (the commonly studied case), as well as a phenomenon we term "reverse attrition", when initial nonresponse is followed by response. We apply our methodology to data from the Household Labor Force Survey (HLFS) in Turkey, which shares a key design feature (namely a rotating sample frame) of popular surveys. Our empirical results show that attrition/reverse attrition in HLFS is a statistically and substantially important concern.
Keywords: Methodology; Other; Public Policy

Essays on Health Economics - Ippolito, Benedic N. (The University of Wisconsin - Madison, 2015)
The first chapter, co-authored with Michael Batty, investigates how financial constraints influence hospital care. Specifically we study the impacts of recently enacted state "Fair Pricing" laws, which explicitly limit how much hospitals can collect from uninsured patients. Using the Nationwide Inpatient Sample, we find that the introduction of a fair pricing law leads to reductions in the amount of care delivered to uninsured patients, but find no evidence of deterioration of short-term quality of care. Overall, our results provide strong evidence that hospitals actively alter their behavior in response to financial incentives, and are consistent with the laws promoting a shift towards more efficient care delivery. In the second chapter I investigate how retirement incentives embedded in health insurance contracts influence labor market decisions of older workers. Employers typically offer one of two types of health plans: tied contracts (coverage ends at retirement) or retiree contracts (coverage continues in retirement). In comparison to a retiree plan, a tied contract provides an obvious incentive to delay retirement, but which workers stay? Particularly, what are the health characteristics of workers who respond to the incentives of the tied contract? I show that, contrary to suggestions in the literature, tied contracts produce advantageous selection. Additionally, I investigate the fact that tied contracts are consistently found to delay retirement even after age 65 - at which point workers are eligible for Medicare coverage. I show that this "excess retention" effect is entirely driven by workers with younger spouses who do not have their own insurance. The final chapter is joint work with Michael Batty and Joseph Levy, and examines how physician behavior responds to the introduction of a "panel-based" compensation structure - where a large portion of compensation is based on the number of patients a provider is responsible for, rather than the amount of work actually done. Taking advantage of a natural experiment at a large academic health system, we show that physician behavior is surprisingly unresponsive to changes in incentives - particularly for those who experienced a clear reduction in production incentives.
Keywords: Employment and Labor Force; Healthcare; Income; Insurance; Methodology; Net Worth and Assets; Retirement Planning and Satisfaction

Essays on Health Economics and Consumer Finance - Batty, Michael M. (The University of Wisconsin - Madison, 2015)
Chapter 1: Recently enacted state laws that limit how much hospitals can charge uninsured patients provide a unique opportunity to study how financial incentives of healthcare providers affect the care they deliver. Using an event study framework, we find that these fair pricing laws lead to a seven to nine percent reduction in the average length of hospital stay for uninsured patients. Although the longer-term effects of these care reductions are uncertain, they are not accompanied by worsening of short-term measures of quality of care. Overall, our results provide strong evidence that hospitals actively alter their behavior in response to financial incentives, and are consistent with the laws promoting a shift towards more efficient care delivery. Chapter 2: The list price for an average unit of care is more than three times what a hospital will be paid for treating a typical patient, and different hospitals charge widely different prices for the same service. These facts may seem innocuous, but many uninsured and out-of-network patients do pay list price. This paper uncovers patterns in hospital list prices, and explores several potential explanations. We find that markups vary much more across hospitals than within, but geography and quality of care explain little of the overall variation. Further, large, urban, well-equipped, for-profit hospitals have the highest list prices. A quirk in the Medicare Outlier Payment formula appears to have contributed to rapid price increases prior to 2004. Overall, our findings are consistent with more financially-sophisticated and profit-motivated hospitals more aggressively pursuing revenue from uninsured and out-of-network patients. Chapter 3: Many researchers and policy makers worry that Americans are not saving adequately for retirement. However, it is difficult to agree upon what constitutes adequate savings. This paper compares wealth accumulation patterns of different cohorts of Americans born in the first half of the 20th century. This comparative standard frames the retirement prospects of future and recent retirees in terms of the documented retirement experiences of older generations. Contrary to common perception, I find that the wealth accumulation of Americans nearing and entering retirement today is very similar to that of older generations.
Keywords: Consumption and Savings; Healthcare; Methodology; Retirement Planning and Satisfaction

Essays on Health Insurance and Annuities - Shepard, Mark (Harvard University, 2015)
Insurance creates an important source of economic well-being by providing for beneficiaries in times of need. But because a variety of forces may inhibit the proper functioning of insurance markets, governments are deeply involved through regulation, subsidies, and direct provision of insurance. This dissertation studies insurance demand, supply, and the role of policy in two types of markets of direct interest to policymakers: health insurance and annuities. I highlight the importance of both traditional market failures (adverse selection and moral hazard) and less standard factors like limited competition (market power) and puzzlingly low insurance demand to influence insurance market outcomes. In the first chapter, I study how health insurers compete in individual insurance markets like those established in the Affordable Care Act. I focus on the role of an increasingly important benefit: plans' networks of covered medical providers. Using data from Massachusetts' pioneer insurance exchange, I show evidence of substantial adverse selection against plans covering the most expensive and prestigious academic hospitals. Individuals loyal to the prestigious hospitals both select plans covering them and are more likely to use these hospitals' high-price care. Standard risk adjustment does not capture their higher costs driven by preferences for using high-price providers. To study the welfare implications of network-based selection, I estimate a structural model of hospital and insurance markets and use the model to simulate insurer competition on premiums and hospital coverage in an insurance exchange. I find that with fixed hospital prices, adverse selection leads all plans to exclude the prestigious hospitals. Modified risk adjustment or subsidies can preserve coverage, benefitting those who value the hospitals most but raising costs enough to offset these gains. I conclude that adverse selection encourages plans to limit networks and star academic hospitals to lower prices, with the welfare implications depending on whether those high prices fund socially valuable services. Chapter 2 also studies health insurance exchanges and the competitive effect of a policy design choice: how the level of subsidies is determined. In the Affordable Care Act exchanges and other programs, subsidies depend on prices set by insurers – as prices rise, so do subsidies. I show that these "price-linked" subsidies incentivize higher prices, with a magnitude that depends on how much insurance demand rises when the price of uninsurance (the mandate penalty) increases. To estimate this effect, I use two natural experiments in the Massachusetts subsidized insurance exchange. In both cases, I find that a $1 increase in the relative monthly mandate penalty increases plan demand by about 1%. Using this estimate, my model implies a sizable distortion of $48 per month (about 12%). This distortion has implications for the tradeoffs between price-linked and exogenous subsidies in many public insurance programs. I discuss an alternate policy that would eliminate the distortion while maintaining many of the benefits of price-linked subsidies. Chapter 3 studies demand for annuities – insurance products that protect retirees against outliving their assets. Standard life cycle theory predicts that individuals facing uncertain mortality will annuitize all or most of their retirement wealth. Researchers seeking to explain why retirees rarely purchase annuities have focused on imperfections in commercial annuities – including actuarially unfair pricing, lack of bequest protection, and illiquidity in the case of risky events like medical shocks. I study the annuity choice implicit in the timing of Social Security claiming and show that none of these can explain why most retirees claim benefits as early as possible, effectively choosing the minimum annuity. Most early claimers in the Health and Retirement Study had sufficient liquidity to delay Social Security longer than they actually did and could have increased lifetime consumption by delaying. Because the marginal annuity obtained through delay is better than actuarially fair, standard bequest motives cannot explain the puzzle. Nor can the risk of out-of-pocket nursing home costs, since these are concentrated at older ages past the break-even point for delayed claiming. Social Security claiming patterns, therefore, add to the evidence that behavioral explanations may be needed to explain the annuity puzzle.
Keywords: Medicare/Medicaid/Health Insurance; Methodology; Net Worth and Assets; Public Policy; Retirement Planning and Satisfaction; Social Security

Essays on Intergenerational Transfers - Sean Fahle (University of California, Los Angeles, 2015)
The chapters of this dissertation examine transfers between generations across three distinct contexts: a potential role for informal care in U.S. long-term care policy (Chapter 1), the effect of caregiving on bequests (Chapter 2), and making inferences about intra-household allocations using data on intergenerational transfers (Chapter 3). The first chapter poses the question: how can government policy leverage family caregiving to make Medicaid financing of long-term care more sustainable without compromising the well-being of elderly beneficiaries and their families? This question is addressed using a partial equilibrium life-cycle model augmented with a repeated game played between an elderly parent and her adult child over long-term care and living arrangements. The results indicate that policies which either expand access to consumer-directed home care or provide direct financial compensation to caregivers can result in a substantial reduction in the use of institutional care, an increase in informal caregiving, and a decrease in government expenditures. The second chapter is one of the first studies to examine bequest patterns and their determinants using data on actual bequests from a large and approximately representative, longitudinal survey of the U.S. population over age 50. The results indicate that caregiving from and co-residence with adult children are important predictors of the division of assets among children, with child caregivers receiving larger bequests than non-caregivers. The effects are strongest for bequests of housing assets. The salience of housing assets is further supported by evidence of a relationship between ownership of housing assets and the receipt of informal care from children near the end-of-life. The third chapter utilizes a novel source of variation, intergenerational financial transfers from parents to children, to recover the intra-household allocation of resources (the "sharing rule") in a collective model of household behavior. The identifying assumption is that financial transfers from a household to, for instance, the wife's own children (the stepchildren of her husband) can be regarded as the private consumption (an "assignable" good) of the wife. The results indicate that married women receive roughly half of household resources and that an increase in a wife's wage increases her share of household income.
Keywords: Adult children; Healthcare; Methodology; Public Policy

Essays on Intergenerational Transfers and Living Arrangements - Fu, Chien-Hao (Economics, 2015)
Intergenerational relationships are playing an increasingly important role in today's family life. In this study, I utilize the data from the Health and Retirement Study (HRS) to explore the linkage between children's residences and their relationships with their parents. I first show that children in closer proximity to their parents are more likely to receive financial transfers from parents, and the differences of the proximity's effect suggest that parents' financial transfers are at least in part to compensate for children's future care provisions. I then present a theoretical framework to analyze adult children's residential decisions in relation to the distance of parents' residences. The model highlights the tradeoff for the children of being closer to the parents for the lower cost of providing care and having easier access to assist parents versus being closer to his or her desired location of residence that provides better amenities or services. The empirical analysis supports the prediction from the theoretical model: children with lower income, who are less educated, or are not working full-time, tend to live closer to the parents, whether comparing children across families or within a family. The results also demonstrate that living arrangements are closely linked to family caregiving arrangements as gender, sibship size, and sibling's residence all play a role in a child's residential decision. Lastly, I examine the Great Recession's impacts on living arrangements and care access for elderly parents and find that for average families, little has changed in terms of their proximity to their children or the gender disparity of care assignment. However, families whose mother was living under the poverty line saw increases in the number of children living in close proximity. Further analysis shows that the changes in living arrangements during the recession are strongly associated with the changes of children's financial situations, but its relationship with parent's conditions are mixed. By presenting the theoretical framework and empirical results about family living and caregiving arrangements, this study helps bridge the gap between the two lines of literature and provides a more integrated view of the intergenerational relationships for the elderly parents.
Keywords: Adult children; Event History/Life Cycle; Healthcare; Methodology; Public Policy

Essays on the economics and econometrics of human capital - Mosso, Stefano (The University of Chicago, 2015)
This thesis is composed by three distinct chapters. They are related by their common theme: the economic analysis of the process of human capital formation. The first chapter distills and extends the recent research on the economics of human development and social mobility. It critically analyzes the literature on the role of early life conditions in shaping multiple life skills with emphasis on the importance of critical and sensitive investments periods in influencing skill development. It develops economic models that rationalize the empirical evidence on treatment effects of social programs and on family influence. It investigates the empirical support of recent claims, made by part of the literature, on the relevance of credit constraints in limiting skill development. It shows how credit constraints are not a major force explaining differences in the amount of parental and self-investments in skills and how untargeted income transfer policies to poor families do not significantly boost child outcomes. The second chapter compares the performance of maximum likelihood and simulated methods of moments in estimating dynamic discrete choice models. It presents a structural model of education and shows how it can be used to estimate heterogeneous returns from schooling choices which account for their continuation values. Continuation values have a large impact on returns, but are ignored in the measures commonly used to assess the value of schooling choices. The estimates from the model are used to compute a synthetic dataset. This is used to assess the ability of maximum likelihood and simulated methods of moments to recover the model parameters. It finally proposes a Monte Carlo exercise to gain confidence on the performance of a simulated method of moments algorithm. The last chapter proposes a method to assess long run impacts on earnings of early interventions even in absence of long-term data collection on earnings histories for program participants. It combines the methodological approaches of the literature on program evaluation, data combination and forecasting to develop estimators of the average treatment effects. This exercise allows a more complete cost-benefit evaluation of social programs accounting for benefits over the whole life cycle.
Keywords: Methodology; Net Worth and Assets; Other

Essays on the economics of aging - Zhao, Zhendong (Economics, 2015)
The increase in life expectancy in the US and the changing labor supply of older workers have raised issues about the fiscal solvency of health care and pension systems, as well as labor market stability and employment opportunities for younger workers. In light of these facts, this dissertation consists of three essays that focus on the economic causes and consequences of changes in the labor supply of older workers due to population aging. The first essay examines the effect of longevity on older Americans' labor supply decisions of retirement and un-retirement. Instead of using self-rated survival probabilities as the proxy of longevity expectations, I use data from the Health and Retirement Study to predict longevity from a Gompertz survival model with a rich set of variables including parental mortality information, current health and socio-economic variables. I find that the predicted longevity fits actual longevity better than subjective survival rates. Using predicted longevity as one of the independent variables in a sequential logit model of retiring and un-retiring, I find that individuals retire and re-enter the labor market as if they knew their true potential longevity, i.e., individuals with higher predicted objective longevity retire later, and are more likely to return to the labor market after initial retirement. I further investigate the consequences of extreme mismatch between subjective survival rates and objective longevity implied by the model's prediction, and I find that the misperception leads to retirees' sub-optimal saving behaviors. The second essay makes an effort to explore the theoretical foundation for the mechanism through which the risk of mortality affects individuals' decisions about work. I construct a life-cycle model of labor supply with health investment and heterogeneous risk of mortality. The heterogeneity in mortality risk is modeled as a frailty parameter which shifts the mortality hazard proportionally. Individuals can invest in health in order to recover from an adverse health shock and revert the high propensity of death which they were born with. I estimate and calibrate the model using data from Health and Retirement Survey. I simulate the life cycle path of labor supply for two groups of representative individuals under the same condition except for different survival curves, one in year 2000 and one projected in 2100 where life expectancy is predicted to be increased by 9 years. I find that in a more favorable survival environment, individuals would choose to work more and spend more on health. The third essay examines a natural follow-up question about the consequence of a larger labor supply of older workers: does the higher labor force participation rate of the elderly crowd out employment opportunities of younger workers? I utilize the Social Security "Notch", a reduction in Social Security benefits for cohorts born after 1916 due to the 1977 Amendments, as an exogenous policy change to identify the effect on younger workers' employment. Using data from Current Population Survey from 1972 to 1981, I do not find any significant crowding-out effect of the notch generation on younger workers age 25-39. I further investigate the variations in different occupational categories and find that changes in employment rates of younger workers vary across occupations. Last, I do not find significant suppressing effect of increasing labor supply of older workers on younger workers' wage income.
Keywords: Demographics; Employment and Labor Force; Health Conditions and Status; Healthcare; Methodology; Retirement Planning and Satisfaction

Evaluating mode differences in longitudinal data : moving to a mixed mode paradigm of survey methodology - Cernat, Alexandru (University of Essex, 2015)
Collecting and combining data using multiple modes of interview (e.g., face-to- face, telephone, Web) is becoming common practice in survey agencies. This is also true for longitudinal studies, a special type of survey that applies questionnaires repeatedly to the same respondents. In this PhD I investigate if and how collecting information using different modes can impact data quality in panel studies. Chapters 2 and 3 investigate how a sequential telephone - face-to-face mixed mode design can bias reliability, validity and estimates of change compared to a single mode. In order to achieve this goal I have used an experimental design from the Understanding Society Innovation Panel. The analyses have shown that there are only small differences in reliability and validity between the two modes but estimates of change might be overestimated in the mixed modes design. Chapter 4 investigates the measurement differences between face-to-face, telephone and Web on three scales: depression, physical activity and religiosity. We use a quasi-experimental (cross-over) design in the Health and Retirement Study. The results indicate systematic differences between interviewer modes and Web. We propose social desirability and recency as possible explanations. In Chapter 5 we investigate using the Understanding Innovation Panel if the extra contact by email leads to increased propensity to participate in a sequential Web - face-to-face design. Using the experimental nature of our data we show that the extra contact by email in the mixed mode survey does not increase participation likelihood. One of the main difficulties in the research of (mixed) modes designs is separating the effects of selection and measurement of the modes. Chapter 6 tackles this issue by proposing equivalence testing, a statistical approach to control for measurement differences across groups, as a front-door approach to disentangle these two. A simulation study shows that this approach works and highlights the bias when the two main assumptions don't hold.
Keywords: Methodology

Familial Caregiving and Timing of Retirement: A Gendered Cohort Analysis - Rachel R Stoiko (West Virginia University, 2015)
Retirement timing has been linked to a host of outcomes for individuals, families, and communities. Well-known predictors of retirement timing include health, wealth, and cognitive capacity; a few studies have also linked gender and family caregiving to retirement timing. In the present study, data from the Health and Retirement Study were used to create profiles of pre-retirement family caregiving (operationalized as time and financial transfers to participants' aging parents and adult children). These profiles, as well as participant gender and cohort, were used to predict later retirement timing. All profiles retired, on average, earlier than their full eligibility for Social Security benefits. The Eldercare profile, which was characterized by high levels of time and financial transfers to aging parents, retired the earliest. On average, women retired earlier than men. Members of the War Babies cohort (b. 1941-1947) retired earlier than members of the HRS cohort (b. 1931-1941). There was not a significant interaction between caregiving profile and gender, revealing that when men enacted female-typical caregiving roles, their retirement timing resembled women's. Implications for individual retirement decision-making and policy are discussed.
Keywords: Adult children; Demographics; Employment and Labor Force; Health Conditions and Status; Healthcare; Methodology; Other; Retirement Planning and Satisfaction

Gender Differences in the Association between Childhood Socioeconomic Status and Cognitive Function in Later Life - Jiyoung Lyu (Journal of Geriatrics, 2015)
Objectives. This study was aimed to explore the gender differences in the association between childhood socioeconomic status (SES) and cognitive function in later life. Methods. Using a nationally representative sample from the Health and Retirement Study, 5,544 females and 3,863 males were analyzed separately. Growth curve models were used to examine memory status and change in memory from 1998 to 2010. Results. The results showed that SES disadvantage in childhood was associated with lower memory at baseline controlling for adult SES and other covariates. In addition, cumulated disadvantage in SES was associated with poor memory in both genders. Statistically, the impact of cumulative SES on memory function at baseline was significantly different by gender. Discussion. These findings suggest that childhood SES has long-term effects on cognitive function among both men and women, and cumulative SES from childhood to adulthood may be more important for men than women with respect to their memory performance.
Keywords: Adult children; Demographics; Health Conditions and Status; Methodology

Go Gentle into That Good Night The Past, Present, and Future of End-of-Life Care - Adam E Singer (The Pardee RAND Graduate School, 2015)
End-of-life care has received increasing attention in recent years as the baby boomers age and health care costs continue to rise. This attention has brought with it remarkable growth in the field and improvement in care, but there remains work to be done in order to more consistently deliver high quality, compassionate, and patient- and family-centered end-of-life care. In this dissertation, I examine the past, present, and future of end-of-life care in order to shed light on the most effective ways to organize and deliver it. In the first analysis, I describe changes in symptom prevalence in the last year of life from 1998 to 2010. I find that the many important and troubling end-of-life symptoms, including pain and depression, became more common over that time frame, and that no symptom became less common. These changes occurred at the same time national efforts were underway to improve end-of-life care, which calls into question the nature of these changes and highlights the need to reexamine aspects of the delivery of end-of-life care. In the second analysis, I review the current evidence for palliative health services interventions to identify the populations that are appropriate for palliative care and the interventions that are effective in improving patient and family quality of life and reducing health care use and costs. I find that there are a broad range of currently available interventions that span a variety of goals, settings, and providers; that certain types of interventions are more or less effective for certain quality of life outcomes; and that health care use and cost outcomes are poorly studied overall. Some of these results enhance the existing understanding of what makes for effective end-of-life care. This information can be used in designing end-of-life care programs and in organizing research priorities for the field. In the third analysis, I simulate how cost and quality of life outcomes could fare through 2040 if three of the most effective palliative health services interventions identified in the second analysis were implemented today. I find that all three interventions lower health care costs, reduce mortality, improve quality-adjusted life years, and reduce pain, depression, and activities of daily living dependencies. These results highlight the benefit to individuals and to society of implementing evidence-based approaches to end-of-life care.
Keywords: Gerontology; Health Conditions and Status; Healthcare; Methodology; Policy; Public Policy; Retirement Planning and Satisfaction

Health Changes after Diabetes Diagnosed in Middle and Old Age: Physical, Mental and Cognitive Health Trajectories and Social Stratification - Ndao-Brumblay, Sokhna Khady (University of Michigan, 2015)
The current study focuses exclusively on middle-aged and old-aged adults with incident diabetes, and describes the course of diabetes in late adulthood in terms of physical, mental, and cognitive health change. To do this, it utilizes time-varying diabetes duration as the measure of time to define health trajectories after diabetes diagnosis. The study consists of three empirical analyses of the Health and Retirement Study, an ongoing representative biennial panel survey of Americans age 50 and older. Each study covers a different domain of health, and together they provide a comprehensive and dynamic view of people's experiences with diabetes. Hierarchical linear models of health change with longer diabetes duration (used as the measure of time), reveals that the course of diabetes is characterized by a quadratic acceleration in physical disability and a linear decline in mental and cognitive health. People who are older at the time of diagnosis, younger cohorts, women (due to lower socioeconomic status), blacks and Hispanics (partly due to socioeconomic disadvantage and health disparities before diagnosis) are generally at increased risk of a poor course of diabetes, when compared to their counterparts. Cumulative or persistent socioeconomic disadvantages were found for all outcomes, with worse health trajectories among older adults whose socioeconomic status was lower, with the exception of those in the top two income quartiles, who experienced a faster decline in mental health despite better scores at diagnosis. The study results confirm that diabetes cannot be viewed as a time-constant individual characteristic. Rather, the clinical course of diabetes in terms of physical, mental, and cognitive health changes with longer diabetes duration. Social variations in these changes need to be better understood so that effective healthcare and policy interventions can be devised to ensure successful and equitable aging with late-onset diabetes.
Keywords: Health Conditions and Status; Healthcare; Methodology

How socioeconomic status shapes health: Essays on the biological and social determinants of human welfare at older ages - Lauren L Schmitz (The New School, 2015)
Economic and epidemiological research has long established that socioeconomic status (SES) and the core characteristics that define it--education, earnings, and occupation--are strongly associated with health and mortality. However, the actual pathway these interventions and life circumstances take to affect health is not well known, and more research is needed to identify how socioeconomic-related health disparities develop and "get underneath the skin." This dissertation considers the influence of early- and late-life occupational stressors in tandem with genetic inheritances and other elements of SES to better understand how biological and social determinants cumulate over the life span and affect the health of greying populations. The first chapter explores whether characteristics of the physical and psychosocial work environment shape the health gradient in the years leading up to retirement. Dynamic panel and instrumental variable (IV) methods are used in combination with a rich data set that combines demographic information from the Health and Retirement Study (HRS), expert ratings on job characteristics from the Occupational Information Network (O*NET), and W-2 earnings records to draw more robust connections between workplace demands and health at older ages. Results indicate physical demands, environmental hazards, and conditions of the psychosocial work environment are all associated with health outcomes after age 50. In particular, there is a strong relationship between the degree of control and influence exercised on the job and improved self-reported health status, blood pressure, musculoskeletal conditions, cognitive function, and depression. The second two chapters use IV methods that exploit an exogenous shock to occupation at a young age--the Vietnam-era draft lotteries--to investigate genotype-by-environment interactions. Instrumented veteran status is interacted with polygenic scores for smoking initiation and educational attainment to test for genetic moderation (i.e. heterogeneous treatment effects) of veteran status on health behaviors, educational attainment, earnings, and labor force participation at older ages. Results reveal conscription both amplified polygenic risk for smoking and moderated the socioeconomic attainment of veterans, indicating genetic inheritances further mediate the gestation of health disparities across the life course.
Keywords: Demographics; Employment and Labor Force; Genetics; Health Conditions and Status; Healthcare; Methodology; Public Policy

How well do individuals predict the selling prices of their homes? - Hugo Benítez-Silva; Selçuk Eren; Frank Heiland; Jimenez-Martin, Sergi (Journal of Housing Economics, 2015)
The accuracy of property values estimated by homeowners is an open empirical question that requires an evaluation of the reported values using a market assessment. Using information on selling prices from the Health and Retirement Study and the American Housing Survey, and after accounting for possible measurement error in reporting and selection regarding those who we observe selling, we find evidence that homeowners overestimate the value of their properties by around 8 with an estimated range between 3.4 and 12.7 (95 CI). 2015.
Keywords: Housing; Methodology

Implications of Homeownership for Endogenous Risk Aversion, Asset Pricing and Portfolio Composition - Liang, Xuan (University of California, San Diego, 2015)
The dissertation studies the role of housing in asset pricing and household asset allocation. Housing is unique in the sense that it is both an asset and a consumption good. In addition, any adjustment in housing consumption will incur a non-convex adjustment cost. This makes housing adjustment infrequent. Due to these unique characteristics, the role of housing in a household portfolio is quite different from financial assets such as stocks and bonds. The first chapter, "The Housing CCAPM with Adjustment Costs and Heterogeneous Agents" examines how the inclusion of housing consumption in the utility function can increase the volatility and countercyclicality of the stochastic discount factor and thus help explain a higher level of equity premium despite only moderate curvature of the utility function. The keys to better performance of the model are (i) existence of the adjustment cost (ii) non-separability between housing goods and nondurable goods in the utility function and (iii) low substitutability between housing consumption and nondurable consumption. It is also shown that the housing CCAPM performs better than a standard CCAPM in explaining the variation of cross-sectional risk premia. Chapter 2, "Implications of the Housing Market for Endogenous Risk Aversion" studies household portfolio choice in a partial equilibrium model with housing consumption, adjustment costs, and varying housing prices. It is shown that household relative risk aversion is dependent on their house value to wealth ratio. Therefore, by changing the household's house value to wealth ratio, variation in house prices can affect household stock holdings through a change in household risk aversion. In addition, the model has two specific implications for households. The first is that volatile house price dynamics leads to more frequent moving. The second is that household moving leads to higher relative risk aversion. In general equilibrium, these effects would imply that volatile housing prices can lead to a higher moving frequency and thus result in a higher level of aggregate risk aversion, which would increase the price of risk in the risky asset markets. We provide empirical evidence that there is a high correlation between housing price volatility and the price of risk. Chapter 3, "Implications of the Housing Model for Moving Frequency, Relative Risk Aversion and the Portfolio Share of Risky Assets" tests the implications of the household portfolio choice model developed in Chapter 2 using household level data from the Panel Study of Income Dynamics and finds that the empirical evidence is consistent with the model. Firstly, we use cross-sectional variation in state level house prices and household moving to study the relationship between the volatility of house prices and moving frequency. Secondly, we use household moving and portfolio data to study the effect of moving on risk aversion. In addition, Chapter 3 also studies the effect of becoming unemployed on household moving by solving a model with housing consumption, adjustment costs, and a stochastic labor income process. The result suggests that the overall effect of unemployment is to reduce the frequency of moving. In addition, a sudden shift to an unemployed status can increase household risk aversion. Thus in general equilibrium, we would expect that a higher unemployment rate will increase economy wide risk aversion, which will in turn decrease the demand for stocks and increase the risk premium required. This provides a new channel (through the change in risk aversion) for the unemployment rate to affect asset prices.
Keywords: Housing; Methodology; Net Worth and Assets; Public Policy; Risk Taking

Instrumental variable estimation in a survival context - Eric J. Tchetgen Tchetgen; Stefan Walter; Vansteelandt, Stijn; Martinussen, Torben; M. Maria Glymour (Epidemiology, 2015)
Bias due to unobserved confounding can seldom be ruled out with certainty when estimating the causal effect of a nonrandomized treatment. The instrumental variable (IV) design offers, under certain assumptions, the opportunity to tame confounding bias, without directly observing all confounders. The IV approach is very well developed in the context of linear regression and also for certain generalized linear models with a nonlinear link function. However, IV methods are not as well developed for regression analysis with a censored survival outcome. In this article, we develop the IV approach for regression analysis in a survival context, primarily under an additive hazards model, for which we describe 2 simple methods for estimating causal effects. The first method is a straightforward 2-stage regression approach analogous to 2-stage least squares commonly used for IV analysis in linear regression. In this approach, the fitted value from a first-stage regression of the exposure on the IV is entered in place of the exposure in the second-stage hazard model to recover a valid estimate of the treatment effect of interest. The second method is a so-called control function approach, which entails adding to the additive hazards outcome model, the residual from a first-stage regression of the exposure on the IV. Formal conditions are given justifying each strategy, and the methods are illustrated in a novel application to a Mendelian randomization study to evaluate the effect of diabetes on mortality using data from the Health and Retirement Study. We also establish that analogous strategies can also be used under a proportional hazards model specification, provided the outcome is rare over the entire follow-up.
Keywords: Health Conditions and Status; Methodology

Inter-Cohort Variation in the Consequences of U.S. Military Service for Men's Mid- to Late-Life Body Mass Index Trajectories - Janet M Wilmoth; Andrew S London; Christine L Himes (A Life Course Perspective on Health Trajectories and Transitions, 2015)
Body mass index (BMI) is an important health indicator that changes with age and may be shaped in important ways by prior military service. While a high proportion of older men in the United States served in the military, to date, there has been no longitudinal, population-representative study of veteran status differences in men s mid- to late-life BMI trajectories. In this chapter, we use data from the 1992 2010 Health and Retirement Study (HRS) and growth curve models to examine veteran status differences in mid- to late-life BMI trajectories for cohorts of men born in the United States during the first half of the twentieth century. Without any controls in the models, veterans exhibit lower BMI, on average, than non-veterans. Once we add controls for birth cohort, early-life characteristics that occur prior to military service, potentially mediating mid- to late-life characteristics, and methodological controls for proxy report, attrition, and death during the study period, the effect of veteran status is small, marginally significant, and positive net of other factors, veterans are marginally heavier than their non-veteran counterparts. Taken together, our analyses demonstrate the large effect of the secular trend in increased weight across the population younger cohorts are substantially heavier than older cohorts regardless of their veteran status and a substantively small but consistent, positive intra-cohort effect of veteran status.
Keywords: Demographics; Health Conditions and Status; Methodology

A Longitudinal Analysis of the Influence of Race on Cognitive Performance - Castora-Binkley, Melissa; Peronto, Carol L.; Edwards, Jerri D.; Brent J. Small (The Journals of Gerontology Series B: Psychological Sciences and Social Sciences, 2015)
Objectives. Whether there are racial and ethnic disparities in the rate of cognitive decline among older adults is not clear. The purpose of this study was to determine if there are differences in cognitive decline among racial and ethnic older adults.Method. Data were from the Health and Retirement Study, waves 1998 2010. Participants were community dwelling at baseline (n = 9,492), mostly female participants (58.8 ), ranged in age from 65 to 105 years (M = 74.41, SD = 6.97), and had education levels that averaged less than high school (M = 11.7, SD = 3.4). Cognition was examined using a combined score from word recall, Serial 7 s, backward counting, and naming tasks. To determine changes in cognition across 12 years, we utilized mixed effects models.Results. Results indicated that after adjusting for covariates, race or ethnicity was unrelated to changes in cognitive performance, but there were significant differences in baseline cognition and these differences were more pronounced after adjusting for age, gender, education, poverty, heart disease, diabetes, high blood pressure.Discussion. It is evident that there are significant differences in baseline cognition, although the rate of cognitive decline across 12 years did not vary significantly by race. These findings support previous assertions that the rate of cognitive decline is not associated with race and suggest that it is likely that baseline cognitive performance is a better indicator of performance over time.
Keywords: Demographics; Health Conditions and Status; Methodology

Long-term and short-term predictors of worries about getting Alzheimer's disease - S. J. Cutler; Bragaru, C. (European Journal of Ageing, 2015)
Cumulative stresses associated with concerns about cognitive functioning and worries about developing Alzheimer's disease (AD) have been shown to be related to poorer health and lower psychological well-being. Among older persons, AD also generates higher levels of fear than any other disease. But much remains to be learned about predictors of worries and fears, especially from a temporal perspective. Thus, the principal objective of the current research is to examine long-term effects of self-perceptions of cognitive functioning on worries about developing AD. Data for the study are drawn from the University of Michigan's Health and Retirement Study. We use up to ten measurements of self-perceived cognitive functioning collected from 1992 to 2010 for respondents 50 years of age and older at the time of their entrance into the study. Demographics (marital status, age, education, and gender); beliefs about the role of genetics, personal knowledge of someone with AD, and their interaction; and depression and health are other variables included in the model. The data are analyzed using the full information maximum likelihood procedure and latent growth curve modeling to account for the long-term effects. The analysis shows evidence of both short-term effects of depression, age, beliefs, and the interaction of beliefs and personal familiarity and long-term effects of cognitive self-assessment on worries about getting AD. Further analyses of these relationships and inclusion of these items in other studies are recommended.
Keywords: Health Conditions and Status; Methodology

Long-Term BMI Trajectories and Health in Older Adults: Hierarchical Clustering of Functional Curves - Zajacova, Anna; Huzurbazar, Snehalata; Greenwood, Mark; Nguyen, Huong (Journal of Aging and Health, 2015)
Objective: This project contributes to the emerging research that aims to identify distinct body mass index (BMI) trajectory types in the population. We identify clusters of long-term BMI curves among older adults and determine how the clusters differ with respect to initial health. Method: Health and Retirement Study cohort (N = 9,893) with BMI information collected in up to 10 waves (1992-2010) is analyzed using a powerful cutting-edge approach: hierarchical clustering of BMI functions estimated via the Principal Analysis by Conditional Expectations (PACE) algorithm. Results: Three BMI trajectory clusters emerged for each gender: stable, gaining, and losing. The initial health of the gaining and stable groups in both genders was comparable; the losing cluster experienced significantly poorer health at baseline. Discussion: BMI trajectories among older adults cluster into distinct types in both genders, and the clusters vary substantially in initial health. Weight loss but not gain is associated with poor initial health in this age group.
Keywords: Demographics; Health Conditions and Status; Methodology

Long-term effects of economic fluctuations on health and cognition in Europe and the United States - Hessel, Philipp (Social Policy, 2015)
Several studies suggest that population health improves during recessions and deteriorates during economic expansions. However, the majority of these studies only focus on the short-term or contemporaneous effects of economic fluctuations on health. As a result, very little evidence exists on potential long-term health effects of exposure to booms or recessions. This can be regarded as a major gap in knowledge, given the fact that most diseases are the results of exposure or behaviours during a longer period of time. Furthermore, a large body of research also suggests that many risks associated with recessions may accumulate over the course of life and lead to a gradual deterioration in health. By focusing only on the short-term effects, most studies thus ignore potential longrun health effects of economic fluctuations. This thesis aims to bridge the gap between studies on the population level assessing the short-term effects of economic fluctuations on health, and studies on the individual level, which have analysed the health-effects of risks associated with a declining economy including unemployment, job loss and job insecurity. In order to assess potential longterm effects of business cycles on health, I linked historical information on macroeconomic fluctuations during the 20th century to individual-level data from the Survey of Health, Ageing and Retirement in Europe (SHARE) as well as the U.S. Health and Retirement Study (HRS). This approach makes it possible to identify the state of the economy during different life-course periods for every respondent and relate it to health outcomes measured in later life. Regarding the macroeconomic conditions at any given age as largely exogenous, the four empirical papers included in this thesis thereby assess the relationship between business cycles and health during three different life-course periods: the time around graduation from full-time education, middle and late adulthood as well as the years nearing retirement. Overall, the results suggest that individuals who experienced less favourable economic conditions during these life-course periods have a higher risk of having additional limitations in physical functioning, lower levels of cognitive functioning, as well as higher risks of cardiovascular disease in later life. In contrast to studies showing that population health improves during recessions, these findings suggest that potential short-term improvements in health may be outweighed by deteriorations in health in the long run. They also raise important questions about the role of potential mechanisms linking differential exposure to the business cycle to health in later life.
Keywords: Cross-National; Event History/Life Cycle; Health Conditions and Status; Methodology; Public Policy; SHARE

Mothering alone: cross-national comparisons of later-life disability and health among women who were single mothers - Lisa F Berkman; Yuhui Zheng; M. Maria Glymour; Mauricio Avendano; Axel Borsch-Supan; Erika L. Sabbath (Journal of Epidemiology and Community Health, 2015)
Background Single motherhood is associated with poorer health, but whether this association varies between countries is not known. We examine associations between single motherhood and poor later-life health in the USA, England and 13 European countries.Methods Data came from 25 125 women aged 50 who participated in the US Health and Retirement Study, the English Longitudinal Study of Ageing and Survey of Health, Ageing and Retirement in Europe. We tested whether single motherhood at ages 16 49 was associated with increased risk of limitations with activities of daily living (ADL), instrumental ADL and fair/poor self-rated health in later life.Results 33 of American mothers had experienced single motherhood before age 50, versus 22 in England, 38 in Scandinavia, 22 in Western Europe and 10 in Southern Europe. Single mothers had higher risk of poorer health and disability in later life than married mothers, but associations varied between countries. For example, risk ratios for ADL limitations were 1.51 (95 CI 1.29 to 1.98) in England, 1.50 (1.10 to 2.05) in Scandinavia and 1.27 (1.17 to 1.40) in the USA, versus 1.09 (0.80 to 1.47) in Western Europe, 1.13 (0.80 to 1.60) in Southern Europe and 0.93 (0.66 to 1.31) in Eastern Europe. Women who were single mothers before age 20, for 8 years, or resulting from divorce or non-marital childbearing, were at particular risk.Conclusions Single motherhood during early-adulthood or mid-adulthood is associated with poorer health in later life. Risks were greatest in England, the USA and Scandinavia. Selection and causation mechanisms might both explain between-country variation.
Keywords: Adult children; Cross-National; Disabilities; Health Conditions and Status; Methodology

No Place Like Home? Disability and Living Arrangements in Later Life - Carrie Elizabeth Henning-Smith (Health Services Research, Policy and Administration, 2015)
Current literature on the relationships between disability and both the physical and social environments of one's living arrangement is scarce. The relationship between disability and living arrangements in later life is inherently complex, yet it has the potential to impact older adults' lives in significant ways. With this dissertation, I sought to address this gap in the literature and add to our understanding of how older adults' environments and functional statuses interact. My specific aims were to: 1.) Describe the living arrangements of older adults with disabilities; 2.) Estimate the risk of developing disability by type of living arrangement (both housing type and household composition) for older adults; and, 3.) Estimate the risk of having a change in living arrangement by disability status for older adults. For all three aims, I also examined how the relationships between living arrangements and disability differed by age and socio-economic status. Data came from the American Community Survey (2012; n=504,371 adults age 65 and older) and the Health and Retirement Study (1998-2012; n=43,182 observations.) In Aim 1, I found that disability was most prevalent for older adults living in situations other than with a spouse only and that the odds of disability was highest for older adults living with children (without a spouse.) Compared with living in a single-family home, the odds of disability were higher for older adults living in mobile homes and large apartment buildings. In Aim 2, I found that living in a nursing home or with others was associated with an increased risk of disability, but that living alone was associated with a decreased risk of disabilities related to Instrumental Activities of Daily Living (IADLs.) This latter finding only held true for more affluent older adults, however; the poorest older adults faced an increased risk of disability if they lived alone. Finally, in Aim 3, I found that having IADL and ADL (Activities of Daily Living) disabilities together was predictive of moving, long nursing home stays, and death. ADL and IADL disabilities separately were predictive of long nursing home stays and death, while prior living arrangements were more predictive of moving than individual ADL or IADL disability status. For all of my findings, disability rates were highest among the poorest and oldest older adults. Older adults with the lowest socioeconomic status were also more likely to live alone, with non-spousal others, in rented homes, and in mobile homes or apartment buildings. This population may need additional resources to foster supportive living arrangements and to mitigate disability risk. These findings can be used to identify where older adults with disabilities live and where to target interventions to prevent worsening disability.
Keywords: Demographics; Health Conditions and Status; Healthcare; Methodology; Public Policy; Retirement Planning and Satisfaction

Obesity and onset of depression among U.S. middle-aged and older adults - Xiang, Xiaoling; An, Ruopeng (Journal of psychosomatic research, 2015)
Objectives: This paper aims to examine the relationship between obesity and onset of depression among U.S. middle-aged and older adults. Methods: Data came from 1994 to 2010 waves of the Health and Retirement Study. Study sample consisted of 6514 community-dwelling adults born between 1931 and 1941 who were free of clinically relevant depressive symptoms in 1994. Body mass index (BMI) was calculated from self-reported height/weight. Body weight status was classified into normal weight (18.5 kg/m2 BMI andlt; 25 kg/m2), overweight (25 kg/m2 BMI andlt; 30 kg/m2), and obesity (BMI 30 kg/m2). A score of 3 on the 8-item Center for Epidemiologic Studies Depression Scale was used to define clinically relevant depressive symptoms. Kaplan Meier estimator and time-dependent Cox proportional hazards model were performed to examine the association between body weight status and onset of clinically relevant depressive symptoms. Results: Unhealthy body weight was associated future onset of depression. Compared with their normal weight counterparts, overweight and obese participants were 13 (hazard ratio HR = 1.13, 95 confidence interval CI = 1.04 1.23) and 9 (HR = 1.09, 95 CI = 1.01 1.18) more likely to have onset of clinically relevant depressive symptoms during the 16 years of follow-up, respectively. The relationship between obesity and depression onset appeared stronger among females and non-Hispanic whites than their male and racial/ethnic minority counterparts. Conclusions: Health care providers should be aware of the potential risk for depression among obese older adults.
Keywords: Demographics; Health Conditions and Status; Methodology

Obesity Over the Life Course: A Study of How Obesity Produces Health Disadvantage and Excess Mortality in the United States - Heide Jackson (The University of Wisconsin - Madison, 2015)
This dissertation explores the influence of obesity on U.S. population morbidity and mortality. Across three essays, I examine the relation of obesity to work disability, activity impairment, and mortality. Chapter 1 looks at how obesity in early adulthood affects work disability at young and middle ages. Using data from the National Longitudinal Study of Youth 1979, I employ logistic regression to assess whether an early onset of obesity affects the likelihood of developing a work disabling condition and use event history analysis to predict the time at which that work disability occurs. Results indicate that early obesity increases the likelihood that a person will develop a work disability and uniformly increases the relative hazard of the disability occurring. The association of obesity and work disability remains robust to the inclusion of covariates and modeling the process that selects a person to become obese. Chapter 2 shifts to looking at how mid-life obesity may alter the effect of occupational exposures on later life limitations in activities of daily living. Using data from the Health and Retirement Study and latent growth curve models, I find that the effects of past occupational exposures differ by whether or not a respondent is obese around retirement. For non-obese respondents, physically demanding occupations are associated with a lower risk of developing health impairments, but no such association is found for obese persons. Instead, although not statistically significant, physically demanding occupations are associated with a greater rate of accumulation in health limitations for obese persons. Chapter 3 moves to examine why it is that older obese adults appear more likely to get sick but less likely to die. Using data from the Health and Retirement Survey and a multi-state modelling framework, I find that the obesity-mortality paradox may be explained by obese adults having a higher risk of becoming ill, losing weight, and subsequently dying having a history of obesity. Together, these three chapters suggest important influences of obesity on the health and well-being of adults throughout the life course and highlight the importance of studying the obesity-health relationship in a longitudinal framework.
Keywords: Demographics; Disabilities; Health Conditions and Status; Healthcare; Methodology; Public Policy

Patient Characteristics and Differences in Hospital Readmission Rates - Barnett, M. L.; John Hsu; J. Michael McWilliams (JAMA internal medicine, 2015)
IMPORTANCE Medicare penalizes hospitals with higher than expected readmission rates by up to 3 of annual inpatient payments. Expected rates are adjusted only for patients' age, sex, discharge diagnosis, and recent diagnoses. OBJECTIVE To assess the extent to which a comprehensive set of patient characteristics accounts for differences in hospital readmission rates. DESIGN, SETTING, AND PARTICIPANTS Using survey data from the nationally representative Health and Retirement Study (HRS) and linked Medicare claims for HRS participants enrolled in Medicare who were hospitalized from 2009 to 2012 (n = 8067 admissions), we assessed 29 patient characteristics from survey data and claims as potential predictors of 30-day readmission when added to standard Medicare adjustments of hospital readmission rates. We then compared the distribution of these characteristics between participants admitted to hospitals with higher vs lower hospital-wide readmission rates reported by Medicare. Finally, we estimated differences in the probability of readmission between these groups of participants before vs after adjusting for the additional patient characteristics. MAIN OUTCOMES AND MEASURES All-cause readmission within 30 days of discharge. RESULTS Of the additional 29 patient characteristics assessed, 22 significantly predicted readmission beyond standard adjustments, and 17 of these were distributed differently between hospitals in the highest vs lowest quintiles of publicly reported hospital-wide readmission rates (P = .04 for all comparisons). Almost all of these differences (16 of 17) indicated that participants admitted to hospitals in the highest quintile of readmission rates were more likely to have characteristics that were associated with a higher probability of readmission. The difference in the probability of readmission between participants admitted to hospitals in the highest vs lowest quintile of hospital-wide readmission rates was reduced by 48 from 4.41 percentage points with standard adjustments used by Medicare to 2.29 percentage points after adjustment for all patient characteristics assessed (reduction in difference: -2.12; 95 CI, -3.33 to -0.67; P = .003). CONCLUSIONS AND RELEVANCE Patient characteristics not included in Medicare's current risk-adjustment methods explained much of the difference in readmission risk between patients admitted to hospitals with higher vs lower readmission rates. Hospitals with high readmission rates may be penalized to a large extent based on the patients they serve.
Keywords: Healthcare; Medicare/Medicaid/Health Insurance; Methodology; Public Policy

Perceived Control, Chronic Stress, and Geriatric Frailty: Explicating Frailty's Psychosocial Etiology - Christopher J Mooney (University of Rochester, 2015)
Frailty in older adults is a highly prevalent syndrome that is characterized by increased vulnerability to stressors and is more generally thought to result from dysregulation across multiple physiologic systems. Although research has long recognized that psychosocial factors including chronic stress and perceived control influence geriatric health outcomes, relatively little research has explored their etiologic role in the development of frailty. Thus, the primary purpose of this study was to close key knowledge and methodological gaps that exist within the extant literature and to develop empirically based insights into the psychosocial etiology of geriatric or phenotypic frailty, using the allostatic load model of stress and a model of perceived control as guiding theoretical frameworks. Using a population-based sample of older adults from the Health and Retirement Study, the present study found a frailty prevalence of 7-8% in study subsamples. In structural equations modeling, the present study found that perceived control fully mediated the chronic stress and baseline phenotypic frailty and change in phenotypic frailty relationship, as well partially mediated the relationship linking socioeconomic status and baseline phenotypic frailty and change in phenotypic frailty. Multiple group analyses supported hypotheses that the mediating role of control was equivalent across gender and racial subgroups. Contrary to hypotheses, the present study found no evidence to support a stress-buffering or moderating effect of perceived control on baseline or change in phenotypic frailty status. Findings from the study advance the understanding of frailty's psychosocial etiology and underscore the importance of psychosocial factors in senescence and older adult health more generally.
Keywords: Demographics; Gerontology; Health Conditions and Status; Healthcare; Methodology; Public Policy

Productive and Social Engagement Following Driving Cessation: A Couple-Based Analysis - Angela L Curl; Proulx, Christine M.; Stowe, James D.; Teresa M Cooney (Research on Aging, 2015)
Drawing on interdependence theory, this study examined the cross-spouse impact of driving cessation on productive (work, formal volunteering, and informal volunteering) and social engagement of older couples aged 65 using longitudinal data from the Health and Retirement Study (1998 2010; N = 1,457 couples). Multilevel modeling results indicate that driving cessation reduced husbands productive and social engagement, and wives productive engagement. Spousal driving cessation reduced husbands likelihood of working or formal volunteering, and wives likelihood of working or informal volunteering. The more time since spousal driving cessation, the less likely husbands were to work and the less likely wives were to formally volunteer. Results suggest the need for greater recognition of the impact of driving cessation on couples, rather than just individuals, as well as the need for enhanced services or rehabilitation efforts to maintain driving even among couples with one remaining driver.
Keywords: Adult children; Employment and Labor Force; Health Conditions and Status; Methodology; Other

Promises and Pitfalls of Anchoring Vignettes in Health Survey Research - Grol-Prokopczyk, Hanna; Emese Verdes-Tennant; Mary McEniry; Márton Ispány (Demography, 2015)
Data harmonization is a topic of growing importance to demographers, who increasingly conduct domestic or international comparative research. Many self-reported survey items cannot be directly compared across demographic groups or countries because these groups differ in how they use subjective response categories. Anchoring vignettes, already appearing in numerous surveys worldwide, promise to overcome this problem. However, many anchoring vignettes have not been formally evaluated for adherence to the key measurement assumptions of vignette equivalence and response consistency. This article tests these assumptions in some of the most widely fielded anchoring vignettes in the world: the health vignettes in the World Health Organization (WHO) Study on Global AGEing and Adult Health (SAGE) and World Health Survey (WHS) (representing 10 countries; n = 52,388), as well as similar vignettes in the Health and Retirement Study (HRS) (n = 4,528). Findings are encouraging regarding adherence to response consistency, but reveal substantial violations of vignette equivalence both cross-nationally and across socioeconomic groups. That is, members of different sociocultural groups appear to interpret vignettes as depicting fundamentally different levels of health. The evaluated anchoring vignettes do not fulfill their promise of providing interpersonally comparable measures of health. Recommendations for improving future implementations of vignettes are discussed. 2015 Population Association of America
Keywords: Health Conditions and Status; Methodology; SAGE

Racial/Ethnic Differences in Cost-Related Nonadherence and Medicare Part D: A Longitudinal Comparison - Bakk, Louanne (Journal of Health Care for the Poor and Underserved, 2015)
Little is known about whether racial and ethnic disparities in cost-related medication nonadherence (CRN) have changed since the implementation of Medicare Part D. This longitudinal study examined the impact of Part D on CRN among racial and ethnic minority Medicare beneficiaries, age 65 and older. Nationally representative data were obtained from the Prescription Drug Study and Health and Retirement Study. A differences-in-differences approach was used to compare CRN among non-Hispanic Blacks, Hispanics, and non-Hispanic Whites. The results indicate CRN was higher among the two minority groups than among non-Hispanic Whites before and after Medicare Part D. Mixed-effects logistic regression analyses show that CRN did not significantly change between pre- and post-Medicare Part D for any of these three groups. However, older non-Hispanic Blacks and Hispanics had a larger reduction in CRN than non-Hispanic Whites. These findings suggest that despite Medicare Part D, racial and ethnic disparities in CRN persist.
Keywords: Demographics; Healthcare; Medicare/Medicaid/Health Insurance; Methodology; Public Policy; Women and Minorities

Relationship of financial literacy to retirement preparedness among female baby-boomer cohorts - Womack, Barbara Klein (School of Public Service Leadership, 2015)
Studies have not examined the impact of components of financial literacy on retirement preparedness nor the relationship between financial literacy and decision-making among female baby-boomers. This study examined data from the 2010 wave of the Health and Retirement Study for females born between 1946 and 1959. This study defined financial literacy as including knowledge of investment strategies, the bond market, risk, and diversity. It defined retirement preparedness as the possession of specific financial assets. Financial decision-making was defined as the potential for mortgage default and carrying balances on credit cards. The study used a synthesis of rational choice and planned behavior theories. Correlation was used to describe the relationships between variables, and Fisher's transformation was used to determine significant differences between cohorts. Multiple linear regression was used to create predictive models for retirement planning, with the resultant finding that age was significant in predicting retirement preparedness ( p < .01). Older cohorts were more prepared, particularly in terms of owning IRA/Keogh plans. Understanding the effects of holding a variety of stocks and foreign stocks were most strongly related to retirement preparedness. There was a significant relationship between financial literacy and the potential for mortgage default ( p < .05) but not for carrying credit card balances. The regression produced a significant ( p < .05) predictive model for retirement preparedness, thought the relationship with financial literacy was slight. The research has implications in terms of housing, health, and municipal sustainability. Further research is necessary to define financial literacy, retirement preparedness, and their relationship.
Keywords: End of life decisions; Health Conditions and Status; Methodology; Net Worth and Assets; Public Policy; Retirement Planning and Satisfaction; Women and Minorities

Revisiting the pathways to retirement: a latent structure model of the dynamics of transition from work to retirement - Tang, Fengyan; Jeffrey A Burr (Ageing and Society, 2015)
A dynamic latent structure model of the work-retirement transition process was identified, focusing on transitions of work and retirement status for men and women aged 51-74 years. Using the Health and Retirement Study data (1998-2004), latent transition analysis was used to identify a best fitting model capturing work-retirement statuses in four samples defined by age and sex. The prevalence of each status was described and the dynamic transition probabilities within the latent structure were examined. Using multinomial logistic regression, socio-demographic, health, family and occupational factors were assessed to determine how each was related to the likelihood of occupying a specific latent status at baseline. Results showed that study respondents were classified into distinct groups: full retiree, partial retiree or part-time worker, full-time worker, work-disabled or home-maker. The prevalence of full retiree status increased, while the prevalence for full-time worker status decreased over time for both men and women. Membership rates in the work-disabled and partial retiree status were generally consistent, with decreased probabilities of the work-disabled status in the older age groups and increased probabilities of partial retirees among younger men. Our findings indicated that many older Americans experience multiple transitions on the pathway to retirement. Future research on late-life labour-force transitions should evaluate the impact of the recent Great Recession and examine the role of larger socio-economic contexts.
Keywords: Employment and Labor Force; Methodology; Retirement Planning and Satisfaction

Self-Rated Health, Social Engagement, and "Older Places" - Eric M Vogelsang (Sociology - LS, 2015)
This dissertation consists of three essays that are motivated by an aging world. Its primary goals are to (a) identify how older adult health and its correlates--with a particular focus on social engagement--systematically differ by residential context; and (b) consider the implications of subjective health changes across older ages. The first chapter explores how the type and intensity of older-adult social participation varies by county-level population density. Using the 2003 and 2011 waves of the Wisconsin Longitudinal Study (n=3,006), I find that older adults living in rural counties with relatively low population densities are less socially active than their counterparts in higher-density counties. I also find that just five (of twelve) social activities are related to better health; while only three are associated with health change. Chapter two examines relationships between older adult health and living in relatively older and younger municipalities. Using a national sample of almost 5,000 Japanese older adults over two decades, I employ growth curve models to estimate how self-rated health and self-rated health trajectories differs by local area age structure. I find older adults living in the "oldest places" of Japan are more likely to report less than good health, when compared to those living in younger areas. In addition, relatively high levels of social engagement among older adults living in oldest areas help mitigate even greater odds of reporting worse health in these places. Chapter three explores how two measures of self-rated health (SRH) change are related to mortality. Data come from the Asset and Health Dynamics survey--the "oldest-old" portion of the Health and Retirement Study--and follow 6,233 individuals over thirteen years. After controlling for morbidity, individual characteristics, and SRH, those who changed SRH categories between survey waves and those who retrospectively reported an improvement in health continue to have a greater risk of death; when compared to those with no change. These findings suggest that the well-established associations between SRH status and mortality may understate the risk of death for oldest-old individuals with recent subjective health improvements.
Keywords: Health Conditions and Status; Healthcare; Methodology

The shadow of the past: Financial risk taking and negative life events - Alessandro Bucciol; Luca Zarri (Journal of Economic Psychology, 2015)
Based on data from the four 2004-2010 waves of the US Health and Retirement Study (HRS), we show that financial risk taking is significantly related to life-history negative events out of an individual's control. Using observed portfolio decisions to proxy for risk taking, we find correlation with two of such individual-specific events: having been victim of a physical attack and (especially) the loss of a child are associated with lower and less frequent investments in risky assets, with an intensity similar to that of the beginning, in 2008, of a collectively experienced event such as the recent financial crisis. We also find evidence that the correlation of risk taking with a child loss is long-lasting, as opposed to the correlation with a physical attack that disappears after few years. Our analysis is more in favor of a preference-based - rather than a belief-based - explanation of the observed change in risk taking. Overall our findings indicate that the past, especially through the loss of a child, casts a long shadow that extends over individuals' current decisions also within unrelated domains. 2015 Elsevier B.V.
Keywords: Health Conditions and Status; Methodology; Net Worth and Assets; Risk Taking

Sicker and Poorer: The Consequences of Being Uninsured for People With Disability During the Medicare Waiting Period - Yin, Na (Health Services Research and Managerial Epidemiology, 2015)
Purpose: Disabled individuals younger than 65 years are entitled to Medicare coverage through the Social Security Disability Insurance (DI) program, but only if they have completed a 2-year waiting period. This is the first study that uses longitudinal panel data, the Health and Retirement Study, and examines whether and to what extent the health and economic status are affected among disability beneficiaries who are uninsured during the Medicare waiting period.Methods: In a quasiexperiment research design, using a difference-in-difference (diff-in-diff) estimator, we compare changes in health and economic outcomes pre-/postentering the DI program for disability beneficiaries with alternative public health insurance and those without.Results: The adjusted diff-in-diff estimates suggest that disability beneficiaries who are uninsured during the waiting period, compared to those who are insured, are 13.6 percentage point more likely to report poor health, 6.3 percentage point less likely to be in excellent health, declare more difficulties in activities of daily living, and 30 higher medical expenditures from out of pocket.Conclusions: The findings highlight punitive health and economic effects of the Medicare waiting period for uninsured disability beneficiaries. We also discuss the implications of the findings for the Affordable Care Act reform.
Keywords: Disabilities; Healthcare; Medicare/Medicaid/Health Insurance; Methodology

Smoking and cognitive functioning at older ages: Evidence from the Health and Retirement Study - Padmaja Ayyagari; Asia Sikora Kessler (Journal of the Economics of Ageing, 2015)
It has long been established that smoking has detrimental health effects on the human body and leads to early mortality. However, the evidence regarding the link between smoking behavior and cognitive function in old age is mixed. While nicotine has been shown to improve cognitive functioning in some medical studies, current smokers typically perform worse than non-smokers on cognitive tests in population based studies. We use the Health and Retirement Study to evaluate the role of unobserved factors in explaining these conflicting findings. Results from individual fixed effects models show that much of the lower cognitive function of current and former smokers relative to never smokers can be attributed to unobserved differences between these groups.
Keywords: Demographics; Health Conditions and Status; Methodology

Smoking, Heavy Drinking, and Depression among U.S. Middle-Aged and Older Adults - An, Ruopeng; Xiang, Xiaoling (Preventive Medicine, 2015)
Objective To examine the relationship between smoking, heavy drinking and depression among U.S. middle-aged and older adults. Method Individual-level data came from 1992 2012 waves of the Health and Retirement Study. Smoking was ascertained from self-reported cigarette smoking status at the time of interview. Heavy drinking was defined as one or more drinks per day on average or four or more drinks on any occasion in the past three months for women, and two or more drinks per day on average or four or more drinks on any occasion in the past three months for men. Depression was defined as scoring three and above on the eight-item Center for Epidemiologic Studies Depression Scale. Cox proportional hazards regressions were performed to examine the relationship between smoking, heavy drinking and depression. Results Compared to non-smokers, smokers free from depression and heavy drinking at baseline were 20 (95 confidence interval: 12 28 ) and 34 (20 50 ) more likely to develop depression and engage in heavy drinking during follow-up period, respectively. Compared to non-depressed participants, participants with depression who were nonsmokers and non-heavy drinkers at baseline were 41 (14 74 ) and 18 (6 31 ) more likely to smoke and engage in heavy drinking during follow-up, respectively. Compared to non-heavy drinkers, heavy drinkers who were nonsmokers at baseline were 60 (26 104 ) more likely to smoke during follow-up. Conclusion Health promotion programs in midlife and older age should be mindful of the associations between smoking, heavy drinking and depression in order to improve intervention effectiveness.
Keywords: Demographics; Health Conditions and Status; Methodology; Other

Social relationships, positivity, and personality in older adulthood - Iveniuk, James (The University of Chicago, 2015)
In this dissertation, I examine the implications of personality traits for social relationships in older adulthood. My work brings together insights from mid-20th century sociological theory, recent work by social network scholars, and personality psychologists. I build upon these insights in order to examine not only if personality traits are important for social relationships, but also under what social and relational circumstances. The personality characteristic that I focus on in this dissertation is Positivity, which I conceptualize as a person's overall positive (i.e. upbeat and socially desirable) characteristic patterns of thought and behavior. I measure Positivity using structural equation modeling techniques, applied to a Big Five personality battery in the National Social Life, Health, and Aging Project (NSHAP), a nationally representative, longitudinal survey of older adults. I then employ Positivity scores in three empirical studies. In the first study, I examine older adults' social networks, and I find that Positivity is associated with feeling closer to one's confidants, and being more likely to open up to them about one's health. I also find that Neuroticism (emotional instability) is associated with being more likely to talk to one's friends about one's health. In the second study I use dyadic data from NSHAP to examine the implications of traits for marital conflict, with a focus on gender. I find that the Positivity of a husband is associated with reduced marital conflict according to the reports of his wife, but that a wife's Positivity is not associated with conflict according to her husband. In the final study I examine the implications of Positivity for the diagnosis of chronic conditions, using a combination of biomeasures and self-reports. I find that individuals who are more positive are more likely to be undiagnosed for their hyperglycemia, but not hypertension. I relate this finding to theories of doctor-patient interaction, as well as differences in medical procedures for diagnosing these two chronic conditions. I conclude by offering possibilities for sociological research on personality, arguing that issues related to personality cut across existing subfields of the discipline, and that these issues relate to key questions in sociological theory.
Keywords: Adult children; Health Conditions and Status; Healthcare; Methodology

Social Resource Factors that Influence Cognitive Functioning of Aging Black Adults - Swett, Laura (The Catholic University of America, 2015)
Social workers have found that aging adults are often challenged by reduced cognitive functioning, which impacts their health and mental health. Recent advances in knowledge indicate that social resources such as quality of emotional support and social integration can slow cognitive decline. Aging Black persons are twice more likely to have cognitive impairment than aging White persons. However, the majority of studies investigating associations or predictors of cognitive health are comprised of primarily White samples, and little is known regarding the effect of social resource factors on cognition in aging Black adults. Data for the study came from the 2010 wave of the Health and Retirement Study (HRS), an ongoing, longitudinal, population-based cohort study of adults ages 50 to 98. The analyzed sample was comprised of 338 men and 699 women who self-identified as African American/Black. Controlling for factors known to influence cognitive functioning, a multiple regression analysis of four categories of social resources was conducted, by gender, to determine their effect on global cognitive functioning: quality of social supports, social networks, social integration, and social influence. For Black men, emotional support from family and frequency of contact with their children were predictive of global cognition. For Black women, emotional support from friends was positively predictive of global cognition. Further, locus of control perceived constraints was inversely related with global cognition in men, while education was positively predictive of global cognition across gender. The findings demonstrate that the evaluative aspects of social relationships (perceptions of support) are important in predicting cognitive functioning for both genders, and the structural components (types of relationships or frequency of contacts) are important in predicting cognitive functioning for men. Additionally, this study validated the role of gender as a moderator between quality of social supports and global cognition, and as a moderator between social networks and global cognition in aging Black persons. Research grounded in intersectionality theory yielded unique information for Black men and women that is applicable for evidence-based practice interventions. Practices targeting the reduction of constraints and strengthening family, friend, and children networks in men, and practices assisting women in strengthening their friendship networks, may mitigate their cognitive decline and increase their global cognition as they age.
Keywords: Demographics; Event History/Life Cycle; Gerontology; Health Conditions and Status; Healthcare; Methodology; Other; Women and Minorities

Sources of Increasing Differential Mortality Among the Aged by Socioeconomic Status - Barry Bosworth; Gary T. Burtless; Zhang, Kan (Boston College, 2015)
This paper uses data from the Health and Retirement Study (HRS) to explore the extent and causes of widening differences in life expectancy by socioeconomic status (SES) for older persons. We construct alternative measures of SES using educational attainment and average (career) earnings in the prime working ages of 41-50. We also use information on causes of death, health status and various behavioral indicators (smoking, drinking, and obesity) that are believed to be predictors of premature death in an effort to explain the causes of the growing disparities in life expectancy between people of high and low SES. The paper finds that: There is strong statistical evidence in the HRS of a growing inequality of mortality risk by SES among more recent birth cohorts compared with cohorts born before 1930. Both educational attainment and career earnings as constructed from Social Security records are equally useful indicators of SES, although the distinction in mortality risk by education is greatest for those with and without a college degree. There has been a significant decline in the risk of dying from cancer or heart conditions for older Americans in the top half of the income distribution, but we find no such reduction of mortality risk in the bottom half of the distribution. The inclusion of the behavioral variables and health status result in substantial improvement in the predictions of mortality, but they do not identify the sources of the increase in differential mortality. The policy implications of the findings are: Indexing the retirement age to increases in average life expectancy to stabilize OASDI finances may have unintended distributional consequences, because most mortality gains have been concentrated among workers in the top half of the earnings distribution. The fact that we cannot identify the sources of the increase in differential mortality contributes to uncertainty about the distributional effects of increases in the retirement age in future years.
Keywords: Demographics; Expectations; Health Conditions and Status; Methodology

Spousal Effects in Smoking Cessation: Matching, Learning, or Bargaining? - McGeary, Kerry Anne (Eastern Economic Journal, 2015)
Previous research studying the correlation in smoking behavior between spouses has discounted the role of bargaining or learning. Using the Health and Retirement Study, which contains information on smoking cessation and spouse s preferences, this paper presents an essential investigation of the impact of spousal bargaining or learning on the decision to cease smoking. We find that, regardless of gender, when one member of a couple ceases smoking this induces the other member to cease smoking through bargaining. Further, we find that women demonstrate either altruistic behavior toward a spouse who has suffered a health shock, or learning from their spouse s health shock.
Keywords: Health Conditions and Status; Methodology; Net Worth and Assets

Subjective health expectations - Kim P. Huynh; Jung, Juergen (Journal of Policy Modeling, 2015)
Subjective health expectations are derived using data from the U.S. Health and Retirement Study (HRS). We first use a Bayesian updating mechanism to correct for focal point responses and reporting errors of the original health expectations variable. We then test the quality of the health expectations measure and describe its correlation with various health indicators and other individual characteristics. Our results indicate that subjective health expectations do contain additional information that is not incorporated in subjective mortality expectations and that the rational expectations assumption cannot be rejected for subjective health expectations. Finally, the data suggest that individuals younger than 70 years of age seem to be more pessimistic about their health than individuals in their 70s. 2015 Society for Policy Modeling.
Keywords: Employment and Labor Force; Expectations; Health Conditions and Status; Healthcare; Methodology; Other

Symptom Trends in the Last Year of Life From 1998 to 2010 A Cohort Study - Adam E Singer; Meeker, Daniella; Joan M Teno; Lynn, Joanne; June R Lunney; Karl A Lorenz (Annals of Internal Medicine, 2015)
Background: Calls for improvement in end-of-life care have focused attention on the management of pain and other troubling symptoms at the end of life. Objective: To describe changes in pain intensity and symptom prevalence during the last year of life from 1998 to 2010. Design: Observational study. Setting: The HRS (Health and Retirement Study), a nationally representative longitudinal survey of community-dwelling U. S. residents aged 51 years or older. Participants: 7204 HRS participants who died while enrolled in the study and their family respondents. Measurements: Proxy-reported pain during the last year of life and other symptoms for at least 1 month during the last year of life. Trends in pain intensity and symptom prevalence were analyzed for all decedents and within the categories of sudden death, cancer, congestive heart failure or chronic lung disease, and frailty. Results: Between 1998 and 2010, proxy reports of the prevalence of any pain increased for all decedents from 54.3 (95 CI, 51.6 to 57.1 ) to 60.8 (CI, 58.2 to 63.4 ), an increase of 11.9 (CI, 3.1 to 21.4 ). Reported prevalences of depression and periodic confusion also increased for all decedents by 26.6 (CI, 14.5 to 40.1 ) and 31.3 (CI, 18.6 to 45.1 ), respectively. Individual symptoms increased in prevalence among specific decedent categories, except in cancer, which showed no significant changes. The prevalence of moderate or severe pain did not change among all decedents or in any specific decedent category. Limitation: Use of proxy reports and limited information about some patient and surrogate variables. Conclusion: Despite national efforts to improve end-of-life care, proxy reports of pain and other alarming symptoms in the last year of life increased from 1998 to 2010.
Keywords: Health Conditions and Status; Methodology; Retirement Planning and Satisfaction

Testing for State Dependence in Binary Panel Data with Individual Covariates by a Modified Quadratic Exponential Model - Francesco Bartolucci; Nigro, Valentina; Pigini, Claudia (Econometric Reviews, 2015)
AbstractWe propose a test for state dependence in binary panel data with individual covariates. For this aim, we rely on a quadratic exponential model in which the association between the response variables is accounted for in a different way with respect to more standard formulations. The level of association is measured by a single parameter that may be estimated by a Conditional Maximum Likelihood (CML) approach. Under the dynamic logit model, the conditional estimator of this parameter converges to zero when the hypothesis of absence of state dependence is true. This allows us to implement a t-test for this hypothesis which may be very simply performed and attains the nominal significance level under several structures of the individual covariates. Through an extensive simulation study, we find that our test has good finite sample properties and it is more robust to the presence of (autocorrelated) covariates in the model specification in comparison with other existing testing procedures for state dependence. The proposed approach is illustrated by two empirical applications: the first is based on data coming from the Panel Study of Income Dynamics and concerns employment and fertility; the second is based on the Health and Retirement Study and concerns the self reported health status.
Keywords: Methodology

Testing for time-invariant unobserved heterogeneity in generalized linear models for panel data - Francesco Bartolucci; Belotti, F.; Peracchi, F. (Journal of Econometrics, 2015)
Recent literature on panel data emphasizes the importance of accounting for time-varying unobservable individual effects, which may stem from either omitted individual characteristics or macro-level shocks that affect each individual unit differently. In this paper, we propose a simple specification test of the null hypothesis that the individual effects are time-invariant against the alternative that they are time-varying. Our test is an application of Hausman (1978) testing procedure and can be used for any generalized linear model for panel data that admits a sufficient statistic for the individual effect. This is a wide class of models which includes the Gaussian linear model and a variety of nonlinear models typically employed for discrete or categorical outcomes. The basic idea of the test is to compare two alternative estimators of the model parameters based on two different formulations of the conditional maximum likelihood method. Our approach does not require assumptions on the distribution of unobserved heterogeneity, nor it requires the latter to be independent of the regressors in the model. We investigate the finite sample properties of the test through a set of Monte Carlo experiments. Our results show that the test performs well, with small size distortions and good power properties. We use a health economics example based on data from the Health and Retirement Study to illustrate the proposed test.
Keywords: Health Conditions and Status; Methodology

Three essays in health econometrics and health economics - Parish, William James (The University of North Carolina at Greensboro, 2015)
This dissertation makes contributions to the field of health econometrics as well as the field of health economics. Chapter II presents a review of the "Cake Debates" literature. I also describe a generic econometric framework, which I use to clarify some points of controversy in the literature. Extant approaches to endogeneity in two-part models have failed to consider "separability." Chapter III presents a novel estimator that accounts for endogeneity without imposing "separability." Chapter IV presents a mediation analysis that explores whether improvements in beneficiary health can explain the negative relationship between Medicare Part D and the use of hospital care.
Keywords: Healthcare; Medicare/Medicaid/Health Insurance; Methodology

Three essays on public economics and policy - Li, Xiaoxue (Syracuse University, 2015)
This dissertation studies the effects of public programs that target at disadvantaged population. In particular, I examine the effects of these programs on individual well-being and whether these programs lead to behavior distortions. The dissertation consists of three essays that focus on different policy contexts and different populations. In the first essay, I examine the effects of an active labor market program on the labor market outcomes of veterans. In the 1990s, the US Department of Defense implemented the Transition Assistance Program (TAP) to help military personnel transition to the civilian labor market. The program provides career counseling, employment workshops, and information briefing on educational and medical benefits through the Department of Veterans Affairs. The goal of this study is to measure the long-run effects of TAP on the labor market outcomes of veterans. To identify these effects, I exploit variation in program accessibility generated by its initial rollout process. Using data from the veterans supplement to the Current Population Survey, survey years 2001, 2003 and 2005, I find that TAP improves the labor market outcomes of veterans, measured approximately ten years after their separation from the military. The effects of TAP on labor market outcomes vary across veterans with different lengths of military experience, and these effects attenuate over time. One possible mechanism is that TAP encourages use of the GI Bill, a program that provides tuition reimbursement and a monthly allowance to attend institutions of higher education. Moreover, the effect of TAP is concentrated among participants who, based on self-reports, find TAP most helpful in career related services. In the second essay, I examine linkages between Medicaid availability, insurance coverage for pregnant women, use of prenatal care and the health outcomes of newborns. Medicaid coverage for pregnant women would potentially improve health outcomes of newborns by providing medical services at no cost. At the same time, Medicaid provides an incentive for eligible individuals to drop private insurance coverage. I exploit variation from two federal Medicaid expansions in mid-1980s, which eliminated the eligibility discontinuity across age groups. The main data come from the National Hospital Discharge Survey and the Vital Statistics Birth Records. I employ a difference-in-differences method. Findings suggest that the expansions led to a relative increase in Medicaid coverage for women from the immediately affected age group by a significant 6.5 percentage points. However, up to 60% of new beneficiaries would have been covered by private insurance, absent of the expansions. Findings do not reveal significant improvement in birth outcomes, or increase in prenatal care utilization. In the third essay, I examine the effect of Medicaid on the asset holding behavior of the elderly. Medicaid provides coverage for nursing home care to elderly with limited resources. The eligibility rule potentially creates an incentive for the elderly to reduce their asset by making transfers to children. This study provides empirical evidence for the effect of Medicaid nursing home care policy on elderly's asset allocation. I exploit a policy change in 2006, the Deficit Reduction Act 2005, which imposed stricter penalty to asset transfer behavior when determining Medicaid eligibility. Using data from the Health and Retirement Survey, I employ a difference-in-differences method. I find that the elderly who anticipated nursing home entry significantly reduced asset transfer behavior by 3.2 to 4 percentage points, in response to the policy change. The result is robust across demographic groups and more pronounced for the elderly with the highest nursing home entry risk. The findings provide evidence of moral hazard in the public insurance market: the elderly would game with the system in anticipation of nursing home needs.
Keywords: Demographics; Employment and Labor Force; Health Conditions and Status; Healthcare; Methodology; Public Policy

Three Essays on the Supply of Long-Term Care Services to the Elderly in the U.S - Arora, Kanika (Syracuse University, 2015)
Situated in the context of a rapidly aging population, this dissertation examines the implications of supplying long-term care (LTC) services to the elderly in the United States. The first two essays investigate private costs of LTC assistance borne by adult children of elderly parents. In contrast, the third essay focuses on the cost of publicly-provided, formal LTC services. The first essay analyzes whether adult children devote less time to exercise as time allocation in parental caregiving increases. The empirical model is a system of four correlated equations, where the dependent variables are hours spent caregiving, frequency of moderate and vigorous physical activity, and hours spent in paid work. I use pooled cross-sectional data from the Health and Retirement Study (HRS) for this analysis. Results from joint estimation of the four equations indicate limited evidence of a competition between time spent in caregiving and frequency of physical activity. Parental factors that increase allocation of care time to parents do not comprehensively induce reductions in the frequency of any type of physical activity, nor in hours of work, among either men or women. The second essay goes beyond time resources and examines whether dementia onset in parents leads to a reduction in adult children's household wealth. Towards this, I construct a longitudinal dataset from seven waves of HRS. Estimates from unconditional quantile regressions indicate that parental dementia substantially reduces household wealth of an unmarried adult child in the upper quantiles of the wealth change distribution in the first two years after parental diagnosis. These effects are more pronounced for unmarried adult children without siblings. Further, this response is observed to persist in the subsequent time period as well. An examination of mechanisms suggests that both, losses in labor income and nursing home expenditures, may play a role in leading to wealth declines. This paper makes two contributions: first, it focuses on a broader outcome of private cost, and second, unlike previous studies, it does not limit the analysis to adult children who are informal caregivers. The final essay examines the cost implications of publicly provided formal care services. Medicaid's Personal Care Services (PCS) State Plan benefit is a key mechanism through which states provide personal assistance services to eligible beneficiaries. But, it is widely claimed that states are reluctant to adopt the program over fears of runaway spending. Surprisingly, there has been very little empirical work on examining the effect of the PCS State Plan benefit on Medicaid expenditures. Using aggregate state-level data from 1975 through 2009, this study finds that PCS State Plan adoption had no overall effect on Medicaid expenditures, except briefly during the early-growth years in 1980s. Further, findings suggest that states make decisions to adopt the program based on financial experiences of other adopting states. This study provides evidence consistent with the interpretation that when faced with the dilemma of balancing increased access and uncontrolled expenditures, state officials adapt the design of an entitlement benefit in an effort to make it less expensive. In its entirety, the dissertation provides new thinking on two dominant themes in conventional long-term care research: "caregiver burden" and "woodwork effect". In particular, the results of the first and third essay question the presence of "caregiver burden" and "woodwork effect" respectively, while the third essay challenges the pervasiveness of "caregiver burden" among unmarried adult children. These findings, which in some aspect are unexpected in the context of existing literature, have important implications for policy intervention and the direction of future research efforts in this area.
Keywords: Adult children; Health Conditions and Status; Healthcare; Medicare/Medicaid/Health Insurance; Methodology; Net Worth and Assets; Public Policy

Treatment Type and Demographic Characteristics as Predictors for Cancer Adjustment: Prospective Trajectories of Depressive Symptoms in a Population Sample - Burton, C. L.; Isaac R Galatzer-Levy; George A. Bonanno (Health Psychology, 2015)
Objective: Prospectively identifying individuals at heightened risk for depression can alleviate the disease burden of distal physical and mental health consequences after cancer onset. Our objective was to identify heterogeneous trajectories of adjustment in cancer patients, using treatment-type as a predictor. Methods: Participants were followed for 6 years within the Health and Retirement Study (HRS), a prospective population-based cohort study. The sample consisted of 1,294 middle-aged participants who were assessed once before and 3 time points after their report of an initial cancer diagnosis. In addition to self-reported depressive symptoms, subjects indicated receipt of surgical, radiological, or chemical interventions as part of their usual oncological care. Results: Four symptom trajectories were identified with Latent Growth Mixture Modeling: an increasing depression (10.5 ), chronic depression (8.0 ), depressed-improved (7.8 ), and stable-low depression (73.7 ). A conditional model using participants with available predictor data (n = 545) showed individuals in the emerging depression class were significantly more likely to have received chemo/medication therapy when compared with the remitting depression, stable-low, and chronic depression classes. Participants in the chronic and depressed-improved classes generally had worse baseline health, and the depressed-improved were also younger in age. Conclusion: Patients who exhibited increasing depressive symptoms had a greater probability of receiving chemo/medication therapy than any other adjustment trajectory group, although the majority of chemotherapy patients did not exhibit depressive symptom changes. These data underscore the diversity of ways that patients adjust to cancer, and suggest cancer treatment, baseline health, and age may influence long-term patterns of psychological adjustment.
Keywords: Health Conditions and Status; Healthcare; Methodology; Other

Using mixed methods to identify the characteristics of older fraud victims - DeLiema, Marguerite (University of Southern California, 2015)
In 2011, 7.3% of U.S. adults ages 65-74 and 6.5% of adults ages 75 and older were victims of financial fraud (Anderson, 2013). In addition to the billions of dollars lost annually to scams, indirect societal costs include paying for the care and support of elders who lost their life savings, and the expense of investigating cases and prosecuting offenders. One of the first steps in stopping fraud is determining who is most vulnerable, yet the research literature on risk factors presents a conflicting narrative. Some research studies and consumer protection agencies report that older adults are the most vulnerable age group due to greater social isolation and impairments in financial decision-making however, national prevalence studies have found that elders are the least likely to experience fraud. According to the Financial Fraud Research Center (2012), research identifying the specific risk factors that make elders susceptible to fraud is important to inform policies and where to target resources. After describing the prevalence, cost, and mechanisms of fraud, this dissertation discusses multiple theoretical explanations for why older adults are vulnerable. Chapter I presents a temporospatial framework for fraud based on the routine activity theory (Cohen & Felson, 1979) and an ecological theory of elder financial exploitation (Rabiner, O'Keefe, & Brown, 2004). The adapted model proposes that targets and scam artists are nested within the broader social and political macrostructure comprised of public policy and legislation on consumer protection, prevention/education efforts to reduce fraud, fraud reporting mechanisms, and society's values, beliefs and attitudes about older adults. In the following three empirical chapters, a mixed methods approach is used to identify the demographic, socioeconomic, psychological and cognitive characteristics of older fraud victims using the nationally-representative Health and Retirement Study (HRS) and a sample of victims in Los Angeles County. Researchers have observed that different types of fraud target different socio-demographic groups (Pak & Shadel, 2011). To identify heterogeneity among the respondents who reported fraud in the HRS, Chapter III employs latent class analysis (LCA) to test the hypothesis that older victims of fraud vary in terms of their socioeconomic and demographic characteristics. Two distinct victim classes (i.e., typologies, profiles) emerged from the analysis. Based on the distribution of socioeconomic and demographic characteristics within each group, Class 1 was descriptively labeled " high-SES middle-age married adults, " and Class 2 was labeled " low-SES older widowed females ." The high-SES middle-aged married adult group was larger than the low-SES older widowed female group, suggesting that the former group of victims is more prominent in the U.S. population over age 50. High-SES middle-aged married adults had higher average levels of cognitive functioning and also experienced a higher average number of stressful life events in the past five years compared to low-SES older widowed females . Using a national sample, this analysis provides comparable results to earlier studies that identified two victim typologies using a smaller sample of older victims identified by law enforcement: "bogus prize promotion" and "investment fraud" victim (Pak & Shadel, 2011; Financial Industry Regulatory Authority; 2006). The main finding of Chapter IV is that although fraud and financial abuse victims share many of the same physiological, environmental, demographic, and psychosocial characteristics, they differ in that fraud victims have significantly higher Mini Mental State Exam scores, better mobility, and are more likely to be childless. A proposed explanation for the similarities is that exploitation has less to do with the characteristics and risk factors associated with the victim, and more to do with the people surrounding the victim (or lack thereof). In othe words, the structure of the victim's social network determines whether he or she is more likely t be a victim of fraud by strangers or financial abuse by family and friends. This analysis illuminates areas where intervention and prevention strategies may differ between each type of exploitation. This dissertation contributes to the literature in several important ways. First, it helps clarify the relationship between fraud susceptibility, age, and socioeconomic status among adults ages 50 and older in the U.S. Second, it uses prospective (pre-fraud) data on individuals to determine whether the purported risk factors for fraud--loneliness, poor cognitive functioning, stressful life events--actually do increase like likelihood of victimization later on. Third, findings from the latent class analysis support previous research using victim complaint data to categorize victims based on their SES and demographic characteristics. And fourth, the qualitative findings in this study reveal the tremendous financial cost of fraud, and also the importance of friends and family members in protecting older adults from predatory strangers. (Abstract shortened by UMI.)
Keywords: Consumption and Savings; Employment and Labor Force; Gerontology; Health Conditions and Status; Healthcare; Methodology; Public Policy

Well-being as a measure of inequality among the retirement-age population: An examination of the role of place, migration, and socioeconomic status in shaping happy and healthy older Americans - Henly, Megan (Sociology, 2015)
The proportion of the U.S. population comprised of seniors – those aged 65 and older – is projected to increase from 13% presently to 20% by 2030. With this demographic change, it is important to consider how older residents are faring, which older residents do best, and what communities are doing to support this population. Rather than examining income or wealth as a dependent variable, I predict two measures of well-being among older U.S. residents– one subjective and one objective. By linking survey data of the 50 and older population from the 2010 Health and Retirement Study (HRS) to a variety of county-level statistics from several government databases, this dissertation characterizes each respondent's community with respect to its demographics, economic structure, natural environment, social norms, and presence of community institutions. I examine the impact of individual and community characteristics, as well as whether someone had migrated within the last four years, on predicting well-being. My findings suggest that certain community variables may influence well-being – namely that social institutions may need to be tailored to support the needs of older residents and that counties we think of as privileged counties (with respect to the racial and socioeconomic make-up of its residents) may need to do more to serve older residents. In sum though, these county characteristics have a very minimal impact in predicting the well-being of older residents. The predictors that seemed to matter more were those of the individuals aged 50 and over themselves: their demographic characteristics, employment status, health, and social connectedness all mattered with respect to understanding which individuals were doing well. Whether someone had moved to a new county in the last four years did not appear to offer value to predicting well-being in a causal manner.
Keywords: Employment and Labor Force; Medicare/Medicaid/Health Insurance; Methodology; Public Policy; Retirement Planning and Satisfaction

What impacts life satisfaction of aging adults following stressful life events?: An examination of the buffering effect of personal resources - Barragan, Cassandra (Wayne State University, 2015)
Purpose: Existing research has shown that elders experience changes in their life satisfaction following stressful life events. There is an abundance of literature supporting the predictive nature of not only stressful life events on life satisfaction, but social support, autonomy, and financial security. What the literature is lacking, is examination of the buffering effect of social support, autonomy, and financial security on the relationship between stressful life events and life satisfaction. This study hypothesizes that increases in social support, autonomy, and financial security will buffer the impact of SLEs for elders and thus, they will experience increases in their life satisfaction over time. It is also expected that social support and financial security will buffer differently among Black and White elders. Methods: The public use files of the Health and Retirement Study (HRS) between the years 2006 and 2012 are used to explore the interaction between social support, autonomy, and financial security with stressful life events and the impact on life satisfaction. Linear regression are conducted to explore each buffering impact on life satisfaction over time. Results: The research findings in this dissertation demonstrate that the changes in personal resources; social support, autonomy, and financial security; play an important role in changes in life satisfaction. Additionally, Black and White elders are impacted differently by changes in financial security. In general, the results from this study demonstrate that individuals who have declines in their personal resources following stressful life events also experience declines in their life satisfaction.
Keywords: Adult children; Demographics; Health Conditions and Status; Healthcare; Methodology; Net Worth and Assets; Other; Retirement Planning and Satisfaction; Women and Minorities

A woman's work is never done? Earlier life child, marital, and work history and older women's relationship to the paid labor force - Shattuck, Anne M. (University of New Hampshire, 2015)
In the past 40 years, women in the U.S. have experienced higher rates of labor force participation and higher rates of divorce and single motherhood. How these changes will affect women when they reach old age is not yet understood. Using a pooled sample from the Health and Retirement Study of 4,350 women born between 1931 and 1943, this dissertation assesses patterns of women's work/retirement circumstances at age 66–68 and evaluates the relationship between those patterns and women's earlier life marital, work, and childrearing history. Latent class analysis revealed four distinct classes of older women: the "retired well" (57.6% of the sample) were not working for pay but were in good or excellent health and had household wealth in the top 75%. "Retired unwell" women (14% of the sample) were also not working but were in fair/poor physical health and had very low household wealth. The "working advantaged" (17.1% of the sample) were healthy women still working, primarily in professional/managerial occupations, earning above median wages, and having the highest median levels of household wealth of the four groups. The "working average" class (11.7% of the sample) were women still in the labor force, overwhelmingly in sales/labor/service jobs and making below median wages. This group had a 1 in 5 chance of being in fair/poor health and a 1 in 3 chance of being in the bottom wealth quartile. Multivariate latent class analysis including covariates revealed several significant relationships between women's earlier life history and latent class at age 66–68. Women who had spent any time as a single mother or who had ever been divorced had higher odds of being retired unwell or working advantaged than retired well. Women with strong attachment to the labor force across their lives were less likely to be retired unwell and more likely to be either working advantaged or working average at age 66–68. Although single motherhood, work history, and marital history had independent effects on women's late life status, race/ethnicity, education, and current marital status had stronger effects. Implications for future cohorts of older women are discussed.
Keywords: Employment and Labor Force; Methodology; Policy

Changes in Memory before and after Stroke Differ by Age and Sex, but Not by Race - Qianyi Wang; Mejía-Guevara, Iván; Pamela M. Rist; Stefan Walter; Benjamin D Capistrant; M. Maria Glymour (Cerebrovascular Diseases, 2014)
Background: Post-stroke memory impairment is more common among older adults, women and blacks. It is unclear whether post-stroke differences reflect differential effects of stroke per se or differences in prestroke functioning. We compare memory trajectories before and after stroke by age, sex and race. Methods: Health and Retirement Study participants aged 50 years (n = 17,341), with no stroke history at baseline, were interviewed biennially up to 10 years for first self- or proxy-reported stroke (n = 1,574). Segmented linear regression models were used to compare annual rates of memory change before and after stroke among 1,169 stroke survivors, 405 stroke decedents and 15,767 stroke-free participants. Effect modification was evaluated with analyses stratified by baseline age ( 70 vs. 70), sex and race (white vs. nonwhite), and using interaction terms between age/sex/race indicators and annual memory change. Results: Older ( 70 years) adults experienced a faster memory decline before stroke (-0.19 vs. -0.10 points/year for survivors, -0.24 vs. -0.13 points/year for decedents, p 0.001 for both interactions), and among stroke survivors, larger memory decrements (-0.64 vs. -0.26 points, p 0.001) at stroke and faster memory decline (-0.15 vs. -0.07 points/year, p = 0.003) after stroke onset, compared to younger adults. Female stroke survivors experienced a faster prestroke memory decline than male stroke survivors (-0.14 vs. -0.10 points/year, p 0.001). However, no sex differences were seen for other contrasts. Although whites had higher post-stroke memory scores than nonwhites, race was not associated with rate of memory decline during any period of time; i.e. race did not significantly modify the rate of decline before or after stroke or the immediate effect of stroke on memory. Conclusions: Older age predicted worse memory change before, at and after stroke onset. Sex and race differences in post-stroke memory outcomes might be attributable to prestroke disparities, which may be unrelated to cerebrovascular disease. 2014 S. Karger AG, Basel.
Keywords: Health Conditions and Status; Methodology

Cumulative Childhood Adversity, Educational Attainment, and Active Life Expectancy Among U.S. Adults - Jennifer Karas Montez; Mark D Hayward (Demography, 2014)
Studies of the early-life origins of adult physical functioning and mortality have found that childhood health and socioeconomic context are important predictors, often irrespective of adult experiences. However, these studies have generally assessed functioning and mortality as distinct processes and used cross-sectional prevalence estimates that neglect the interplay of disability incidence, recovery, and mortality. Here, we examine whether early-life disadvantages both shorten lives and increase the number and fraction of years lived with functional impairment. We also examine the degree to which educational attainment mediates and moderates the health consequences of early-life disadvantages. Using the 1998 2008 Health and Retirement Study, we examine these questions for non-Hispanic whites and blacks aged 50 100 years using multistate life tables. Within levels of educational attainment, adults from disadvantaged childhoods lived fewer total and active years, and spent a greater portion of life impaired compared with adults from advantaged childhoods. Higher levels of education did not ameliorate the health consequences of disadvantaged childhoods. However, because education had a larger impact on health than did childhood socioeconomic context, adults from disadvantaged childhoods who achieved high education levels often had total and active life expectancies that were similar to or better than those of adults from advantaged childhoods who achieved low education levels.
Keywords: Adult children; Demographics; Health Conditions and Status; Methodology

Dependence in binary outcomes: A quadratic exponential model approach - Maboobeh Zangeneh Sirdari; M. Ataharul Islam; Norhashidah Awang (Bulletin of the Malaysian Mathematical Sciences Society, 2014)
Repeated measurements data appear in many applications of study subjects such as correlated binary data. Most of studies often focus on the dependence of marginal response probabilities. There is a lack of study based on joint probability distributions that yield estimation and test procedure using conditional probabilities, marginal means and correlated binary data. In this paper, the quadratic exponential form model has been extended for a Markov chain framework. This study extends the quadratic exponential model for displaying the estimation procedure for the nature and extent of dependence among the binary outcomes. In addition, a test procedure is extended to test for the goodness of fit of the model as well as for testing the order of the underlying Markov chain. The proposed model and the test procedures have been examined thoroughly with an application to elderly population data from the Health and Retirement Study (HRS) data.
Keywords: Methodology; Other

Depression and older, community-dwelling, African American women - Tamika C. Baldwin (Morgan State University, 2014)
Using data from the Health and Retirement Study (HRS) 2010 wave, this research examined depression among community-dwelling, African American women, age 50 and over. Depression among this population was examined in relation to age, social support, religion, caregiving, and physical health. Intersectionality and social construction were used as theoretical frameworks for the study. Drawn from an original sample of 22,034 individuals, the sample for this research consisted of 2,249 respondents. Multiple logistic regression was used to predict depression among community-dwelling African American women. Findings indicated significant relationships between depression and age, social support, and physical health. However, religion and caregiving were not found to be significant predictors of depression among this population. Implications for future research, practice and policy are also discussed.
Keywords: Adult children; Health Conditions and Status; Healthcare; Methodology; Women and Minorities

Determinants of spouse/partner informal caregiving and its impacts on informal caregivers' physical, psychological health and economic well-being: evidence from the health and retirement study - Wang, Ming Sheng (University of Illinois at Urbana-Champaign, 2014)
State policies have recently trended towards encouraging home and community-based services (HCBS) over institutionalized care because of the relative higher costs and lower quality in institutions. Studies suggest, however, that this cost-saving strategy has hidden individual and societal costs that may only surface when the informal caregivers grow older themselves. For example, intense caregiving can negatively impact the caregivers' long-term physical, mental/psychological, and economic well-being. However, the determinants of caregiving duration and their impacts on caregivers' later physical health and psychological health and economic well-being have never been examined holistically. Prior studies touching on these issues have narrowly emphasized the influence of either the elderly recipients' or caregivers' characteristics on informal caregiving and caregivers' outcomes. To address these limitations, this study examined the following questions: Q1) What are the determinants of informal caregivers' time spent on caregiving? Q2) How do caregiving hours impact informal caregivers' later physical health, psychological health, and economic well-being? Furthermore, this study examined the associations between predisposing, enabling, and need factors from the viewpoints of both care recipients and caregivers. It also examines differing lengths of caregiver commitments and how they impact the caregivers' outcomes (physical health, psychological health, and economic well-being) in the future across various caregiver characteristics. Using longitudinal, nationally representative data of the Health and Retirement Study from two waves (2008 and 2010), I looked at 496 dyad units (including care recipients and couples/partners as caregivers) of community-dwelling elderly to evaluate the impact of relative factors on the length of informal caregiving hours and whether providing more caregiving hours cause greater negative impacts on caregivers' later physical health, psychological health, and economic well-being. To answer Q1, I used a hierarchical ordinal logistic regression model to identify predisposing, enabling, and need factors from both care recipients and care recipients' and their impacts on caregiving hours. For Q2, multivariate ordinal logistic regression or ordinal least square (OLS) regression models were separately used to examine the impact of three durations of caregiving hours (providing fewer, medium, and longer caregiving hours) at Time 1 on caregivers' physical, psychological, and economic well-being at Time 2. Findings indicate that recipients with higher functional impairment (activities of daily living (ADL) and instrument activities of daily living (IADL)) and usage of home care service by caregivers have a significant, negative impact on caregivers' length of caregiving hours. In addition, caregivers who are older and employed are more likely to provide a greater number of hours. Furthermore, caregivers who provide more hours are more likely to have a higher level of chronic illness (objective physical health). On the other hand, I found no significant associations between caregiving intensity and self-rated health (subjective physical health), psychological health, or household wealth (including assets and income). The analysis considering predisposing, enabling, and need factors from both care recipients and caregivers to unravel the complicated caregiving phenomena are presented. Implications for research, practice, and policy are drawn based on the results.
Keywords: Healthcare; Methodology; Public Policy

Dynamic Implications of Subjective Expectations: Evidence from Adult Smokers - Wang, Yang (American Economic Journal: Applied Economics, 2014)
We set up a dynamic discrete choice model with subjective expectations data to explain adult smokers' find important differences between subjective survival probabilities and those estimated using observed mortality data. Subjectively, individuals attach less weight to their health conditions and smoking choices and more weight to such factors as age, race, and parents' longevity. Moreover, adult smokers are found to care more about their health and to be more forward-looking than predicted by a rational expectations framework. We further show the importance of unobserved heterogeneity in agents' subjective survival probabilities, and discuss policy implications of subjective expectations.
Keywords: Consumption and Savings; Expectations; Health Conditions and Status; Methodology; Other

Dynamic models of individual and household retirement behavior - Merkurieva, Irina S. (The University of Wisconsin - Madison, 2014)
Chapter 1: Estimating the Returns of Attending a Selective University on Earnings using Regression Discontinuity with Multiple Admission Cutoffs. Abstract: The first chapter estimates the effect attending a selective university has on earnings. I show that using the admission cutoffs of two related majors offered by selective universities is enough to identify the isolated "university effect" on wages. To do so, I propose a novel identification framework using the cutoffs of two related majors in a regression discontinuity design that distinguishes the effect of graduating from a selective university from the effects of the confounding factors correlated with the student application and enrollment decision. This design requires a system with strict cutoffs and simultaneous decision making of university and major upon application. The university admission system in Chile has a strict admission criteria based solely on the university selection test and high school grades, and has students choose their school and major simultaneously. This admission system leads naturally to a regression discontinuity design because we can compare the earnings of those above and below the cutoff to estimate the "university effect". My main findings suggest that, on average, attending a selective university in Chile significantly increases earnings, that is, selective universities not only select the best students, but also play a role increasing their future earnings. Chapter 2: The Effects of Private High Schools, University Rankings and Employer Learning on Wages in Chile. Abstract: The second chapter studies the effects of attending a private high school, university ranking and employer learning on wages. My empirical strategy is based on the Mincer-type wage regressions. I carry out my analysis using individual-level data from Chile. I find a large and significant effect on wages at the beginning of workers' careers from attending a private high school and from attending a highly ranked university. These findings can be rationalized by the statistical discrimination and employer learning model since the effects of attending a private high school or highly ranked university decrease with experience. I construct an employer learning model to explain these decreases and find employers decrease by fifty percent the weight they place on university ranking when setting wages in three years. My findings further indicate that incorporating university admission test percentile rankings in employment applications can significantly improve the market's ability to appropriately assign wages by decreasing the information gap between potential employees and employers. Chapter 3: College-Major Choice to College-Then-Major Choice. Abstract: Many countries use college-major-specific admissions policies that require a student to choose a college-major pair jointly. Motivated by potential student-major mismatches, we explore the equilibrium effects of postponing student choice of major. We develop a sorting equilibrium model under the college-major-specific admissions regime, allowing for match uncertainty and peer effects. We estimate the model using Chilean data. We introduce the counterfactual regime as a Stackelberg game in which a social planner chooses college-specific admissions policies and students make enrollment decisions, learn about their fits to various majors before choosing one. We compare outcomes and welfare under the two different regimes.
Keywords: Adult children; Cross-National; Employment and Labor Force; Methodology; Other; Public Policy; Retirement Planning and Satisfaction

The economic security of an aging minority population: A profile of Latino baby boomers to inform future retirees - Zachary Gassoumis (University of Southern California, 2014)
The United States is facing dramatic demographic changes due to the aging of the Baby Boom Generation and increasing diversity, including rapid growth of the Latino population. Questions have been raised regarding the economic security of the aging baby boomers' generational cohort once they retire, which are of particular relevance to minority and Latino members of the cohort. Latinos tend to have lower levels of financial security than their white, non-Latino counterparts, but there is little research that examines individuals who fall into the intersection of these two groups: the Latino baby boomers. Because Latino boomers are a largely hidden population, their economic status and prospects are difficult to estimate. The first empirical chapter (Chapter 2) looks at the characteristics of the Baby Boomer population living in the 50 U.S. states and the District of Columbia, broken down by Latino ethnicity and citizenship status. Drawing from several U.S. Census Bureau data sources, it revealed three key findings: 1) there were 80 million baby boomers in the U.S. in 2000--more than previously reported--of which 8.0 million (10%) were Latinos; 2) U.S.-born Latino boomers were more similar to non-Latino boomers in terms of demographic characteristics, whereas foreign-born citizens and non-citizens scored less well on key demographic indicators; and 3) compared to non-Latino baby boomers, U.S.-born Latino baby boomers had somewhat less favorable economic characteristics. The second empirical chapter identifies the magnitude of racial/ethnic structural disadvantage for income and wealth in the years preceding retirement for the Baby Boom Generation, then compares their structural disadvantage with that of members of the Silent Generation cohort when they were the same age. After adjusting for sociodemographic variables (age, gender, citizenship status, education, marital status, and labor force participation), the structural effects of race/ethnicity on income--using the American Community Survey--and wealth--using the Health and Retirement Study--were considerably reduced, confirming two of the chapter's four hypotheses; however, the expected reduction in structural effects from the Silent Generation to the Baby Boom Generation was seen for wealth but not for income, confirming only one of the remaining two hypotheses. This reduction of structural disparities in wealth from the Silent Generation to the Baby Boom Generation follows the expectation that these disparities would be reduced over time, which signals good news for the younger members of the Baby Boom Generation, Generation X, and future generational cohorts. But large gaps still exist between racial/ethnic groups, even after sociodemographic adjustment; future reduction in those structural inequalities can help decrease those gaps, an especially important consideration for low-income racial/ethnic minority groups. The third empirical chapter takes an initial step toward disaggregating by age the effect of naturalization on income growth. Using linear growth curve modeling on data from the Survey of Income and Program Participation's 2004 panel, it attempts to replicate past findings across the entire lifespan, but fails to detect an effect of naturalization on income growth; only non-citizens had a significantly higher level of income growth during the study period than U.S.-born citizens. In subsetting the analysis for older and younger working-age groups, an effect of naturalization was not detected for either group, and the positive effect for non-citizens was seen only for the younger age group. The predictor variables on the whole had minimal relationships with slope in the model, with less than 1% of variance explained in each model. Although a stronger effect of the predictor variables, including an effect of naturalization, may have appeared were more years of data available, it was not detected over the 4-year study period. Two unexpected findings were: 1) individuals in the younger sample who had naturalized before the study had higher intercepts than U.S.-born citizens but no such difference emerged in the older sample; and 2) in a bivariate context, those who naturalized during the study represented a socioeconomic midpoint of sorts--on racial/ethnic composition, education, and income--naturalized prior to the study. In sum, these chapters shed light on the Baby Boom cohort's characteristics and dynamics in the period leading up to their retirement age. This dissertation provides insights into the characteristics, demographic history, and socioeconomic patterns of the upcoming cohort of retirees. Implications of these findings have the potential to inform and to modify practice and policy for the next cohort: Generation X. The findings underscore the importance of reducing disparities in education and, to a degree, citizenship as a mechanism for countering the persistent effects of structural inequality on income. These insights have implications for both theory and policy and lay a foundation for a wide range of future research, which is discussed in the final chapter.
Keywords: Demographics; Income; Methodology; Net Worth and Assets; Women and Minorities

The Effect of Community-Based Services on Functional Limitations of American Older Adults in Retirement Community - So Jung Park; Kim, Min Hee (Korea Social Welfare Research, 2014)
Being discussed among the various environmental factors for the year, with an independent discourse on successful aging, we examine the relationship between health and community services for the elderly using American study. The review is limited in most cases to be vulnerable older people to explore the relationship between the two previous studies, which focused on the effectiveness of many individual services. The present study was derived using the Health and Retirement Study (1998 2008) panel data, and the use of the service pattern of the individual review of the relevant health service use patterns and trends. In addition, the effect of the use of service resources and informal health services were analyzed with the factors that affect the relationship between health map. Was limited to senior living senior housing community with information about the service analysis, we used the daily living skills scores about healthy level and trend are (instrumental). Configured to use the pattern for the official services (housework, care, care, transportation, meals) in the community through the cluster analysis results did not use all the services a large number of elderly (group 1), in addition to using all of the services that the elderly could be classified as elderly (groups 3 and 4), although the nature (group 2), most of the details to use the service. Analysis of the relation of the health services through a growth curve model (Growth Curve Model) results, in the group compared to the group with all of the services that are not used at all, the service tends to be deteriorated health. But if you take advantage of the informal resources around them showed that mitigation is steep trend deteriorating health. The significance of that is then used to present the major reasons for this study is that no magazine to help in maintaining the health community service use, its extent. Suggests that informal, to study the effect of an integrated formal resources and medical necessity of the service area to review the impact of community service than what it.
Keywords: Health Conditions and Status; Healthcare; Methodology; Public Policy

The Effect of Job Loss on Health: Evidence from Biomarkers - Pierre-Carl Michaud; Eileen M. Crimmins; Michael D Hurd (Bonn, Germany, Institute for the Study of Labor, 2014)
The effect of job loss on health may play an important role in the development of the SES-health gradient. In this paper, we estimate the effect of job loss on objective measures of physiological dysregulation using longitudinal data from the Health and Retirement Study and biomarker measures collected in 2006 and 2008. We use a variety of econometric methods to account for selection and reverse causality.Distinguishing between layoffs and business closures, we find no evidence that business closures lead to worse health outcomes. We also find no evidence that biomarker health measures predict subsequent job loss because of business closures. We do find evidence that layoffs lead to diminished health. Although this finding appears to be robust to confounders, we find that reverse causality tends to bias downward our estimates. Matching estimates, which account for self-reported health conditions prior to the layoff and subjective job loss expectations, suggest even stronger estimates of the effect of layoffs on health as measured from biomarkers, in particular for glycosylated hemoglobin (HbA1c) and C-reactive protein (CRP). Overall, we estimate that a layoff could increase annual mortality rates by 9.4 , which is consistent with other evidence of the effect of mass layoffs on mortality.
Keywords: Demographics; Employment and Labor Force; Health Conditions and Status; Methodology

The effect of state non-group health insurance market regulations on labor and insurance markets: From theory to policy - Lin, Lee-Kai (Indiana University, 2014)
Health insurance coverage among the working nonelderly population is highly concentrated on employer sponsored health insurance (ESI). State governments in the early 1990s and the Federal Health Insurance Portability and Accountability Act (HIPAA) of 1996 made efforts to provide health insurance to individuals who do not have access to ESI by regulating the non-group market. In the first chapter, I propose a theoretical framework to analyze the effects of state non-group health insurance market regulations on the market equilibrium and on the job choices focusing on the guaranteed issue, rating restriction and the combination of these two regulations. In the second chapter I estimate the impact of these regulations on the retirement decision by difference-in-difference regressions using data collected from the Health and Retirement Study (HRS) and the Current Population Survey (CPS). My results provide evidence that guaranteed issue significantly increases the retirement rate by 1.2 percentage points. Guaranteed issue several plans with rating restrictions also significantly increases retirement rate by 1.5 percentage points. Workers who have chronic health problems are more likely to retire in response to both types of regulations than the healthy. I study the effects of these state regulations on the non-group health insurance coverage and on the transition from group to non-group health plans in the third chapter. The results suggest that guaranteed issue alone encourages individuals to transition from group to non-group health coverage. If guaranteed issue, together with rating restrictions, is forced upon some of the health plans, the transition from group to non-group coverage would increase while the non-insured also increases. If all plans are guaranteed issue with rating restrictions, non-group coverages are not affected but more people become uninsured.
Keywords: Insurance; Methodology; Public Policy; Retirement Planning and Satisfaction

Effects of cost-related medication nonadherence on financial health and retirement decisions among adults in late midlife - Gail A Jensen; Yong Li (Journal of Pharmaceutical Health Services Research, 2014)
Objectives Suboptimal adherence to prescribed medications due to cost is known to adversely affect physical health. In this study, we examine whether cost-related nonadherence (CRN) also affects financial health , e.g. an individual's personal finances or the timing of their retirement. Methods We examine this issue for 2927 adults in late midlife with chronic medical conditions who participated in the Health and Retirement Study and who reported regularly taking medication(s) for their condition over the period 1994 to 2004. We hypothesize CRN may indirectly influence financial health by contributing to the occurrence of negative health shocks. We estimate two sets of models, one to quantify the effects of CRN on the occurrence of adverse health events, and another to quantify the effects of adverse health events on personal finances in 2004 and the timing of retirement. We then derive estimates of the indirect effects of CRN on financial health and on retirement decisions. Key findings Among adults in late midlife, CRN contributes significantly to reduced earnings and premature retirements. These effects happen because CRN raises the risk that serious health shocks occur over time, and such adverse events subsequently limit an individual's ability to continue working and accumulating wealth. Conclusions CRN can threaten more than just personal health. In late midlife, CRN can threaten an individual's ability to continue working and saving towards retirement.
Keywords: Employment and Labor Force; Health Conditions and Status; Healthcare; Methodology; Net Worth and Assets; Other; Retirement Planning and Satisfaction

Efficient Use of Commercial Lists in U.S. Household Sampling - Valliant, Richard; Hubbard, Frost; Lee, Sunghee; Chang, Chiungwen (Journal of Survey Statistics and Methodology, 2014)
Sampling households using commercial lists has the potential to reduce costs and efficiently identify some subgroups for which target sample sizes are desired. However, the information on the lists for demographics like age is usually incomplete and inaccurate. We demonstrate that this inexact information can still be used to improve the efficiency with which some, but not all, demographic subgroups can be located during sampling. The article also illustrates the use of nonlinear programming as a means for finding sample allocations that are subject to a variety of practical constraints. A commercial address list and data from the National Survey of Family Growth and the Health and Retirement Study are used to illustrate the calculation of allocations to strata of housing units defined by information on the list.
Keywords: Methodology

Essays in Urban and Labor Economics - Ringo, Daniel (University of Rochester, 2014)
This dissertation contributes to two literatures: Urban Economics and Labor Economics. In the first chapter I estimate the effect of home ownership on individual workers' unemployment and wage growth, as well as other labor market outcomes. Because of higher moving costs, home owners will be less willing than renters to relocate for work and could therefore face longer unemployment spells. To elaborate on this hypothesis, credited to Oswald (1996), I build a simple search model and obtain a set of labor market predictions to test. The current microeconomic literature has reached mixed results regarding home ownership's impact, with most studies concluding that home ownership reduces unemployment. I show that the instruments used are likely to be invalid because of, among other reasons, Tiebout (1956) type sorting into housing markets. I use an instrumental variable free of the endogeneity present in other work: the county level home ownership rate when and where the worker grew up. This IV affects workers' preferences for housing but not, conditional on my covariates, their labor market ability. My results indicate that home ownership is a significant hindrance to mobility, and homeowners suffer longer unemployment spells and slower wage growth because of it. In the second chapter I use a dynamic model of neighborhood choice to estimate household preferences over the demographic characteristics of a neighborhood. I focus on the racial mix, average income and housing price level of a neighborhood, and whether households prefer neighbors that are similar to themselves. Identification of these preferences is complicated by the social aspect of neighborhood amenities. A household's valuation of a particular choice (neighborhood) is a function of the choices other households in the market have made and will make in the future. I show that demographic characteristics of a neighborhood are therefore endogenous to neighborhood quality. Standard estimates of preferences over neighbors may be biased by the presence of such unobservable local amenities. I develop a framework to correct this problem based on a careful delineation of the information households could have access to before and after they make their decisions. The model I build has the advantage over the literature of being able to produce self-consistent predictions about demographic changes. I deal with the low frequency of observations in my data set, the decennial census, by simulating local housing markets between data collection periods. After controlling for type-specific preferences for the physical amenities of neighborhoods, I find a universal preference for higher income neighbors. In contrast to much of the literature, my results suggest white households have no aversion to minority neighbors. In the third chapter I estimate the effect of parental credit scores on the child's probability of attending and completing college. Parents in the US are increasingly supplementing the student loans available to their children with unsecured debt in their own name. This is the first paper on this topic to make use of direct observations of credit scores, rather than rely on proxies such as wealth shocks. I find that good parental credit significantly improves the child's probability of attending college, with a smaller (although still significant) effect on the probability of completing a four-year degree. I provide evidence that the estimated relationship is causal and not biased by, for example, unobserved ability. Additionally, I show that credit scores may affect attendance through channels other than access to the student loan market. I hypothesize households substitute the potential to borrow for precautionary savings.
Keywords: Consumption and Savings; Demographics; Employment and Labor Force; Event History/Life Cycle; Housing; Methodology; Net Worth and Assets

Essays on health and retirement - Basu Roy, Subhasree (Georgia State University, 2014)
The essays in this dissertation explore issues related to health and retirement of older Americans, using longitudinal data on older Americans from ten waves of the Health and Retirement Study (1992-2010). The first essay explores the effect of both subjective and relatively more objective physical and mental health conditions on the probability of exit from full-time employment. Eight health indices (factors) are created from a wide range of health measures by principal component analysis. The effect of these health factors on the time until exit from full-time employment is empirically examined in a proportional hazard model. Single and competing risk specifications are estimated that allow for multiple spells of full-time employment and control for unobserved heterogeneity. The main results suggest that increase in functional limitation factor makes an individual more likely to exit via any route in general and the complete retirement route in particular. For mental health problems, increase in the depression factor increases the likelihood of exit from full-time employment via the complete retirement, part-time work and unemployment routes. While increase in cognitive disorders factor has no significant effect on the likelihood of exit via complete retirement, but increases the likelihood of exit via the disability route. These results have implications for public policies targeted towards retaining older workers within the labor market. The second essay examines the effect of retirement on post retirement physical and mental health and the extent to which the effects differ across these different health outcomes. The inherent issue of reverse causality between health and retirement that leads to endogeneity is addressed by using multiple sample stratification and instrumental variable estimation strategies. The stratified samples include individuals who are physically and mentally healthy prior to their retirement so that pure effect of retirement on post retirement health may be found. Five different instruments for complete retirement are also used to deal with endogeneity. The sample stratification results unanimously indicate that complete retirement has adverse effect on post retirement physical and mental health. While the instrumental variables approach results are mixed and are based on the choice of instrument for complete retirement.
Keywords: Employment and Labor Force; Health Conditions and Status; Methodology; Public Policy; Retirement Planning and Satisfaction; Risk Taking

Essential Demographic Methods - Kenneth W. Wachter (Harvard University Press, 2014)
Keywords: Methodology

A factor mixture model for analyzing heterogeneity and cognitive structure of dementia - Cagnone, Silvia; Cinzia Viroli (AStA Advances in Statistical Analysis, 2014)
The Health and Retirement Study (HRS) is funded by the National Institute on Aging of US with the aim of investigating the health, social and economic implications of the aging of the American population. The participants of the study receive a thorough in-home clinical and neuropsychological assessment leading to a diagnosis of normal, cognitive impairment but not demented, or dementia. Due to the heterogeneity of the participants into three classes, we analyze some overall cognitive functioning responses through a factor mixture analysis model. The model extends recent proposals developed for binary and continuous data to general mixed data and to the situation of observed heterogeneity, typical of the HRS study.
Keywords: Health Conditions and Status; Methodology; Other

Frailty and Depression: A Latent Trait Analysis - Matthew C. Lohman (Virginia Commonwealth University, 2014)
Background: Frailty, a state indicating vulnerability to poor health outcomes, is a common condition in later life. However, research and intervention progress is hindered by the current lack of a consensus frailty definition and poor understanding of relationships between frailty and depression. Objectives: The goal of this research is to understand the interrelationships between frailty and depression among older adults. Specifically, this project aims 1) to examine the construct overlap between depression and three definitions of frailty (biological syndrome, medical burdens, and functional domains), 2) to determine the degree to which this overlap varies by age, gender, race/ethnicity and other individual characteristics, 3) to evaluate how the association between frailty and depression influences prediction of adverse health outcomes. Methods: This project uses data from the 2004-2012 Health and Retirement Study (HRS), an ongoing, nationally-representative cohort study of adults over the age of 55. Frailty was indexed by three alternative conceptual models: 1) biological syndrome, 2) cumulative medical burdens, and 3) functional domains. Depressive symptoms were indexed by the 8-item Center for Epidemiologic Studies Depression (CESD) scale. Latent class analysis and confirmatory factor analysis were used to assess the construct overlap between depressive symptoms and frailty. Latent growth curve modeling were used to evaluate associations between frailty and depression, and to estimate their joint influence on two adverse health outcomes: nursing home admission and falls. Results: The measurement overlap of frailty and depression was high using a categorical latent variable approach. Approximately 73% of individuals with severe depressive symptoms, and 85% of individuals with primarily somatic depressive symptoms, were categorized as concurrently frail. When modeled as continuous latent factors, each of the three frailty latent factors was significantly correlated with depression: biological syndrome (ρ = .67, p <.01); functional domains (ρ = .70, p <.01); and medical burdens (ρ = .62, p <.01). Higher latent frailty trajectories were associated with higher likelihood of experiencing nursing home admission and serious falls. This association with adverse health outcomes was attenuated after adjustment for depression as a time-varying covariate. Conclusions: Findings suggest that frailty and frailty trajectories are potentially important indicators of vulnerability to adverse health outcomes. Future investigations of frailty syndrome, however it is operationalized, should account for its substantial association with depression in order to develop more accurate measurement and effective treatment.
Keywords: Health Conditions and Status; Methodology; Public Policy

Fundamental resource dis/advantages, youth health and adult educational outcomes - Elman, Cheryl; Linda A. Wray; Xi, Juan (Social Science Research, 2014)
Recent studies find lasting effects of poor youth health on educational attainment but use young samples and narrow life course windows of observation to explore outcomes. We apply a life course framework to three sets of Health and Retirement Study birth cohorts to examine early health status effects on education and skills attainment measured late in life. The older cohorts that we study were the earliest recipients of U.S. policies promoting continuing education through the GI Bill, community college expansions and new credentials such as the GED. We examine a wide range of outcomes but focus on GEDs, postsecondary school entry and adult human capital as job-related training. We find that older U.S. cohorts had considerable exposure to these forms of attainment and that the effects of youth health on them vary by outcome: health selection and ascription group effects are weak or fade, respectively, in outcomes associated with delayed or adult attainment. However, poorer health and social disadvantage in youth and barriers associated with ascription carry forward to limit attainment of key credentials such as diplomas and college degrees. We find that the human capital - health gradient is dynamic and that narrow windows of observation in existing studies miss much of it. National context also matters for studying health-education linkages over the life course.
Keywords: Adult children; Demographics; Event History/Life Cycle; Health Conditions and Status; Healthcare; Methodology

Gender Differences in Functional Health: Latent Curve Analysis Assessing Differential Exposure - Leah Rohlfsen; Jennie J. Kronenfeld (Journals of Gerontology Series B-Psychological Sciences and Social Sciences, 2014)
Objectives. To examine gender difference in trajectories of functional limitations among middle-aged and older adults using a comprehensive set of predictors and method not previously used to examine this topic. Method. Two-part latent curve models were used to analyze data from the Health and Retirement Study. These models differentiate the occurrence of limitations from the number of limitations at both baseline and over time. Results. Females had 3.70 times greater odds of having any limitations and had 28 more limitations at baseline compared with males, but there was no gender difference in the onset of limitations over time or in the number of limitations over time. Differences in employment status, income, wealth, depressive symptoms, arthritis, cancer, and eyesight partially explained the gender gap. Discussion. Females are disadvantaged in terms of occurrence and number of limitations at baseline but the gender gap remains stable over time, suggesting differences occur before late-middle and old age. Females' lack of full-time employment, and lower levels of income and wealth translate into worse functional health. It is important to improve the socioeconomic status of females while also addressing the health conditions that contribute to functional limitations for males and females.
Keywords: Demographics; Health Conditions and Status; Methodology

Gender Differences in Trajectories of Self-Rated Health in Middle and Old Age: An Examination of Differential Exposure and Differential Vulnerability - Leah Rohlfsen; Jennie J. Kronenfeld (Journal of Aging and Health, 2014)
Objective: This research examined gender differences in self-rated health (SRH) using the differential exposure and differential vulnerability explanations of gender differences in health. Method: Trajectories of SRH were estimated using data that spanned 12 years (1992-2004) from the Health and Retirement Study. Results: There was no gender difference in SRH at baseline, but SRH declined faster for males over time. Factors that mediated the gender difference included changes in employment status, smoking behavior, and the onset of health conditions. Moreover, were it not for gender differences in various structural and health status factors, females would have better SRH at baseline and over time. Discussion: Our results differ from previous research, which often shows a female disadvantage that is reduced or disappears at older ages. Furthermore, gender differences in the predictors of SRH (exposure) contribute more to understanding gender differences in SRH than different responses to the predictors (vulnerability).
Keywords: Demographics; Health Conditions and Status; Methodology

Grandparenting Roles and Volunteer Activity - Jennifer R. Bulanda; Jendrek, Margaret Platt (The Journals of Gerontology Series B: Psychological Sciences and Social Sciences, 2014)
Objectives. We examine whether grandparenting roles are related to formal volunteering among older adults.Method. Logistic regression is used to examine the likelihood of volunteering based on grandchild care using data from the 2004 wave of the Health and Retirement Study (n = 13,785). Longitudinal analyses utilize treatment effects models to examine changes in volunteering for grandparents who begin nonresidential grandchild care between the 2004 and 2008 waves (n = 10,811).Results. Results show that grandparents raising coresidential grandchildren have lower odds of volunteering than grandparents providing no regular grandchild care. However, grandparents who provide nonresidential grandchild care are more likely to volunteer than grandparents not providing grandchild care and those raising a coresidential grandchild. Grandparents who provide nonresidential care for grandchildren engage in more volunteering before assuming grandchild care, and their volunteerism increases after becoming a caregiver for a grandchild.Discussion. Consistent with resource theory and the accumulation of roles, providing nonresidential grandchild care may draw grandparents into formal volunteer activity. The lower human capital resources evidenced by grandparents raising coresidential grandchildren may play a role in their lower likelihood of formal volunteering.
Keywords: Adult children; Demographics; Methodology; Public Policy

Health insurance coverage and personal behavior - Chen, Tianxu (Boston University, 2014)
Subsidies, taxes, premiums, and eligibility for health insurance can potentially cause "marriage lock," in which couples stay married for the sake of health insurance coverage, and marriage lock may change under the Affordable Care Act. In the first two chapters, marriage lock is examined in the context of two key health insurance decisions: divorce decisions upon qualification for Medicare at age 65, and marriage and divorce decisions associated with the introduction of the Massachusetts insurance mandate and health insurance exchange market reforms in 2006. In the first chapter, using the Health and Retirement Study data, I find evidence of a 7 percentage point increase in the number of divorces upon achieving Medicare eligibility at age 65 for people with spousal insurance coverage relative to those without it. In the second chapter, using the American Community Survey data, I find that the 2006 Massachusetts healthcare reform increased incentives for marriage in the health insurance exchange market relative to control states. Specifically, the Massachusetts reform appears to have reduced the divorce rate by 0.5 percentage point and increased marriage rate by 1.4 percentage points. In the third chapter, I use data from the China Household Finance Survey (CHFS) to explore three decisions potentially affected by the implementation of Medical Savings Accounts (MSAs). First, I find that individuals with MSAs incur 17 RMB more medical expenses per 1000 RMB increase in their MSAs balance, while I find no significant effect of after-tax income on medical expenses. Second, I study preference heterogeneity as revealed by three types of risky behaviors. I find undertaking risky investments is associated with 23% more medical expenditures, while always using a seatbelt and obeying traffic signals are associated with 16% and 22% higher medical expenditures, respectively. Finally, I find evidence suggesting that individuals become more risk adverse with MSAs than without, specifically by increasing their use of seatbelts and obeying traffic signals. These findings, using recent Chinese data, suggest that MSAs play an important role when consumers make health expenditure decisions, and that preferences involving risk and prevention also appear to be influenced by the MSA scheme.
Keywords: Adult children; Medicare/Medicaid/Health Insurance; Methodology

Health Literacy and Related Psychosocial Factors and Measurement Issues: A Qualitative Study and a Secondary Analysis of the Health and Retirement Study - Dena M. Fernandez (University of Michigan, 2014)
Purpose: Despite the well-known positive relationship between inadequate health literacy and adverse health outcomes, little is known about the impact of health literacy and health literacy testing on patient psychosocial factors. Meanwhile, experts have advised against routine health literacy screening due to potential for shame-related harm, and providers remain largely unaware of their patients' health literacy and health literacy-related challenges. The purpose of this dissertation was to (1) examine relationships between health literacy and psychosocial factors in a Health and Retirement Study sample of adults, (2) learn about the health literacy-related healthcare experience from the perspectives of African American adults with hypertension, and (3) learn about the health literacy testing experience through cognitive interviewing with African American adults with hypertension. Methods: In a secondary analysis of Health and Retirement Study data, logistic regression was conducted to examine relationships between health literacy and psychosocial and health behavioral variables in a subsample who partook in health literacy testing (n=373). In an original study, qualitative data was collected from a sample of African American adults with hypertension (n=15). Narrative interviews were conducted to explore the health literacy-related healthcare experience, and cognitive interviews were conducted to learn about the cognitive and experiential dimensions of health literacy testing. Results: Quantitative results provided evidence that health literacy is related to breast screening practices, tobacco and exercise behaviors, and perceptions of control over health and social standing in the HRS sample. Qualitative analysis of narrative interviews indicated that health literacy-related experiences in the healthcare setting involve practical challenges (primarily related to medication), negative emotions (feeling of anxiety and stigmatization), and both adaptive and maladaptive coping techniques. Findings from cognitive interviews revealed that participants at times felt discomfort, embarrassment, and stress with each of the instruments used in this study; additionally, findings suggest there may be a potential bias in some of the content of the tests.
Keywords: Health Conditions and Status; Methodology

Heterogeneous Risks - Kenneth W. Wachter (Essential Demographic Methods, 2014)
...uses themes from the individual lifecourse, history, and global change to convey the meaning of concepts such as exponential growth, cohorts and periods, lifetables, population projection, proportional hazards, parity, marity, migration flows, and stable populations.
Keywords: Demographics; Methodology; Public Policy

A holistic approach to understanding retirement preparedness - Yook, Miyoung (Kansas State University, 2014)
There has been increased interest in understanding the significant disparity in U.S. households' retirement preparedness due to concern about the stability of Social Security benefits, the shift from defined benefit plans to defined contribution plans, and the decreased rate of saving. This dissertation explores a model that can be utilized to understand and enhance retirement preparedness by individuals, educators, practitioners, and policy makers. Retirement preparedness was measured in two different ways--using the income replacement rate and the capital accumulation ratio--for two separate empirical models. The general conceptualization of the framework is based on the retirement planning work of Hershey (2004). This study utilized the 2008 Rand version (Version L) of the Health and Retirement Study (HRS) and 2006, 2008, and 2010 psychosocial and lifestyle questionnaire. The Rand HRS data file is a user-friendly version of the HRS data and contains cleaned data. The two hierarchical regressions were used to analyze the association between retirement preparedness and the theoretical concepts of cultural influence, environmental influence, task components, and psychological influence. Entering the conceptual components as four separate blocks allows for observation of changes in R 2 based on the addition of the conceptual components. This research investigates the following research questions: (a) How strongly are cultural influences associated with retirement preparedness?, (b) How strongly are environmental influences associated with retirement preparedness?, (c) How strongly are task components associated with retirement preparedness?, and (d) How strongly are psychological influences associated with retirement preparedness? Current retirement planning practices are often based on structural profiles such as financial resources, financial needs, and goals. The holistic approach used for this dissertation is based on the awareness of the influence of psychological and personal factors on financial decision making. The results showed that the variables positively associated with the retirement income replacement rate were self-perception of aging, homeownership, stock ownership, household pension ownership, IRA/Keogh ownership, and business ownership. Pre-retirement income log had a highly negative association with the retirement income replacement ratio. Big Five personality and perceived mastery were not significant. However, when asset ownership (excluding homeownership) was not controlled, conscientiousness and low emotional stability became significant and showed a positive association for conscientiousness and a negative association for low emotional stability. Self-perception of aging was a significant psychological variable in both models. The significant variables from the second model measured by the capital accumulation ratio were asset ownerships including homeownership, stock ownership, IRA ownership, real estate ownership, and business ownership. None of the psychological variables were significant, except for agreeableness, which was related negatively to the capital accumulation ratio when the asset ownerships (excluding home ownership) were not controlled. Other significant variables, when asset ownership was not controlled, were home ownership, pre-retirement income log, being non-White.
Keywords: Adult children; Health Conditions and Status; Healthcare; Methodology; Retirement Planning and Satisfaction; Social Security

How does personality contribute to retirement savings? - Chan, Wai (Purdue University, 2014)
The aim of this dissertation was to explore how personality factors explain retirement savings over time. Past studies did not systematically examine individual characteristics on financial preparation for retirement or did not adopt a monetary outcome to exemplify retirement investments. Thus, this dissertation modeled two outcomes for retirement savings, i.e., Individual Retirement Accounts (IRAs) ownership and IRA balances. Guided by the Investor Behavior Model and the Behavioral Economics Perspective, conscientiousness and personal mastery were hypothesized to bolster IRA investments, while agreeableness and perceived constraints were hypothesized to undermine IRA investments. Multilevel model techniques were applied to depict the trajectory of IRA investments with longitudinal data from the Health and Retirement Study (HRS 2006, 2008, 2010). Findings were partly consistent with hypotheses. The Individual Sample ( N = 4,117) documented that higher levels of conscientiousness and personal mastery predicted greater odds of IRA ownership. Perceived constraints were associated with lower odds of IRA ownership, while agreeableness was linked to lower IRA balances. Saving horizons and financial controls were found to partially mediate the relationship between personality factors and IRA investments. Based on the findings from the Individual Sample, a Spousal Sample ( N = 4,257) was developed to examine whether perceived spousal relationship qualities accounted for IRA investments above and beyond personality factors. In addition, perceived spousal relationship qualities were explored to mitigate or accentuate the effects of personality factors. Relationship strain was found to undermine IRA ownership while spousal support was associated with higher IRA balances. Interaction effects of spousal relationships were detected only for exploratory personality traits (i.e., openness and extraversion) for IRA ownership. Overall, findings provided empirical support for theoretical perspectives that include personality factors as impacting retirement preparations. Likewise, personality factors demonstrated differential effects on IRA outcomes. With regard to practical implications, this dissertation provides educators and policymakers with insights to improve the existing financial education and social welfare systems.
Keywords: Adult children; Health Conditions and Status; Methodology; Pensions; Public Policy; Retirement Planning and Satisfaction

The Identification of Regions of Significance in the Effect of Multimorbidity on Depressive Symptoms Using Longitudinal Data: An Application of the Johnson-Neyman Technique - Rast, P.; Rush, J.; Andrea M Piccinin; Scott M Hofer (Gerontology, 2014)
Background: The investigation of multimorbidity and aging is complex and highly intertwined with aging-related changes in physical and cognitive capabilities, and mental health and is known to affect psychological distress and quality of life. Under these circumstances it is important to understand how the effects of chronic conditions evolve over time relative to aging-related and end-of-life changes. The identification of periods in time where multimorbidity impacts particular outcomes such as depressive symptoms, versus periods of time where this is not the case, reduces the complexity of the phenomenon. Objective: We present the Johnson-Neyman (J-N) technique in the context of a curvilinear longitudinal model with higher-order terms to probe moderators and to identify regions of statistical significance. In essence, the J-N technique allows one to identify conditions under which moderators impact an outcome from conditions where these effects are not significant. Methods: To illustrate the use of the J-N technique in a longitudinal sample, we used data from the Health and Retirement Study. Analyses were based on time-to-death models including participants who died within the study duration of 12 years. Results: Multimorbidity differentially affects rates of change in depression. For some periods in time the effects are statistically significant while in other periods the same effects are not statistically different from zero. Conclusion: The J-N technique is useful to continuously probe moderating effects and to identify particular interactions with the model for time when certain effects are or are not statistically significant. In the context of multimorbidity this method is particularly useful for interpreting the complex interactions with differential change over time. 2014 S. Karger AG, Basel.
Keywords: Health Conditions and Status; Methodology

The Impact of Health Insurance on Stockholding: A Regression Discontinuity Approach - Christelis, Dimitris; Dimitris Georgarakos; Anna Sanz-de-Galdeano (Bonn, Germany, Institute for the Study of Labor, 2014)
Using data from the US Health and Retirement Study, we study the causal effect of increased health insurance coverage through Medicare and the associated reduction in health-related background risk on financial risk-taking. Given the onset of Medicare at age 65, we identify our effect of interest using a regression discontinuity approach. We find that getting Medicare coverage induces stockholding for those with at least some college education, but not for their less-educated counterparts. Hence, our results indicate that a reduction in background risk induces financial risk-taking in individuals for whom informational and pecuniary stock market participation costs are relatively low. Tables, Figures, Appendixes, References.
Keywords: Medicare/Medicaid/Health Insurance; Methodology; Net Worth and Assets; Risk Taking

International sex and age differences in physical function and disability - Felicia V Wheaton (University of Southern California, 2014)
Worldwide population aging will undoubtedly be accompanied by an increase in the number of disabled older adults. Female gender and increased age are two of the most widely identified risk factors for poor physical functioning and disability. Yet the contexts in which people are aging vary markedly across countries. Countries differ greatly in their level of economic development, both past and present. Economic development is in turn related to improvements in infrastructure, health care, public health, education, etc. that are hypothesized to be related to improved physical function and less disability. Therefore, this dissertation examined whether sex and age differences/changes in both objectively-measured physical performance and reported difficulties with functional tasks and activities of daily living (ADLs) were similar or varied across seven countries whose per capita GNP ranged from $200 to $40,100 (United Sates, Taiwan, Korea, Mexico, China, Indonesia, and the Tsimane of Bolivia). It also sought to determine if sex differences and age differences varied systematically in terms of macro-level indicators including GDP, life expectancy, and measures of gender equality. Overall, sex differences were remarkably consistent across countries with very different contexts. Sex differences in physical performance and functional limitations were more pronounced than sex differences in difficulty with basic self-care tasks, but the magnitude of differences did not vary systematically in relation to country-level measures of development or gender equality. This may be because gender equality can be either protective or detrimental, depending on the domain. In terms of age differences, it was necessary to consider both the level of performance/prevalence of difficulty at younger ages as well as age differences, since poor performance/high levels of difficulty among the young-old indicate that "aging" has already occurred. Some populations did appear to be "aging" more rapidly, particularly those at the lowest end of the development spectrum, however, there was no clear evidence for a linear correlation between macro-level indicators of development and age differences. Interestingly, findings showed that functioning in some domains could be fairly well maintained despite declines in other domains, and these varied across countries. For example, Indonesians appeared to be "aging" more rapidly in terms of upper body strength, but showed relatively high levels of lower body function and less age-related decline. This may be due to differences across populations in patterns of work, physical activity, the built environment, etc.
Keywords: CHARLS; Cross-National; Demographics; Disabilities; Health Conditions and Status; IFLS; KLoSA; Methodology; MHAS

Item response theory for measurement validity - Frances Margaret Yang; Solon T. Kao (Shanghai Archives of Psychiatry, 2014)
Summary: Item response theory (IRT) is an important method of assessing the validity of measurement scales that is underutilized in the field of psychiatry. IRT describes the relationship between a latent trait (e.g., the construct that the scale proposes to assess), the properties of the items in the scale, and respondents' answers to the individual items. This paper introduces the basic premise, assumptions, and methods of IRT. To help explain these concepts we generate a hypothetical scale using three items from a modified, binary (yes/no) response version of the Center for Epidemiological Studies-Depression scale that was administered to 19, 399 respondents. We first conducted a factor analysis to confirm the unidimensionality of the three items and then proceeded with Mplus software to construct the 2-Parameter Logic (2-PL) IRT model of the data, a method which allows for estimates of both item discrimination and item difficulty. The utility of this information both for clinical purposes and for scale construction purposes is discussed. Copyright 2014 by Editorial Department of the Shanghai Archives of Psychiatry.
Keywords: Health Conditions and Status; Methodology

Job Displacement, Retirement and the Roles of Government Programs among Older American Workers - Liu, Jieruo (State University of New York at Stony Brook, 2014)
The world has been going through one of worst economic recessions in history with severe job market downturns. In October 2009, the U.S. civilian unemployment rate reached a historical 10% and nearly 50% of the unemployed exhausted their 26-week regular Unemployment Insurance (UI) benefits and in consequence, UI was extended to 99 weeks. This dissertation examines the empirical facts of job displacement among the older American workers during the recent economic crisis, and studies their subsequent labor market and retirement decisions, with focus on the roles of government programs including UI and Social Security Old-Age Benefits (OA). Job displacement is empirically shown to have both short term and long term negative effects on workers' future employment. While young and prime-aged workers usually increase labor supply to compensate for the drops in assets and incomes, it is ambiguous how older workers would response and whether premature retirement would follow. For workers who are approaching their retirement age when OA becomes available, both OA and UI could be claimed for that purpose. The extent to which they rely on these two programs is affected by factors including age, wealth, income profiles and the institutional details of UI and OA. Using data from the Health and Retirement Study (HRS), I estimate a dynamic life-cycle utility maximization model with separate decisions on consumption/savings, labor market status and OA take-ups. With the structural model, I am able to isolate the effects of changes in UI coverage from changes in other relevant aspects including changes in the Normal Retirement Age (NRA), and analyze such effects in a deteriorating labor market. I conduct several experiments on UI generosities and evaluate the consequences on the mean individual as well as across the distributions of wealth and income. I find that in a severe labor market downturn, those who are on the lower end of wealth and income distributions are forced to claim OA early while the wealthier and high-income individuals typically postpone OA claiming to reduce early claiming penalties. However, with the extra help of a 99-week UI, some of the poor and low-income individuals can also afford to postpone OA claiming using UI as a stepping-stone. Specifically, among those who originally claim OA at an early 62 years old during a severe labor market downturn, 6.34% of the poorest individuals and 2.52% of the lowest-incomers postpone OA take-ups, resulting in slight increases in the average OA entitlement ages. However, the role of UI as a stepping stone is more prominent among those with high income profiles whose OA take-ups are postponed for almost a quarter year.
Keywords: Demographics; Employment and Labor Force; Methodology; Public Policy; Retirement Planning and Satisfaction; Social Security

Left with Bias? Quantile Regression with Measurement Error in Left Hand Side Variables - Stacy, Brian (Hamburg, Germany, German National Library of Economics Leibniz Information Centre for Economics, 2014)
This paper examines the effect of measurement error in the dependent variable on quantile regression, because unlike OLS regression, even classical measurement error can generate bias. I examine the pattern and size of the bias using both simulation and an empirical example. The simulations indicate that classical error can cause bias and that non-classical measurement error, particularly heteroskedastic measurement error, has the potential to produce substantial bias. Also, the size and direction of the bias depends on the amount of heterogeneity in the effects across quantiles and the regression error distribution. Using restricted access Health and Retirement Study data containing matched IRS W-2 earnings records, I examine whether estimates of the returns to education statistically differ using a precisely measured and mismeasured earnings variable. I find that returns to education are over-stated by roughly 1 percentage point at the median and 75th percentile using earnings reported by survey respondents.
Keywords: Methodology; Public Policy; Social Security

A longitudinal analysis of body mass and morbidity: evidence from the health and retirement study - Boydstun, Jamie (Mississippi State University, 2014)
This dissertation aimed to investigate the direct and indirect pathways between body mass and three indicators of morbidity - health conditions, disability, and self-rated health status - and how these associations differed across birth cohorts. Using data from the Health and Retirement Study, a nationally representative longitudinal sample of adults age 51 or older, I used latent growth curve modeling to investigate the association of body mass on morbidity for five cohorts. Latent growth curve models allow for changes in body mass, health conditions, disability, and self-rated health over several waves of data to be assessed. To determine if the influence of education on health has declined, I also stratified each cohort by educational attainment groups. The results show that starting body mass is positively associated with starting health conditions; no other pathway examined was significant for all cohorts. In the three youngest cohorts, higher starting body mass was associated with worse self-rated health. Changes in body mass over time were not significantly associated with changes in self-rated health over time for the two youngest cohorts, perhaps indicating that adults at older ages do not perceive higher body mass as detrimental to overall well-being. Education was a significant predictor of body mass and self-rated health for all cohorts. When cohorts were stratified based on educational attainment, adults with at least some college had fewer health conditions than their less educated peers in all cohorts except the youngest cohort. The relationship between the rate of change in body mass and the rate of change in health conditions was not significant for the most educated group in the youngest cohort. However, higher starting body mass resulted in worse self-rated health regardless of cohort or education. Despite inconsistent findings, the results potentially support an expansion of morbidity because the onset of illness does seem to be occurring at younger ages. The effect of education on body mass and health was mostly consistent across cohorts. Stratifying the data by educational attainment suggests that the youngest and best educated cohort has not benefited from the increased level of education relative to the older cohorts in the study.
Keywords: Disabilities; Health Conditions and Status; Methodology; Public Policy

Longitudinal analysis of self-reported health status by mixture latent auto-regressive models - Francesco Bartolucci; Bacci, S.; Pennoni, F. (Journal of the Royal Statistical Society. Series C: Applied Statistics, 2014)
Motivated by an application to a longitudinal data set coming from the Health and Retirement Study about self-reported health status, we propose a model for longitudinal data which is based on a latent process to account for the unobserved heterogeneity between sample units in a dynamic fashion. The latent process is modelled by a mixture of auto-regressive AR(1) processes with different means and correlation coefficients, but with equal variances. We show how to perform maximum likelihood estimation of the proposed model by the joint use of an expectation-maximization algorithm and a Newton-Raphson algorithm, implemented by means of recursions developed in the hidden Markov model literature. We also introduce a simple method to obtain standard errors for the parameter estimates and suggest a strategy to choose the number of mixture components. In the application the response variable is ordinal; however, the approach may also be applied in other settings. Moreover, the application to the self-reported health status data set allows us to show that the model proposed is more flexible than other models for longitudinal data based on a continuous latent process. The model also achieves a goodness of fit that is similar to that of models based on a discrete latent process following a Markov chain, while retaining a reduced number of parameters. The effect of different formulations of the latent structure of the model is evaluated in terms of estimates of the regression parameters for the covariates. 2013 Royal Statistical Society.
Keywords: Expectations; Methodology

Longitudinal Associations of Subjective Memory With Memory Performance and Depressive Symptoms: Between-Person and Within-Person Perspectives - Hueluer, Gizem; Hertzog, Christopher; Ann M. Pearman; Ram, Nilam; Denis Gerstorf (Psychology and Aging, 2014)
Clinical diagnostic criteria for memory loss in adults typically assume that subjective memory ratings accurately reflect compromised memory functioning. Research has documented small positive between-person associations between subjective memory and memory performance in older adults. Less is known, however, about whether within-person fluctuations in subjective memory covary with within-person variance in memory performance and depressive symptoms. The present study applied multilevel models of change to 9 waves of data from 27,395 participants of the Health and Retirement Study (HRS; mean age at baseline = 63.78; SD = 10.30; 58 women) to examine whether subjective memory is associated with both between-person differences and within-person variability in memory performance and depressive symptoms and explored the moderating role of known correlates (age, gender, education, and functional limitations). Results revealed that across persons, level of subjective memory indeed covaried with level of memory performance and depressive symptoms, with small-to-moderate between-person standardized effect sizes (0.19 for memory performance and -0.21 for depressive symptoms). Within individuals, occasions when participants scored higher than usual on a test of episodic memory or reported fewer-than-average depressive symptoms generated above-average subjective memory. At the within-person level, subjective memory ratings became more sensitive to within-person alterations in memory performance over time and those suffering from functional limitations were more sensitive to within-person alterations in memory performance and depressive symptoms. We take our results to suggest that within-person changes in subjective memory in part reflect monitoring flux in one's own memory functioning, but are also influenced by flux in depressive symptoms.
Keywords: Expectations; Health Conditions and Status; Methodology

The Long-Term Effect of Health Insurance on Near-Elderly Health and Mortality - Black, Bernard; José-Antonio Espín-Sánchez; Eric French; Litvak, Kate (Evanston, IL, Northwestern University Law Schoo, 2014)
We use the best available longitudinal dataset, the Health and Retirement Survey, and a battery of causal inference methods to provide both central estimates and bounds on the effect of health insurance on health and mortality among the near elderly (initial age 50-61) over an 18-year period. Those uninsured in 1992 consume fewer healthcare services, but are not less healthy and, in our central estimates, do not die sooner than their insured counterparts. We discuss why a zero average effect of uninsurance on mortality and health is plausible, some selection effects that might explain our full results, and methodological concerns with prior studies.
Keywords: Health Conditions and Status; Healthcare; Medicare/Medicaid/Health Insurance; Methodology

Long-term exposure to income inequality: implications for physical functioning at older ages - de Vries, Robert; Blane, David; Netuveli, Gopalakrishnan (European Journal of Ageing, 2014)
The 'inequality hypothesis' proposes that higher levels of societal income inequality have a direct negative causal effect on health. Support for this hypothesis has been mixed; particularly among older people. However, most previous studies have not accounted for people's exposure to inequality over the long-term. We aimed to address this problem by examining the implications of long-term inequality exposure for older people's physical health. Data on individual health and covariates were drawn from three large, comparable surveys of older people, covering 16 countries: the English Longitudinal Study of Ageing, the Survey of Health and Retirement in Europe and the U.S. Health and Retirement Study. Historical inequality information was derived from the Standardised World Income Inequality Database. We used multilevel regression methods to model the association between long-term average inequality and three measures of physical functioning: grip strength, lung function and self-reported activity limitation. Exposure to higher average long-term levels of inequality was significantly negatively related to objectively measured grip strength and lung function, but unrelated to self-reported limitations (although increasing inequality over time was positively related to self-reported limitations). The grip strength and lung function associations were partially explained by between-country differences in height, and in the latter case this factor may fully account for the apparent effect of inequality. We discuss implications of these results for the inequality hypothesis.
Keywords: Health Conditions and Status; Income; Methodology; Other

Midlife trends in activities and disability - Verbrugge, Lois M.; Xian Li (Journal of Aging and Health, 2014)
Objectives: This is the first analysis that demonstrates empirically the likely tie between activities (time spent) and disability (health-related difficulty in activities). We compare trends in activities and disability for Americans ages 55 to 69 in recent years, and assess cross-sectional linkages of activities and disability. Methods: Data are from the Health and Retirement Study, a longitudinal survey of community-dwelling U.S. adults. Trends are estimated by mixed-effects regression models (MRMs) with time, age, and time-age interaction predictors. Links of activities and disability also use MRM. Results: For midlife adults, hobbies/leisure and sports/exercise increased, repairs/yard decreased, and several activities had convex patterns; by contrast, disability prevalence was stable. Personal care hours rise with disability, but most activities decline. Discussion: Activities are more dynamic than disability, and time use is associated with disability. Taken together, the results encourage broader activities in disability measures to capture better disability's scope and dynamics.
Keywords: Demographics; Disabilities; Event History/Life Cycle; Health Conditions and Status; Methodology; Other

A Multilevel Dyadic Study of the Impact of Retirement on Self-Rated Health: Does Retirement Predict Worse Health in Married Couples? - Angela L Curl; Aloen L. Townsend (Research on Aging, 2014)
Objectives: This study examined the effects of retirement on self-rated health for married couples, using interdependence and social stratification theoretical frameworks. Method: Dyadic multilevel modeling of data (N = 2,213 non- Hispanic couples) from 1992 to 2010 of the Health and Retirement Survey. Results: Retirement was associated with worse self-ratings of health (SRH) short term (ST) for both husbands and wives during the first couple of years of retirement. In addition, the longer the husbands (but not wives) were retired, the worse was their SRH. Cross-spouse effects varied by gender: When wives retired, their husbands SRH improved ST, but when husbands retired their wives SRH improved long term. Spouse education moderated the relationship between years since spouses retirement and SRH for wives. Discussion: Practitioners can use this information to help married couples through retirement planning and transitions. Results suggest that models of retirement in couples should pay greater attention to gender and other social stratification factors, spousal interdependence, and length of time since retirement.
Keywords: Adult children; Demographics; Health Conditions and Status; Healthcare; Methodology; Retirement Planning and Satisfaction

Older Adults as Consumers: An Examination of Differences by Birth Cohort - Fin, Debra N.; Yoon, Carolyn; Hartsell, Debra L.; Toni C Antonucci; Noah J Webster; McCullough, Wayne R. (The interdisciplinary science of consumption, 2014)
The U.S. and much of the developed world are currently undergoing a demographic transition marked by fundamental changes in the age structure of the population. These changes pose a number of challenges for society such as understanding the consumption patterns of middle aged and older people. In this chapter, the authors use data from the Health and Retirement Study to explore consumption patterns among five cohorts of adults age 50 and older. They found that older, compared to younger, birth cohorts of older adults reported less spending on food, transportation, trips and vacations, and durable goods; they spent more on donations and gifts; all cohorts reported similar levels of spending on health-related expenses. Results also identified a critical middle age group (i.e. ages 70 to 80), in which the greatest differences in consumption patterns were evident. Such findings may be useful for industry and organizations allowing them to be responsive and competitive by helping them target goods and products that meet the changing needs of an aging society
Keywords: Demographics; Methodology

Patterns of Widowhood Mortality - Allison R Sullivan; Andrew Fenelon (The Journals of Gerontology Series B: Psychological Sciences and Social Sciences, 2014)
Objectives. Becoming widowed is a known risk factor for mortality. This article examines the magnitude of, explanations for, and variation in the association between widowhood and mortality. Previous research on widowhood mortality has revealed variation by socioeconomic status (SES), in that SES is not protective in widowhood, and by gender, such that men s mortality increases more than women s mortality after the death of spouse.Method. Using data from the Health and Retirement Study, we estimated Cox proportional hazard models to estimate the association between widowhood and mortality.Results. Becoming widowed is associated with a 48 increase in risk of mortality. Approximately one third of the increase can be attributed to selection, in that those who become widows are socioeconomically disadvantaged. In contrast to previous studies, SES is protective for widows. Widowhood mortality risk increases for men if their wives deaths were unexpected rather than expected; for women, the extent to which their husbands death was expected matters less.Discussion. Widowhood s harmful association with mortality show how strongly social support and individual s health and mortality are related. These findings support the larger literature on the importance of social support for health and longevity.
Keywords: Adult children; Health Conditions and Status; Methodology; Net Worth and Assets

Perceived weight discrimination and C-reactive protein - Angelina R Sutin; Yannick Stephan; Martina Luchetti; Antonio Terracciano (Obesity, 2014)
Objective: Perceived weight discrimination has been linked to health outcomes, including risk of obesity. Less is known about how discrimination is associated with intermediate physiological markers of health, such as systemic inflammation. This research examined the association between weight discrimination and C-reactive protein (CRP) and whether it varied by participants' body mass index (BMI). Methods: Cross-sectional design using data from the Health and Retirement Study. Among participants who were overweight or obese (N=7,394), regression analysis was used to test for an association between weight discrimination and CRP and whether this association was moderated by BMI. Similar associations among seven other attributions for discrimination were tested. Results: The association between weight discrimination and CRP varied as a function of BMI: At BMI between the thresholds for overweight and obesity (BMI 25-30), weight discrimination was associated with higher circulating levels of CRP; there was no association between weight discrimination and CRP as BMI approached Class 3 obesity (BMI 40). A similar pattern emerged for discrimination based on a physical disability, but not for the other attributions for discrimination (e.g., race, age). Conclusions: Weight discrimination is associated with higher circulating CRP, an association that is moderated by BMI. .
Keywords: Health Conditions and Status; Methodology

Personality change associated with chronic diseases: pooled analysis of four prospective cohort studies - Markus Jokela; Hakulinen, C.; Archana Singh-Manoux; Mika Kivimäki (Psychological Medicine, 2014)
Background: Common chronic conditions, such as heart disease and cancer, are associated with increased psychological distress, functional limitations and shortened life expectancy, but whether these diseases alter aspects of personality remains unclear. Method: To examine whether the onset of heart disease, stroke, diabetes, cancer, hypertension, arthritis and respiratory disease is associated with subsequent changes in personality traits of the five-factor model, we pooled data from the Health and Retirement Study, the Midlife in the United States Survey, and the graduate and sibling samples of the Wisconsin Longitudinal Study for an individual-participant meta-analysis (total n = 17 493; mean age at baseline 55.8 years). Results: After adjustment for age, we observed consistent decreases in extraversion -0.25 T-scores per one disease; 95 confidence interval (CI) -0.40 to -0.10 , emotional stability (-0.40, 95 CI -0.61 to -0.19), conscientiousness (-0.44, 95 CI -0.57 to -0.30) and openness to experience (-0.25, 95 CI -0.37 to -0.13) but not in agreeableness (-0.05, 95 CI -0.19 to 0.08) after the onset of chronic diseases. The onset of each additional chronic disease accelerated the average age-related personality change by 2.5 years in decreasing extraversion, 5.5 years in decreasing conscientiousness, and 1.6 years in decreasing openness to experience, and attenuated the increasing levels of emotional stability by 1.9 years. Co-morbid conditions were associated with larger changes than single diseases, suggesting a dose-response association between morbidity and personality change. Conclusions: These results support the hypothesis that chronic diseases influence personality development in adulthood. Copyright Cambridge University Press 2014.
Keywords: Health Conditions and Status; Methodology

Personality measures in the national social life, health, and aging project - Iveniuk, James; Laumann, Edward O.; Linda J. Waite; McClintock, Martha K.; Andrew D. Tiedt (The journals of gerontology. Series B, Psychological sciences and social sciences, 2014)
OBJECTIVES: Provide recommendations for researchers on the use of the Big Five personality battery in the National Social Life, Health, and Aging Project (NSHAP), and ensure that the battery does proxy the Big Five. Also, describe the levels of Big Five traits across gender and age. METHOD: We used an Exploratory Structural Equation Model (ESEM) to analyze NHSAP's personality battery, comparing NSHAP with the National Longitudinal Study of Midlife in the United States (MIDUS) and the Health and Retirement Study (HRS). RESULTS: ESEM revealed a 5-factor structure in the NSHAP battery, but with considerable cross-loadings. When these cross-loadings were not included in the model, model fit notably worsened. Reliabilities of Big Five scales were comparable to the HRS and MIDUS, even though NSHAP's battery is shorter. Women were considerably more Agreeable than men, although this gender gap closed among the oldest in the sample (80 years or older). DISCUSSION: Researchers will be able to make use of NSHAP's personality battery to examine a range of social, biological, and psychological factors at older ages, in light of individuals' general traits. We recommend models which allow for cross-loadings.
Keywords: Health Conditions and Status; Methodology

Personality traits as risk factors for stroke and coronary heart disease mortality: pooled analysis of three cohort studies - Markus Jokela; Pulkki-Raback, Laura; Marko Elovainio; Mika Kivimäki (Journal of Behavioral Medicine, 2014)
We examined whether personality traits are differently associated with coronary heart disease and stroke mortality. Participants were pooled from three prospective cohort studies (Health and Retirement Study, Wisconsin Longitudinal Study graduate and sibling samples; n = 24,543 men and women, mean age 61.4 years, mortality follow-up between 3 and 15 years). There were 423 coronary heart disease deaths and 88 stroke deaths during 212,542 person-years at risk. Higher extraversion was associated with an increased risk of stroke (hazard ratio per each standard deviation increase in personality trait HR = 1.41, 95 CI 1.10 1.80) but not with coronary heart disease mortality (HR = 0.93, 0.83 1.05). High neuroticism, in turn, was more strongly related to the risk of coronary heart disease (HR = 1.16, 1.04 1.29) than stroke deaths (HR = 0.95, 0.78 1.17). High conscientiousness was associated with lower mortality risk from both coronary heart disease (HR = 0.74, 0.67 0.81) and stroke (HR = 0.78, 0.63 0.97). Cardiovascular risk associated with personality traits appears to vary between main cardiac and cerebral disease endpoints.
Keywords: Health Conditions and Status; Methodology

Physical activity and personality development across adulthood and old age: Evidence from two longitudinal studies - Yannick Stephan; Angelina R Sutin; Antonio Terracciano (Journal of Research in Personality, 2014)
Personality traits are associated with a number of health-related factors; less is known about how such factors contribute to adult personality development. Based on evidence for the protective role of physical activity for individual functioning, the present study tests whether physical activity contributes to personality stability and change. Using longitudinal data from the Midlife in the United States study (N= 3758) and the Health and Retirement Study (N= 3774), we found that more physically active individuals declined less on conscientiousness, extraversion, openness and agreeableness, and had higher rank-order stability and profile consistency over time. These findings suggest that physical activity may help preserve personality stability and prevent maladaptive personality changes across adulthood and old age. 2013 Elsevier Inc.
Keywords: Event History/Life Cycle; Health Conditions and Status; Methodology

Positive and Negative Social Exchanges and Cognitive Aging in Young-Old Adults: Differential Associations Across Family, Friend, and Spouse Domains - Tim D Windsor; Denis Gerstorf; Pearson, Elissa; Lindsay H Ryan; Kaarin J. Anstey (Psychology and Aging, 2014)
We examined how positive and negative social exchanges with friends, family, and spouses were related to cognitive aging in episodic and working memory, and perceptual speed. To do so, we used a large sample of cognitively intact young-old participants from the PATH Through Life Study ( PATH; aged 60 to 64 years at baseline, n = 1,618) who were assessed on 3 occasions over 8 years. Additional replication analyses were conducted using the Health and Retirement Study (HRS), which provided data on episodic memory. The main analysis of PATH Through Life showed that positive exchanges with friends and family were associated with less decline in perceptual speed, with these associations attenuated by adjustment for physical functioning and depressive symptoms. Negative exchanges with spouses were associated with poorer working memory performance. Positive exchanges with friends were associated with better initial episodic memory in both PATH and HRS. More frequent negative exchanges with friends and family were associated with better episodic memory in the PATH sample. However, these findings were not replicated in HRS. Our findings provide indirect support for the role of social exchange quality in contributing to cognitive enrichment. However, the inconsistent pattern of results across cognitive and social exchange domains points to possibilities of reverse causality, and may also indicate that social exchange quality plays a less important role for cognitive enrichment than other psychosocial characteristics.
Keywords: End of life decisions; Event History/Life Cycle; Health Conditions and Status; Methodology; Other; Retirement Planning and Satisfaction

Predictors of Long-Term Nursing Home Placement Under Competing Risk: Evidence from the Health and Retirement Study - Castora-Binkley, Melissa; Meng, Hongdao; Hyer, Kathryn (Journal of the American Geriatrics Society, 2014)
Objectives:To examine predictors of long-term nursing home placement (LTNHP) while controlling for mortality as a competing risk event. Design: Longitudinal. Setting: Health and Retirement Study, 1998-2010. Participants: Nationally representative sample of community-living older adults (N=10,385). Measurements: Longitudinal data were used with a maximum follow-up of 12years. First, a traditional Cox proportional hazards model was estimated treating death as an uninformative censoring event. A joint cause-specific hazards model that accounts for the competing risk of mortality in estimating the risk of LTNHP was then estimated. Results: The effect of adjusting for competing risk of mortality is evident for nearly all predictors of LTNHP. Predictors were over- or underestimated in the traditional Cox model, and several predictors changed in the direction of the association, whereas others changed in magnitude. For example, after controlling for mortality, women aged 85 and older had more than twice the risk (hazard ratio=7.23, 95 confidence interval=5.18-10.10) of LTNHP than evidenced in the traditional Cox model. Conclusion: Whenever possible, the competing risk of mortality should be recognized and adjusted in developing screening tools and predictive risk models for LTNHP.
Keywords: Health Conditions and Status; Healthcare; Methodology; Risk Taking

Racial and Educational Disparities in Mobility Limitation Among Older Women: What Is the Role of Modifiable Risk Factors? - Kenzie Latham (The Journals of Gerontology Series B: Psychological Sciences and Social Sciences, 2014)
Objectives. This research explores whether modifiable risk factors (MRFs) are potential mediators and/or moderators of racial/ethnic and educational mobility limitation disparities among older women.Method. Utilizing Waves 2 9 (1994 2008) of the Health and Retirement Study (HRS), discrete-time event history models with multiple competing events were estimated using multinomial logistic regression.Results. Black women were more likely to develop mobility limitation relative to White women. This disparity was partially mediated by body mass index. Educational disparities were also observed, yet MRFs did not appreciably influence this disparity. The effect of vigorous physical activity on mobility limitation onset varied by race; physical activity was not as protective for Black women compared with White women. Being overweight appeared to weaken the benefit of additional years of education.Discussion. These results reiterate the importance of health promotion via MRFs; however, they also illustrate that the effect of MRFs on mobility limitation varies by race and education among older women, which has implications for health professionals interested in functional health interventions. Future recommendations include the development of interventions and health promotion aimed at increasing participation in positive health behaviors that address salient social factors among at-risk older women.
Keywords: Demographics; Health Conditions and Status; Methodology; Risk Taking

Reducing the Economic Burden of Work-Related Injuries - McLaren, Christopher F. (The Pardee RAND Graduate School, 2014)
This study examines the effectiveness of employer return to work programs in reducing the average duration of absences from work-related injuries. It finds that workers injured with an employer return to work program in place return to sustained employment approximately 1.38 times sooner after an injury. The biggest reductions in work-injury absence are experienced by men and by workers with a permanent disability. Modifying work equipment is associated with the greatest reductions in injury durations relative to other program components. Back-of-the-envelope calculations indicate that these programs are cost effective for large, self-insured employers. Keywords: workers' compensation, injuries and employee return to work, workplace injuries and employer self-insurance
Keywords: Employment and Labor Force; Health Conditions and Status; Methodology; Public Policy

Reliability of Self-reports of Financial Data in Surveys: Results From the Health and Retirement Study - Duane F. Alwin; Zeiser, K.; Gensimore, D. (Sociological Methods and Research, 2014)
This article reports an investigation of errors of measurement in self-reports of financial data in the Health and Retirement Study (HRS), one of the major social science data resources available to those who study the demography and economics of aging. Results indicate significantly lower levels of reporting reliability of the composite variables in the HRS relative to those found for summary income approaches used in other surveys. Levels of reliability vary by type of income source-reports of monthly benefit levels from sources such as Social Security or the Veterans Administration achieve near-perfect levels of reliability, whereas somewhat less regular sources of household income that vary across time in their amounts are measured less reliably. One major area of concern resulting from this research, which may be beneficial to users of the HRS surveys, involves the use of imputation in the handling of missing data. We found that imputation of values for top-end open income brackets can produce a substantial number of outliers that affect sample estimates of relationships and levels of reliability. Imputed income values in the HRS should be used with great care. The Author(s) 2013.
Keywords: Income; Methodology; Other

Representativeness of the Low-Income Population in the Health and Retirement Study with Supplementary Analyses for 1991 and 1997 - Erik Meijer; Lynn A Karoly (Ann Arbor, MI, Michigan Retirement Research Center (MRRC) Working Paper, WP 2014-316, 2014)
We study to what extent the Health and Retirement Study (HRS) is representative of all income groups, but with a particular emphasis on low-income groups. To focus on the HRS sample composition and abstract from potential measurement issues associated with measures of income and program participation, we exploit the SSA administrative data matched to the HRS sample and compare their distribution against the distribution of the same variables for the same population in the SSA databases. We find that overall, for cohorts and years that can be most reliably compared, the distributions are very similar and conclude that the HRS is representative for the population it covers. However, for some subgroups in the low-income population (e.g., recipients of Supplemental Security Income, Medicaid beneficiaries), there are some differences and thus we caution against estimating population totals for such small subpopulations. The HRS samples for which restricted matched administrative data are available are often not representative of a broad population of interest, because not all HRS respondents were asked permission to match in any given year. Therefore, the restricted HRS datafiles are generally not suitable for estimating population distributions, although they are still very useful for modeling purposes.
Keywords: Income; Methodology; Social Security

A Research Note on the Relationship Between Long Working Hours and Weight Gain for Older Workers in the United States - Murat Anil Mercan (Research on Aging, 2014)
Working long hours may be related to obesity in older adults. No studies have focused on older workers and long work hours, although the risk of obesity is high among this population group. This study is the first attempt to investigate the relationship between obesity and the older workforce. Panel data from the Health and Retirement Study are examined using Cox regression techniques. We found that older workers who work more than 59 hr a week are more likely to gain weight than older workers who work less than 59 hr per week.
Keywords: Employment and Labor Force; Health Conditions and Status; Methodology

The role of satisfaction and switching costs in Medicare Part D choices - Han, Jayoung; Michelle J Ko; Julie M. Urmie (Research in Social and Administrative Pharmacy, 2014)
Background Most U.S. states had over 50 Medicare Prescription Drug Plans (PDPs) in 2007. Medicare beneficiaries are expected to switch Part D plans based on their health and financial needs; however, the switching rate has been low. Such consumer inertia potentially has negative effects on both beneficiaries and the insurance market, resulting in a critical need to investigate its cause. Objectives To 1) describe how Medicare beneficiaries who were satisfied with their current Part D plan differed from those who were not satisfied; 2) examine the effect of switching costs on consideration of switching among Medicare beneficiaries who were dissatisfied with their current Part D plan. Methods Data from the 2007 Prescription Drug Study supplement to the Health and Retirement Study (HRS) survey were used in this study. The satisfied and dissatisfied groups were compared in terms of cost variables, switching costs, and perception of Part D complexity. Structural equation modeling was used to examine relationships among switching costs, Part D complexity, cost variables, and consideration of switching for beneficiaries who were dissatisfied with their current Part D coverage. Results Out of 467 participants, a total of 255 (54.6 ) were satisfied with their current Part D plan. The satisfied group paid lower out-of-pocket costs ( 50.63 vs. 114.60) and premiums ( 30.88 vs. 40.77) than the dissatisfied group. They also had lower switching costs. Only 11.3 of the dissatisfied beneficiaries switched plans. Among respondents who were dissatisfied with their current plan, those who perceived Part D as complex had high switching costs and were less likely to consider switching plans. Out-of-pocket cost did not have a statistically significant association with consideration of switching. Conclusions Medicare beneficiaries who were satisfied with their current Part D plans had lower out-of-pocket costs and premiums as well as higher switching costs. Among beneficiaries who were dissatisfied with their current Part D plan, those who had higher switching costs were less likely to consider switching Part D plans.
Keywords: Medicare/Medicaid/Health Insurance; Methodology; Retirement Planning and Satisfaction

Rounding, focal point answers and nonresponse to subjective probability questions - Kristin J. Kleinjans; Arthur H.O. vanSoest (Journal of Applied Econometrics, 2014)
We develop a panel data model explaining answers to subjective probabilities about binary events and estimate it using data from the Health and Retirement Study on six such probabilities. The model explicitly accounts for several forms of 'reporting behavior': rounding, focal point '50 ' answers and item nonresponse. We find observed and unobserved heterogeneity in the tendencies to report rounded values or a focal answer, explaining persistency in 50 answers over time. Focal 50 answers matter for some of the probabilities. Incorporating reporting behavior does not have a large effect on the estimated distribution of the genuine subjective probabilities. 2013 John Wiley and Sons, Ltd.
Keywords: Expectations; Methodology

Self-employment of older Americans: do recessions matter? - Biehl, Amelia M.; Gurley-Calvez, Tami; Hill, Brian (Small Business Economics, 2014)
As high unemployment rates linger following the latest recession, job opportunities can be sparse, especially for older workers. This might prompt older Americans to seek out opportunities in self-employment. Alternatively, recession-related decreases in economic activity might make self-employment less attractive. Using the Health and Retirement Study, we find that unemployed respondents are more likely to enter self-employment and that these decisions are clearly affected by recessions, although the effects differ by recession and gender. Unlike men, women s self-employment decisions are very sensitive to other sources of household income, and women are less likely to become self-employed the deeper the recession.
Keywords: Demographics; Employment and Labor Force; Methodology; Other; Public Policy

Sex differences in the construct overlap of frailty and depression: evidence from the health and retirement study - Matthew C. Lohman; Dumenci, Levent; Briana Mezuk (Journal of the American Geriatrics Society, 2014)
OBJECTIVES: To determine the degree of diagnostic overlap between frailty and depression and to investigate whether sex differences in symptom endorsement influence this overlap. DESIGN: Cross-sectional latent class analysis. SETTING: Data were from the 2008 wave of the Health and Retirement Study, a nationally representative longitudinal survey of health characteristics of older adults. PARTICIPANTS: Community-dwelling adults aged 65 and older completing a general health questionnaire and consenting to physical measurements (N=3,665). MEASUREMENTS: Frailty was measured using criteria developed in the Cardiovascular Health Study, and depressive symptoms were measured using the eight-item Center for Epidemiologic Studies Depression scale. RESULTS: Frailty and depression were best modeled as two distinct but highly correlated constructs with three and four classes of symptom response, respectively. Measurement overlap was high in men and women. Approximately 73 of individuals with severe depressive symptoms and 86 with primarily somatic depressive symptoms were categorized as concurrently frail. The degree of construct overlap between depression and frailty did not significantly vary according to sex, but women were significantly more likely to endorse all frailty and depressive symptoms. CONCLUSION: Measures of depression and frailty identify substantially overlapping populations of older men and women. More-frequent endorsement of depressive symptoms, but not differential endorsement of somatic symptoms, may contribute to the higher prevalence of frailty in women. The symptom of exhaustion is particularly important to the correlation between these two conditions. Findings will inform clinician and researcher efforts to refine the definition of geriatric syndromes such as frailty and to develop effective interventions.
Keywords: Health Conditions and Status; Methodology

Snapshots of Mixtures of Affective Experiences in a Day: Findings from the Health and Retirement Study - Jacqui Smith; Lindsay H Ryan; Tara L Queen; Sandra E Becker; Gonzalez, Richard (Journal of Population Ageing, 2014)
In 2009, a representative subsample of participants in the Health and Retirement Study (HRS: N = 5333; Age 50 101) responded to a short day reconstruction self-administered questionnaire that asked about their time and experiences on seven activities the previous day. We evaluate the quality and reliability of responses to this 10-min measure of experienced well-being and compare the properties and correlates of three intensity-based composites reflecting mixtures of activity-linked affective experiences (Activity-Positive Affect, Activity-Negative Affect, and Net Affect), and a frequency-based index, Activity Affective Complexity, that summarizes the proportion of activities that include a mixture of positive and negative affective experiences regardless of intensity. On average, older adults reported that 36 of the activities in their day provided some mixture of feelings (e.g., interested and frustrated). Regression models revealed differential associations for the four constructs of affective well-being with socio-demographic factors, physical and mental health, and proximal indicators of the day s context. We conclude that the HRS short day reconstruction measure is reliable and discuss the conceptual issues in assessing, summarizing, and interpreting the complexity of emotional experience in older adults.
Keywords: Demographics; Expectations; Health Conditions and Status; Methodology

The social environment, APOE-e4, and dementia: The social environment as a moderating factor among individuals genetically predisposed to develop dementia - Judith L Poey (University of Massachusetts Boston, 2014)
Many studies have shown a relationship between the APOE-e4 allele and dementia, as well as a relationship between the social environment and dementia. However, relatively little investigation into the potential moderating effect of the social environment on the relationship between the APOE-e4 allele and cognitive well-being has been reported. Further, studies that did examine these relationships typically have employed clinical populations, along with regional and non-U.S. samples. This study contributed to the research literature, in part, by using the first U.S. nationally representative sample of older adults that included clinical diagnosis of cognition and dementia (Aging, Demographics, and Memory Study from the Health and Retirement Study). A combination of descriptive analyses and multinomial logistic regression models were used to investigate these relationships. Overall, the prevalence of unique APOE genotypic combinations was similar in the ADAMS sample as compared to samples taken from other developed nations. Descriptive results also showed that respondents with and without the APOE-e4 allele were only found to differ on race and ethnic status. Regression results indicated that the APOE-e4 allele was associated with a higher risk of cognitive difficulty, and that being more socially engaged and more socially connected to others was associated with a lower risk of cognitive difficulty and dementia. All aspects of the social environment, except social engagement, were found to moderate the relationship of the APOE-e4 allele to cognitive diagnosis. The relationship of the social environment to dementia, as well as its moderating influence, indicated a need for further investigation into the unique contributions of the social environment for cognitive well-being in later life.
Keywords: Demographics; Genetics; Health Conditions and Status; Methodology

Three Essays in Health, Education, and Retirement - Arons, Robert (University of Rochester, 2014)
In chapter one I examine the impact of Health Maintenance Organization (HMO) coverage on the provision of preventive medicine procedures and undiagnosed disease. Rates of missed preventive care and undiagnosed conditions are substantially lower for middle-aged HMO enrollees compared to non-HMO enrollees. I control for selection with a novel quasi-experiment: turnover in group health insurance contracts at the firm level creates exogenous variation in plan type. The large age heterogeneity in the effect of HMO contracts is consistent with incentive structures in HMOs playing a role in the quality of patient care. In chapter two I use a regression discontinuity framework to analyze the No Child Left Behind (NCLB) Act's attempt to reduce the achievement gap by requiring sociodemographic groups meet group based proficiency count targets. Using a panel of North Carolina public school students in grades three through eight from 2003-2012, I find when a student's group is added to the set of existing accountable groups, it has a small positive impact on subject matter proficiency and test scores. Variation in the application of these laws comes the fact that groups are only held to academic proficiency standards if there are 40 or more tested students in the group within the school. In chapter three I estimate the potential earnings of retirees. Estimating the earnings structure of those no longer working is complex, because (1) health and cognition decline at older ages and drive workers into retirement, (2) retirement may cause changes in health and cognition, and (3) unobserved wage shocks may also drive workers into retirement and bias estimates depending on the direction of selection. Issue (1) is solved by using health and cognitive measures from the data, the Health and Retirement Study. Issues (2)-simultaneity of retirement with health and cognition, and (3)-selection out of the labor force, are controlled for with four instruments, self-reported probability of retirement at age 62 and 65 reported at age 55 and age dummies for 62 and 65. We find that retirees would earn less than a selection corrected estimator would suggest by about $13,000 per year.
Keywords: Adult children; Demographics; Employment and Labor Force; Health Conditions and Status; Healthcare; Methodology; Retirement Planning and Satisfaction

Three essays in labor economics and the economics of education - Stacy, Brian (Michigan State University, 2014)
In the first chapter of my dissertation, I examine the robustness of typical teacher quality measures to alternate ranking systems factoring in the dispersion of value-added. The typical measure used by researchers and school administrators to evaluate teachers is based on how the students' achievement increases after being exposed to the teacher, or based on the teacher's ``value-added''. When teacher value-added is heterogeneous across her students, then the typically used measure reflects differences in the average value-added the teacher provides. However, researchers, administrators, and parents may care not just about the average value-added, but also its variance. Encouragingly, ranking systems factoring in the dispersion produce similar rankings as the ranking system based only on the mean. In the second chapter, I examine the effect of measurement error in the dependent variable on quantile regression, because unlike OLS regression, even classical measurement error can generate bias. I examine the pattern and size of the bias using both simulation and an empirical example. The simulations indicate that classical error can cause bias and that non-classical measurement error, particularly heteroskedastic measurement error, has the potential to produce substantial bias. Using restricted access Health and Retirement Study data containing matched IRS W-2 earnings records, I examine whether estimates of the returns to education statistically differ using a precisely measured and mismeasured earnings variable. I find that returns to education are over-stated by roughly 1 percentage point at the median and 75th percentile using earnings reported by survey respondents. In the third chapter, my coauthors and I investigate how the precision and stability of a teacher's value-added estimate relates to student characteristics. We find that the year-to-year stability of teacher value-added estimates can depend on the previous achievement level of a teacher's students. The stability level of the estimates are typically 25% to more than 50% larger for teachers serving initially higher performing students. We offer a policy simulation demonstrating that teachers who serve low-achieving students may be differentially likely to be the recipient of sanctions in a high stakes policy based on value-added estimates.
Keywords: Demographics; Employment and Labor Force; Methodology; Public Policy; Social Security

Zeta Estimates of Wealth Volatility and Financial Planning Horizon - Grable, John; Chatterjee, Swarn (Ewha Journal of Social Sciences, 2014)
The intention of this study was to document how closely households follow normative descriptions of financial behavior in relation to their financial planning horizon. Modern Portfolio Theory predicts that households, in general, exhibit risk aversion. Aversion to wealth volatility should correspondingly be highest among those households with the shortest planning horizons. This study estimated percentage changes in wealth and wealth volatility over time categorized by financial planning horizon using data from the 2002 through 2010 waves of Health and Retirement Study. Modigliani ratios were computed for the entire population and by planning horizon. Zeta estimates were made by calculating the difference between the Modigliani ratios for each planning horizon and the ratio for the short-term horizon. Contrary to the conceptualized relationship between planning horizon and financial wealth volatility, results from this study show that respondents with the shortest financial planning horizons experienced lower risk-adjusted returns and greater wealth volatility. The findings of this study underscore an unmet and perhaps unrealized need for professionally provided financial planning.
Keywords: Methodology; Net Worth and Assets

Analysis of panel data with informative missing responses - Zhang, Jie (The University of Wisconsin - Madison, 2013)
Missing responses is a common problem existing in panel data collection. In some studies, one can argue that the missingness does not depend on unobserved responses given all observed information. However, in many other studies, the missing pattern is more likely to be dependent on the unobserved responses. When this dependence is indirect through some panel level random effects, it is called ``informative missingness''. Some parametric and semi-parametric estimation methods have been proposed in the literature for informative missing responses, where the estimation processes are mainly likelihood-based. In this thesis work, we proposed a semi-parametric method to solve this estimation problem. Because no specific distribution assumption is needed in our method, this method can be easily employed in practice without worrying about model mis-specification and struggling with maximization of complicated likelihoods. The estimation process contains two steps as we partition the parameters into two parts based on their relationship to the random effects. Parameters not related to random effects are estimated first, with the introduction of a linear transformation. In the second stage, these parameters are replaced by their estimates, and the remaining parameters can be estimated. Grouping of panels may be necessary if some panels do not have enough observation. The resulting estimators are proved to be unbiased and asymptotically normal. Simulation studies comparing our estimator to some other existing estimators are conducted, which shows advantage of our methods under certain informative missingness setting. This proposed method is applied to a real data examples: the Health and Retirement Study.
Keywords: Methodology; Other

Cognitive and Physical Health of the Older Populations of England, the United States, and Ireland: International Comparability of The Irish Longitudinal Study on Ageing - Savva, George M.; Maty, Siobhan C.; Setti, Annalisa; Feeney, Joanne (Journal of the American Geriatrics Society, 2013)
This article discusses the contribution that international comparisons of the health and well-being of older people make. The comparability of the HRS family of studies that have been modeled on the U.S. Health and Retirement Study (HRS) is discussed. The Irish Longitudinal Study of Ageing (TILDA) is introduced, and the comparability of TILDA data with respect to the HRS family and other studies is described, along with what TILDA will add to international aging research. Data from the 2010 waves of TILDA,HRS and the English Longitudinal Study of Ageing are used to compare the physical and cognitive health of older Irish adults with that of the U.S. and English populations. The study shows that the physical and cognitive health of older people in Ireland is closer to that of their English counterparts than of those in the United States and that similar health inequalities exist in all three countries.
Keywords: Cross-National; ELSA; Health Conditions and Status; Methodology; TILDA

Diabetes is associated with cognitive impairment no dementia in the aging, demographics, and memory study (ADAMS) - Christine E Gould; Sherry A. Beaudreau; Salman, Huma (International Psychogeriatrics, 2013)
Individuals with diabetes mellitus have a 1.39 times increased risk of Alzheimer's disease, a 2.38 times increased risk of vascular dementia, and a faster rate of cognitive decline compared to individuals without diabetes (Lu et al., 2009). In a study, over a 9-year follow-up diabetes was associated with accelerated progression from mild cognitive impairment (MCI) to dementia, but was not associated with progression from no impairment to MCI (Xu et al., 2010). Many previous studies on cognitive impairment and diabetes are limited by the use of cognitive screens to diagnose and assess cognitive impairment. A few studies diagnosing cognitive impairment with comprehensive neuropsychological batteries provide mixed results. For instance, Luchinger et al. (2007) found that diabetes was correlated with the presence of MCI, whereas diabetes was not associated with the presence of dementia versus no dementia in the Aging, Demographics, and Memory Study ADAMS; (Llewellyn et al., 2010).
Keywords: Health Conditions and Status; Methodology; Risk Taking

Differences in diabetes mellitus onset for older Black, White, and Mexican Americans - A. R. Quinones; Jersey Liang; Wen Ye (Ethnicity and disease, 2013)
OBJECTIVES: Our research examines the differences in estimated odds of developing diabetes mellitus for White, Black, and Mexican Americans age 51 and over for a period of 11 years. DESIGN, SETTING, AND PARTICIPANTS: Longitudinal data came from 14,783 respondents of the Health and Retirement Study (1995-2006) who reported being diabetes-free at the first time period. Discrete-time survival models were used to analyze ethnic variations in the probability of developing diabetes. MAIN OUTCOME MEASURE: Estimated odds of developing diabetes mellitus. RESULTS: The odds of newly diagnosed diabetes increased between 1995 and 2006, with 11 cumulative incidence for all study participants. The probability of incident diabetes among Black Americans was .01 during the period of 1995/96-1998, which increased to .03 during 1998-2000 and remained at .03 throughout subsequent periods, with cumulative incidence over the 11 years at 12 . In contrast, for Mexican Americans the probability more than doubled from .02 in 1995/ 96-1998 to .05 in 2004-2006, with cumulative incidence at 19 . White Americans had 11 cumulative incidence during the 11 year period. CONCLUSIONS: Relative to White Americans, Mexican Americans had significantly elevated odds of developing diabetes throughout the 11-year period of observation even after controlling for differences in demographic, socioeconomic, and time-varying health characteristics.
Keywords: Health Conditions and Status; Methodology; Women and Minorities

Documentation of Biomarkers in the 2006 and 2008 Health and Retirement Study - Eileen M. Crimmins; Jessica Faul; Jung K Kim; Heidi M Guyer; Kenneth M. Langa; Mary Beth Ofstedal; Amanda Sonnega; Robert B Wallace; David R Weir (Institute for Social Research, University of Michigan, 2013)
Biomarkers refer to the general range of physiological, metabolic, biochemical, endocrine and genetic measures that can be obtained in living organisms. The term is most commonly used to refer to one-time biochemical or hematological measures made on blood or other available bodily fluids, but perhaps the term should be used for a broader range of measures. In 2006 and 2008, HRS included the following biomarkers measurements, administered in this order: Saliva collection for DNA extraction; Blood spot collection for cholesterol, hemoglobin A1C, CRP and cystatin C analysis (results for C-reactive protein and cystatin C are forthcoming). This report describes the following for each of the measures listed above: Rationale and key citations; Sample description; Measure description; Equipment; Protocol description; Special instructions.
Keywords: Health Conditions and Status; Healthcare; Methodology

Editorial: Dawning of a New Age for Longitudinal Cohort Data - Richard M. Suzman; Harper, Sarah (Journal of Population Ageing, 2013)
Issue Title: Special Issue: Longitudinal Cohort Data
Keywords: Demographics; Health Conditions and Status; Methodology; Other

Education and Dementia Risk: Results From the Aging Demographics and Memory Study - Rashmita Basu (Research on Aging, 2013)
This study examined importance of education on dementia risk among older adults. It explored to what extent this relationship represents an independent effect of education on dementia risk. A cross-sectional sample of adults age 70 years or older was selected from the Aging Demographics and Memory Study, a supplement to the Health and Retirement Study, to examine the association between education and dementia risk and to mitigate the possibility of self-selection bias (unobserved variable bias) in explaining this correlation. An identification strategy using parental and sibling characteristics as instrumental variables for education was used to remove bias from the estimate of education parameter s effect on dementia risk. The association between education and dementia risk was observed after accounting for self-selection bias. Results from the two-stage ordered logit model suggest that the impact of education on dementia risk is not an artifact but rather the observed association between education and dementia incidence has a causal component.
Keywords: Demographics; Health Conditions and Status; Methodology; Risk Taking

Essays in public economics - Lee, Insook (University of California, Berkeley, 2013)
My dissertation, "Essays in Public Economics," is comprised of three chapters. The first one, titled "Altruism, Reciprocity, and Equity: A Unified Motive for Intergenerational Transfers" is to address the following question: Why do parents divide bequests equally while transferring inter vivos gifts unequally? Across times and places, why have there mainly been only two extreme choices of distribution of bequests: either to give them to just one child (unigeniture) or to divide them equally (equigeniture)? How can a motive for intergenerational transfers explain both "equal division puzzle" (the former) and polarized inheritance patterns (the latter)? This chapter presents a behavioral model that coherently rationalizes these empirical realities. Namely, as head of a family, a parent altruistically cares about children but also wants them to spend effort for family. However, effort is costly and individual level of each child is unverifiable to a third party adjudicator. Given this incomplete information, there rise only two stable equilibria: either equigeniture or unigeniture. When the productivity of effort rises, the evolution of inheritance pattern from unigeniture to equigeniture occurs. So equigeniture is eventually adopted due to a rise in the productivity throughout industrialization. Furthermore, if the parent wants to counterbalance inequality among children who exert equal effort, the greater amount of inter vivos gift is transferred to a child with lower relative income compared to his siblings, while bequests remain equally divided. This model is consistent with the aforementioned empirical realities but also lends itself to further empirical tests. The second chapter "Retirement and Exposure of Pension to Financial Market Fluctuations" studies how exposure of pension wealth to stock market fluctuations affects retirement behavior both theoretically and empirically. Characteristics of optimal plan for retirement are elaborated with reflecting that liquidizing pension wealth is more tied to retirement decisions than non-pension wealth as well as embodying time-sensitive restrictions on availability of pension benefits. Theoretical analysis finds that exposure of pension to financial market fluctuations does not always entail perfectly symmetric response of retirement. Exposure of pension to a positive shock actually brings responses of retirement only if the magnitude of the positive shock is large enough to compensate for foregone labor earnings and demand for resources necessary for post-retirement consumptions. In particular, whereas exposure of pension to a small negative shock leads to a decrease in retirement, exposure of pension to a positive shock with the same magnitude might not yield an increase in retirement. The third chapter, titled "Optimal Income Taxation and Optimal Revenue Mobilization," analyzes characteristics of nonlinear optimal income taxation and optimal revenue mobilization when the tax enforcement of a government is not costless (and thus not presumed to be perfect). The government cannot observe and verify an individual's innate ability although that ability turns out to cause inequality amongst them. This prevents the government from avoiding efficiency loss in the taxation, since each taxpayer can take advantage of private information over their own ability by reducing working hours to pretend to be less able than he truly is. Optimal income tax schedule is designed to minimize the efficiency loss from deterring such behavior to maximize social welfare. Moreover, the desired expenditure of the government is set for enhancing minimum living standard of society. In executing the tax schedule to finance this, however, tax evasion occurs due to imperfect enforcement. Although the government can verify the true amount of taxpayer's earnings, unlike their ability, it is costly to increase the enforcement rate. The optimal rate equalizes a gain of net increase in the tax revenue with a loss of decreased utility of risk-averse taxpayers from an incre ent in the rate. Notably, this cha ter shows that aggregate loss of tax revenue can theoretically justify non-zero tax rate on top earners. (Abstract shortened by UMI.)
Keywords: Adult children; Methodology; Net Worth and Assets; Public Policy

Essays on elderly asset management the role of medical expenses and housing - Li, Li (State University of New York at Albany, 2013)
With baby-boomers approaching their retirement age, the financial security of elderly Americans has become increasingly crucial for both policy-makers and retirees themselves. Based on the data from the Health and Retirement Survey (HRS), this dissertation examines how healthcare costs and housing affect retirees' saving and investment decisions. In chapter 1, I investigate the pattern of asset allocation among elderly Americans and test if large out-of-pocket (OOP) medical expenses were preventing older households from holding risky assets. My results show that the elderly are more likely to own risky financial assets while less likely to own housing assets as their OOP medical expenses go up. And conditional on ownership, relatively large OOP medical expenses are significantly correlated with high share of risky financial assets and low share of housing assets. These results imply that large OOP medical expenses may be capturing something other than poor health, which I explain by a "mechanical" effect that older households sell their houses to finance their large OOP medical expenses, driving up the risky financial assets share. In chapter 2, I develop a life-cycle dynamic programming model that particularly assumes elder homeowners would sell their houses to finance large medical expenses such as nursing home costs. My model finds that retirees with housing are less sensitive to the magnitude of medical expense shocks and thus maintain fewer precautionary savings. Without housing assets, retirees tend to take fewer risks while investing at the early stage of their retirement, but may have to take chances to finance elevated medical expenses as they approach the end of their life cycle. In chapter 3, I relax the borrowing constraint assumed in the prior two chapters and study the impact of health problems and related expenses on elderly households' financial security. I estimate the probability of medical default among 65 and above age group using various qualitative choice models. Results indicate that high medical debt to income ratio rather than OOP medical expense itself contributes to the high probability of default.
Keywords: Housing; Medicare/Medicaid/Health Insurance; Methodology; Net Worth and Assets; Public Policy

Essays on formal and informal long-term health insurance markets - Woldemichael, Andinet D. (Georgia State University, 2013)
This dissertation consists of two essays examining formal and informal long term health insurance markets. The first essay analyzes heterogeneity of Long-Term Care Insurance policyholders in their lapse decision, and how their ex-ante and ex-post subjective beliefs about the probability of needing Long-Term Care affect their lapse decisions. In this essay, I develop a model of lapse decision in a two-period insurance framework with a Bayesian learning process and implement several empirical specifications of the model using longitudinal data from the Health and Retirement Study. The results show that policyholders' ex-ante point predictions of their probabilities and their uncertainties about them have a persistent but declining impact on lapse decisions. Those who believe that their risk is higher are indeed more likely to remain insured. However, as their uncertainties surrounding their ex-ante point predictions increase, their chances of lapsing increase regardless of their initial perception biases. These results are heterogeneous across cohorts and policyholders and, in particular, show that those in the older group near the average age of Nursing Home entry have a precise prediction of their risk levels compared to the younger cohort. Policy simulations show that a more informed initial purchase decision reduces the chance of lapsing down the road. The second essay examines the extent to which informal risk sharing arrangement provides insurance against health shocks. I develop a comprehensive model of informal risk sharing contract with two-sided limited commitment which extends the standard model to a regime with the following features. Information regarding the nature of realized health shocks is imperfect and individuals' health capital stock serves as a storage technology and is a factor of production. The theoretical results show that, in such a regime, Pareto optimal allocations are history dependent even if participation constraints do not bind. I perform numerical analysis to show that risk sharing against health shock is less likely to be sustainable among non-altruistic individuals with different levels of biological survival rates and health capital productivity. The results also show that optimal allocations vary depending on the set of information available to individuals. Using panel data of households from villages in rural Ethiopia, I test the main predictions of the theoretical model. While there is negative history dependence in transfers among non-altruistic partners, history dependence is positive when risk sharing is along bloodline and kinship. However, neither short-term nor long-term health shocks are insured through informal risk sharing arrangements among non-altruistic individuals.
Keywords: Health Conditions and Status; Healthcare; Medicare/Medicaid/Health Insurance; Methodology; Other

Essays on gender differences in occupational choices and cohort analysis of saving adequacy - Li, Hsueh-Hsiang (The University of Wisconsin - Madison, 2013)
The first chapter analyzes how human capital depreciation affects occupational gender segregation. Prior studies are biased because, given an occupational depreciation rate, female workers endogenously choose the duration of leave. I address this problem by proposing an alternative depreciation measure utilizing involuntary job displacement shocks. Using this depreciation proxy along with additional pecuniary and non-pecuniary occupational attributes, I estimate a conditional logit model of occupational choices separately for male and female college graduates using NLSY79 data. The results show that men and women differ largely in selection on many occupational attributes, however, the gender difference in depreciation is statistically insignificant after accounting for additional variance from the generated depreciation regressor. The second chapter explores the trend of gender differences in selection on occupational mobility. Women who interrupt their career and return to the labor force face the uncertainty of forming a new job match. This uncertainty can be large if the skills they acquired are occupational-specific. I estimate discrete occupational choices by different cohorts using cross-sectional Current Population Survey (CPS) from 1979 to 2008.I find that over the past 30 years, the consideration of occupational mobility has abated in female occupational decisions. In addition, gender gaps in work hours and visual perception also narrow over the past thirty years. Increasing female representation is evident in occupations with high entry barriers, long work hours, and visual intensive tasks. In the third chapter, we extend the dynamic programming approach used in Scholz, Seshadri, and Khitatrakun (2006) to assess the adequacy of retirement wealth preparation in 2008, using a sample of Americans born before 1954. We examine whether these households have accumulated the wealth necessary to maintain pre-retirement living standards in retirement. Our preliminary results suggest that over 70 percent of the households in our sample had accumulated sufficient resources in 2008. The results suggest a less optimistic view about the adequacy of Americans' retirement preparation than the findings for 1992 in Scholz, Seshadri, and Khitatrakun (2006). Economically disadvantaged households are significantly more likely than others to be under-saving and hence are natural targets for outreach and other efforts to improve financial capabilities.
Keywords: Consumption and Savings; Demographics; Employment and Labor Force; Methodology; Net Worth and Assets

Essays on health economics - Beck, Laurel (The University of Wisconsin - Madison, 2013)
Chapter 1: Medicare provides nearly-universal health insurance for individuals aged 65 and older. The discontinuity in eligibility for Medicare provides an instrument for assessing the effects of insurance coverage on health outcomes. Using regression discontinuity analysis and data from the BRFSS, this paper finds an increase in utilization of preventive health services, as well as an improvement in self-reported health, at age 65. The effects vary across education level and gender. However, these results would be biased by high retirement rates at age 65. To address this issue, I run similar analysis at age 62, when individuals are first eligible to collect Social Security. I find that utilization is positively correlated with insurance but not retirement. The implications of these findings for assessing the cost-effectiveness of preventive care are limited, because the cross-sectional data do not capture the long-term benefits of diagnostic procedures. Chapter 2: This paper assesses the effects of working on the health of less-educated women, particularly mothers. These effects are difficult to estimate because health status affects labor force participation. To address this endogeneity problem, I use an instrumental variables estimation approach. Throughout the 1990s, changes in the EITC and the transition from AFDC to TANF provided exogenous incentives for women to enter the work force, independent of their own health status. This paper builds on the literature by including the incentives created by welfare reform and EITC which vary by state. It also includes measures of both physical and mental self-reported health, giving a broad picture of the effects of entering the labor force on the health of this population. Chapter 3: This chapter (with Atsuko Tanaka), examines the effect of depression on various labor force outcomes, including hours worked and wages. We use panel data from the Japanese Panel Survey of Consumers (JPSC) and the Health and Retirement Study (HRS) to follow respondents over several years, using questions about both mental health and labor force outcomes. In order to understand the causal effect of depression on work participation and compensation, we use deaths of the parents of respondents as an exogenous shock to mental health.
Keywords: Employment and Labor Force; Health Conditions and Status; Insurance; Methodology; Other; Retirement Planning and Satisfaction; Women and Minorities

Essays on Labor Economics - Tanaka, Atsuko (The University of Wisconsin - Madison, 2013)
This dissertation investigates determinants of labor supply decision and worker productivity. In the first two chapters, I investigate inefficiency due to statistical discrimination, in which employers---who do not observe the individual worker's labor force intention---offer a female worker fewer human capital investment opportunities than a male worker because of women's weaker labor force attachment. Owing to imperfect information, productivity inefficiency arises when women receive the same amount of investment despite the fact that women with shorter job tenure are potentially less productive than other workers. To study such a situation, I develop a model of statistical discrimination with a screening mechanism. In the third chapter, a joint project with Laurel Beck, I shift focus from statistical discrimination to worker's mental health as determinants of worker productivity. The first chapter applies the above model empirically to Japanese data, whose features exhibit evidence for statistical discrimination. The Japanese female labor market is found to be in a pooling equilibrium, thereby allowing statistical discrimination. I then estimate the effects of child-care subsides on the degree of statistical discrimination. The counterfactual analysis shows that child-care subsides could bring a drastic change in efficiency to Japan by altering the equilibrium of the worker-firm game from pooling to separating. The second chapter theoretically examines the factors that further complicate the screening process. I argue that long-term wage contracts implicitly distribute compensation from the employed to the unemployed and thus provide workers collective bargaining over wages. This finding allows us a new way to understand long-term contracts. The third chapter examines the effect of depression on various labor force outcomes. We use panel data from the Japanese Panel Survey of Consumers (JPSC) and the Health and Retirement Study (HRS) to follow respondents over several years, using questions about both mental health and labor force outcomes. In order to understand the causal effect of depression on work participation and compensation, we use deaths of the parents or children of respondents as an exogenous shock to mental health, and assess the impact of that event over time.
Keywords: Cross-National; Employment and Labor Force; Health Conditions and Status; Methodology; Net Worth and Assets; Other

Essays on migration and health insurance - Amy E. Knaup (University of Maryland, College Park, 2013)
Migration is often thought of as a risky endeavor in which a migrant trades a known low return for an unknown but potentially higher return. However, migration has been empirically linked to insurance mechanisms through remittances. Chapter 1 unifies the risk-taking and insurance-seeking behaviors of migration into a single framework by framing the migration decision as one of income diversification in which multiple agents within a household to decide whether or not to migrate. Each migration strategy (no migration, partial migration, and full household migration) has its associated risks which are weighed against the returns the household could gain through choice of that particular migration strategy. I test the framework by estimating the probability of each migration strategy for Indonesian households during the period 1993-1998. The framework performs reasonably well in the case of urban households. However, the framework's predictions do not hold as well for rural households, which may be linked to the fact that they function within a larger insurance network than the nuclear family. In Chapter 2, I find that the response of return migration to GDP per capita can differentiate migrants who are seeking increased consumption for their household (i.e., consumption-oriented migrants) from migrants with intentions to invest at origin (i.e., investment-oriented migrants). Each type of migrant should have differential responses to GDP per capita at destination and may have differential responses to GDP per capita at origin. Using data on Mexican households between 1992-2002, I show that migrants returning from the USA exhibit characteristics of consumption-oriented migrants and migrants returning from internal locations exhibit characteristics of investment-oriented migrants. Chapter 3 is a published work in collaboration with Sandra Decker, Jalpa Doshi, and Daniel Polsky which uses Medicare claims data linked to two different surveys--the National Health Interview Survey and the Health and Retirement Study--to describe the relationship between insurance status before age 65 years and the use of Medicare-covered services beginning at age 65 years. Although we do not find statistically significant differences in Medicare expenditures or in the number of hospitalizations by previous insurance status, we do find that individuals who were uninsured before age 65 years continue to use the healthcare system differently from those who were privately insured.
Keywords: Demographics; Insurance; Medicare/Medicaid/Health Insurance; Methodology

Essays on Saving Behavior - Meryl Motika (University of California, Irvine, 2013)
This dissertation combines three projects studying saving behavior. The first chapter presents a model of reference-dependent retirement saving behavior using a gain-loss utility function drawn from prospect theory. I show that this model predicts empirical characteristics of retirement saving behavior including adherence to defaults, under-saving, and the positive correlation between saving rates and financial knowledge. An additional testable implication of the model is that more financially-knowledgeable individuals will have wider variance than people with low financial knowledge. Using data from the Health and Retirement Study, I show that this implication is also supported by empirical results. The second chapter investigates the effects of financial training and planning on saving in a laboratory experiment. Subjects choose when to use tokens to watch video clips over the course of a 50-minute session. Boredom encourages subjects to use tokens immediately, while increased video length in later rounds creates an incentive to use them later. Subjects who receive minimal instructions tend to use their tokens early. Intensive training increases saving rates. The planning treatment has no effect on low-training subjects, but leads intensively trained subjects to smooth tokens across the five rounds rather than spending early or waiting until the end. Evidence from correlations between spending tokens early and high elicited discount rate, as well as subjects' comments about struggling to wait before using tokens, provide support for the external validity of this experiment design. The third chapter examines the relationship between `Big 5' personality traits and low saving rates. Several traits are shown to predict under-saving, with low conscientiousness being particularly important and robust. I then investigate whether personality traits also explain the effects of education, financial literacy, and financial planning. This might occur if certain personality types tended to participate in these activities and also tended to save. I find that the effects of education and financial literacy are robust to personality. The influence of financial planning might be explainable by personality-based selection.
Keywords: Consumption and Savings; Health Conditions and Status; Methodology; Net Worth and Assets

Essays on the Economics of Tobacco Harm Reduction and on Financial Literacy and Retirement Decision-Making - Maki, Jennifer Anne (North Carolina State University, 2013)
This dissertation consists of four essays exploring policies and practices that highlight the role of information on decision making. The first two essays can be broadly described as evaluating policies pertaining to tobacco harm reduction--the practice of recommending the use of a less harmful tobacco alternative to those smokers who are unwilling or unable to quit smoking. If oral tobacco use is less harmful than cigarette smoking, consumers may be better off by substituting one product for the other. Although the risk associated with oral tobacco use has been studied in the past, previous estimates may be biased as they did not account for the role of risky behavior which is correlated with both health outcomes and tobacco use. To address this, I undertake an analysis of the association between oral tobacco and oral cancer, while controlling for risky health behaviors. My findings show that when controlling for risky sexual behavior, the estimated causal effect of oral tobacco use on oral cancer is significantly diminished. A better understanding of the true costs (in terms of health risks) associated with use of oral tobacco will allow individuals to make consumption decisions which maximize utility and encourage cost effective and efficient tobacco control policies. If smokers are made aware of the differing health risks between cigarette smoking and oral tobacco use, they may be able to improve their well-being by substituting one product for the other. However, labeling oral tobacco as a less harmful alternative may induce usage by those who would have otherwise abstained from tobacco use. To better understand these opposing consequences, I explore a policy change in Finland. Finland implemented a ban on the sale of oral tobacco when joining the European Union in 1995. I estimate that removing this less harmful alternative from the market increased the smoking rate, relative to what it would have been, by using the neighboring country of Sweden as a counterfactual. The second two essays look at improving employee retirement readiness through actions undertaken at the firm level. The employer sponsored 401(k) plan can be an effective tool in saving for retirement, yet many employees do not participate. If non-participation is due to low levels of financial literacy or due to inertia, an intervention may be effectual in encouraging participation. In my third essay, I report on the effectiveness of a simple informational intervention that highlighted the value of saving in conjunction with the employer match. This one page flyer demonstrated how saving today can lead to substantial wealth accumulation over time. I find that the intervention increases participation rates among younger employees relative to a control group. In the final essay, I explore the effect of pre-retirement seminars on the financial literacy and retirement plans of older employees at several large firms. These seminars are designed to provide information which will assist employees in making the important decisions they will face when transiting into retirement. Results suggest that participation did lead to an increase in financial literacy and that this learning is associated with a change in retirement plans. These last two essays underscore the importance of financial literacy in retirement planning, preparedness, and decision-making.
Keywords: End of life decisions; Methodology; Net Worth and Assets; Risk Taking

An Evaluation of HRS Sample Weights - Gouskova, Elena (Social Science Research Network, 2013)
The Health and Retirement Study (HRS) documentation describes HRS sample weights as post-stratified by age, race/ethnicity, marital status and gender (Ofstedal, et al., 2011). Yet, we find systematic differences between distributions of these variables in the HRS and the Current Population Survey (CPS). In particular, in the HRS, minorities totals are under-estimated in older cohorts and over-estimated in younger cohorts in 2004, 2006 and 2008 survey waves. We hypothesize that these discrepancies result from of a simplified post-stratification approach, with post-stratification by race/ethnicity not being done jointly with all other factors. Given the HRS study design, however, a joint post-stratification is called for.
Keywords: Methodology; Women and Minorities

An Examination on Un-Retirement: Retirees Returning to Work - Guillermo Ernest Gonzales (Washington University in St. Louis, 2013)
Research that examines retirees returning to work--defined here as un-retirement--is important, given increases in life expectancy and retirement insecurity. Unfortunately research in this area is nascent, limited in scope, and riddled with mixed findings. The current study is guided by three research questions: (1) how do economic resources, as well as human and social capital, relate to un-retirement?; (2) how do other productive activities, including formal and informal volunteering and caregiving, relate to un-retirement?; and (3) how does the retirement experience, including reasons to retire and retirement satisfaction, relate to un-retirement? The empirical literature on wealth and its association with un-retirement is mixed, and thus, an exploratory approach is taken. It is hypothesized that other economic resources (income, pension presence, and health insurances) are negatively related to un-retirement; for example, people with lower levels of income are more likely to return to work. It is hypothesized that higher levels of human capital and social capital are positively associated with un-retirement. It is also hypothesized that productive activities both compete with, and complement each other, and it depends on intensity and timing of events. Specifically, volunteering is a positively associated with un-retirement; that is volunteering complements going back to work. It is also suggested that caregiving is a barrier to un-retirement; that is, the two activities compete. It is hypothesized that forced retirement is positively associated with un-retirement. And finally, it is hypothesized that retirement satisfaction is negatively associated with un-retirement. Data were drawn from the Health and Retirement Study (HRS) which provided a nationally representative sample of fully retired older adults aged 62 and older in 1998 (n=8,334). This sample was followed to 2008, which offered a 10-year period to observe factors associated with un-retirement. The fully conditional specification imputation method was used to complete all missing values of the study variables. Survival analysis tested the hypotheses and yielded information on the significant factors associated with un-retirement. Findings reveal that total household net worth and income were not significantly related to un-retirement. Retirees who possessed a pension (p <.05, hazard ratio (HR):0.78, confidence limits (CL):0.63-0.97) and employer sponsored retiree health insurance (p <.05, HR:0.77, CL:0.62-0.95) were 22% and 23% less likely to return to work when compared to people who did not possess such economic resources for retirement. Generally, individuals with higher levels of human capital--better health (p <.0001, HR:1.31, CL:1.20-1.44), high-skilled (p <.05, HR:1.82, CL:1.20-2.75) and mid-skilled occupational workers (p <.05, HR:1.57, CL:1.07-2.28)--were more likely to return to work when compared to low-skilled occupational workers. This suggests that the probability of returning to work increased by 31% for every one unit increase in self-rated health; and the probability of returning to work were 82% and 57% higher for high and mid-skilled workers compared to low-skilled workers. Education, however, was negatively related to un-retirement when other productive activities were examined ( p <.05, HR: 0.96, CL:0.93-0.99), which suggests that for every unit increase in education, the probability of returning to work decreased by 4%. Certain dimensions of social capital were also significantly related to un-retirement; where the probability of returning to work increased by 75% for people who were married to an employed spouse/partner ( p <.0001, HR:1.75, CL:1.36-2.23). Formal and informal volunteering were significant predictors to work; where volunteers were between 38% and 58% more likely to return to work when compared to non-volunteers. However, providing care to a spouse was a major barrier to returning to work; where caregivers were approximately 80% less likely to return to work in subsequent waves when ompared to non-caregivers ( p <.01
Keywords: Adult children; Employment and Labor Force; Healthcare; Methodology; Net Worth and Assets; Other; Retirement Planning and Satisfaction

Financial Ratios and Perceived Household Financial Satisfaction - Garrett, Scott; Russell N. James III (Journal of Financial Therapy, 2013)
This paper tests the relative strength of three objective measures of financial health (using the solvency, liquidity, and investment asset ratio) in predicting a household s subjective feeling of current financial satisfaction. Using a sample of 6,923 respondents in the 2008 Health and Retirement Study this paper presents evidence of two main findings: 1) the solvency ratio is most strongly associated with financial satisfaction levels based on a cross-sectional design and 2) changes in the investment asset ratio are most strongly associated with changes in financial satisfaction over time.
Keywords: Methodology; Net Worth and Assets

Financial Ratios and Perceived Household Financial Satisfaction - Garrett, Scott; Russell N. James III (Journal of Financial Therapy, 2013)
This paper tests the relative strength of three objective measures of financial health (using the solvency, liquidity, and investment asset ratio) in predicting a household s subjective feeling of current financial satisfaction. Using a sample of 6,923 respondents in the 2008 Health and Retirement Study this paper presents evidence of two main findings: 1) the solvency ratio is most strongly associated with financial satisfaction levels based on a cross-sectional design and 2) changes in the investment asset ratio are most strongly associated with changes in financial satisfaction over time.
Keywords: Methodology; Net Worth and Assets

Functional limitations and chronic conditions predict CES-D-8 depression scores - Liu, Ying (California State University, Los Angeles, 2013)
The role of functional limitations and self-reported chronic disease on CES-D-8 depression scores was investigated in the Health and Retirement Study's 2008 data. The sample included 5835 respondent's ranging in age from 50-83. Multivariate adaptive regression splines (MARS) modeling was employed to identify multiple linear splines. Possible predictors included functional limitations (ADL, IADL), chronic diseases (back pain, stroke, arthritis, cancer, high blood pressure, heart disease, lung disease, & diabetes) and demographic measures (age, education, gender, being white, being Hispanic). The MARS modeling process resulted in selection of the following measures in the final model: ADL limitations, IADL limitations, back pain, stroke, education, being female, and being Hispanic. The results indicated that ADL limitations included two splines with a large increase in depression score from zero to one limitation, and a more shallow increase from one to three limitations. IADL limitations included two splines with a linear increase in depression score from zero to two limitations and a decrease in score from two to three limitations. Reporting back pain or stroke resulted in higher depression scores compared to absence of disease. Two splines were identified for education in which the highest depression scores were associated with zero to 7 years of education; there was a linear decline in depression from seven to 17 years of education. Females and Hispanics were associated with higher depression scores compared to males and non-Hispanics. Results emphasize the importance of functional status and selected chronic health conditions on depression scores and provide more detailed descriptions of change than traditional regression-based models.
Keywords: Health Conditions and Status; Healthcare; Methodology; Women and Minorities

Gender preference and transfers from parents to children: an inter-regional comparison - Edwin S. Wong (International Review of Applied Economics, 2013)
This paper examines whether parents exhibit gender preference in the allocation of family resources to their adult children. Gender preference is defined in the context of an altruistic model for inter-vivos transfer from parents to children extended to include educational investment. Data from the Health and Retirement Study (United States) and the Korean Longitudinal Study of Ageing are used to show that the degree of gender preference differs across these culturally distinct regions. Among Korean families, empirical results point to male preference as sons receive larger inter-vivos transfers and attain higher levels of education compared with daughters. In contrast, the evidence pertaining to gender preference among American families points to daughter preference as inter-vivos transfers and educational investment is generally higher among female adult children. PUBLICATION ABSTRACT
Keywords: Adult children; Cross-National; Demographics; Methodology; Net Worth and Assets

Health and Functional Limitations Predict Depression Scores in the Health and Retirement Study: Results Straight from MARS - Robert F. Kennison; Cox, John (Californian Journal of Health Promotion, 2013)
To examine the effects of chronic health conditions and functional status limitations on depression scores in a large representative sample of Americans. Method: The data included 27,461 respondents ages 50 to 90 who completed up to eight test occasions from the Health and Retirement Study. Multivariate adaptive regression splines (MARS) modeling was applied. Possible covariates of depression included arthritis, lung disease, back pain, diabetes, heart disease, high blood pressure, cancer, 28 pairwise combinations of the aforementioned conditions, ADL functional limitations, age, education and being female, being white, and being Hispanic. Results: The best fitting model had a GRSq of 0.18 (comparable to R2) and included 12 of 42 covariates. Depression score was predicted by: 1) ADL limitations, 2) education, 3) back pain, 4) lung disease, 5) being female, 6) being Hispanic, 7) heart disease, 8) being white, 9) high blood pressure plus stroke, 10) age, 11) back pain plus arthritis, and 12) back pain plus diabetes. Conclusions: Functional limitations was the strongest predictor of depression; reporting one limitation increased depression scores by nearly double the increase associated with two or more limitations. Back pain and lung disease were the strongest chronic disease predictors of depression; both are associated with considerable discomfort.
Keywords: Health Conditions and Status; Methodology

Healthier, Wealthier, and Wiser: A Demonstration of Compositional Changes in Aging Cohorts Due to Selective Mortality - Zajacova, Anna; Sarah A. Burgard (Population Research and Policy Review, 2013)
The gradual changes in cohort composition that occur as a result of selective mortality processes are of interest to all aging research. We present the first illustration of changes in the distribution of specific cohort characteristics that arise purely as a result of selective mortality. We use data on health, wealth, education, and other covariates from two cohorts (the AHEAD cohort, born 1900-1923 and the HRS cohort, born 1931-1941) included in the Health and Retirement Survey, a nationally representative panel study of older Americans spanning nearly two decades (N = 14,466). We calculate sample statistics for the surviving cohort at each wave. Repeatedly using only baseline information for these calculations so that there are no changes at the individual level (what changes is the set of surviving respondents at each specific wave), we obtain a demonstration of the impact of mortality selection on the cohort characteristics. We find substantial changes in the distribution of all examined characteristics across the nine survey waves. For instance, the median wealth increases from about 90,000 to 130,000 and the number of chronic conditions declines from 1.5 to 1 in the AHEAD cohort. We discuss factors that influence the rate of change in various characteristics. The mortality selection process changes the composition of older cohorts considerably, such that researchers focusing on the oldest old need to be aware of the highly select groups they are observing, and interpret their conclusions accordingly. PUBLICATION ABSTRACT
Keywords: Health Conditions and Status; Methodology; Net Worth and Assets

How do couples influence each other's physical activity behaviours in retirement? An exploratory qualitative study - Barnett, Inka; Guell, Cornelia; Ogilvie, David (BMC Public Health, 2013)
Physical activity patterns have been shown to change significantly across the transition to retirement. As most older adults approach retirement as part of a couple, a better understanding of how spousal pairs influence each other's physical activity behaviour in retirement may help inform more effective interventions to promote physical activity in older age. This qualitative study aimed to explore and describe how couples influence each other's physical activity behaviour in retirement. A qualitative descriptive study that used purposive sampling to recruit seven spousal pairs with at least one partner of each pair recruited from the existing EPIC-Norfolk study cohort in the east of England, aged between 63 and 70 years and recently retired (within 2-6 years). Semi-structured interviews with couples were performed, audio-recorded, transcribed verbatim and analysed using data-driven content analysis. Three themes emerged: spousal attitude towards physical activity, spouses' physical activity behaviour and spousal support. While spouses' attitudes towards an active retirement were concordant, attitudes towards regular exercise diverged, were acquired across the life course and were not altered in the transition to retirement. Shared participation in physical activity was rare and regular exercise was largely an individual and independent habit. Spousal support was perceived as important for initiation and maintenance of regular exercise. Interventions should aim to create supportive spousal environments for physical activity in which spouses encourage each other to pursue their preferred forms of physical activity; should address gender-specific needs and preferences, such as chances for socialising and relaxation for women and opportunities for personal challenges for men; and rather than solely focusing on promoting structured exercise, should also encourage everyday physical activity such as walking for transport.
Keywords: Adult children; Demographics; Health Conditions and Status; Healthcare; Methodology; Other; Public Policy; Retirement Planning and Satisfaction

How Do People Form Longevity Predictions? The Effect of Parents and Parents-in-law s Death on Beliefs about Mortality Risk - Chen, Lizi; Economics (Wellesley, MA, Wellesley College, 2013)
In this paper, we use data from the Health and Retirement Study (HRS) panel, which surveys a representative sample of US seniors about their longevity prospects to examine whether the Bayesian assumption holds. Specifically, I test for (1) whether people s longevity predictions are responsive to new information, e.g., recent parental death which conveys information about genetic risks, lifestyle-related health risks, etc; (2) whether people s longevity predictions respond more to the arrival of precise information (parental death) than less clear information (parent-in-law s death); (3) whether the magnitudes of these updates are in accordance with theoretical predictions. We find that individuals longevity predictions are responsive to new health-related information, and consistently more responsive to precise information (parental death) than imprecise information (parent-in-law s death). The magnitudes of these updates lie between the predicted lower and upper bounds of rational updates, but do not perfectly coincide with the predicted values and are sensitive to model specifications. We conclude that there is no strong evidence against the Bayesian assumption. We point out that the Bayesian assumption is only one aspect of the rationality hypothesis. From qualitative survey data, We find evidence of inattention to government subsidy of long-term care insurance, mistaken beliefs that long-term care is covered by Medicare and tendency to procrastinate on long-term care insurance purchasing decision. The evidence suggests irrationality may cause individuals to under-insure through these other venues.
Keywords: Health Conditions and Status; Healthcare; Methodology; Retirement Planning and Satisfaction

How do trends in women's labor force activity and marriage patterns affect social security replacement rates? - April Yanyuan Wu; Nadia S. Karamcheva; Alicia H. Munnell; Patrick J. Purcell (Social Security Bulletin, 2013)
This article examines how women's increased labor force participation, increased earnings, and reduced marriage rates affect Social Security replacement rates over time. Based on data from the Health and Retirement Study and Modeling Income in the Near Term, our estimates show that Social Security replacement rates have dropped sharply at both the household and individual levels, and the declines will continue for future retirees. We also find that this aggregate change masks a complex relationship between replacement rates and the marital status and income levels of individuals. The decline in replacement rates over time is largest for married couples with husbands having higher earnings. Increases in the labor force activity and earnings of women explain more than one-third of the change. By contrast, the impact of changing marital patterns is relatively small. Changes to the full retirement age and the timing of benefit claiming explain much of the remaining decline.
Keywords: Adult children; Employment and Labor Force; Methodology; Women and Minorities

How Representative Is the ACTIVE Sample? A Statistical Comparison of the ACTIVE Sample and the HRS Sample - John J. Prindle; John J McArdle (Journal of Aging and Health, 2013)
Objective: This research is designed to examine demographic differences between the ACTIVE sample and the larger, nationally representative Health and Retirement Study (HRS) sample. Method: After describing some relevant demographics (age, education, sex, and race/ethnicity), we use three statistical methods to determine sample differenceslogistic regression modeling (LRM), decision tree analysis (DTA), and post-stratification and raking methods. When some differences are found, we create sample weights that other researchers can use to adjust these differences. Results: The ACTIVE sample is younger, more likely to be female, Black, and more highly educated than the HRS sample. Sample weights were created. Discussion: By using the resulting sample weights, all results of ACTIVE analyses can be said to be nationally representative based on HRS demographics.
Keywords: Demographics; Methodology

Illness-related diabetes social support and glycemic control among middle aged and older adults - Mondesir, Favel L. (University of South Carolina, 2013)
Objective: The objective of this study is to investigate the association between illness-related diabetes social support (IRDSS) and glycemic control (GC) among a racially diverse sample of middle aged and older adults. In gender-stratified models we examine whether the relationship between IRDSS and GC is modified by race/ethnicity. Additionally, we explore the association between eight individual types of IRDSS and GC. Methods: We used the Health and Retirement Study (HRS) 2002 and the 2003 Diabetes Survey. The final analytic sample consisted of 914 study respondents. Gender-stratified multivariable logistic regression models were used to calculate odd ratios (ORs) and 95% confidence intervals (CIs) for the association between IRDSS and GC, test an interaction between race/ethnicity and IRDSS, and investigate the association between individual IRDSS variables and GC. Final models were adjusted for socio-demographic characteristics, lifestyle factors and clinical characteristics. Results: 79.5% and 76.7% of males and females respectively are classified as having adequate glycemic control. Among females, there was a significant association between IRDSS and GC (OR: 2.39; 95% CI: 1.44, 4.00), but no significant association was observed among males. There was a significant interaction between race/ethnicity and IRDSS (p-value < 0.10). Among Hispanic females, there was a higher odds (OR: 5.75; 95% CI: 1.01, 32.63) of adequate glycemic control in those who had high levels of IRDSS. The strongest association was found between high levels of emotional oriented social support and GC among females (OR=2.05; 95% CI: 1.18, 3.54). Conclusion: Our findings suggest that the relationship between IRDSS and GC varied by gender, where we only observed an association among females. Although we found a significant interaction between Hispanic race/ethnicity and IRDSS among females, our results should be interpreted with caution due to small sample sizes for the groups. We found that type of social support for self-care activities may play a role in achieving GC, where emotional support was most important. Further studies should aim at identifying factors which may determine gender differences in the association between IRDSS and GC. Race/ethnicity as an effect modifier of this association also needs further exploration in studies with larger sample sizes.
Keywords: Adult children; Demographics; Health Conditions and Status; Healthcare; Methodology; Public Policy; Women and Minorities

Inheritance Reporting in the Health and Retirement Study Data: Evidence of Forward Telescoping - Gouskova, Elena (Ann Arbor, MI, Institute for Social Research, 2013)
Intergenerational transfers are often under-reported in household surveys (Laitner and Sonnega, 2010). This paper demonstrates that over-reporting can be an issue as well. Using data from the 1992-2008 Health and Retirement Study, a biannual longitudinal survey, we find that the first autocorrelations of inheritance reports are substantially higher than autocorrelations at longer lags. This evidence is consistent with over-reporting due to forward telescoping. We estimate that, of all inheritances reported in a survey wave, 5 to 10 had been already reported in the prior wave. This results in a similar magnitude overestimation of total two-year amounts of inheritance transfers. Additionally, this reporting error affects regression estimates, when inheritance measures are used as independent variables. In an example of regression analysis, we find that parameter estimates of inheritance variables are biased toward zero by about 2 to 12 . To mitigate forward telescoping in inheritance reports, it is advisable to employ bounded/dependent interviewing in longitudinal surveys.
Keywords: Adult children; Event History/Life Cycle; Methodology; Net Worth and Assets

Investigating the relationship between recent dental visits, memory, and dementia risk factors - Carlson, Holly I. (Fielding Graduate University, 2013)
Research has concluded in recent years that oral health status is associated with dementia. However, little has been understood about how dental visits, which are a modifiable lifestyle variable, affect memory. The current study applied generalized estimating equations models to the RAND Health and Retirement Study nationally representative longitudinal database in order to determine whether recent dental visits predicted (a) higher memory scores, (b) subjective memory status, and (c) perceived change in self-rated memory. Results indicated that persons with recent dental visits obtained better episodic memory scores, had better self-rated memory, and reported perceived change in self-rated memory. The findings suggested that visiting the dentist and maintaining oral health are crucial for healthy cognitive aging. It is concluded that older adults should regularly visit the dentist in order to maintain memory capabilities.
Keywords: Gerontology; Health Conditions and Status; Healthcare; Methodology; Risk Taking

Labor outcomes of health shocks and dependent coverage expansions - Burgdorf, James R., Jr. (The Pardee RAND Graduate School, 2013)
The traditional bundling of health insurance with employment in the United States may distort workers' labor market choices by encouraging full-time wage and salary employment relative to part-time work, self-employment, and not working. However, disentangling the effects of employer-provided health insurance on labor market outcomes is a challenging empirical issue. To overcome this issue, I conduct three studies which exploit three sources of variation in individual valuation of employer-provided group health care. The first study considers the differential impact of health shocks on self-employed workers and wage and salary workers using panel data from the Health and Retirement Study. I find that among older workers in perfect health, health shocks have a larger effect on exits from self-employment than on exits from wage and salary work, implying that extending group coverage to small firm owners may reduce the number of health-related firm failures. The second study uses data from the Current Population Survey's Annual Social and Economic Supplement (ASEC), and was originally intended to examine the effect of state-level dependent coverage expansions on employment outcomes for young adults. Instead, I uncover new evidence that these reforms have had a more limited impact on young adults' insurance rates than indicated by previous research. The third study again uses ASEC data, but considers the effects of the Affordable Care Act's federal-level dependent coverage expansion on young adults' labor market outcomes. I find that these reforms did effectively increase the reported holding of non-spousal dependent coverage, and initial results indicate a significant association with reduced labor force participation. However, further investigation reveals that the target population's relative withdrawal from the labor force began prior to the implementation of the insurance reform, and is likely driven by the economic recession. ii
Keywords: Employment and Labor Force; Health Conditions and Status; Healthcare; Insurance; Medicare/Medicaid/Health Insurance; Methodology; Public Policy

Leaving Retirement: Age-Graded Relative Risks of Transitioning Back to Work or Dying - Ben Lennox Kail; David F Warner (Population Research and Policy Review, 2013)
Demographic research has documented the age-graded risk of returning to work after a period of retirement; few studies, however, have disaggregated this risk into the different forms work takes in later life. Moreover, prior research has not explored the age-graded risk of re-retiring after reentry. This study uses the 1992-2008 Health and Retirement Study to first examine the age-graded and duration dependent risks of transitioning to full-time work, part-time work, and mortality from full retirement. Second, this study documents the age-graded duration of reemployment, and the age-graded risk of re-retiring. Results from multi-decrement life tables indicate reemployment both occurs more frequently and lasts longer than previously estimated. The gender differences in risk of reemployment are modest, although women are at greater risk of returning to part-time work, whereas men are at greater risk of returning to full-time work. Additionally, retirees from services-producing industries are at lower risk of transitioning to work, but greater risks of mortality, suggesting retirement is a less permanent feature in the life course of retirees from goods-producing industries. Finally, the results suggest Social Security benefit eligibility plays a part in reducing reentry at later ages.
Keywords: Employment and Labor Force; Health Conditions and Status; Methodology; Public Policy; Retirement Planning and Satisfaction; Risk Taking

Life expectancy as a constructed belief: Evidence of a live-to or die-by framing effect - Payne, John W.; Sagara, Namika; Shu, Suzanne B.; Appelt, Kirstin C.; Johnson, Eric J (Journal of Risk and Uncertainty, 2013)
Life expectations are essential inputs for many important personal decisions. We propose that longevity beliefs are responses constructed at the time of judgment, subject to irrelevant task and context factors, and leading to predictable biases. Specifically, we examine whether life expectancy is affected by the framing of expectations questions as either live-to or die-by, as well as by factors that actually affect longevity such as age, gender, and self-reported health. We find that individuals in a live-to frame report significantly higher chances of being alive at ages 55 through 95 than people in a corresponding die-by frame. Estimated mean life expectancies across three studies and 2300 respondents were 7.38 to 9.17 years longer when solicited in a live-to frame. We are additionally able to show how this framing works on a process level and how it affects preference for life annuities. Implications for models of financial decision making are discussed. PUBLICATION ABSTRACT
Keywords: Expectations; Health Conditions and Status; Healthcare; Methodology; Net Worth and Assets; Retirement Planning and Satisfaction

Mechanisms of the effect of involuntary retirement on older adults' health and mental health - Min-Kyoung Rhee (University of Southern California, 2013)
The purpose of the present study is to provide in-depth information on older adults' experience of involuntary retirement by examining mechanisms of the effect of involuntary retirement on self-rated health and mental health among adults aged 50 years or older. Although it is a normative expectation to perceive retirement as a phase of life in which older adults become disengaged from paid work, volunteer, and enjoy leisure time with family, not everyone has the luxury of maintaining control over their retirement decisions. Approximately one third of retirees perceive their retirement as forced rather than voluntary. Involuntary retirees are likely to face greater challenges than voluntary retirees during their postretirement adjustment period because they have multiple burdens of health, mental health, and job displacement issues that may have partially led them to involuntarily retire. The prevalence of involuntary retirement is likely to increase because older adults are expected to work longer due to increased financial responsibility despite the challenge of securing or maintaining employment. Although an expanding body of research has addressed various topics of retirement including preretirement planning and decision making, relatively few studies on retirement have focused on the voluntariness of retirement or its varied contexts. Research that has explored health and mental health outcomes after retirement without accounting for voluntariness has reported mixed findings. Considering the fact that retirement has become a more complex and diverse life transition, it is critical to consider the nature of retirement as well as its contexts. To fill this gap of knowledge in research and practice, this study had two specific aims: (1) to explore the prevalence of involuntary retirement among older adults and the extent to which the characteristics of involuntary retirees are different from voluntary retirees or those who did not retire, and (2) to investigate the mechanisms of the health and mental health effect of involuntary retirement by examining the potential mediating effects of financial control, positive and negative family relationships, and social integration. The research questions and hypotheses were formulated based on the life course perspective and latent deprivation theory. Using two waves of longitudinal data extracted from Health and Retirement Study (2006 and 2010), a final sample of 1,280 individuals working for pay at baseline who responded to a lifestyle questionnaire in both waves was selected. Univariate, bivariate, and regression-based path analyses were conducted using SPSS 18.0. This study employed a multiple mediation model that considered four mediators simultaneously and the model was estimated in three phases. Results of the study found that 29.3% (n = 429) of the sample retired between 2006 and 2010, and 37.2% (n = 155) of those individuals reported that they retired involuntarily. Results of Phase 1, a multiple mediator model that did not account for voluntariness of retirement using a binary independent variable (retired or not), indicated that there was no significant direct or indirect effects of retirement on self-rated health and mental health outcomes. In Phase 2, in which the same model was estimated using a multicategorical independent variable (involuntarily retired, voluntarily retired, not retired), involuntary retirement had an direct adverse health effect compared to not retiring, whereas voluntary retirement had an indirect positive health effect via financial control. In terms of mental health outcomes, the positive mental health effect of voluntary retirement was mediated by financial control, whereas involuntary retirement had no significant effect. Results of Phase 3, a model that considered retirees only, revealed direct adverse health effects of involuntary retirement compared to voluntary retirement. Involuntary retirement also had an indirect effect on mental health via financial control. Findings of this stu y indicate the significance of specifying the nature of retirement when conducting retirement research and the need to pay more attention to potential detrimental effects of involuntary retirement. Implications of the findings are discussed with regard to retirement policy, research, and social work.
Keywords: Health Conditions and Status; Healthcare; Methodology; Other; Public Policy; Retirement Planning and Satisfaction

Medicare HMO coverage selection and its impact on the accumulated health spending over the first four years of Medicare coverage in the US - Yi-Sheng Chao; Chao-Jung Wu (Journal of Global Health Care Systems, 2013)
Introduction: this study aims 1) to determine the association between individual characteristics before Medicare coverage (pre-Medicare) and the selection into Medicare HMOs (health maintenance organizations) and 2) to quantify the financial impact of Medicare HMO coverage on total and out-of-pocket (OOP) health spending in the first four years of Medicare coverage. Methods: individuals eligible for Medicare because of age in the Health and Retirement Study from 1992 to 2008 were chosen. Individuals interviewed from age 65 to 68 years were included. Pre-Medicare characteristics were used to predict the propensity of selecting into Medicare HMOs and adjust its effect on health spending as well as to quantify the financial impact of Medicare HMO coverage in the first four years, compared to traditional Medicare from 1992 to 2008. There were 1,841 and 4,126 eligible Medicare enrollees included in total and OOP spending models. Results: The pre-Medicare characteristics that were significantly associated with selection into Medicare HMOs included blacks, Hispanic origin, regions of residence and pre-Medicare health plans. The results showed that the average HMO effect on total spending was insignificant, 2,651.0 less than the traditional Medicare plans (SE = 3,761.2, p = 0.46). The saving on OOP spending was significantly 1,411.5 (SE = 620.8, p = 0.03). Conclusion: the HMOs provide better financial protection in OOP health spending for Medicare enrollees in the first four years of Medicare coverage. However, this effect is not significant for total spending.
Keywords: Healthcare; Medicare/Medicaid/Health Insurance; Methodology

Mental retirement and schooling - Bingley, Paul; Martinello, Alessandro (European Economic Review, 2013)
We assess the validity of differences in eligibility ages for early and old age pension benefits as instruments for estimating the effect of retirement on cognitive functioning. Because differences in eligibility ages across country and gender are correlated with differences in years of schooling, which affect cognitive functioning at old ages, they are invalid as instruments without controlling for schooling. We show by means of simulation and a replication study that unless the model incorporates schooling, the estimated effect of retirement is negatively biased. This explains a large part of the mental retirement effects which have recently been found.
Keywords: Cross-National; Health Conditions and Status; Methodology; Other; Retirement Planning and Satisfaction

Methods for Analysis of the Financing and Use of Long-Term Services and Supports - United States Congressional Office (Washington, DC, 2013)
This document describes the data and methods underlying the 23 exhibits presented in Congressional Budget Office, Rising Demand for Long-Term Services and Supports for Elderly People (June 2013). Most of the statistics presented in Rising Demand for Long-Term Services and Supports for Elderly People are based on tabulations of data from the Health and Retirement Study (HRS, http://hrsonline.isr.umich.edu/) and the Access to Care files of the Medicare Current Beneficiary Survey (MCBS, http://go.usa.gov/b7TP). The statistics are population-weighted averages of measurements taken from the data available in those surveys from 2000 to 2010.
Keywords: Health Conditions and Status; Healthcare; Methodology; Public Policy

Modelling and predicting complex patterns of change using growth component models: An application to depression trajectories in cancer patients - Axel Mayer; Geiser, Christian; Frank J Infurna; Fiege, Christiane (European Journal of Developmental Psychology, 2013)
In this paper we present a general and flexible framework for constructively defining growth components to model complex change processes. Building on the concepts of the latent state-trait theory (LST theory; Steyer, Ferring, and Schmitt, 1992), we develop structural equation models containing latent variables that represent latent growth (change) components of interest. We formulate these models based on an approach presented by Mayer, Steyer and Mueller (2012). We discuss an application to the longitudinal course of depression in 2,794 individuals from the Health and Retirement Study, who experienced cancer diagnosis over the course of the study. We found that (1) on average, the depression trajectories showed a steep increase after diagnosis as well as an adaptation phase where levels returned back to levels prior to diagnosis, and (2) individual differences in change were large and could be partly explained by marital status and cognitive functioning.
Keywords: Health Conditions and Status; Methodology; Public Policy

Motives for Care that Adult Children Provide to Parents: Evidence from Point Blank Survey Questions - Cox, Donald; Beth J Soldo (Journal of Comparative Family Studies, 2013)
Adult children who care for aging parents. incur costs along psychic, monetary, emotional, and even physical dimensions. What motivates them? Is it altruism, guilt, obligation, or gratitude? Perhaps the anticipation of a bequest? Familial norms, or desire for recognition? Understanding motivation for care is high on the agenda of both economics and sociology. A primary focus of economics is the prospect that public transfers may supplant or stimulate private transfers, depending on the motivation of the private donor. Motives are usually inferred indirectly, on the basis of observed behavior. In contrast, sociologists focus on how familial bonds and networks might be forged and maintained. We depart from each of these approaches to focus on direct questions from a special module in the Health and Retirement Study, which contains questions on motivations for, and concerns about, the provision of familial assistance. Our (deliberately) simple descriptive work reveals abundant new information about motivation for familial transfers and care. These not always provided free of pressure from relatives, for example, and obligations and traditions appear to matter. Findings suggest that the standard economic considerations like utility interdependence or exchange provide an incomplete account of transfer behavior, and that insights from sociological models are essential. We also find that women are far more likely to provide care and take seriously family obligations. Past experience in the provision of financial help and care matters as well, sometimes in intriguingly anomalous ways. Though self-reported motivations must be interpreted carefully, we nonetheless conclude that point-blank questions provide a worthwhile complement to conventional methods for unraveling motivations for private, intergenerational transfers.
Keywords: Adult children; Healthcare; Methodology; Other; Risk Taking; Social Security

A multistate transition model for analyzing diseases in elderly population - Noor, Norlida Mohd; M. Ataharul Islam; Zalila Ali (World Applied Sciences Journal, 2013)
In this study, a competing risk model is proposed to analyze the transitions to diseases among elderly people employing the proportional hazards model. This study provides important findings regarding the disease pattern among the elderly people and the factors associated with such transitions. The Health and Retirement Study data are considered for the period of 1992-2000. The major diseases or complications considered in this study are stroke, lung diseases, diabetes mellitus, blood pressure and arthritis. The transitions to different diseases or complications are explained by selected covariates such as gender, race, marital status, smoking, drinking, physical exercise and BMI. The results indicate that gender, race, smoking and BMI are significantly associated with transitions to different diseases or complications. The results are displayed for transitions to each disease or complication separately for competing risk framework as well as for the combined transition to any of the selected diseases or complications. This paper reveals some important health issues related to the transitions to the selected diseases or complications among the elderly people and the factors associated with such transitions are identified.
Keywords: Demographics; Health Conditions and Status; Methodology; Other; Risk Taking

Multivariate fractional response models in a panel setting with an application to portfolio allocation - Carlton, Michael Anthony (Michigan State University, 2013)
Several papers use subjective survival probabilities as a measure of mortality risk in studying economic behavior. The first chapter "Wealth Holdings, Asset Allocation and Mortality: A Test of the Information Content of Subjective Survival Probabilities" studies whether subjective survival probability measures contain any additional information that can explain differential wealth holdings and asset allocation among households. We find some evidence that survival probabilities can explain differences in household wealth holding and allocation once we control for other factors that affect decision-making. We also find that the estimated impact of subjective survival is sensitive to the inclusion of reported survival probabilities of one. Some fractional response variables, like the proportion of financial wealth allocated across multiple assets, must satisfy an adding up restriction. In the second chapter "A Model for Multivariate Fractional Responses with an Application to Asset Allocation", we develop a twostep procedure where we estimate a model with multiple fractional response variables exploiting the fact that these variables sum to one in each period and are correlated over time. The first step entails estimation of the multivariate fractional responses using the multinomial quasi-likelihood function which explicitly imposes the adding-up restriction and the second step uses the Classical Minimum Distance estimator to account for serial correlation. Many panel data estimators implicitly assume that we have a balanced panel at our disposal. Unfortunately this is rarely the case and dropping observations is an unsatisfactory solution to the problem. Estimation of fractional responses in a panel requires assumptions about the distribution of the unobserved effect and its relationship with observables, which requires special treatment in an unbalanced panel. In the third chapter, "Estimation of a Multivariate Fractional Response Model with Unbalanced Panel Data", we extend the approach in Wooldridge (2010) to the case of multiple fractional responses and apply this to unbalanced panel data on the allocation of financial wealth across several assets.
Keywords: Methodology; Net Worth and Assets

The Nature and Correlates of Change in Depressive Symptoms With Cancer Diagnosis: Reaction and Adaptation - Frank J Infurna; Denis Gerstorf; Ram, Nilam (Psychology and Aging, 2013)
Major life events trigger change processes in mental health. We examined how depressive symptoms change in conjunction with cancer diagnosis during adulthood and old age, and whether sociodemographic variables, cognitive and health resources, and cancer-specific mortality risks moderate event-related reaction and adaptation. Specifically, we applied multiphase growth models to prospective longitudinal data from 2,848 participants (age at diagnosis: M = 69, SD = 9.91; 46 women) in the Health and Retirement Study (HRS) who reported receiving a cancer diagnosis while enrolled in the study. On average, individuals experienced a significant increase in depressive symptoms within 2 years of cancer diagnosis, still-elevated levels 2 years postdiagnosis, and smaller increases in depressive symptoms postdiagnosis relative to the increases observed prediagnosis. Better memory and lower cancer-specific mortality risks were protective against increases in depressive symptoms within 2 years of diagnosis and were associated with reporting fewer depressive symptoms 2 years postdiagnosis. Findings suggest that diagnosis-related changes in depressive symptoms are typically characterized by a multiphase pattern, but tremendous between-person differences also emerged within each phase. Follow-up analyses comparing a matched group (N = 2,272) who did not experience cancer provided an additional layer of evidence supporting our inferences. Results indicate that, on average, people adapt and adjust to the challenges accompanying a cancer diagnosis, and illustrate the utility of using natural experiments such as major life events as a paradigm for studying developmental change processes.
Keywords: Event History/Life Cycle; Expectations; Health Conditions and Status; Methodology

Neighborhood racial residential segregation and changes in health or death among older adults - Joseph J Sudano; Perzynski, Adam; Wong, David W.; Colabianchi, Natalie; Litaker, David (Health and place, 2013)
We assessed relationships between neighborhood racial residential segregation (RRS), individual-level health declines and mortality using Health and Retirement Study data. We calculated the census-tract level Location Quotient for Racial Residential Segregation (LQRRS), and estimated adjusted relative risks (ARR) of LQRRS for declines in self-reported health or death 1992-2000, controlling for individual-level characteristics. Of 6653 adults, 3333 lived in minimal, 2242 in low, 562 in moderate, and 516 in high LQRRS tracts in 1992. Major decline/death rates were: 18.6 , 25.2 , 33.8 and 30.4 in minimal, low, moderate and high tracts, respectively. Adjusting for demographic characteristics, residence in low, moderate and high LQRRS census tracts was associated with greater likelihood of major decline/death compared to minimal LQRRS. Controlling for all variables, only moderate LQRRS predicted major decline/death, ARR=1.31 (95 CI 1.07, 1.59; p .05).
Keywords: Demographics; Health Conditions and Status; Healthcare; Methodology; Public Policy; Women and Minorities

New Measures of Fluid Intelligence in the HRS - Gwenith G Fisher; John J McArdle; Ryan J McCammon; Amanda Sonnega; David R Weir (Institute for Social Research, University of Michigan, 2013)
This user guide describes how measures designed to test quantitative reasoning, verbal reasoning and verbal fluency were implemented in the 2010 and 2012 waves of the Health and Retirement Study. The Number Series test and Retrieval Fluency test were administered in the 2010 and 2012 waves of HRS to the full sample. The Verbal Analogies test was administered to a 10 percent random sample of the full HRS sample in 2012. Number Series measures quantitative reasoning, a specific type of fluid cognitive ability or fluid intelligence. Quantitative reasoning ability involves reasoning with concepts that depend upon mathematical relationships. The number series task requires the respondent to look at a series of numbers with a number missing from the series. The respondent must determine the numerical pattern and then provide the missing number in the series. Retrieval Fluency measures an aspect of long-term retrieval : fluency of retrieval from stored knowledge. It was first incorporated in the HRS in the 2010 wave . This test is a typical neuropsychology test and was adapted by McArdle and Woodcock from the WJ-III Tests of Achievement: Retrieval Fluency ( Riverside Publishing). The measure consisted of a single item in which respondents were asked to name as many animals as they could within a 60-second time limit. This measure is consistent with animal fluency measures commonly administered in other neuropsychological exams (e.g., the CERAD animal fluency measure; Morris et al., 1989) . Administration protocols, test scoring, and data quality review procedures are discussed for each measure.
Keywords: Health Conditions and Status; Methodology

Paradata for Nonresponse Adjustment - Olson, Kristen (The ANNALS of the American Academy of Political and Social Science, 2013)
Survey researchers and practitioners use nonresponse adjustment weights to mitigate the effects of survey nonresponse on sample estimates. One challenge in creating these weights is finding useful auxiliary data that predict both the probability of participating in the survey and the survey variables of interest. This article reviews the use of paradata for nonresponse adjustment. Five different types of paradata are considered: neighborhood observations, observations of the sampled housing unit, observations of persons in the sampled housing unit, call records, and observations about the interviewer-householder interaction. Empirical evidence about the predictive value of these paradata for predicting both participation and survey variables is examined. Challenges of using these paradata are also identified, along with outstanding issues and opportunities related to the use of paradata for nonresponse adjustment.
Keywords: Methodology

A parsimonious model of subjective life expectancy - Ludwig, Alexander; Zimper, Alexander (Theory and Decision, 2013)
On average, young people underestimate whereas old people overestimate their chances to survive into the future. Such subjective survival beliefs violate the rational expectations paradigm and are also not in line with models of rational Bayesian learning. In order to explain these empirical patterns in a parsimonious manner, we assume that self-reported beliefs express likelihood insensitivity and can, therefore, be modeled as non-additive beliefs. In a next step we introduce a closed form model of Bayesian learning for non-additive beliefs which combines rational learning with psychological attitudes in the interpretation of information. Our model gives a remarkable fit to average subjective survival beliefs reported in the Health and Retirement Study.
Keywords: Expectations; Health Conditions and Status; Methodology; Other

Pathways of Adult Children Providing Care to Older Parents - Barnett, Amanda E. (Journal of Marriage and Family, 2013)
Guided by life course and stress process theory, this study investigated pathways of adult child caregivers' family (caregiving, marital, parenting) and nonfamily (employment) roles. Eight waves of data from the Health and Retirement Study were analyzed for 1,300 adult child caregivers. Latent class analysis provided strong evidence for a 4-class model of caregivers' role pathways. The four pathways were (a) Not-Married, Early-Transition to Not-Working Caregivers (34 ), (b) Married, Not-Working Caregivers (26 ), (c) Married, Late-Transition to Not-Working Caregivers (23 ), and (d) Married, Not-Working Caregivers with Coresiding Child (17 ). Caregivers' background characteristics and contexts predicted pathway membership. Adult child caregivers have structurally diverse life pathways that have implications for theory, research, and practice.
Keywords: Adult children; Event History/Life Cycle; Healthcare; Methodology

Perceived Weight Discrimination and Obesity - Angelina R Sutin; Antonio Terracciano (PLoS One, 2013)
Weight discrimination is prevalent in American society. Although associated consistently with psychological and economic outcomes, less is known about whether weight discrimination is associated with longitudinal changes in obesity. The objectives of this research are (1) to test whether weight discrimination is associated with risk of becoming obese (Body Mass Index 30; BMI) by follow-up among those not obese at baseline, and (2) to test whether weight discrimination is associated with risk of remaining obese at follow-up among those already obese at baseline. Participants were drawn from the Health and Retirement Study, a nationally representative longitudinal survey of community-dwelling US residents. A total of 6,157 participants (58.6 female) completed the discrimination measure and had weight and height available from the 2006 and 2010 assessments. Participants who experienced weight discrimination were approximately 2.5 times more likely to become obese by follow-up (OR = 2.54, 95 CI = 1.58-4.08) and participants who were obese at baseline were three times more likely to remain obese at follow up (OR = 3.20, 95 CI = 2.06-4.97) than those who had not experienced such discrimination. These effects held when controlling for demographic factors (age, sex, ethnicity, education) and when baseline BMI was included as a covariate. These effects were also specific to weight discrimination; other forms of discrimination (e.g., sex, race) were unrelated to risk of obesity at follow-up. The present research demonstrates that, in addition to poorer mental health outcomes, weight discrimination has implications for obesity. Rather than motivating individuals to lose weight, weight discrimination increases risk for obesity.
Keywords: Demographics; Employment and Labor Force; Health Conditions and Status; Methodology; Other; Retirement Planning and Satisfaction

Physical symptoms, chronic and life-threatening illness trajectories among minority and aging populations - Beverly P. Lyons; Helisse Levine (Journal of Health and Human Services Administration, 2013)
The purpose of this study is to determine the relationship across race/ethnicity relative to reported subjective physical symptoms and clinically assessed medical conditions among the aging minority population using the Health and Retirement Study data for years 1998-2000. Poisson and negative binomial regressions were used to estimate three count dependent variables: physical symptom, chronic, and life-threatening medical conditions. Results indicate that while Black respondents were 18 more likely to report physical symptoms when compared to White respondents (B = .171, p .01, e sup .171 = 1.18) and 1.06 times more likely to report life-threatening medical conditions (B = .058, p .01, e sup .058 = 1.06), when SES variables were added being Black was no longer significantly associated with physical symptoms and chronic conditions. However, being Black did remain statistically significant and positively associated with life-threatening conditions, even after controlling for SES. Results bear statistical and clinical significance, given that we are examining racial and ethnic groups. First, Blacks are at higher risk for premature death for a variety of reasons; this has implications on financial expenditures and on the quality of life. Second, growth among the Hispanic population is outpacing both White and Black populations. Policy initiatives, including geriatric health education, partnerships with community and grass-roots leaders will promote awareness. PUBLICATION ABSTRACT
Keywords: Demographics; Healthcare; Methodology; Other; Public Policy; Women and Minorities

The predictive validity of subjective mortality expectations: evidence from the health and retirement study - Todd E. Elder (Demography, 2013)
Several recent studies suggest that individual subjective survival forecasts are powerful predictors of both mortality and behavior. Using 15 years of longitudinal data from the Health and Retirement Study, I present an alternative view. Across a wide range of ages, predictions of in-sample mortality rates based on subjective forecasts are substantially less accurate than predictions based on population life tables. Subjective forecasts also fail to capture fundamental properties of senescence, including increases in yearly mortality rates with age. To shed light on the mechanisms underlying these biases, I develop and estimate a latent-factor model of how individuals form subjective forecasts. The estimates of this model's parameters imply that these forecasts incorporate several important sources of measurement error that arguably swamp the useful information they convey.
Keywords: Expectations; Health Conditions and Status; Methodology; Retirement Planning and Satisfaction

Preference for increasing wages: How do people value various streams of income? - Duffy, Sean; Smith, John (Judgment and Decision Making, 2013)
Prior studies have found that subjects prefer an improving sequence of income over a constant sequence, even if the constant sequence offers a larger present-discounted value. However, little is known about how these preferences vary with the size of the wage payments. In each of four studies, we find a positive relationship between the preference for increasing payments and the size of the payments. We find no evidence that our measure of the decreasing marginal utility of money is associated with this relationship. Additionally, we find weak evidence in support of a theoretical prediction that the difference between the preference for increasing wage payments and the preference for increasing nonwage payments will be largest for intermediate amounts. We do not find a relationship between the preference for increasing payments and the preference for improving nonmonetary sequences. Finally, the relationship between the preference for increasing payments and the size of the payments does not appear to be sensitive to the precise specification of the increases.
Keywords: Employment and Labor Force; Income; Methodology

Quantifying the Unquantifiable: The Measurement and Meanings of Chronic Pain - Grol-Prokopczyk, Hanna (The University of Wisconsin - Madison, 2013)
Chronic pain is an extremely common, costly, and consequential health problem--and one that defies easy quantification. How do (or could) health researchers define and measure this invisible, subjective, and temporally complex phenomenon? This dissertation addresses this question in three empirical chapters, each using different data sources and methods. The first empirical chapter, based on close analysis of 79 medical studies of low back pain (LBP) and 20 interviews with international pain experts, documents the diversity of pain measures used in contemporary LBP research, and seeks to understand why these measures are poorly standardized. Findings reveal several factors undermining standardization, including the locality and multiplicity of the concepts of "validity" and "comparability," as well as the loose networks of the LBP research community. In addition, some pain researchers, responding to the considerable challenges of treating pain intensity , redefine their work around other, putatively more treatable domains, such as disability or social participation. The diversity of measures of low back pain is thus attributable less to pain's epistemological fragility than to its therapeutic intractability. The next chapter uses 11-country data from the World Health Organization and the Health and Retirement Study (HRS) to test whether a recently developed survey method, anchoring vignettes, can improve intergroup comparability of self-ratings of pain. Results show that, except in rare circumstances, existing anchoring vignettes substantially violate critical measurement assumptions, and thus should not be used. The final empirical chapter highlights the dimension of time in its measurement of chronic pain, using 7 waves of biennial HRS data to identify patterns and socioeconomic disparities in long-term pain trajectories. Latent growth curve models reveal striking disparities in pain experiences by sex, education, wealth, and survival status, but a surprising lack of expected disparities by age and race-ethnicity. These findings do not appear to be artifacts of group differences in reporting styles (though they do appear to result partially from mortality selection). Overall, this dissertation integrates sociological theories, advanced statistical methods, and empirical data to explore the measurement of chronic pain, with a goal of enhancing future research on this important area of health research.
Keywords: Cross-National; Health Conditions and Status; Healthcare; Methodology; Other

Racial/Ethnic inequality among older workers: Focusing on whites, blacks, and latinos within the cumulative advantage/disadvantage framework - Choi, Eunhee (University of Pittsburgh, 2013)
As the number of older workers increases, scholars from variable fields have made an effort to understand what makes the current older generation want to remain in the labor market; however, our knowledge of older minority workers is fragmentary. The experience of older minority workers, defined as Blacks and Latinos in this study, may differ from that of their White counterparts because of persistent racial/ethnic differences among older workers, especially in four domains: 1) financial resources for retirement, 2) health, 3) career patterns, and 4) education. Existing literature has little to offer for older minority workers because of limited methodological approaches and a dearth of appropriate theories. Thus, this study aims to identify factors that explain older Americans' labor market participation after retirement age and whether there are racial/ethnic differences among those factors. It also presents fragmentary knowledge from existing studies within the framework of the cumulative advantage/disadvantage (CAD) theory. Using the 1,114 pre-retirement aged workers from the 2004 and 2008 datasets of the Health and Retirement Study (HRS), probit analysis was run to estimate the analytic model. Racially separate analyses were performed to treat race as a major indicator for the outcome (workers' labor market status after age 65) and to systematically compare factors by race. The results showed that, after adjusting for covariates, factors influencing older individuals' employment after age 65 were conditioned by race. Whereas health and the meaning of work most influence Whites, financial resources (particularly home ownership) most affect Blacks, while health alone most concerns Latinos. Overall, this study suggests that access to the labor market--as opposed to personal preference, financial necessity, or job dissatisfaction-- most influences the labor market participation of minorities. These findings of this study highlight the role of race, suggesting that one universal model cannot fully explain older individuals' labor market participation among different race/ethnic groups. Furthermore, this study's inclusion of Latinos expanded the scope of the existing literature, finding that both Black and Latino workers experience a lifetime accumulation of disadvantages. However, their employment experiences differ significantly: while class differences potentially exist among Black workers, Latinos can be more disadvantaged as a whole, experiencing substantial barriers related to education level and language in the workplace. This study helps to correct theoretical limitations in studies of older workers by using the more revealing CAD framework to interpret results. Racial/ethnic inequality among older workers should be understood not as sudden occurrences in old age, but as a byproduct of the interplay between the individual's lifetime experiences in the labor market and the social structures that impose cumulative advantages/disadvantages on the individual. This study also contributes to the field of social work by stressing the importance of both financial and nonfinancial factors to better comprehend issues surrounding older workers.
Keywords: Methodology; Public Policy

Religiousness, Physical Activity and Obesity among Older Cancer Survivors: Results from the Health and Retirement Study 2000-2010 - Nathenson, Sophia Lyn (International Journal of Religion and Spirituality in Society, 2013)
The health behaviors of cancer survivors are an important research agenda in light of mounting evidence that aspects of health such as diet and exercise have salutary effects both mentally and physically for cancer survivors, a rapidly growing population in the United States and elsewhere. This paper analyzes data from the Health and Retirement Study 2000-2010 to determine if religious salience impacts the likelihood of obesity, changes in body mass index, and weekly vigorous activity. Two theories propose different hypotheses about the relationship. The health belief model would suggest the more religious may have the perception that healthy behaviors are positive and will be more likely to have a healthy body weight and get exercise. Conversely, high religious salience may signify a God locus of health control, leading to lesser likelihood of engagement in preventive health behaviors. Using logistic and regression analysis controlling for health behaviors at baseline (2000), these theories are tested, in addition to the explanatory power of lifestyle as a potential mechanism in the relationship of religiousness to body weight. Results show that high levels of religious salience may correspond to greater likelihood of obesity and lesser likelihood of getting regular exercise. Policy implications may include a greater emphasis on diet and physical activity in religious settings that may instead stress other health behaviors such as abstinence from smoking and alcohol. ABSTRACT FROM AUTHOR
Keywords: Demographics; Health Conditions and Status; Healthcare; Methodology; Other

Representativeness of the Low-Income Population in the Health and Retirement Study - Erik Meijer; Lynn A Karoly (Ann Arbor, The University of Michigan, 2013)
We study to what extent the Health and Retirement Study (HRS) is representative of all income groups, but with a particular emphasis on low-income groups. To focus on the HRS sample composition and abstract from potential measurement issues associated with measures of income and program participation, we exploit the SSA administrative data matched to the HRS sample and compare their distribution against the distribution of the same variables for the same population in the SSA databases. We find that overall, for cohorts and years that can be most reliably compared, the distributions are very similar and conclude that the HRS is representative for the population it covers. However, for some subgroups in the low-income population (e.g., recipients of Supplemental Security Income, Medicaid beneficiaries), there are some differences and thus we caution against estimating population totals for such small subpopulations. The HRS samples for which restricted matched administrative data are available are often not representative of a broad population of interest, because not all HRS respondents were asked permission to match in any given year. Therefore, the restricted HRS datafiles are generally not suitable for estimating population distributions, although they are still very useful for modeling purposes.
Keywords: Demographics; Methodology

A Review of Longitudinal Datasets on Ageing - Kaiser, Angelika (Journal of Population Ageing, 2013)
Issue Title: Special Issue: Longitudinal Cohort Data The growth in longitudinal datasets on ageing have resulted from a recent global initiative, in a large part encouraged and partially funded by the NIA, over the past 20 years in numerous countries eager to understand the complexities of their ageing societies. In the main these studies aim to collect data on population ageing in terms of social, medical and environmental factors. Accordingly the studies being compared in this review focus primarily on health, wellbeing and social issues. These studies have made it possible to measure, evaluate and understand a wide variety of determinants of population change and helped to identify the challenges faced on many levels for the twenty first century and beyond. They have enabled organisations, health care service providers and government more readily able to anticipate and be responsive to the need of the dynamics of the population change as not only the population rapidly increases but faces a significant rise in the percentage of elderly persons. This review looks at the aim of each study, comparisons in methodology, key policy themes, benefits, collaborations with other datasets, gaps and challenges and key findings to date. For further information, an appendix is attached with the contact details of the Principal investigator and study website. PUBLICATION ABSTRACT
Keywords: Demographics; Health Conditions and Status; Methodology

Rising Demand for Long-Term Services and Supports for Elderly People - United States Congressional Office (Washington, DC, 2013)
By 2050, one-fifth of the total U.S. population will be elderly (that is, 65 or older), up from 12 percent in 2000 and 8 percent in 1950. The number of people age 85 or older will grow the fastest over the next few decades, constituting 4 percent of the population by 2050, or 10 times its share in 1950. That growth in the elderly population will bring a corresponding surge in the number of elderly people with functional and cognitive limitations. Functional limitations are physical problems that limit a person s ability to perform routine daily activities, such as eating, bathing, dressing, paying bills, and preparing meals. Cognitive limitations are losses in mental acuity that may also restrict a person s ability to perform such activities. On average, about one-third of people age 65 or older report functional limitations of one kind or another; among people age 85 or older, about two-thirds report functional limitations. One study estimates that more than two-thirds of 65-year-olds will need assistance to deal with a loss in functioning at some point during their remaining years of life.3 If those rates of prevalence continue, the number of elderly people with functional or cognitive limitations, and thus the need for assistance, will increase sharply in coming decades.
Keywords: Health Conditions and Status; Healthcare; Methodology; Public Policy

Rural African American grandmothers raising grandchildren: The impact of chronic illness - Woods, Tamara M. (Capella University, 2013)
The purpose of this qualitative phenomenological study was to explore the experiences of eight African American grandmothers residing in rural North Carolina caring for their grandchildren, while suffering from chronic health issues. The research questions for this study are as follows: (1. What is the perceived impact of chronic health issues on African American grandmothers raising their grandchildren in rural North Carolina? (2. How do grandmothers who reside in rural communities describe how their health issues have impacted their ability to care for their grandchild? (3. Do perceptions of social support and life transitions impact grandmother's health? The research examined the health, physical functioning, well-being, social support, and resources of these grandmothers. Family development theory and Wellness theory formed the theoretical frameworks for understanding the impact of the health issues on these grandmothers. The grandmothers reported challenges and needs which included their own health issues, financial difficulties, limited support, transportation difficulties, and childcare concerns. A major finding was that the grandmother's health did not negatively impact their ability to care for their grandchildren. Developing health education programs and other formal supports which focus on the health of the grandmothers, their financial difficulties, transportation needs, respite, and childcare may help address grandmother's perceptions of their changing health and level of community and social support.
Keywords: Adult children; Demographics; Health Conditions and Status; Healthcare; Methodology; Women and Minorities

Is Self-Rated Health Comparable Between Non-Hispanic Whites and Hispanics? Evidence From the Health and Retirement Study - Su, Dejun; Wen, Ming; Kyriakos S Markides (The Journals of Gerontology, 2013)
Using subsequent all-cause mortality as a yardstick for retrospective health, this study assessed the comparability of self-rated health (SRH) between non-Hispanic whites and Hispanics. Based on longitudinal data from 6,870 white and 886 Hispanic respondents aged between 51 and 61 in the 1992 Health and Retirement Study, we related SRH in 1992 to risk of mortality in the 1992-2008 period. Logit models were used to predict white-Hispanic differences in reporting fair or poor SRH. Survival curves and cox proportional hazard models were estimated to assess whether and the extent to which the SRH-mortality association differs between non-Hispanic whites and Hispanics. Hispanic respondents reported worse SRH than whites at the baseline, yet they had similar risk of mortality as whites in the 1992-2008 period. Overall, Hispanics rated their health more pessimistically than whites. This was especially the case for Hispanics who rated their health fair or poor at the baseline, whereas their presumed health conditions, as reflected by subsequent risk of mortality, should be considerably better than their white counterparts. Health disparities between whites and Hispanics aged between 51 and 61 will be overestimated if the assessment has been solely based on differences in SRH between the two groups. Findings from this study call for caution in relying on SRH to quantify and explain health disparities between non-Hispanic whites and Hispanics in the United States.
Keywords: Demographics; Health Conditions and Status; Methodology; Retirement Planning and Satisfaction; Women and Minorities

Sense of Control and Self-Reported Health in a Population-Based Sample of Older Americans: Assessment of Potential Confounding by Affect, Personality, and Social Support - Ward, Michael M. (International Journal of Behavioral Medicine, 2013)
Sense of control has been linked to improved health outcomes, but it is unclear if this association is independent of other psychosocial factors. The aim of this study is to test the strength of association between sense of control and self-reported health after adjustment for positive and negative affect, Big 5 personality factors, and social support. Data on sense of control (measured by personal mastery, perceived constraints, and a health-specific rating of control), affect, personality, social support, and two measures of self-reported health (global rating of fair or poor health and presence of functional limitations) were obtained on 6,891 participants in the Health and Retirement Study, a population-based survey of older Americans. The cross-sectional association between sense of control measures and each measure of self-reported health was tested in hierarchical logistic regression models, before and after adjustment for affect, personality, and social support. Participants with higher personal mastery were less likely to report fair/poor health (odds ratio 0.76 per 1-point increase) while those with higher perceived constraints were more likely to report fair/poor health (odds ratio 1.37 per 1-point increase). Associations remained after adjustment for affect, but adjustment for affect attenuated the association of personal mastery by 37 and of perceived constraints by 67 . Further adjustment for personality and social support did not alter the strength of association. Findings were similar for the health-specific rating of control, and for associations with functional limitations. Sense of control is associated with self-reported health in older Americans, but this association is partly confounded by affect.
Keywords: Adult children; Health Conditions and Status; Healthcare; Methodology; Other

Social relationships and dental care service utilization among older adults - Jeffrey A Burr; Lee, Hyo Jung (Journal of Aging and Health, 2013)
This study described the association between dental care service utilization and two domains of social relationships (social integration and social support) among older adults. The study employed data from the 2008 Health and Retirement Study, examining regression models for whether a person visited a dentist in the past 2 years, including adjustments for demographic, socioeconomic, and health characteristics. Social interaction, social participation, neighborhood cohesion, and marital status were related to an increased likelihood of having visited a dentist. Older persons exhibiting loneliness and having received financial aid from network members demonstrated a decreased likelihood of visiting a dentist. The increased likelihood of visiting a dentist when a child lives nearby only occurred after introducing health covariates. The article discusses the implications of the study findings as they relate to social relationships and oral health and recommends some additional research directions to explore the etiology of dental care use.
Keywords: Adult children; Demographics; Health Conditions and Status; Healthcare; Methodology

Socioeconomic Status and Health Well-Being during Later Life: Potential Mediating Factors - Hsu, Tze-Li; Cossman, Jeralynn S. (Sociological Spectrum, 2013)
This study explores the socioeconomic status (SES)-perceived health association, with special attention on living arrangements. It improves upon existing explanations of causal mechanisms underlying the impact of SES on health among the elderly. Using Health and Retirement Study to run ordered logistic regression, it addresses the importance of living arrangements for self-reported health. Income and education are both important predictors of self-reported health and that after controlling them, living arrangements also affect self-reported health. Future research should highlight nuanced measures of living arrangements and should explore longitudinal analyses to determine the long-term effects of these factors on self-reported health.
Keywords: Demographics; Health Conditions and Status; Healthcare; Methodology; Retirement Planning and Satisfaction

Spousal Effects in Smoking Cessation: Matching, Learning, or Bargaining? - McGeary, Kerry Anne (NBER Working Paper, 2013)
Previous research studying the correlation in smoking behavior between spouses has discounted the role of bargaining or learning. Using the Health and Retirement Study (HRS), which contains information on smoking cessation and spouse s preferences, this paper presents an essential investigation of the importance of spousal bargaining or learning on the decision to cease smoking. We find, regardless of gender, when one member of couple ceases smoking this induces the other member to cease smoking through bargaining. Further, we find females demonstrate either altruistic behavior toward a spouse, who has suffered a health shock, or learning from their spouse s health shock.
Keywords: Health Conditions and Status; Healthcare; Methodology; Other; Risk Taking

SSI Participation Among the Elderly: A Hazard Model Approach - Jin H. Kim (Journal of Poverty, 2013)
This study revisits the historic policy concern over nonparticipation in the Supplemental Security Income (SSI) program. The most contemporary research model suggests that from a cross-sectional perspective, the elderly take-up decision is primarily determined by the financial situation of the eligible individuals. Yet extant studies have yet to establish a longitudinal model of SSI participation that explicitly takes into account the changing circumstances of the elderly. As such, this study extends the current literature by exploring the time-varying processes leading to eventual take-up of benefits among the elderly. Methodologically, the research relies on event history analysis of data from the Health and Retirement Study spanning the years 1996 to 2006 to explain the varying rates of participation over time as well as the role of life events on the take-up decision. 2013 Copyright Taylor and Francis Group, LLC.
Keywords: Demographics; Event History/Life Cycle; Methodology; Other; Retirement Planning and Satisfaction; Social Security

Three Essays in Applied Microeconomics - Zhang, Xuelian (Economics, 2013)
This dissertation contains three chapters in applied microeconomics. All three chapters try to answer one question: what factors determine labor market outcomes like employment probability, occupational choice and earnings? Chapter 1 investigates the effects of multidimensional personality traits on employment status, occupational choice and earnings. Using the United Kingdom National Child Development Study, the analysis deals with the problems of reverse causality and measurement error by instrumental variable methods. The results indicate that personality traits play an important role in explaining the variation in labor market outcomes. The more agreeable and conscientious, and the less imaginative a person is, the more likely he is employed. The more outgoing and the less imaginative a person is, the more likely he works in a managerial occupation, but the less likely in a non-manual occupation. Agreeableness reduces one's probability of being in a professional occupation. Being outgoing and conscientious leads to higher earnings for paid employees. Chapter 2 uses the United States Health and Retirement Study to study the effects of elder care provision on one's job choice with respect to flexibility. Fixed effects panel data models are used to control for time-invariant individual heterogeneity. Compared to non-caregivers, both male and female caregivers are significantly more likely to sort into flexible jobs or occupations, though they realize job flexibility through different channels: caregiving women are more likely to choose jobs with direct flexible work arrangements like flexible schedules, while caregiving men are more likely to realize flexibility indirectly by sorting into flexible occupation categories. Chapter 3 uses the Brazil Living Standards Measurement Study Survey to examine the long-run consequences of child labor on an adult's income, health and educational attainment. The analysis leads to the following conclusions. Early working has a substantial negative impact on earnings for rural residents but no impact on urban residents. For health, child labor has an adverse consequence in the long run. As for the schooling effect, the earlier one enters the labor market, the fewer years of schooling he obtains. I also discover appreciable differences of child labor effects between urban and rural residents.
Keywords: Adult children; Employment and Labor Force; Health Conditions and Status; Healthcare; Methodology

Three essays in family economics - Chan, Kwok Ho (Boston College, 2013)
This dissertation contains three essays. It provides analysis on issues concerning about family economics. The first essay investigates issues about intergenerational transfer in China. Does parental support in China respond to low income of the elderly? Intergenerational transfers from adult children to their parents are thought to contribute a significant portion of old-age support in China. With a fast growing elder population and an increasing old-age dependency ratio, it is important to understand these transfers. This study investigates the determining factors of intergenerational transfers in China. This line of research is still lacking due to the scarcity of detailed household data. Past studies on private transfers in China could not differentiate between intergenerational versus intragenerational transfers. Using pilot data from the newly released China Health and Retirement Longitudinal Study (CHARLS), I found that around half of the sampled households received transfers from adult children and the amount of transfer is as much as two-thirds of household income per capita. Data also showed that poorer households are more likely to receive transfers. Data suggested that people in the poor province (Gansu) have a higher degree of dependence on adult children, as the source of providing old-age support and living arrangement. Seeing how private transfers are large, widespread, and responsive to income, the benefits from instituting appropriate public policy would likely accrue in part to younger generations by lessening their burden of familial support. The second essay examines the effect of social father on the well-being of out-of-wedlock children. Social fathers, defined as stepfathers or unrelated cohabiting romantic partners of biological mothers, have become more widespread as a result of the increasing out-of-wedlock childbearing. With more young children living with social fathers, it is important to understand the effect of social fathers on the well-being of children. Previous research focused more on such effect on older children or adolescents. Using data from the Fragile Families and Child Wellbeing Study (FFCWS), I find that children with social fathers scored around three points less in a cognitive ability test than children living only with biological mothers. I used the propensity score matching method to address the selection issue for which the child's mother self-selected into having a new partner. Social fathers will be more common because of the widespread of non-marital births. Any negative effect caused by the social fathers will affect a large portion of child population. The third essay evaluates the association between the timing of parenthood and the timing of retirement. Is late parenting associated with late retirement? The trend of parenthood timing is under drastic change. The birth rate for women aged 30-34 rose from 52.3 births per 1000 women in 1975 to 96.5 births per 1000 women in 2010 while the birth rate for women aged 20-24 went down from 113 births to 90 births per 1000 women during the same period. The children may still be very young when their parents enter their retirement age. In the Health and Retirement Study (HRS), 20% of respondents' children lived with them while nearly 30% of these children were below 18 years of age. Despite the potential importance of this issue, economists have not done much research on it. Using the HRS, this study found that parents who have their first child before or at age 30 retire earlier than parents who have their first child after age 30. This positive association holds for different sub-groups of the sample. With significant portion of people delaying their parenthood and a large group of people entering their retiring age, it is very important for policy makers and economists to understand how the timing of parenthood associates with the timing of retirement.
Keywords: Adult children; Cross-National; Event History/Life Cycle; Methodology; Retirement Planning and Satisfaction

Three essays in public economics - Anderson, Michael Throan (The University of Wisconsin - Madison, 2013)
The first and second chapters of this dissertation consider household financial decision making. In the first chapter I examine the phenomenon of early claiming for Social Security retirement benefits. Previous work has shown that early claiming, in particular by the primary earner in married couples, is not consistent with household benefit maximization nor is it predicted by models of utility maximization. I show that observed claiming behavior is explained well by a model in which the primary earner chooses when to claim without taking into consideration the effect of the choice on the secondary earner's spousal and survivor benefits. I find that the decrease in the value of household benefits due to early claiming is borne almost entirely by the surviving spouse. In the second chapter, with John Karl Scholz and Ananth Seshadri, we use the insight of a lifecycle model to better understand the factors that affect household retirement savings targets. Two of the most important determinants of savings targets are households' location in the lifetime income distribution and number of children. We measure the deviation of a set of financial guidelines for retirement saving from the optimal asset accumulation implied by the lifecycle model and suggest an alternate savings heuristic that takes into account insights from the lifecycle model. The third chapter applies a novel estimation strategy to measure the benefit of hazardous waste site remediation. In contrast to previous estimates, this method calculates the benefit of site remediation allowing for diminishing marginal utility. Using data on home sales in Cincinnati, Ohio in 2000 I find the median willingness to pay for a one mile increase to the nearest hazardous waste site is $228 per year. This is lower than previous estimates which range from $284 to $1,065 per year.
Keywords: Health Conditions and Status; Methodology; Net Worth and Assets; Other; Public Policy; Social Security

The Use and Effects of Incentives in Surveys - Singer, Eleanor; Ye, Cong (The ANNALS of the American Academy of Political and Social Science, 2013)
This article is intended to supplement rather than replace earlier reviews of research on survey incentives, especially those by Singer (2002); Singer and Kulka (2002); and Cantor, O Hare, and O Connor (2008). It is based on a systematic review of articles appearing since 2002 in major journals, supplemented by searches of the Proceedings of the American Statistical Association s Section on Survey Methodology for unpublished papers. The article begins by drawing on responses to open-ended questions about why people are willing to participate in a hypothetical survey. It then lays out the theoretical justification for using monetary incentives and the conditions under which they are hypothesized to be particularly effective. Finally, it summarizes research on how incentives affect response rates in cross-sectional and longitudinal studies and, to the extent information is available, how they affect response quality, nonresponse error, and cost-effectiveness. A special section on incentives in Web surveys is included.
Keywords: incentives; Methodology; Nonresponse; nonresponse bias; response rates

Volunteering among surviving spouses: The impact of volunteer activity on the health of the recently widowed - Kimberly J. Johnson (Gerontology, 2013)
Numerous studies link volunteering to positive mental and physical health for older adults, and recent studies have suggested that volunteering may be particularly beneficial for those who are widowed. This research examines the potential of volunteering to buffer participants from stress-related health declines associated with the death of a spouse. Using the Health and Retirement Study (HRS), this research investigates the moderating role of volunteering on the self-rated health and depressive symptoms of recently widowed older adults. Consecutive waves of the HRS are used to identify respondents who experience the death of a spouse or who remain married, and those married or widowed respondents who participate in volunteer work over a two-year period. Waves 1998 through 2004 are used to construct three observation periods: 1998-2000, 2000-2002, and 2002-2004. A series of logistic and negative binomial regression analyses are used to estimate the direct effect and interactive effect of widowed status and volunteer status on self-rated health and depressive symptoms respectively. Results indicate that while volunteering decreases the odds of being in fair or poor health and decreases the expected number of depressive symptoms for volunteers compared with nonvolunteers, volunteering does not buffer recent widows from declines in self-rated health or reduce the risk of more depressive symptoms. The results do not support the idea that volunteering serves as a source of social support for older adults when dealing with the stress of spousal loss. However, the findings do support the idea that participating in volunteering helps older adults remain socially integrated through a meaningful role in their community.
Keywords: Adult children; Health Conditions and Status; Healthcare; Methodology; Net Worth and Assets

What Good Is Wealth Without Health? The Effect Of Health On The Marginal Utility Of Consumption - Finkelstein, Amy; Erzo F. P. Luttmer; Matthew J Notowidigdo (Journal of the European Economic Association, 2013)
We estimate how the marginal utility of consumption varies with health. To do so, we develop a simple model in which the impact of health on the marginal utility of consumption can be estimated from data on permanent income, health, and utility proxies. We estimate the model using the Health and Retirement Study's panel data on the elderly and near-elderly, and proxy for utility with measures of subjective well-being. Across a wide range of alternative specifications and assumptions, we find that the marginal utility of consumption declines as health deteriorates, and we are able to clearly reject the null of no state dependence. Our point estimates indicate that a one-standard-deviation increase in the number of chronic diseases is associated with a 10 -25 decline in the marginal utility of consumption relative to this marginal utility when the individual has no chronic diseases. We present some simple, illustrative calibration results that suggest that state dependence of the magnitude we estimate can have a substantial effect on important economic problems such as the optimal level of health insurance benefits and the optimal level of life-cycle savings.
Keywords: Consumption and Savings; Demographics; Expectations; Health Conditions and Status; Medicare/Medicaid/Health Insurance; Methodology

Cross-national insights into the relationship between wealth and wellbeing: a comparison between Australia, the United States of America and South Korea - Kim, Sarang; K. A. Sargent-Cox; D. J. French; Kendig, H.; Kaarin J. Anstey (Ageing and Society, 2012)
ABSTRACT The positive relationship between wealth and wellbeing has received considerable attention over the last three decades. However, little is known about how the significance of wealth for the health and wellbeing of older adults may vary across societies. Furthermore, researchers tend to focus mainly on income rather than other aspects of financial resources even though older adults often rely on fixed income, particularly after retirement. Using data from the Household, Income and Labour Dynamics in Australia (HILDA) survey (N=1,431), the Health and Retirement Study (HRS) in the United States of America (USA; N=4,687), and the Korean Longitudinal Study of Ageing (KLoSA; N=5,447), this exploratory cross-national study examined the relationship between wealth satisfaction and objective wealth and wellbeing (measured as self-rated health and life satisfaction) among older Australians, Americans and Koreans (50 years). Regression analyses showed that wealth satisfaction was associated with wellbeing over and above monetary wealth in all three countries. The relationship between monetary wealth and self-rated health was larger for the US than Australian and Korean samples, while the additional contribution of wealth satisfaction to life satisfaction was larger for the Korean than the Australian and US samples. These findings are discussed in terms of the cultural and economic differences between these countries, particularly as they affect older persons. PUBLICATION ABSTRACT
Keywords: Demographics; Health Conditions and Status; Healthcare; KLoSA; Methodology; Net Worth and Assets

Determinants of the retirement assets and the amount in stock within retirement assets: Evidence from the Survey of Consumer Finances and the Health and Retirement Study - Ting-Ying Yang; Feinberg, Richard A. (Purdue University, 2012)
The purpose of this research was to investigate the determinants of the retirement assets held in Individual Retirement Accounts, Keogh accounts, and current and future pensions. A second purpose was to investigate the determinants of the amount in stock within those retirement assets. Building upon the theory of human capital, the theory of planned behavior, and the bargaining power model, this study proposed that human capital, attitudes related to finances, and the relative bargaining power of the spouse would influence an individual's retirement assets and the amount in stocks within the retirement assets. Using data from the Survey of Consumer Finances, Study 1 explored the relationship between the three proposed domains and the amount in retirement assets and the amount in stock within the retirement assets. In Study 2, the relationship between the proposed domains was examined using similar variables but with a relatively older sample (e.g., the Health and Retirement Study). The results of both studies supported the theory of human capital and the theory of health capital. Those who had higher education and those who had better health were more likely to have more in retirement assets, and they have more in the amount of stock within retirement assets. Those who saved regularly and were more likely to take risk when saving and investing had more retirement assets and they have more in the amount of stock within retirement assets. The results on the influence of the spouse on retirement assets and the amount in stock within retirement assets showed some support for the bargaining power model. The retirement assets and the amount in stocks within retirement assets were influenced by the spouse. Age, education, working status of the spouse, and who was the more financial knowledgeable person among the two would influence the retirement assets and the amount in stock within retirement assets of the household head. The results of the study supported the existing literature on human capital and health capital. There was some support for the bargaining power model. The results suggest that educators and financial advisors should encourage couples to discuss their plans about saving for retirement with each other and their advisors. However, many people will be single during some or all of their retirement so individual plans for retirement savings should also be carefully developed. This is an important role for educators and financial advisors. However, older adults with fewer resources (e.g. education, employer-sponsored pension plans) will continue to need the support of Social Security.
Keywords: Health Conditions and Status; Methodology; Net Worth and Assets; Other; Pensions; Retirement Planning and Satisfaction

Disability Insurance in General Equilibrium - Wang, Ruwei (University of Virginia, 2012)
The Social Security Disability Insurance (DI) Program, which provides income protection to qualified workers who suffer from disabilities, is now facing rapid growth in the number of recipients. The DI program also discourages exit by workers whose health improves by penalizing work heavily. In the first chapter, I build a dynamic general equilibrium model to provide a quantitative analysis of the welfare effects of the DI program and the impact of DI policy reforms on the program's financial health and on worker behavior and welfare. A recently proposed policy to provide two extra years of partial benefits for DI beneficiaries returning to work would reduce the size of the DI beneficiary population, lowering total DI payments and the tax rate and raising welfare of a healthy newborn by 0.33%. Increasing the Social Security Normal Retirement Age from 65 to 67 raises the number of DI recipients by 8.9%. Policy changes strengthening the strictness of disability criteria increase social welfare mainly due to the reduction in the tax rate. Lastly, simulation results for the case of eliminating the DI program shows a large welfare gain in the new steady state, implying that the distortionary effects of taxation outweigh the gains from providing insurance. The second chapter takes into consideration that people can also obtain financial protection from public and private health insurance programs to have medical costs covered when they suffer health problems. I build a dynamic general equilibrium model to quantitatively analyze the impact of policy reforms on the DI program and on workers' behavior and welfare when Medicare, Medicaid, and employer-sponsored health insurance programs interact with the DI program. A policy change strengthening the strictness of the DI admission process increases social welfare mainly due to the reduction in the tax rate and the increase in the wage level. Expanding Medicaid eligibility, which is a provision in the Affordable Care Act, reduces the number of DI recipients by 4.0% and increases general equilibrium welfare by 0.1%. However, the welfare effects differ by education.
Keywords: Disabilities; Event History/Life Cycle; Methodology; Other; Public Policy; Social Security

Disease as a predictor of depression in aging adults - Gray, Mikea R. (California State University, Los Angeles, 2012)
The purpose of this study is to examine the effects of self-reported chronic health conditions and functional status on the Center for Epidemiologic Studies depression scale using data from the Health and Retirement Study (HRS). The analysis consisted of fitting multivariate adaptive regression splines (MARS) modes to the extant data. Possible covariates included: age, gender, being white, being Hispanic, high blood pressure, heart disease, arthritis, lung disease, back pain, diabetes, stroke, cancer, ADL and IADL functional limitations. Data included 27,461 respondent's longitudinal data, which was collected on eight test occasions. Four hypotheses were formed. Results indicated that back pain and lung disease predicted depression scores which support the second hypothesis. ADL and IADL functional limitations were the most important predictors of depression score, confirming the third and fourth predictions. While chronic disease can lead to elevated depression scores, it appears that functional limitations may be more strongly related to depression.
Keywords: Health Conditions and Status; Healthcare; Methodology

Does health insurance reduce illness-related worker absenteeism? - Xu Xu; Gail A Jensen (Applied Economics, 2012)
The objective of this article is to examine whether having health insurance reduces illness-related absenteeism among older workers. A nationally representative sample of 1780 workers in the United States, aged 52-64, are drawn from the 2004-2006 Health and Retirement Study (HRS). Binary logistic regressions and censored Tobit models are estimated for workers' likelihood of missing work days due to illness and the number of illness-related work days missed, respectively, while explicitly addressing the possibility of insurance-selection effects. The findings suggest that over a 12-month period, older workers without health insurance are as likely as insured workers to miss work days due to illness and there are no differences in the number of days missed between insured and uninsured workers. However, there is strong evidence that poor baseline health, onset of new diseases and longer hospitalization significantly increase an older worker's absenteeism at work. These results suggest that having health insurance does not affect illness-related absenteeism among older workers in the US. Future research examining other aspects of worker productivity, such as 'presenteeism', and the longer term effects of insurance on productivity can extend our understanding of the role of health insurance in the workplace. PUBLICATION ABSTRACT
Keywords: Employment and Labor Force; Medicare/Medicaid/Health Insurance; Methodology; Other

Does stock market performance influence retirement intentions? - Gopi Shah Goda; John B. Shoven; Sita Nataraj Slavov (Journal of Human Resources, 2012)
Media reports predicted that the stock market decline in October 2008 would cause changes in retirement intentions, due to declines in retirement assets. We use panel data from the Health and Retirement Study to investigate the relationship between stock market performance and retirement intentions during 1998-2008, a period that includes the recent crisis. While we find a weak negative correlation between stock returns and retirement intentions, further investigation suggests that this relationship is not driven by wealth shocks brought about by stock market fluctuations, but by other factors that are correlated with both the stock market and retirement intentions. PUBLICATION ABSTRACT
Keywords: Methodology; Net Worth and Assets; Public Policy; Retirement Planning and Satisfaction

Dynamic Models of Labor Supply and Retirement - Fan, Xiaodong (The University of Wisconsin - Madison, 2012)
This dissertation contains three separate essays on the dynamic models of labor supply and retirement. The first essay documents "sharp retirement"--retirement accompanied by a discontinuous decline in labor supply--across three data sets, which previous literature found difficult to explain. I propose and estimate a life-cycle labor supply model with habit persistence wherein sharp retirement can be explained by workers quitting "cold turkey." In much the same way that one might quit smoking, workers with accumulated "working habit" exit the labor force with a pronounced, discontinuous decline in labor supply. The working habit model is consistent with the data, where workers reduce yearly labor supply by scaling back more in hours worked per week (over 50% reduction) than in weeks worked per year (20% reduction). The fixed costs approach, which has been the standard model used to understand sharp retirement, cannot explain these trends. After estimating the model, counterfactuals show that reducing Social Security benefits by 20% causes individuals work an additional 8.6 months. Individuals choosing sharp retirement respond mostly on the extensive margin by delaying retirement eight months, while individuals choosing smooth retirement respond mostly on the intensive margin by increasing yearly labor supply and delaying retirement only one month. The second essay develops and estimates a Ben-Porath human capital model in which individuals make decisions on consumption, human capital investment, labor supply, and retirement. The model allows both an endogenous wage process (which is typically assumed exogenous in the retirement literature) and an endogenous retirement decision (which is typically assumed exogenous in the human capital literature). This integration is important to obtain unbiased estimates, which are critical for most counterfactual analysis. For instance, when evaluating the effect of increasing the Social Security Normal Retirement Age (NRA) on workers' labor supply and retirement decisions, not only does one have to consider how the policy change affects the retirement decision directly, one also needs to consider how it affects the wage process and therefore affects retirement indirectly. We estimate the model using the Method of Simulated Moments to match the life-cycle profiles of wages and hours from the PSID data. Counterfactuals of delaying NRA and removing Social Security earnings test are conducted. We find significant increases in one individual's human capital investment at old ages, which leads to over 20% increase in the wage profile near retirement. Finally, the third essay tests for asymmetric employer learning in the labor market using a three-period model with a match component of wages. When a worker makes her quit/stay decision in a labor market with three periods, she must consider the signaling effect of her decision in subsequent periods. This breaks down some implications derived from two-period models, which are mostly used in the empirical literature. The unconditional quit rate is not necessarily negatively connected with ability in this three-period asymmetric learning model. I suggest two alternative hypothesis tests for asymmetric employer learning in the model. The first test scrutinizes the negative relationship between conditional quit rates and abilities. The second test examines the evolution of weighted average within-group ability variation. Under this model, the variation should decrease over one worker's career history due to sorting on ability. I use the NLSY79 Work-History data and find evidence of asymmetric employer learning from these tests.
Keywords: Employment and Labor Force; Methodology; Net Worth and Assets; Other; Retirement Planning and Satisfaction; Social Security

Dynamic Wage and Employment Effects of Elder Parent Care - Meghan M. Skira; Department of Economics (Boston College, 2012)
This paper formulates and estimates a dynamic discrete choice model of elder parent care and work to analyze how caregiving affects a woman's current and future labor force participation and wages. Intertemporal tradeoffs, such as decreased future earning capacity due to a current reduction in labor market work, are central to the decision to provide care. The existing literature, however, overlooks such long-term considerations. I depart from the previous literature by modeling caregiving and work decisions in an explicitly intertemporal framework. The model incorporates dynamic elements such as the health of the elderly parent, human capital accumulation and job offer availability. I estimate the model on a sample of women from the Health and Retirement Study by efficient method of moments. The estimates indicate that intertemporal tradeoffs matter considerably. In particular, women face low probabilities of returning to work or increasing work hours after a caregiving spell. Using the estimates, I simulate several government sponsored elder care policy experiments: a longer unpaid leave than currently available under the Family and Medical Leave Act of 1993; a paid work leave; and a caregiver allowance. The leaves encourage more work among intensive care providers since they guarantee a woman can return to her job, while the caregiver allowance discourages work. A comparison of the welfare gains generated by the policies shows that half the value of the paid leave can be achieved with the unpaid leave, and the caregiver allowance generates gains comparable to the unpaid leave.
Keywords: Consumption and Savings; Employment and Labor Force; Healthcare; Methodology; Public Policy; Time Use; Women and Minorities

The Effect of Risk Attitudes on the Migration Decision - Rimi, Tamanna Afreen (Tufts University, 2012)
In this paper, I examine the impact of risk attitudes on migration decision. I use the "Two Sample Two-Stage Instrumental Variable (TS2SIV)" technique to measure relative risk aversion and its impact on migration. Using the probit model, I find that more risk averse people are less likely to migrate. The results also indicate that the impact of risk attitude on migration varies by other demographic characteristics such as age, sex etc. In addition, I test whether there is any network effect on migration and how risk attitudes vary with network effect. I consider two ethnic groups; Asian and Hispanic, and find that the size of one's own ethnic group in a source location has significant effect on the migration decisions. In addition, I also find the evidence that risk attitudes vary with network effect.
Keywords: Demographics; Methodology; Risk Taking

The effect of spatial access on utilization of health care services among the elderly - Lin, Chun-Lin (The University of Texas at San Antonio, 2012)
Barriers exist between potential health care users and their actual access. Compared to other age groups, the elderly population faces more spatial obstacles to health care because of diminishing mobility. The object of this dissertation is to examine the extent to which spatial factors affect utilization of health care among the elderly. This dissertation investigates the main hypothesis that seniors who live in neighborhoods with high levels of spatial access will have higher levels of health care utilization. Data from the 2008 Texas physician record were applied to construct the indicator of spatial access using the Two-Step Floating Catchment Area method. This dissertation also used the Health and Retirement Study 2008 core and 2005-2009 American Community Survey 5-year data to estimate the average level of health care utilization as a function of spatial access and other individual and contextual characteristics. Results showed that older adults who lived in a Census tract with higher spatial access actually had lower mean values of health care utilization. After adding interaction terms, however, spatial access did have positive effect on health care utilization for seniors with very good or excellent health status compared to their counterparts who had fair or poor health status. The findings suggested that spatial access did influence seniors' health care utilization, but the effects varied by an individual's health status. Future studies should control for beneficial contextual factors that might potentially offset the effect of spatial access on health care utilization.
Keywords: Health Conditions and Status; Healthcare; Methodology

Emotional distress in older adults with cancer: A multilevel longitudinal study - Tara J Schapmire (Social Work, 2012)
Data from the Health and Retirement Study (HRS) were used to examine factors that influence emotional distress in older adults with cancer, and to learn whether these distress trajectories are different from older adults without cancer. The model investigated the influence of life course factors, internal, external and health-related resources on distress over eight years among a nationally representative sample of older adults ages 50-91. Methods : This longitudinal panel study tested a multilevel random intercept multinomial ordered categorical model with a two-nested-level structure using empirical Bayes Markov chain Monte Carlo (MCMC) estimation. The model examined individual differences in distress over eight years (2000-2008), testing multiple potential predictors which were either time-variant within-person or time-invariant between-person data measured at five consecutive time periods. All those with a first diagnosis of cancer in 1998-2000 were included in study (n=200) together with a representative subsample of all noncancer cases (n=1190), for a total of 1390. Results : In each step, the model fit improved significantly using the DIC statistic. Overall, 33 percent of sample reported one or more depression symptoms in 2000, and by 2008 the number decreased to 30 percent. Keeping all main effects constant, those with cancer had one percent lower probability of depression symptoms over time than those without cancer. Significant two-way interaction effects were detected between having cancer and absence of spouse/partner in the home, and cancer and lower life expectancy; each resulted in higher probabilities of depression symptoms. A significant three-way interaction effect was detected between cancer, gender, and social support with women with a caner history and low social support having the highest probability of distress. Conclusions : Those with four or five depression symptoms at the beginning of the study tended to stay the same over time, while those with one to three symptoms tended to improve slightly. A small significant protective factor of cancer on distress over time was detected. A large protective factor of cancer existed for older adults with a partner present in the home, but cancer became a significant risk factor for distress with no partner presence. The protective factor remained for older adults with cancer and longer life expectancy, but cancer became a significant risk factor for distress low life expectancy. While there was a large protective factor of cancer among women with high social support, cancer history became a risk factor for women with low social support.
Keywords: Demographics; Health Conditions and Status; Methodology; Risk Taking

Essays in Dynamic Macroeconomic Policy - Shourideh, Ali (University of Minnesota, 2012)
In this dissertation, we study optimal macroeconomic policy in dynamic environments. In Chapter 1, we focus on optimal tax policies in environments with idiosyncratic capital income risk. We develop a model in which entrepreneurs are subject to idiosyncratic shocks to their capital income. Shocks to capital income have two components: (1) a component that is known to the entrepreneur at the time of investment, (2) a residual component that is realized after investment. This creates two types of incentive problems: a hidden type problem and a hidden action problem. We show that, absent private markets for insurance of idiosyncratic risk, entrepreneurial and non-entrepreneurial capital income should be taxed differently. Moreover, the government should subsidize non-entrepreneurial capital income when the known and lowest value. Furthermore, for a wide variety of distributions, the optimal tax schedule is progressive with respect to entrepreneurial capital income. Finally, the results regarding taxation of entrepreneurial income depend on the extent to which incentives and insurance are provided by private contracts. In particular, private contracts can approximately implement the efficient allocation if convertible securities are available. The prevalence of these securities in venture capital contracts suggest that the forces identified here are important in practice. In Chapter 2, we study optimal intergenerational transmission of consumption and wealth with endogenous fertility. We use an extended Barro-Becker model of endogenous fertility, in which parents are heterogeneous in their labor productivity, to study the efficient degree of consumption inequality in the long run when parents productivity is private information. We show that a feature of the informationally constrained optimal insurance contract is that there is a stationary distribution over per capita continuation utilities, i.e. there is an efficient amount of long run inequality. This contrasts with much of the earlier literature on dynamic contracting where "immiseration'" occurs. Further, the model has interesting and novel implications for the policies that can be used to implement the efficient allocation. Two examples of this are: (1) estate taxes are positive and (2) there are positive taxes on family size. In Chapter 3, we focus on optimal design of pension systems in providing incentives for efficient retirement. We study lifecycle environments with active intensive and extensive labor margins. First, we analytically characterize Pareto efficient policies when the main tension is between redistribution and provision of incentives: while it may be more efficient to have highly productive individuals work more and retire older, earlier retirement may be needed to give them incentives to fully realize their productivity when they work. We show that, under plausible conditions, efficient retirement ages increase in lifetime earnings. We also show that this pattern is implemented by pension benefits that not only depend on the age of retirement but are designed to be actuarially unfair. Second, using individual earnings and retirement data for the U.S. as well as intensive and extensive labor elasticities, we calibrate policy models to simulate robust implications: it is efficient for individuals with higher lifetime earning to retire (i) older than they do in the data and (ii) older than their less productive peers, in sharp contrast to the pattern observed in the data. In Chapter 4, we focus on optimal policies in remedying problems in secondary loan markets. Loan originators often securitize some loans in secondary loan markets and hold on to others. New issuances in such secondary markets collapse abruptly on occasion, typically when collateral values used to secure the underlying loans fall and these collapses are viewed by policymakers as inefficient. We develop a dynamic adverse selection model in which small reductions in that a variety of policies intended to remedy market inefficiencies do not do so.
Keywords: Event History/Life Cycle; Methodology; Net Worth and Assets; Other; Pensions; Public Policy

Essays on Bayesian inference of time-series and ordered panel data models - Park, Jeehyun (Rutgers The State University of New Jersey, 2012)
At the heart of my dissertation is the study of Markov chain Monte Carlo algorithms and their applications. My dissertation consists of three essays as follow. The first chapter is on MCMC algorithms for the dynamic ordered probit model with random effects. I have tried to estimate the model with four representative MCMC algorithms: two algorithms by Albert and Chib (1993) and Albert and Chib (2001), Liu and Sabatti (2000), and Chen and Dey (2000). I have found that the autocorrelations still remain high in the cutoffs compared to other parameters even though the levels of autocorrelation are reduced in the algorithms by Liu and Sabatti (2000), and Chen and Dey (2000). In the second chapter, I have developed the dynamic ordered probit model studied in the first chapter. It is natural for panel data to have missing data problem because there is no guarantee that subjects will stay over the study periods. This chapter provides Bayesian statistical methods that permit non-ignorable missing data in panel datasets. In order to incorporate non-random missing data in the model, I jointly model observed and non-ignorable missing ordinal data with selection model approach. In the empirical section, I have used the model to examine determinants of self-rated health of old people in the Health and Retirement Study. I have concluded that in this elderly American population, the longest occupation that respondents have held over their careers is strongly associated with self-rated health. In the third chapter of my dissertation, I analyze financial time-series data before and after the Wall Street meltdown in 2008. In this chapter, I develop MCMC algorithms for the CKLS model and examine (1) time-series characteristics of the credit default swap index, stock index and federal funds rate from January 2007 to September 2009, the highly volatile period. (2) The lead-lag relationship between the credit default swap and stock markets are examined using the CKLS model employing multivariate analysis.
Keywords: Health Conditions and Status; Methodology; Public Policy

Essays on gender and health - Medalia, Carla (University of Pennsylvania, 2012)
The relationship between gender and health is complex. Although women live longer than men in almost every country throughout the world, women also tend to be sicker than men. While biological sex differences likely contribute to sex gaps in health, cross-national, historical, and life course variation suggest that social factors also play a role. This dissertation is composed of three chapters which examine social explanations for gender gaps in mortality and morbidity. The first chapter looks at the relationship between gender equality in the public sphere, and sex gaps in life expectancy throughout the world. I find that influence of gender equality on the sex gap in life expectancy depends on the level of economic development. The second chapter takes an historical perspective to examine the trend in the sex gap in depression in the United States between 1971 and 2008. In examining this trend, I find that the sex gap in depression has decreased over the past forty years, due to a decrease in depression among women that is primarily attributable to an increase in women's labor force participation and attachment. In the third chapter, I examine the relationship between gender, aging, and depression using longitudinal data for the population over age fifty in the United States. In doing so, I find that age does not increase depression until age 75, after which point depression increases for both sexes, but particularly for men, leading to a reversal in the sex gap in depression at the end of the lifespan. Furthermore, while the majority of the age effect on depression is explained by social and health changes, I conclude that there is a net effect of age per se on depression after age 75.
Keywords: Demographics; Expectations; Health Conditions and Status; Healthcare; Methodology; Women and Minorities

Essays on impact of risk preference on health and occupational choice - Beri, Meenakshi (Economics, 2012)
This dissertation re-examines Health and Retirement Study (HRS) data in order to ascertain whether there exists behavioral heterogeneity among people regarding health risk as compared to that of financial risk as well as whether there exists racial-ethnic and gender heterogeneity in the health state dependence of marginal utility. Given heterogeneous risk and time preferences of individuals, this study investigates the impact of those preferences on sorting into occupations and industries using various measures of job risk. I construct three measures of risk across jobs, cross-categorized by occupation and industry: a fatal injury rate, non-fatal injury and illness rate, and a measure of inter-person income variability. Using these measures, I analyze how risk and time preference of an individual affects his occupational choice. This study finds that there are different domains of risk and that individuals do not think of these in the same way. Using Health and Retirement Study data, I find that there exists a behavioral inconsistency in health risks versus income risk. This dissertation advises against the use of health risk proxy for making inferences about financial risk. This dissertation then examines the heterogeneity in health dependence of utility and contingent upon the findings of heterogeneity, it examines the factors contributing to utility heterogeneity. To examine this empirically, I begin with theoretical and empirical models used by Finkelstein, et al. (2011) relaxing the assumptions of those models to allow for differential effects by race, gender and ethnicity. Using happiness as a utility proxy and objective health measures in our baseline model, I find strong evidence of heterogeneity in health state dependence of utility among males and females, hispanic and non-hispanic and white, and black; not only in seven objective health conditions but also functionality limitations; not only by using happiness as a utility proxy but also with CES-D score. Since, there is slight evidence of heterogeneity in the health state dependence of utility among different health states, the policies like Medicare, and Medicaid would have varying impact on people depending upon race, ethnicity and gender. The non-linear B-O decomposition of utility unfolds that the significant contributors towards the explained gender, racial and ethnic gap in utility proxy (happiness and CES-D Score) are: marital status, number of diseases, log adjusted income, risk attitudes and ethnicity. Approximately 80 percent of the gender utility gap and 100 percent race utility gap is explained by the endowment effect. Thus, this dissertation reaffirms the findings of Halliday (2008) that there may be larger potential gains to identifying as well as targeting factors that influence individual heterogeneity since the health state dependence of utility is mostly driven by individual characteristics, as has been found to be the case in B-O decomposition of utility in the current study.
Keywords: Health Conditions and Status; Methodology; Public Policy

Essays on informal care, labor supply and wages - Meghan M. Skira (Graduate School of Arts and Sciences, 2012)
This dissertation examines how caregiving for an elderly parent affects an adult child's labor supply and wages. In the first chapter (co-authored with Courtney H. Van Houtven and Norma B. Coe) we identify the relationship between informal care and labor force participation in the United States, both on the intensive and extensive margins, and examine wage effects. We control for time-invariant individual heterogeneity; rule out or control for endogeneity; examine effects for men and women separately; and analyze heterogeneous effects by task and intensity. We find modest decreases--1.4-2.4 percentage points--in the likelihood of working for caregivers providing personal care. Male and female chore caregivers, meanwhile, are more likely to retire. For female care providers who remain working, we find evidence that they decrease work by 3-10 hours per week and face a 2.3-2.6 percent wage penalty. We find little effect of caregiving on working men's hours or wages except for a wage premium for male intensive caregivers. In the second chapter I formulate and estimate a dynamic discrete choice model of elder parent care and work to analyze how caregiving affects a woman's current and future labor force participation and wages. Intertemporal tradeoffs, such as decreased future earning capacity due to a current reduction in labor market work, are central to the decision to provide care. The existing literature, however, overlooks such long-term considerations. I depart from the previous literature by modeling caregiving and work decisions in an explicitly intertemporal framework. The model incorporates dynamic elements such as the health of the elderly parent, human capital accumulation and job offer availability. I estimate the model on a sample of women from the Health and Retirement Study by efficient method of moments. The estimates indicate that intertemporal tradeoffs matter considerably. In particular, women face low probabilities of returning to work or increasing work hours after a caregiving spell. Using the estimates, I simulate several government sponsored elder care policy experiments: a longer unpaid leave than currently available under the Family and Medical Leave Act of 1993; a paid work leave; and a caregiver allowance. The leaves encourage more work among intensive care providers since they guarantee a woman can return to her job, while the caregiver allowance discourages work. A comparison of the welfare gains generated by the policies shows that half the value of the paid leave can be achieved with the unpaid leave, and the caregiver allowance generates gains comparable to the unpaid leave.
Keywords: Adult children; Employment and Labor Force; Healthcare; Methodology; Public Policy

Essays on Innovation, Productivity, and Talent Allocation - Shu, Pian (Massachusetts Institute of Technology, 2012)
This thesis contains three essays on innovation, productivity, and talent allocation. The first essay explores a novel channel through which short-term economic fluctuations affect the long-term innovative output of the economy: innovators' accumulation of human capital. Using a newly constructed data set on the patenting history of all individuals obtaining a bachelor's degree from the Massachusetts Institute of Technology (MIT) between 1980 and 2005, I find that cohorts graduating during booms produce significantly fewer patents over the subsequent two decades. Initial economic conditions do not affect inventors' long-term occupational affiliation, suggesting that the main differences lie in their long-term level of inventive human capital. The decrease in patent output of cohorts graduating during booms is mainly from inventors with relatively low GPAs, and marginal patents receive fewer citations than the rest. The second essay uses the 2008 financial crisis as a natural experiment to study the characteristics of recent graduates from MIT bachelor programs who pursued a career in finance immediately after graduation. I find that finance competes against science and engineering graduate programs for the best talent from MIT but values academic skills less. As a result of endogenous skill development during college, financiers have significantly lower academic skills than students entering graduate school at graduation, despite having similar levels of raw academic talent measured at college entrance. Marginal financiers have lower starting salaries than average financiers, suggesting that there is positive selection into finance. The third essay examines the asset accumulation and labor force participation of Social Security Disability Insurance applicants. Using the RAND Health and Retirement Study panel data, I provide empirical support for the theory that an imperfectly screened disability insurance program encourages individuals who dislike work to save more in the present and plan to apply for disability insurance in the future, regardless of their future health. Despite exhibiting lower labor force attachment and earning less than accepted applicants, rejected applicants have significantly more assets immediately prior to their application, but not in the several years before. Although imperfect, the current screening differentiates the applicants in meaningful ways without using assets as an additional criterion. (Copies available exclusively from MIT Libraries, Rm. 14-0551, Cambridge, MA 02139-4307. Ph. 617-253-5668; Fax 617-253-1690.)
Keywords: Disabilities; Employment and Labor Force; Methodology; Other

Estimating Second Order Probability Beliefs from Subjective Survival Data - Péter Hudomiet; Robert J. Willis (NBER Working Paper, 2012)
Based on subjective survival probability questions in the Health and Retirement Study, we use an econometric model to estimate the determinants of individual-level uncertainty about personal longevity. This model is built around the Modal Response Hypothesis (MRH), a mathematical expression of the idea that survey responses of 0, 50 or 100 percent to probability questions indicate a high level of uncertainty about the relevant probability. We show that subjective survival expectations in 2002 line up very well with realized mortality of the HRS respondents between 2002 and 2010. We show that the MRH model performs better than typically used models in the literature of subjective probabilities. Our model gives more accurate estimates of low probability events and it is able to predict the unusually high fraction of focal 0, 50 and 100 answers observed in many datasets on subjective probabilities.
Keywords: Methodology

Family Decision Making and Resource Protection Adequacy - Patryk D. Babiarz; Robb, Cliff A.; Woodyard, A. (The Journal of Consumer Affairs, 2012)
This study examines the correlation between resource protection and the intrahousehold distribution of bargaining power. Using data from the Health and Retirement Study, the analysis quantifies potential changes in the surviving individual's living standard to evaluate the adequacy of resource protection. Individuals who generate a larger share of family income, are more financially knowledgeable, or have the final say in family decisions leverage their bargaining power to secure higher protection of their hypothetical widowhood living standard. Consequently, spouses with more bargaining power are less likely to experience declines of their living standard in the event of their spouse passing away and are more likely to be overprotected.
Keywords: Consumption and Savings; End of life decisions; Income; Methodology; Other

A functional use of response time data in cognitive assessment - John J. Prindle (University of Southern California, 2012)
The stimulus for the current body of work comes from the desire of researchers to have concise and accurate cognitive tasks implemented in their surveys. The main purpose of this work was to introduce collateral information as a way of making up for lost or forgone information when adaptive frameworks are adopted. The nature of ongoing surveys and the ubiquity of computers provides ample collateral, or nonintrusive, information which can help improve score accuracy. Information such as how long a respondent spends on certain items, their age, education, and other characteristics can improve score prediction beyond simple item responses. The importance of this work included methods to effectively decrease the number of items given to participants, as well as keep the accuracy high despite the loss in information. In the current study, the Woodcock Johnson - III (WJ-III) Number Series (NS) task was presented with 30 previously unpublished items as stimuli. First, a couple of scoring models were implemented to test for model fit and compare the implications of the fit values. Then methods outlined below systematically adjusted patterns of missingness to mimic reduced and adapted subsets. Once the smaller NS item sets were delineated, several methods of adding predictive accuracy were tested and compared. In scoring respondents a traditional Item Response Theory (IRT) model as proposed by Rasch (1960) was first used to provide evidence for a uni-dimensional scale and obtain baseline statistics for item difficulty and person abilities. The next model was a Conditionally Independent Response Time (CIRT) model. The latter model includes a response model as well as a joint response time model for scoring. It was shown that with the full item set these two models provide identical ability estimates and item parameters. The response time model of the CIRT framework provides ability scores and speededness scores based on response time patterns. Next, focus was placed on effectively decreasing the number of items used in scoring each respondent. Methods included item reduction, test forms in which the same item sets were used to score each respondent, and adaptive tests, where each respondent could receive a different item set. Reduced item sets fared better when item difficulties more closely matched sample ability levels (r=0.72-0.90). Adaptive item sets were more consistent in measuring ability (i.e. half-adaptive, block adaptive, fully adaptive), but accuracy was best for the fully adaptive method used (r=0.79-0.91). The last steps of analysis involved introducing response time and demographic variables as additional predictors of the 30 item scores. Item response, response times, and response/response time interactions provided small improvements in explained variance when used as predictors (1-8%). When CIRT ability and speededness scores were used as predictors, speededness provided limited improvements (<1%) to prediction. The addition of age, education, and gender to response models improved explained variance to a moderate degree (1-5%). In conclusion, we note that sample had a higher than average ability level for the NS task and this should color our findings for the methods outlined. The item sets that did not match respondent abilities as well were improved more so by response time and demographic data. If one can correctly identify the ability ranges of a sample before administration, then a more focused reduced item set would be advantageous. Adaptive item sets seem advantageous in a more general testing situation where ability levels are more variable. The advantage of using collateral information in predicting cognitive scores is the amount of time saved by omitting items, potentially lowering costs, and allowing researchers to move onto more tasks if desired. While the improvement due to response time in these methods was limited with NS, there is a good foundation for other cognitive tasks administered in computer assisted designs.
Keywords: Health Conditions and Status; Healthcare; Methodology; Other

Harmonization of Cross-National Studies of Aging to the Health and Retirement Study: Cognition - Regina A Shih; Jinkook Lee; Lopamudra Das (RAND Working Paper, 2012)
This paper summarizes and compares measures of cognitive health and decline in the Health and Retirement Study (HRS) and its sister surveys from other countries: the English Longitudinal Study of Ageing (ELSA), the Survey of Health, Ageing, and Retirement in Europe (SHARE), the Korean Longitudinal Study of Aging (KLoSA), the Japanese Study on Aging and Retirement (JSTAR), the Chinese Health and Retirement Longitudinal Study (CHARLS), the Mexican Health and Aging Study (MHAS), the Indonesian Family Life Survey (IFLS), The Irish Longitudinal Study on Aging (TILDA), Study on Global Aging (SAGE), and the Longitudinal Aging Study in India (LASI). The authors analyze and discuss the extent to which these measures are comparable, the methodological differences in the way information was collected for these measures, and the implications for secondary data analysis. This paper is one in a series of similar papers, each comparing different domains (e.g., chronic medical conditions, employment and retirement, expectations, transfers, income, and wealth) across these surveys with an aim to encourage rigorous, cross-national and international comparison research on aging populations
Keywords: CHARLS; Cross-National; ELSA; IFLS; JSTAR; KLoSA; LASI; Methodology; MHAS; SAGE; SHARE; TILDA

Harmonization of Cross-National Studies of Aging to the Health and Retirement Study: Income Measures - Marco Angrisani; Jinkook Lee (RAND Working Paper, 2012)
This paper summarizes and compares measures of household and individual income in the Health and Retirement Study (HRS) and its sister surveys from other countries: the English Longitudinal Study of Ageing (ELSA), the Survey of Health, Ageing, and Retirement in Europe (SHARE), the Korean Longitudinal Study of Aging (KLoSA), the Japanese Study on Aging and Retirement (JSTAR), the Indonesian Family Life Survey (IFLS), The Irish Longitudinal Study on Aging (TILDA), the Chinese Health and Retirement Longitudinal Study (CHARLS), and the Longitudinal Aging Study in India (LASI). The authors analyze and discuss the extent, to which these measures are comparable, the methodological differences in the way information was collected for these measures, and the implications for secondary data analysis. This paper is one in a series of similar papers, each comparing different domains (e.g., chronic medical conditions, cognition, expectations, transfers, and wealth) across these surveys with an aim to encourage rigorous, cross-national and international comparison research on aging populations.
Keywords: CHARLS; Cross-National; ELSA; IFLS; JSTAR; KLoSA; LASI; Methodology; SHARE; TILDA

Harmonization of Cross-National Studies of Aging to the Health and Retirement Study: Financial Transfer - Julie M Zissimopoulos; Jinkook Lee; Joanna Carroll (RAND Working Paper, 2012)
This paper summarizes and compares measures of financial transfers in the Health and Retirement Study (HRS) and its sister surveys from other countries: the English Longitudinal Study of Ageing (ELSA), the Survey of Health, Ageing, and Retirement in Europe (SHARE), the Korean Longitudinal Study of Aging (KLoSA), the Japanese Study on Aging and Retirement (JSTAR), the Chinese Health and Retirement Longitudinal Study (CHARLS), and the Longitudinal Aging Study in India (LASI). The authors analyze and discuss the extent, to which these measures are comparable, the methodological differences in the way information was collected for these measures, and the implications for secondary data analysis. This paper is one in a series of similar papers, each comparing different domains (e.g., chronic medical conditions, cognition, employment and retirement, expectations income, and wealth) across these surveys with an aim to encourage rigorous, cross-national and international comparison research on aging populations.
Keywords: CHARLS; Cross-National; ELSA; JSTAR; KLoSA; LASI; Methodology; SHARE

Living Well: Empirical Evaluations of Economic Welfare and Subjective Well-Being - Horner, Elizabeth Mokyr (University of California, Berkeley, 2012)
This thesis presents findings from three related but independent research projects on how policies and programs affect subjective well-being and psychological health, both generally and along specific domains. As I discuss in the Introduction (Chapter 1), the subjective experience is an important component of overall welfare, and tools for measuring Subjective Well-Being (SWB) are well validated. These measures are particularly useful when measuring the impact of policies, programs, and decisions for which income is a poor indicator of well-being. The first project, "Subjective Well-Being and Retirement: Analysis and Policy Recommendations" (Chapter 2) examines how individual-level happiness is on average influenced by the transition into retirement. By exploiting discontinuities in retirement incentives in 16 countries, an instrumental variables approach is utilized to estimate retirement so that it is exogenous to individual-level characteristics. Removing selection bias reveals a large, short-term positive effect followed by a steep decline. This supports theories of a multi-stage adjustment to retirement. Further, individuals facing later formal retirement experience a boost in SWB that is roughly equivalent in total value to those individual facing earlier retirement, suggesting that raising the formal retirement age is relatively neutral with regard to SWB in the long-term. The second project, "Whose Fault Is It?: No Fault Divorce and the Decline in Women's Happiness" (Chapter 3) explores the impact of the no-fault revolution, wherein the legal and economic barriers to divorce were drastically reduced in many states throughout the 70s and 80s. I expand upon previous research by including SWB as an important outcome, including overall SWB as well as marital-happiness, a domain-specific SWB measure. I find that women under low-barriers to divorce regimes are significantly less happy than other women, while men are significantly happier. The final project, "Paradox Lost?: Job Satisfaction, Gender Segregation, and the Paradox of the Contented Female Worker" investigates whether gender segregation has played a role in the well-documented "paradox of the contented female worker" (Crosby, 1982), wherein women report higher job satisfaction despite worse work conditions. Job satisfaction is a domain-specific form of SWB which is particularly important from an economic perspective, as high SWB at work is related to better productivity and lower turnover. I find that both men and women are happier in jobs that are dominated by women, suggesting that men and women may on average be making different decisions with regard to satisfaction / income tradeoffs. Although the chapters are meant to be stand-alone essays, in concert these papers argue that: 1) SWB is an important outcome variable and high levels of SWB is an important social goal; and 2) policies affect SWB and therefore SWB must be considered in cost-benefit analyses of policy impacts.
Keywords: Adult children; Employment and Labor Force; Expectations; Health Conditions and Status; Methodology; Public Policy; Women and Minorities

Longitudinal Data Analysis: a Practical Guide for Researchers In Aging, Health, And Social Sciences - Jason T Newsom; Richard N Jones; Scott M Hofer (Routledge, 2012)
This book provides accessible treatment to state-of-the-art approaches to analyzing longitudinal studies. Comprehensive coverage of the most popular analysis tools allows readers to pick and choose the techniques that best fit their research. The analyses are illustrated with examples from 12 major longitudinal data sets including practical information about their content and design. Illustrations from popular software packages offer tips on how to interpret the results. Each chapter features suggested readings fur further study and a list of articles that further illustrate how to implement the analysis and report the results. An accompanying website provides syntax examples for several software packages for each of the chapter examples. Although many of the examples address health or social science questions related to aging, readers from other disciplines will find the analyses relevant to their work. In addition to demonstrating statistical analysis of longitudinal data, the book shows how to interpret and analyze the results within the context of the research design. Although most chapters emphasize the use of large studies collected over long term periods, much of the book is also relevant to researchers who analyze data collected in shorter time periods. The book opens with issues related to using publicly available data sets including a description of the goals, designs, and measures of the data. The next 10 chapters provide non-technical, practical introductions to the concepts and issues relevant to longitudinal analysis, including: weighting samples and adjusting designs for longitudinal studies; missing data and attrition; measurement issues related to longitudinal research; the use of ANOVA and regression for averaging change over time; mediation analysis for analyzing causal processes; growth curve models using multilevel regression; longitudinal hypotheses using structural equation modeling (SEM); latent growth curve models for evaluating individual trajectories of change; dynamic SEM models of change; and survival (event) analysis. Examples from longitudinal data sets such as the Health and Retirement Study, the Longitudinal Study of Aging, and Established Populations for Epidemiologic Studies of the Elderly as well as international data sets such as the Canadian National Population Health Survey and the English Longitudinal Study of Aging, illustrate key concepts. An ideal supplement for graduate level courses on data analysis and/or longitudinal modeling taught in psychology, gerontology, human development, family studies, medicine, sociology, social work, and other behavioral, social, and health sciences, this multidisciplinary book will also appeal to researchers in these fields.
Keywords: Cross-National; Health Conditions and Status; Methodology

Market Performance And The Timing Of Retirement - Yao, Rui; Park, Eric (Journal of Personal Finance, 2012)
This study is the first to utilize nine interview waves of the Health and Retirement Study and multilevel discrete-time survival analysis to investigate the effect of market returns on individual elective retirement decisions. Individuals who retire at a market peak have an increased risk of shortening the longevity of their retirement income. Unfortunately, market returns were found to have a significant positive effect on the probability of retirement. Researchers, employers, financial educators and financial practitioners should help pre-retirees overcome the stock market's influence on their decision-making to avoid the negative effect of market sequencing on their retirement wealth. PUBLICATION ABSTRACT
Keywords: Consumption and Savings; Methodology; Net Worth and Assets; Retirement Planning and Satisfaction

Mismeasurement of Pensions Before and After Retirement: The Mystery of the Disappearing Pensions with Implications for the Importance of Social Security as a Source of Retirement Support - Alan L Gustman; Thomas L. Steinmeier; N. Tabatabai (MRDRC Working Paper, 2012)
A review of the literature suggests that when pension values are measured by the wealth equivalent of promised DB pension benefits and DC balances for those approaching retirement, pensions account for more support in retirement than is suggested when their contribution is measured by incomes received directly from pension plans by those who have already retired. Estimates from the Health and Retirement Study (HRS) for respondents in their early fifties suggest that pension wealth is about 86 percent as valuable as Social Security wealth. In data from the Current Population Survey (CPS), for members of the same cohort, measured when they are 65 to 69, pension incomes are about 56 percent as valuable as incomes from Social Security. Our empirical analysis uses data from the Health and Retirement Study to examine the reasons for these differences in the contributions of pensions as measured in income and wealth data. A number of factors cause the contribution of pensions to be understated in retirement income data, especially data from the CPS. One factor is a difference in methodology between surveys affecting what is included in pension income, especially in the CPS, which ignores irregular payments from pensions. In CPS data on incomes of those ages 64 to 69 in 2006, pension values are 59 percent of the value of Social Security. For the same cohort, in HRS data, the pension value is 67 percent of the value of Social Security benefits. Some pension wealth disappears at retirement because respondents change their pension into other forms that are not counted as pension income in surveys of income. Altogether, 16 percent of pension wealth is transformed into some other form at the time of disposition. For those who had a defined benefit pension just before termination, the dominant plan type for current retirees, at termination 12 percent of the benefit was transformed into a state that would not count as pension income after retirement. For those who receive benefits soon after termination, there is a 3.5 percent reduction in DB pension value at termination compared to the year before termination. One reason may be the form of annuitization that is chosen. A series of caveats notwithstanding, the bottom line is that CPS data on pension incomes received in retirement understates the full contribution pensions make to supporting retirees.
Keywords: Methodology; Net Worth and Assets; Pensions; Retirement Planning and Satisfaction

Neighborhood Conditions and Gender Differences in Depressive Symptoms - Clinton, Eliva Atieno (University of California, Los Angeles, 2012)
Depression is a major public health challenge affecting millions of people worldwide, particularly women. Intra-individual explanations of gender differences in depression include biology (e.g., neurotransmitters, genes, hormones) and psychological factors (e.g., self-concept and esteem, mastery). Social explanations focusing on exposure to stressors (e.g., low socioeconomic status) and social role occupancy (e.g., marital and employment status) also have been considered. The recognition that environmental factors may influence mental health has given rise to studies examining the relationship between neighborhood conditions and risk for depression and psychological distress, but gender differences in neighborhood effects have yet to receive the needed research attention. This dissertation sought an understanding of: (a) gender differences in neighborhood effects on depressive symptoms, and (b) neighborhood influences on variation in depressive symptoms among women. The research is guided by the neighborhood stress process framework focusing on stressors and psychosocial resources as mediators and moderators of the relationships among neighborhood conditions and depressive symptoms. Individual-level cross-sectional data come from the Health and Retirement Survey (HRS: baseline, 2006/2008 interviews and psychosocial questionnaire supplement). The HRS is a U.S. national probability sample of adults over the age of 50. Analyses are performed within a multilevel framework and urban neighborhood data come from the 2000 U.S. Census. Among eight indicators of neighborhood disadvantage, including neighborhood socioeconomic disadvantage (NSD), and five measures of neighborhood advantage examined for gender differences in their effects on depressive symptoms, two were statistically significant but not in the expected direction. Neighborhood proportion non-family households was associated with fewer depressive symptoms among women and it had no effect among men. Neighborhood proportion married-couple households was not significantly related to depressive symptoms among women, but among men, living in a neighborhood with more married-couple households with children was associated with fewer symptoms. Overall, the impact on depressive symptoms of neighborhood characteristics do not differ for men and women. Gender differences in neighborhood effects on three individual-level stressors and three individual-level psychosocial resources also were examined. Nine interactions were statistically significant. Consistent with expectations, people who reside in neighborhoods with more vacant housing units perceived more disorder and less social cohesion in their neighborhoods, and the effects were larger for women than men. Relative to men, women's perceptions of neighborhood social cohesion and social support are more sensitive to neighborhood economic conditions. In general, with a few notable exceptions, neighborhood effects on stressors and psychosocial resources do not vary by gender. In analyses that only included women, NSD was positive and significantly associated with depressive symptoms and neighborhood proportion adults aged 65 and older was negative and significantly associated with symptoms. Perceived neighborhood social cohesion fully mediated the effect of NSD--and partially mediated the effect of neighborhood proportion older adults--on depressive symptoms. The effect on depressive symptoms of neighborhood disadvantage did not vary significantly by levels of stressors and psychosocial resources except for three significant cross-level interactions. Living in a neighborhood with more vacant housing units was associated with more depressive symptoms, and the effect was greater among women who perceived high levels of disorder in the neighborhood than those who perceived less disorder. Also as hypothesized, NSD had the largest positive effect on depressive symptoms among women with less social support than women with more support. However, mastery did not funct on as a stress-buffer. The effect on depressive symptoms of neighb rhood advantage varied significantly by psychosocial factors. Living in a neighborhood with higher proportions of older adults was associated with fewer depressive symptoms more so for women who report low levels of perceived neighborhood physical disorder than women who report average levels of disorder. Also consistent with expectations, higher neighborhood proportion of affluent households and owner-occupied housing units were associated with fewer depressive symptoms, and the effects were larger for women with high levels of mastery than women with low mastery. However, these neighborhood characteristics were less beneficial to the mental health of women with high than low levels of social support. The findings from this dissertation largely indicate that relationships among components of the neighborhood stress process model do not differ by gender or by levels of stressors and psychosocial resources. However, the significant results that emerged make a valuable contribution to the research literature by identifying urban neighborhood conditions that are consequential to the mental health of middle-aged and older adults and that should be the target of interventions.
Keywords: Demographics; Health Conditions and Status; Healthcare; Methodology; Public Policy; Women and Minorities

A New Test of Borrowing Constraints for Education - Brown, Meta; John Karl Scholz; Ananth Seshadri (The Review of Economic Studies, 2012)
We discuss a simple model in which parents and children make investments in the children's education and investments for other purposes and parents can transfer cash to their children. We show that for an identifiable set of parent-child pairs, parents will rationally underinvest in their child's education. For these parent-child pairs, additional financial aid will increase educational attainment. The model highlights an important feature of higher education finance, the expected family contribution (EFC) that is based on income, assets, and other factors. The EFC is neither legally guaranteed nor universally offered: our model identifies the set of families that are disproportionately likely to not provide their full EFC. Using a common proxy for financial aid, we show, in data from the Health and Retirement Study, that financial aid increases the educational attainment of children whose families are more likely than others to underinvest in education. Financial aid has no effect on the educational attainment of children in other families. The theory and empirical evidence identifies a set of children who face quantitatively important borrowing constraints for higher education. PUBLICATION ABSTRACT
Keywords: Adult children; Demographics; Education; Methodology

Non-Invasive Sensor Solutions for Activity Recognition in Smart Homes - Srinivasan, Vijay (University of Virginia, 2012)
Smart home sensor systems that infer residents' activities enable a number of exciting medical monitoring and energy conservation applications. Existing home activity recognition systems are invasive , since they require significant manual effort from the end user in installing or training the system, inconvenience the resident by requiring them to constantly wear tags, or require invasive cameras or expensive sensors. Our main hypothesis is that by effectively using data fusion techniques, leveraging the existing smart meter infrastructure in homes, and using only weak biometric sensing, we can build convenient, accurate home activity recognition solutions for the end user. The key challenges for home activity recognition systems addressed in this dissertation include reducing configuration effort from the end user, reducing sensor installation effort, and identifying residents in multi-person homes without using invasive sensors. To reduce user configuration effort, we develop an unsupervised activity recognition algorithm called AUTOLABEL that leverages data fusion and cross-home activity models to accurately recognize resident activities without user training. To eliminate many direct sensors in the home for activity recognition, we develop effective Bayesian data fusion techniques, which combine the existing smart meter infrastructure in homes, with one low cost, non-invasive sensor per room. In our WaterSense approach, we combine a single smart water meter per home, with an occupancy sensor per room to eliminate direct sensors on individual water fixtures. In our LightSense approach, we combine a single smart energy meter per home with a light sensor per room, to eliminate direct sensors on individual light fixtures. Finally, we propose the use of resident height, which is a weak biometric, in an effective data fusion approach, to identify residents for activity recognition in multi-person homes. We evaluate our proposed activity recognition solutions through short term prototype sensor deployments in home environments lasting from 7 to 10 days each. We show that our low cost, convenient solutions satisfy the activity recognition needs of numerous smart home applications, such as remote medical monitoring for elderly residents, and fine-grained resource consumption monitoring of light and water fixtures in the home. Finally, we observe that our unsupervised activity recognition algorithm can be used in a wireless snoop attack on smart homes, to infer the residents' daily activities with high accuracy in spite of encrypted wireless transmissions. We propose and evaluate a suite of privacy solutions to mitigate the inference accuracy of such an attack without affecting the performance or functionality of the home activity recognition system.
Keywords: Health Conditions and Status; Methodology; Other

Obesity, Depression, and Employment Related Outcomes Among Workers Near Retirement - Mustafa C. Karakus; Okunade, A. (Ageing International, 2012)
Obese individuals with comorbid depression face greater risks of atrophied health status alongside the associated adverse consequences, such as limitations of daily living and/or work related activities. This study uses the U.S. Health and Retirement Study database to investigate the likelihood of early retirement decisions (before age 62) of older working-age adults (ages 50 to 62). We find that obese subjects with comorbid depression are significantly more likely to reduce work-hours and seek early retirement. Survival models confirm the negative association between obesity with comorbid depression and the duration to early retirement. The bidirectional association between obesity and depression suggest that more carefully designed public policy interventions are necessary for improving the labor market attachments of the older working-age adults that are obese and clinically depressed. PUBLICATION ABSTRACT
Keywords: Health Conditions and Status; Methodology; Public Policy; Retirement Planning and Satisfaction

Retirement Consumption Behavior: Evidence from HRS CAMS 2001-2009 - Chiang, Mei-Fang (Human Ecology, 2012)
Recent studies across a number of countries evidence a substantial decline in household consumption expenditure around the time of retirement. This phenomenon, coined as the retirement consumption puzzle, brings a challenge to the traditional life-cycle model. The life-cycle model implies that household consumption should be continuous over time including the transition to retirement, provided that retirement is a foreseeable event. To address the retirement consumption puzzle, this dissertation brings current evidence by carrying out four studies on U.S. household consumption behavior at retirement. Study 1 is a cross-sectional study using the latest available data wave from 2009 HRS CAMS. The main interest is to compare consumption behavior between non-retired and retired households. Based on the life cycle hypothesis, regardless of employment status, households sharing similar socioeconomic characteristics should exhibit similar consumption behavior. The empirical findings, however, show that the consumption behavior between non-retired and retired households is significantly different, holding all other factors constant. Spending for retired households is 8.5% lower than spending for non-retired households. Study 2 is an aggregate-panel study using data from 2001-2009 HRS CAMS. The difference between Study 1 and Study 2 is that Study 2 tracks household consumption behavior over time and investigates whether there is a significant change in consumption pattern after retirement. Fixed-effects analysis is conducted to appropriately account for the effect of individual heterogeneity. The life cycle hypothesis predicts that when retirement is as planned by the household, there is no significant change in consumption after retirement. The fixed-effects regression indicates that there is an insignificant increase of 3% in household consumption after retirement. The discrepancy in the results from Study 1 and Study 2 regarding the retirement consumption puzzle comes from the lack of control of individual heterogeneity in the cross-sectional analysis. Study 3 is a subsamples-panel study. Within the life-cycle framework, if retirement is voluntary and expected, there should be no significant change in household consumption after retirement. However, if the household head is laid-off or experiencing poor health, this household may be forced to be out of the labor market, resulting in early retirement. Because involuntary early retirement reduces the household's lifetime resources, the household must reduce consumption and re-allocate to a new optimal consumption path. As predicted by the life-cycle model, the findings show that households with voluntary retirement have an insignificant increase in household consumption after retirement by 6%. Involuntary-retirement results in a decrease in consumption after retirement by 6-7%. The percentage difference in the household consumption change between these the two groups of households is 11-12% and statistically significant. Accordingly, these findings suggest that household consumption behavior differs by household type (voluntary versus involuntary retirement). These three studies use log consumption as the dependent variable. Alternatively, Study 4 uses consumption growth as the dependent variable to test the retirement consumption puzzle. The regression results provide no evidence of a retirement consumption puzzle, finding an insignificant 3% increase in consumption after retirement.
Keywords: Consumption and Savings; Demographics; Event History/Life Cycle; Healthcare; Methodology; Net Worth and Assets; Retirement Planning and Satisfaction

A simple measure with complex determinants: investigation of the correlates of self-rated health in older men and women from three continents - D. J. French; Chris Browning; Kendig, H.; Luszcz, M. A.; Saito, Yasuhiko; K. A. Sargent-Cox; Kaarin J. Anstey (Bmc Public Health, 2012)
Background: Self-rated health is commonly employed in research studies that seek to assess the health status of older individuals. Perceptions of health are, however, influenced by individual and societal level factors that may differ within and between countries. This study investigates levels of self-rated health (SRH) and correlates of SRH among older adults in Australia, United States of America (USA), Japan and South Korea. Methods: Cross-sectional data were drawn from large surveys of older respondents ( = 65 years) in Australia (n = 7,355), USA (n = 10,358), Japan (n = 3,541) and South Korea (n = 3,971), collected between 2000 and 2006. Harmonized variables were developed to represent socioeconomic, lifestyle and health indicators. We then assessed whether these variables, and their potentially different impact in different countries, could account for cross-national differences in levels of SRH. Results: SRH differed significantly between countries, with older Koreans reporting much poorer health than those in the other three nations. This was not the result of biases in response patterns (for example central versus extreme tendency). Health-related correlates of SRH were similar across countries; those with more medical conditions, functional limitations or poor mental health gave poorer ratings. After accounting for the differential impact of determinants in different national contexts, Australians reported better SRH than other nations. Conclusions: We conclude that when examining correlates of SRH, the similarities are greater than the differences between countries. There are however differences in levels of SRH which are not fully accounted for by the health correlates. Broad generalizations about styles of responding are not helpful for understanding these differences, which appear to be country, and possibly cohort specific. When using SRH to characterize the health status of older people, it is important to consider earlier life experiences of cohorts as well as national and individual factors in later life. Further research is required to understand the complex societal influences on perceptions of health.
Keywords: Cross-National; Health Conditions and Status; KLoSA; Methodology

Social Determinants and Depression in Later Life - Cross-Denny, Bronwyn (Fordham University, 2012)
The social determinants of health and mental health have come to the forefront as a global issue as a result of the World Health Organization's (WHO) initiative to close the health equity gap. The aim of this study is to examine social determinants and the impact on depression over the life span utilizing Cumulative Disadvantage Theory. A secondary data analysis was conducted on the 2010 wave of data from the Health and Retirement Study. A path analysis was used to determine predictors of depression in later life. Findings indicated that age and neighborhood cohesion were predictors of perceived discrimination. Although total causal effects were small for predictors of depression, results indicate a possible protective factor provided by neighborhood cohesion and social support. Implications for social work research and practice are discussed for addressing service needs of the growing older adult population.
Keywords: Adult children; Demographics; Health Conditions and Status; Methodology

Three Essays on Estimation with Unpriced Amenities - Ryan D. Nunn; Daniel S. Silverman (University of Michigan, 2012)
Variation in the quality of job matches is an important determinant of workers' search decisions and the distribution of wages. I develop a structural search model that allows job match quality to depend on unpriced job amenities as well as monetary productivity, permitting match quality estimation that is robust to both unobserved amenities and selection. I estimate the model with wage and tenure data from the 1979 NLSY, finding that the standard deviation of job amenities is nearly as large as that of monetary productivity. I then use the model to investigate the welfare consequences of wage taxation and unemployment insurance. Traditional estimates of deadweight loss from wage taxation are increasingly overstated as job amenity dispersion rises. Reported happiness provides a new way to evaluate unpriced goods and experiences. In the wake of important life events, measures of subjective well-being often exhibit considerable mean reversion, which has not been fully incorporated into the economic analysis of happiness. This can lead to bias when comparing events. In the second chapter, Miles Kimball, Daniel Silverman, and I provide a flexible, extensible econometric framework that accommodates adaptation and permits the comparison of happiness-relevant life events with dissimilar hedonic adaptation paths. The method is used to analyze a variety of events in the Health and Retirement Study panel. The costly, endogenous supply of job amenities by firms has a number of interesting implications for labor markets and public policy. In the third chapter, Brendan Epstein and I show that it is necessary to estimate the heterogeneity and parameters of amenity supply in order to correctly infer deadweight loss from taxation. Deadweight loss is generally overestimated in work that omits explicit consideration of amenities, and this overestimation is proportional to the quantitative significance of heterogeneity in amenities across job matches. The endogenous supply of amenities, rather than exogenous endowment, is shown to exacerbate this overestimation. Examination of a static, non-search economy reveals that this is not just an artifact of search. Finally, we examine the dynamic response of taxable income and social welfare to unexpected tax changes.
Keywords: Employment and Labor Force; Methodology; Public Policy

Three essays on health care spending - Yoo, Minkyoung (Rutgers The State University of New Jersey, 2012)
This dissertation is composed of three essays that consider the determinants and persistence of health care spending and how policies that control increasing health care costs affect the distribution of health care spending in the U.S. In the first essay, I study the association between education and health care spending for a set of health conditions amenable to self-management. Empirical findings from estimated health expenditure models reveal strong inverse relationships between education and health care spending among elderly adults with hypertension and/or asthma. Additionally, I find that greater educational attainment is associated with a reduced likelihood of being in the top 5% of health care spenders for elderly adults with hypertension and nonelderly adults with diabetes, and also with less severe conditions. The second essay assesses how the distribution of family out-of-pocket health care spending has been affected by changes in recent cost-sharing to understand the effectiveness of the risk protection function of private health insurance against high medical care expenses. The results suggest that families who rely more on health care because of one or more their member's existing health conditions are most affected by changes in cost sharing during the period 2001-2005 and the increased exposure to out-of-pocket spending occurrs primarily for families at higher percentiles of the out-of-pocket spending distribution, thus reducing the "return" to risk protection from holding private health insurance. The final essay examines the dynamics of out-of-pocket health care spending by looking at the persistence of such spending among Medicare beneficiaries. The findings suggest that having a certain chronic condition or a health shock clearly increases the probability of out-of-pocket health care spending persistence. Additionally, having an existing health insurance that supplements Medicare coverage or the acquisition of a new supplementary health insurance has a significant impact on the probability of persistence.
Keywords: Demographics; Health Conditions and Status; Healthcare; Medicare/Medicaid/Health Insurance; Methodology; Other; Risk Taking

Three essays on the health and family behavior - Sikora, Joanna E. (Cornell University, 2012)
This dissertation is comprised of three papers on health and household behavior. Two of the papers focus on the influence of family on health outcomes. The third paper examines household member preferences and their association with outcomes for other individuals within the family unit. The first paper tests the relationship of adult-child and elderly-parent contact frequency on elderly cognitive functioning (dementia) using the Health and Retirement Study (HRS). The paper examines various mechanisms through which the intensity of contact with adult, nonresident children impacts elderly cognitive functioning. An instrumental variables model is used to account for the endogeneity in the level of parent-child contact. Results indicate a positive association between intensity of contact from nonresident adult children and mothers' cognitive functioning; however, no causal relationship is found suggesting that higher levels of contact are due to selection. The second paper examines the prediction of stated, altruistic, preferences on an individual's revealed preferences, observed intergenerational family transfers. Measures of altruism toward children and parents are constructed, using hypothetical questions in the 1996 wave of the HRS that assess individuals' willingness to transfer income to others, and evaluated for their additional explanatory power, within traditional models of intergenerational transfers, on observable transfer behavior. Results indicate that higher levels of altruistic preferences are associated with higher probabilities of transfers and larger transfer amounts from respondents to children; however, transfers to parents do not appear to be related to the altruism measure. The final paper investigates the link between relationship status and body mass index. There are four hypotheses (selection, protection, social obligation and marriage market) that might explain the relationship between marital status transitions and changes in Body Mass Index (BMI). Using the National Longitudinal Survey of Youth 1979, individual fixed effects models are estimated to examine associations between the change in log BMI, and the incidence of overweight and obesity, and changes in relationship status. There is no support for the marriage protection hypothesis. Rather evidence supports the social obligation and marriage market hypotheses--BMI increases for both men and women during marriage and in the course of a cohabiting relationship.
Keywords: Adult children; Demographics; Health Conditions and Status; Methodology; Public Policy

Three Essays on the Labor Supply, Savings and Investment Behavior of Older Workers - Clift, Jack W. (The Pardee RAND Graduate School, 2012)
In this dissertation, I provide three distinct analyses addressing labor supply, saving and investment behavior of (older) workers, in the context of the incentives and constraints they face due to employer and government policies. In the first paper, I examine labor supply flexibility and its effect on the labor supply decisions of older workers. Previous literature suggests that people would like to reduce hours of work gradually over time as they get older, but do not have the flexibility to do so in their job, and consequently may retire early rather than continue to work high hours at older ages. If greater flexibility allows individuals to stay in the labor force longer, this could increase total labor supply, helping to increase both private resources for retirement and tax revenue to support public programs. Following a sample of older Americans for 16 years from 1992 to 2008, I find that there are noticeable differences in labor outcomes between those who had flexibility over their hours in 1992 and those who were not able to adjust their hours: those with flexibility worked fewer hours in their 50s, but tended to stay in the labor force longer; the major difference between groups occurred when individuals were in their early-mid 60s, at which time those who did not have flexibility in 1992 were much more likely to retire than those with flexibility. This work provides support for the theory that people prefer gradual retirement to more abrupt departures from the labor force, and indicates that flexibility around key retirement ages might have an impact on behavior. The overall effect on total labor supply of providing flexibility at all points of the lifecycle is ambiguous. In the second paper, we examine whether labor supply flexibility affects investment behavior. Individuals can receive higher returns (on average) on their investments if they are willing to bear more risk, which allows people to reach retirement with greater resources (on average) than if they had pursued low-risk strategies; but the fear of suffering big losses discourages people from taking risks. Theoretical work has argued that individuals with flexibility over their labor supply over the lifecycle can bear more risk in their portfolio of investments, as they can increase their labor to offset any losses they might suffer. Using a new survey we fielded in the American Life Panel (ALP), we examine how different measures of labor supply flexibility are related to measures of risk-taking in investments: individual participation in the stock market, and the percentage of an individual's financial wealth held in stocks. We find no evidence that flexibility over number of hours worked per week is related to investments in stocks. We find weak evidence that other flexibility measures--an individual's belief that they would be able to continue to work longer to make up for any negative wealth shocks, and the absence of factors that make it difficult to sustain a job into old age--may be related to greater risk-taking in investments. These results may indicate that flexibility at the extensive margin (ability to extend a career) may be more relevant to investment decision-making than flexibility at the intensive margin (ability to adjust hours). In the third paper, I describe the construction and characteristics of a unique dataset with which I lay the foundations for understanding pension system incentives and how they influence work and savings behavior over the lifecycle. Public pension systems across the developed world are in need of reform, but it is important to understand how the incentives in these systems affect behavior if we are to predict the consequences of different possible reforms. Previous literature has argued that public pensions displace private savings, but with elasticity of less than 1; this suggests that possible reductions in pension benefits through reforms would be partially (but not fully) offset by increases in private saving. Using new retrospective earnings history data for five European countries, in conjunction with linked survey data describing household wealth, I construct a dataset that captures the heterogeneous pension system incentives faced, and labor supply decisions made, at each point in the lifecycle for a large group of European men. My exploratory analysis of this dataset is consistent with the hypotheses that more generous income replacement by pension plans leads to lower private wealth accumulation, and greater reward within the pension system for continued work leads to later retirement. However, these statistical associations admit of plausible alternative explanations; the work documented in this paper cannot provide definitive answers on the incentive effects of pension systems, but provides the groundwork for significant extensions of research in this field, and eventually for detailed policy simulation of pension reform. (Abstract shortened by UMI.)
Keywords: Employment and Labor Force; Healthcare; Methodology; Net Worth and Assets; Pensions; Public Policy; Retirement Planning and Satisfaction; Social Security

Utility of the Abbreviated Fuld Object Memory Evaluation and MMSE for Detection of Dementia and Cognitive Impairment not Dementia in Diverse Ethnic Groups - Rideaux, T.; Sherry A. Beaudreau; Fernandez, S.; Ruth O'Hara (Journal of Alzheimers Disease, 2012)
To address the growing need for ethnically unbiased cognitive screening, we examined whether the Mini Mental State Exam (MMSE), the abbreviated Fuld Object Memory Evaluation (FOME), or a combination of the two provided optimal detection of dementia in an ethnically diverse group of older adults with no cognitive impairment (normal); cognitive impairment not dementia (CIND); and dementia. Participants included 509 Caucasians, 124 African Americans, and 68 Latinos ( 70 years old) from the Aging, Demographics, and Memory Study who completed the MMSE and FOME. Empirically derived decision trees were computed using signal detection software for receiver operator characteristics (ROC). Among the three ethnic groups, ROC analyses revealed that lower cut-scores on both the MMSE and FOME provided better detection of CIND or dementia. Sensitivity and specificity of the MMSE was augmented by the addition of the FOME among Caucasian and African American older adults. The MMSE alone was the best screen in Latino older adults to distinguish any cognitive impairment from normal. When comparing CIND versus dementia, however, the FOME alone was best for detecting dementia among Latinos. The abbreviated FOME is recommended to increase clinical validity and thus minimize ethnic biases when administering the MMSE to Caucasian and African American older adults. The MMSE alone is preferred for older Latinos unless comparing CIND and dementia, in which case the FOME alone would then be recommended. Findings suggest that ethnicity is important in the selection of an appropriate cognitive screen and cut-score to use with older adults.
Keywords: Health Conditions and Status; Methodology

Bricks and slaughter - Palmer, Andrew (The Economist (US), 2011)
The focus of the article is on the property cycle; the author asserts that "construction of exceptionally tall buildings is a reliable indicator of economic crises in the making" and goes on to discuss the burst housing bubble of 2007. [The article quotes a 2008 paper by Hugo Benitez-Silva et al., that used the Health and Retirement Study data to analyze respondent perceptions of housing values.]
Keywords: Consumption and Savings; Demographics; Methodology; Other

Changes in retirement decisions: Determinants of plans and timing - Giuriceo, Katherine Dodge (Gerontology, 2011)
Purpose. This study examined dynamic factors in a worker's background, resources, jobs or health which influence their expectations about future decisions to work or retire at ages 62 or 65, as well as how these influences and expected timing change as the individual approaches retirement. Design and methods . Employing a conceptual framework based on Andersen's (1995) model of health care utilization, the first research question used Generalized Estimating Equations (GEE) to determine which predictors were associated with workers' expected retirement timing. The second question examined changes in expectations over time in response to changes in predictors, using a two-level approach modeled on Singer and Willett (2003). Utilizing the Core sample of the Health and Retirement Study (HRS); data on 5,989 individuals (48.3% female) were examined longitudinally across seven waves, 1992 and 2006. Results . For research question one, female gender was associated with a lower expectations to continue working at both early (62), and normal (65) retirement ages. Non-married status had a similar effect for 62 but not for age 65. Differences emerged among sub-groups with non-married females reporting greater plans to continue working at both retirement ages; non-married blacks however were less likely to report plans to continue working at age 65 only. Non-whites with poorer subjective health or health that limited work were less likely to expect to work at age 62, but there was no impact on plans for age 65. Changes were also important. Leaving married status was linked with changes in plans to work at 65 but not 62. Gaining employer sponsored benefits (pension and health coverage) increased likelihood of continued work at both ages. Implications . Findings confirmed that known predictors of retirement decisions are also associated with workers' expectations well before retirement age is reached. Andersen's model was useful for understanding the dynamic process leading up to retirement. Results also support the importance of employer sponsored benefits, such as pension and health insurance, on changes in plans as individuals approach retirement. Policy makers interested in prolonging work lives should look to modifiable factors (pensions and health insurance), which may impact retirement timing.
Keywords: End of life decisions; Expectations; Methodology; Retirement Planning and Satisfaction

Cohort Based Analysis of Income Shocks Over the Life Cycle - Jeremy G. Moulton (University of California, Davis, 2011)
The following three chapters investigate the first job, retirement decisions, and bequests of birth cohorts born between 1908 and 1926. I employ cohort based natural experiments using the Great Depression and Social Security Amendments of 1972 and 1977 to estimate the effect of entering the labor market during a recession, choice of retirement age in response to a retirement benefit shock, and financial transfers with children when facing a late life income shock. The first chapter uses a regression discontinuity framework to show that less educated workers entering the labor market during the Great Depression experienced 7 to 10% lower earnings roughly ten years after the onset of the Great Depression, in 1940. These effects fade substantially ten more years later in the 1950 Census. More educated workers entering the labor market experienced no loss to earnings in 1940 and positive earnings in the 1950 census, but these results may be driven by the effects of World War II or a more favorable job market for educated laborers during the Great Depression. Using the same regression discontinuity framework, I also show that young workers did not significantly delay their entry into the labor market during the Great Depression by prolonging their stay in high school. The second chapter reinvestigates and helps explain the findings of Krueger and Pischke (1992), who find no significant response of retirees in response to the Social Security Notch (Amendments of 1972 and 1977). Using a hazard model and data from the AHEAD cohort of the Health and Retirement Study, we find that using a long-term incentive measures, of the form found in Coile and Gruber (2000), provides a better estimate of retirement decision making than single year accrual measures. We find that individuals respond to both the long-term incentive measure (decreases the hazard of retiring) and the present value of their Social Security wealth (increases hazard). However, using the exogenous variation caused by the Social Security Notch results in opposite signed effects for the incentive measure. We show that this odd result and the reason that Krueger and Pischke do not find a significant change in retirement is that the Social Security Notch is one experiment, but has two offsetting, but correlated treatments. The Social Security amendments increased both the incentive measure and Social Security wealth for the cohorts subject to the 1972 amendments (Pre-Notch cohort) and the opposite for those subject to the 1977 amendments (Notch cohort). We show that the lack of retirement response is not due to no response, but to large offsetting effects. The last chapter investigates intergenerational wealth transmission between fathers and children using the 1972 and 1977 Amendments to the Social Security Act. As shown in chapter 2, individuals did not change their retirement age in response to these amendments, so those affected by the 1972 amendments experienced increased growth in Social Security benefits while those subject to the 1977 amendments experienced a negative shock (the "Notch Generation"). Using the Health and Retirement Study, I find that sons with fathers born in the Notch Generation have significantly lower wealth levels than those with fathers born in surrounding cohorts, most notably the cohort born just prior. Further evidence suggests that the wealth difference is likely due to a higher probability of providing financial support to parents and a lower probability of receiving an inheritance and financial assistance from parents.
Keywords: Adult children; Employment and Labor Force; Methodology; Retirement Planning and Satisfaction; Social Security

Compression of morbidity and the labour supply of older people - Romeu Gordo, Laura (Applied Economics, 2011)
This article tests whether there is evidence of compression of morbidity using Health and Retirement Study (HRS) data and analyses the effects of this on the labour supply of older people. We find younger cohorts to suffer less from functional problems than older cohorts at given ages. Furthermore, we observe that instrumentalized disability has a negative effect on labour force participation. According to the cohort analysis and the multivariate analysis, it can be concluded that individuals will be able to work longer because of the delay in the onset of disability problems.
Keywords: Demographics; Employment and Labor Force; Health Conditions and Status; Methodology; Public Policy

Consumption and Differential Mortality - Michael D Hurd; Susann Rohwedder (Michigan Retirement and Disability Research Center Project, 2011)
It is well-established that differential mortality according to wealth or income introduces bias into age profiles of these variables when estimated on cross-sectional or synthetic cohort data. However, little is known about whether this association is also found with consumption, and if so, how strong this association is. In this paper we use panel data on total household spending from the Health and Retirement Study (HRS) and its supplemental study, the Consumption and Activities Mail Survey (CAMS), to estimate differences in consumption by survival status to the next survey wave. We quantify the bias in age profiles of consumption that results from differential mortality when estimating the age profiles on cross-sectional data or on synthetic cohort data. We find that the bias is smaller than that found for wealth or income.
Keywords: Consumption and Savings; Demographics; Health Conditions and Status; Methodology

Debt and negative net worth among near-retirees - Brown, Susan M. E. (Family, Consumer and Human Development, 2011)
Going into retirement, near-retirees are looking at increased debt levels, which can offset any asset accumulations and reduce retirement income. By using data from the 2008 Health and Retirement Study (HRS), this study examines the debt and negative net worth of near-retirees. This study further investigates what factors are associated with the likelihood of holding consumer debt, holding mortgage debt, and holding home equity debt over holding no debt, and what factors are associated with the likelihood of holding negative net worth over holding a high level of net worth among near-retirees. The study sample includes 3,745 individuals between the ages of 51 and 64. The results of the multinomial logistic regression analysis indicate that, all else being equal, human capital factors such as education, physical health problems, and depression symptoms play a significant role in predicting the likelihood of holding debt and negative net worth. In particular, education is positively associated with the likelihood of holding consumer, mortgage, and home equity debt over holding no debt, while it is negatively associated with the likelihood of having negative net worth over having a high level of net worth. Among the socioeconomic characteristics that influence the likelihood of near-retirees holding debt and negative net worth are household income, working in the labor force, and race. In particular, household income positively influences the likelihood of holding mortgage debt over holding no mortgage debt as well as the likelihood of holding home equity debt over holding no home equity debt. However, household income negatively influences the likelihood of having negative net worth over having a higher level of net worth. The findings of this study could help financial educators, financial planners, and policymakers understand the differences in human capital and socioeconomic characteristics of near-retirees who hold some levels of debt over no debt and who hold no net worth or a lower level of net worth over a higher level of net worth. This study concludes that it is important for professionals, consumer educators, and financial planners to provide those who hold higher levels of debt and lower levels of net worth with financial literacy education; therefore, these individuals might be able to attain economic well-being in retirement.
Keywords: Adult children; Methodology; Net Worth and Assets; Other; Retirement Planning and Satisfaction

The Dynamics of Living Arrangements Among the Elderly - Witvorapong, Nopphol (The University of North Carolina at Chapel Hill, 2011)
Combining care arrangements and whom the elderly live with, I study the mechanisms behind changes in living arrangements. I estimate a dynamic model of living arrangements, savings, intergenerational transfers and health outcomes. I use the nonlinear discrete factor random effects estimation method to control for unobserved heterogeneity. I use the rich data available in the 1995 - 2006 waves of the Health and Retirement Study (HRS) and supplement them with data on Medicaid and costs of care, resulting in a unique data set. I find that living arrangements are strongly influenced by health and savings. In particular, functional health is the strongest predictor of living arrangements. Inter vivos transfers and bequest intent affect living arrangements only to the extent that they impact the distribution of unobserved heterogeneity, indicating the absence of the exchange hypothesis as far as living arrangements are concerned. Public policies have a small but significant effect in the determination of living arrangements. For example, a twofold increase in the probability of receiving nursing home benefits among Medicaid eligibles increases the use of nursing home only by a 0.1 percentage point. The effects of public policies are more pronounced among elderly individuals with poor initial health and low initial wealth.
Keywords: Healthcare; Methodology; Public Policy

Economic Measurement in the Health and Retirement Study - Steven F Venti (Forum for Health Economics and Policy, 2011)
The Health and Retirement Study (HRS) is widely use for research on the well-being of the elderly. This paper assesses the quality of economic and financial variables in the HRS. I find the coverage is comprehensive and the quality of the data is uniformly high. Thus the HRS has earned its position as the most widely used data source for research on retirement, saving adequacy, pension policy and a host of other aging-related topics. I identify two general areas that continue to merit special attention. The first is measurement error, particularly errors arising from item non-response and from inaccurate respondent reports of the ownership and level of assets. The second is the quality of the pension data. Where appropriate, I make suggestions for improving economic measures in the HRS.
Keywords: Methodology; Pensions; Retirement Planning and Satisfaction

Effects of Increasing the Incentive Size in a Longitudinal Study - Willard L Rodgers (Journal of Official Statistics, 2011)
To assess the possible impacts of increasing the incentive size on response rate and data quality, at one wave of a longitudinal study sample members were randomly assigned to receive one of three incentives: the same 20 incentive per person they had received in previous waves; 30; or 50. Those offered 50 had a higher response rate than those offered 20, and this positive impact persisted for at least the next four waves of biennial data collections. There is some evidence that higher incentives improve data quality as indicated by probabilities of failing to answer questions and of giving responses that would reduce the interview length.
Keywords: Healthcare; Methodology

Essays in Labor Economics - McFall, Brooke Helppie (University of Michigan, 2011)
This dissertation is composed of two essays, both which use data from original survey projects to examine issues related to work choice. The first essay examines the labor supply effects of the wealth losses during the stock market crash of 2008 and 2009. A life-cycle model incorporating both consumption and retirement timing implies that exogenous wealth losses should delay optimal retirement timing. Using data from the Cognitive Economics Study and the Health and Retirement Study, this essay quantifies the wealth losses suffered by older Americans in terms of the additional length of time they would have to work to maintain the pre-crash consumption plan implied by their wealth holdings and expected retirement timing. Using these measures, Tobit regressions and a novel method for reducing the impact of error-ridden observations are used to examine the relationship between this measure of wealth loss and retirement planning. Several potential sources of heterogeneity in individuals' reactions to the crash are also examined. Results imply that wealth losses of 2008 and 2009 are associated with an increase in planned retirement age on the order of a few weeks to a few months for the average older American, but up to several months for some segments of the population. These results are consistent with results of recent studies and the life-cycle model, but stand in contrast to other examinations of wealth shocks on the general population of older Americans. The second essay is a product of the Job Seekers Study. The essay extends Mincer's seminal theory of family migration to allow couples to adjust to migration constraints by living apart, and examine the ways in which new PhD economists adjust to migration constraints imposed on them by their spouses or partners. Both the impact of migration constraints on job outcomes and the impact of job considerations on relationship outcomes are analyzed. The essay finds that migration constraints result in small costs in terms of job outcomes, relative to many existing studies, and that adjustment through living apart is common. These results imply that existing studies may overestimate the job impact of migration constraints.
Keywords: Health Conditions and Status; Methodology; Net Worth and Assets; Public Policy; Retirement Planning and Satisfaction

Family Data and Research in the Health and Retirement Study - Suzanne M. Bianchi (Forum for Health Economics and Policy, 2011)
I discuss the data in the Health and Retirement Study (HRS) that can be used to study family change and intergenerational family relationships and offer suggestions about what might be done to enhance the uses of the HRS family data going forward. A number of family demographic behaviors are altering the family context of more recent cohorts of the HRS. These family changes need to be well-captured in the data collection and and should also inform future design decisions. Changes include the higher rates of childlessness, delayed marriage and childbearing after age 30 among the Baby Boom cohorts just now being enrolled in the HRS. Cohorts coming into the study also have higher rates of (lifetime) labor force participation on the part of women and much higher rates of nonmarital childbearing, marital disruption, and informal cohabitation than the original HRS cohorts. There is also great heterogeneity in family patterns by race and class among Baby Boom cohorts. Many of these changes increase the value of collecting family data in the HRS but also complicate the collection of useful data on transfers between parents and children or among siblings. I offer four suggestions for enhancing data collection in the HRS in light of these family changes. These include the following: 1) Reevaluate decisions about the family members on whom to gather information, particularly the decisions about when to collect data on siblings. 2) Consider collecting more information directly from each spouse (and perhaps expanding the definition of spouse to include cohabiting partners as cohabitation is on the rise among cohorts now entering the HRS). 3) Begin to experiment with interviewing adult children of HRS respondents and consider broadening the content to include more on parent-child relationship quality and/or on everyday activities and exchanges. 4) Make the family data in the HRS easier to access and use.
Keywords: Adult children; Methodology

The gender gap in depressive symptoms among elders in the United States and Japan: Social support, coresidence and somatic health as mediating factors - Andrew D. Tiedt (Fordham University, 2011)
Cross-national research on gender and aging has discussed a persistent gender gap in depressive symptoms among elders, indicating that women report more frequent symptoms than men. In light of recent attention given to both depression and elder care issues in a global context, this dissertation examined the prevalence of depressive symptoms among elder men and women in the United States and Japan. Both nations are facing complications related to aging populations and have similar economic foundations, educational systems and representative governments. Yet the cultural underpinnings of household arrangements and family support obligations are distinct. The analyses used two waves of the Nihon University Japanese Longitudinal Study of Aging (NUJLSOA) and the Health and Retirement Study (HRS) to analyze the conditions resulting in the expression of depressive symptoms. One prominent cultural difference between nations is the persistence of intergenerational coresidence among elders and younger generations in Japan, despite more recent shifts in preference towards independent living. This dissertation posited that changing attitudes concerning filial obligations would result in more frequent depressive symptoms among Japanese women due to increased instances of conflict between coresiding elder women and daughters-in-law. Next, the dissertation posited reductions in the gender gap in depressive symptoms over time due to elder men transitioning to retirement, widowhood and disability. The analyses revealed that household relationships were more prominent as predictors of depressive symptoms in Japan than the United States. This was attributed to the persistence of filial piety. There was also evidence of the increased importance of gender in terms of late life transitions such as marital dissolution in Japan, while there was less variation in the correlates of depressive symptoms by gender in the United States. Coresidence proved to be both a buffer and aggravator of depressive symptoms among Japanese women, while coresidence was likely to buffer male mental health in either nation. However, there was evidence that living with children and receiving instrumental support exacerbated depressive symptoms among American men. These findings suggest the importance of within-gender as well as between-gender analytical approaches in order to interpret the role of culture in influencing contemporary family support relationships.
Keywords: Cross-National; Demographics; Health Conditions and Status; Healthcare; Methodology

Genome-Phenome Linkages in Human Population Surveys, with Special Emphasis on the Health and Retirement Survey - Singer, Burton (Forum for Health Economics and Policy, 2011)
We review a diversity of genome-wide association studies (GWAS) with particular emphasis on precision in specifying phenotypes. This implies that examination of any specific phenotype involves considering the likely genetic contributions to it from the entire genome. We consider a variety of phenotypes specifiable with data from the Health and Retirement Survey (HRS). However, evidence from other large population studies is also incorporated as part of the process of developing and refining pathway representations from the genome thru a hierarchy of intermediate endpoints to behavioral, cognitive, and economic phenotypes. Any causal modeling focused on genome-phenotype connections must, of necessity, include consideration of intermediate endpoints (endophenotypes) as mediators of such associations. We also discuss metabolic and gene expression consequences of gene-environment interactions as a next research step beyond GWAS, not only for HRS but also for an integrated set of human population surveys that can provide much more statistical power than any one of them used alone. A variety of concrete examples based on physiological, psychological, sociological, and economic outcomes are carried along throughout our discussion.
Keywords: Genetics; Methodology

Household Stock Market Beliefs and Learning - Kezdi, Gabor; Robert J. Willis (NBER Working Paper, 2011)
This paper characterizes heterogeneity of the beliefs of American households about future stock market returns, provides an explanation for that heterogeneity and establishes its relationship to stock holding behavior. We find substantial belief heterogeneity that is puzzling since households can observe the same publicly available information about the stock market. We propose a simple learning model where agents can invest in the acquisition of financial knowledge. Differential incentives to learn about the returns process can explain heterogeneity in beliefs. We check this explanation by using data on beliefs elicited as subjective probabilities and a rich set of other variables from the Health and Retirement Study. Both descriptive statistics and estimated relevant heterogeneity of the structural parameters provide support for our explanation. People with higher lifetime earnings, higher education, higher cognitive abilities, defined contribution as opposed to defined benefit pension plans, for example, possess beliefs that are considerably closer to what historical time series would imply. Our results also suggest that a substantial part of the reduced form relationship between stock holding and household characteristics is due to differences in beliefs. Our methodological contribution is estimating relevant heterogeneity of structural belief parameters from noisy survey answers to probability questions.
Keywords: Consumption and Savings; Expectations; Methodology; Net Worth and Assets

How Does Occupational Status Impact Bridge Job Prevalence - Kevin E. Cahill; Michael D. Giandrea; Joseph F. Quinn; Office of Productivity and Technology (Economic Working Paper, 2011)
Is bridge job prevalence reduced significantly if a change in occupation is required in addition to the hours and tenure requirements that typically define bridge job employment. Prior research has shown that the majority of older Americans with career employment do not exit the labor force directly from their careers. Rather, most career individuals take on a 'bridge job' later in life, that is, a job that follows full-time career (FTC) employment and precedes complete labor force withdrawal (i.e., retirement). One criticism of this finding is that bridge job prevalence may be overstated because the definition of a bridge job in the existing literature does not require a change in occupation. This paper investigates the extent to which bridge jobs involve a change in occupation or a switch to part-time status, both of which may signal retirement transitions as opposed to continued career employment, albeit with a different employer. We use the Health and Retirement Study (HRS), a nationally-representative longitudinal dataset of older Americans that began in 1992 as the basis for our analysis. We find that, among HRS respondents who were on a FTC job at the time of the first interview and who changed jobs in subsequent waves, 48 percent of the men and 40 percent of the women also changed occupations, using 2-digit occupation codes. Further, when hours worked are also considered, we find that more than three quarters of FTC respondents who changed jobs later in life had either a change in occupation or a switch from full-time to part-time status. Finally, an examination of those career workers who changed jobs but not occupations and who remained working full time reveals that, as a whole, they resemble those who took bridge jobs rather than those who remained on their FTC job. We conclude that the vast majority of career workers who changed jobs later in life did in fact do so as part of a retirement transition.
Keywords: Employment and Labor Force; Health Conditions and Status; Methodology; Retirement Planning and Satisfaction

How Does the Personal Income Tax Affect the Progressivity of OASI Benefits? - Norma B Coe; Karamcheva, Zhenya; Richard W Kopcke; Alicia H. Munnell (Center for Retirement Research at Boston College Working Papers, 2011)
This study calculates the impact of federal income taxes on the progressiveness of the Old Age and Survivors Insurance (OASI) program. It uses the Health and Retirement Study (HRS) data linked with the Social Security Earnings Records to estimate OASI contributions and benefits for individuals and households, before and after income taxes, for three birth cohorts. It uses two measures of progressivity: redistribution by decile (the difference between the share of total benefits received and the share of total taxes paid) and effective progression (the change in the Gini coefficient). Under both measures, the results without the income tax confirm previous findings: Social Security is progressive on an individual basis, but that progressivity is dramatically cut when one calculates it on a household basis. Adding income taxes could make the program either more or less progressive. On the one hand, the tax treatment of contributions makes the system even less progressive than generally reported. On the other hand, the taxation of benefits makes it more progressive. The net result is that adding the personal income tax to the analysis makes Social Security more progressive than without taxes, on both the individual and household bases. Importantly, however, the impact of taxation on redistribution increases significantly among younger cohorts. Under current law, the Social Security system becomes more progressive over time.
Keywords: Methodology; Public Policy; Social Security

The Impact of Family and Non-Family Roles on Caregiver Health Over Time - Matzek, A. (Family Social Science, 2011)
Using stress process and life course theory, this dissertation investigated pathways of adult child caregivers' family (caregiving, marital, parenting) and non-family (employment) roles and their relation to caregiver psychological and physical health over time. Eight waves of data (1992-2006) from the Health and Retirement Study were analyzed for 1,300 adult child caregivers. Latent class analysis provided strong substantive and statistical evidence for a 4-class model of caregivers' role pathways. The four pathways were (a) Married, Working Caregivers (22.5%), (b) Married, Retired Caregivers with Co-Residing Child (12.5%), (c) Married, Retired Caregivers (30.5%), and (d) Not Married, Retired Caregivers (34.6%). Married, Working Caregivers , who were more likely to be male, White, and younger than most other pathways, had more optimal psychological and subjective physical health, but were more likely to have high blood pressure compared to caregivers in other pathways. Results suggest that (a) adult child caregivers have distinct family and non-family role pathways, (b) caregivers' gender, race/ethnicity, and age predict pathway membership, and (c) caregivers' role pathways are connected to psychological and physical health over time. Future research should explore how adult child caregivers' role pathways structurally differ for male versus female and younger versus older caregivers to further explain the heterogeneity of adult child caregivers' role pathways. Family practitioners may be helpful in identifying practices and policies that help adult child caregivers manage their diverse range of long-term family and non-family roles.
Keywords: Adult children; Event History/Life Cycle; Healthcare; Methodology; Other

Impact of Health Conditions on Cognitive Change in Later Life: A Cross-Study Comparative Analysis - Sparks, Catharine (University of Victoria (Canada), 2011)
Relatively few studies have considered how changes in health are associated with changes in cognition in aging populations. Even fewer have investigated the similarities and differences of the health-cognition link evidenced across independent longitudinal studies of aging that differ in country and birth cohort. The main objective of the current research is to evaluate aging-related cognitive change in the context of physical health conditions and to compare patterns and synthesize results across several longitudinal studies of aging. This cross-study evaluation is based on data from three longitudinal studies of aging: 1) the OCTO-Twin Study, a longitudinal investigation of same-sex twin pairs drawn from the population-based Swedish Twin Registry (N = 702; 67% female; mean age is 83.5), 2) the Health and Retirement Study (HRS), a study of middle-aged and older adults in the U.S. (N = 21,364; 57% female; mean age is 65.8), and 3) the English Longitudinal Study of Aging (ELSA), a study of middle-aged and older adults in the U.K. (N = 11,397; 54% female; mean age is 65.3). Data were analyzed using latent growth curve (LGC) analysis to evaluate 1) the impact of diagnosed health conditions and 2) the additive impact of comorbidity on level and rate of change in distinct cognitive outcomes. Our findings indicate that particular health conditions significantly impact initial status and rate of change in cognition, but do so differently across longitudinal studies of aging. The argument is made that the inclusion of health in our predictive models is essential as we try to parse out the effects of pathological aging vs. normative age-related change in cognition. The results of this study show the importance of replication in longitudinal research and for contrasting patterns of effects across independent studies in order to build a cumulative basis for further understanding of the dynamics among aging, health, and cognition in populations that differ in cohort, culture, and country.
Keywords: Cross-National; Health Conditions and Status; Methodology; Public Policy

Intrinsic Rewards of Work, Future Time Perspective, the Economy in the Future and Retirement Planning - Ting-Ying Yang; DeVaney, Sharon A. (The Journal of Consumer Affairs, 2011)
This study incorporated intrinsic rewards of work, future time perspective and perspective on the economy in the future to create a model for the psychological mechanism of planning for retirement. The data set included those who were not retired (N = 2,266) in the 1992 Health and Retirement Study. Confirmatory factor analyses and structural equation modeling were used. The analyses were conducted separately on the different types of retirement plans. The results suggest that human resource professionals should (1) encourage employees who perceive high intrinsic rewards of work to plan for their retirement, and (2) remind employees that retirement might be closer than they anticipate. PUBLICATION ABSTRACT
Keywords: Health Conditions and Status; Methodology; Other; Retirement Planning and Satisfaction

Introduction to the Health and Retirement Study: An Evaluation and Scientific Ideas for the Future - James P Smith (Forum for Health Economics and Policy, 2011)
Keywords: Methodology

Modeling social participation as predictive of life satisfaction and social connectedness: Scale or index? - Zelenka, Anne T. (University of Denver, 2011)
Social participation in late adulthood through activities such as volunteering with charities, playing sports, and joining clubs can increase life satisfaction, directly by providing enjoyable engagement and indirectly by increasing a person's sense of social connectedness. When reported levels of different types of activities are used to measure social participation, conventional measure development procedures based on classical test theory lead to a proliferation of small participation subscales that don't show good reliability, don't have theoretical power, and don't match researchers' conceptions of the dimensions of participation. Based on the poor performance of conventional approaches, some researchers have suggested that social participation should be modeled as an index composed of its indicators rather than as a scale in which indicators reflect an underlying latent factor. Typical approaches in psychosocial research rely on reflective-indicator models, which correspond to scale development, rather than incorporating composite variables with causal indicators. The latter approach, where manifest indicators are specified as causing the unobserved construct, is sometimes known as formative measurement , since the construct of interest is formed by its indicators. This study compared a scale model of social participation based on reflective measurement to an index model based on formative measurement. Using a sample representative of community-dwelling U.S. adults over age 65 from the Health and Retirement Study's 2008 wave of data collection, two alternative measurement models of participation were constructed using sixteen items that recorded frequency of participation in different activities. Because patterns of participation differed for males and females, gender-specific models were developed. The scale models assigned participation items to subscales based on item intercorrelations. The index model assigned items to participation composites based on predictive associations with the outcomes of social connectedness and life satisfaction. The index construction process led to a unidimensional representation of participation, composed of six of the original sixteen participation activity items. The initial attempts to build a scale model led to structures with many small factors and poor predictive validity. Based on the findings of unidimensionality for the index model, a single-factor scale model was explored for female respondents only. Results showed that both index and scale approaches have the potential to produce participation models that are parsimonious, well-fitting, and externally valid even though conventional scale development rules-of-thumb and current conceptions of the domains of participation lead the researcher to non-parsimonious, poorly-fitting solutions lacking predictive capability. Participation measurement instrument developers often theorize the existence of three or more dimensions of participation. Whether they use conventional (reflective indicator) or more radical (formative indicator) models, they are advised, based on this study's results, to evaluate a single-dimensional structure among their candidate models.
Keywords: Health Conditions and Status; Healthcare; Methodology; Retirement Planning and Satisfaction

Pensions and Household Wealth Accumulation - Gary V. Engelhardt; Kumar, Anil (The Journal of Human Resources, 2011)
Economists have long suggested that higher private pension benefits crowd out other sources of household wealth accumulation. We exploit detailed information on pensions and lifetime earnings for older workers in the 1992 wave of the Health and Retirement Study and employ an instrumental-variable (IV) identification strategy to estimate crowd-out. The IV estimates suggest statistically significant crowd-out: each dollar of pension wealth is associated with a 53 67 cent decline in nonpension wealth. With less precision, we use an instrumental-variable quantile regression estimator and find that most of the effect is concentrated in the upper quantiles of the wealth distribution.
Keywords: Adult children; Employment and Labor Force; Methodology; Net Worth and Assets; Pensions

Potential Enhancements to Data on Health Insurance, Health Services, and Medicare in the Health and Retirement Study - John Z. Ayanian; Meara, Ellen; J. Michael McWilliams (Forum for Health Economics and Policy, 2011)
As a nationally representative cohort of middle-aged and elderly adults with longitudinal data spanning nearly two decades, the Health and Retirement Study (HRS) is an important resource for researchers studying the dynamics of health insurance coverage in the United States and the relation of insurance coverage to the use of health services and to health outcomes. We assessed the strengths and limitations of currently available HRS data for such research, focusing on survey items in these domains and Medicare claims data that have been linked to HRS survey data. The process for researchers to obtain Medicare claims has greatly improved in recent years. The additions of biomarkers (e.g. blood pressure and serum cholesterol) and objective measures of physical functioning for HRS participants have also been notable improvements. We propose changes to the HRS to enhance its value for health services research, particularly regarding the effects of health care reform as the Patient Protection and Affordable Care Act of 2010 is implemented over the next decade.
Keywords: Health Conditions and Status; Healthcare; Medicare/Medicaid/Health Insurance; Methodology

A Rationale for Including a Brief Assessment of Hedonic Well-being in Large-scale Surveys - Arthur A. Stone (Forum for Health Economics and Policy, 2011)
Subjective well-being is comprised of both evaluative (life satisfaction) and hedonic (affect) components, and there has been a call to include both aspects of well-being in large-scale surveys. This paper presents a rationale for the feasibility of including a brief measure hedonic well-being based on the measurement of yesterday s affect and experience. It discusses issues of the distinctiveness of hedonic well-being from life satisfaction, the sensitivity of a single day s affect, the sample sizes required for detecting group differences, and the experiential content that could also be collected to extend the value of affective reports. I conclude that a brief assessment is feasible and, in conjunction with measures of evaluative well-being, could add to our understanding of well-being in populations.
Keywords: Health Conditions and Status; Methodology; Retirement Planning and Satisfaction

Results from the Health and Retirement Study Biomarker Validation Project - Eileen M. Crimmins; Jung K Kim; Heather McCreath; Teresa Seeman (Ann Arbor, The University of Michigan, 2011)
Keywords: Health Conditions and Status; Methodology

Self Assessed Health, Anchoring Vignettes, and Unobserved Heterogeneity in the Health and Retirement Study - Noroski, Paul J. (Economics, 2011)
This dissertation examines the subtleties inherent to socioeconomic models of health. The relative contributions of unobserved heterogeneity and state dependence in explaining the dynamics of health in the U.S. are controlled for as the average partial effects of socioeconomic status are estimated. In addition to these investigations, I use anchoring vignette data from the Health and Retirement Study to investigate health perceptions in the U.S. and how they affect the comparability of self assessments of health across the population. The results imply that just over 30% of the unexplained variation in self-assessed health is attributable to unobserved heterogeneity in the form of a time invariant individual effect. Although attrition bias is detected in the panel, estimates obtained using an inverse probability weighted specification reveal that attrition has virtually no effect on the estimated relationships between health and socioeconomic status. Regarding the vignette analyses, many of the characteristics that affect health status are also found to affect perceptions of health. For example, I find that respondents in lower income groups tend to be more tolerant of mental health problems than the rest of the population and that recipients of federal disability insurance may be more likely to rate a given health problem as being disabling. Upon identifying which personal characteristics influence reporting behavior, I estimate models of self-reported health that enhance comparability of survey responses across the population. I find that failing to account for reporting heterogeneity ultimately leads to a distortion of the estimated relationships between health and socioeconomic status.
Keywords: Demographics; Disabilities; Health Conditions and Status; Methodology

Social Connectedness in Health, Morbidity and Mortality, and Health Care The Contributions, Limits and Further Potential of Health and Retirement Study - Pescosolido, Bernice (Forum for Health Economics and Policy, 2011)
This part of the mid-term review of the Health and Retirement Study (HRS) provides an overall assessment of the utility of HRS data for research targeting the nature and influence of social connectedness. As one of the major dimensions of the social aspects of psychosocial influences, social connectedness is among the most complicated in terms of definition, conceptualization, and measurement. However, the century-long body of theory and findings couple with a recent resurgence of research on the critical impact of these ties for health, illness, and health care to call for an examination of the richness in and limitations of current HRS data. This assessment is comprised of three broad steps: 1) an overview of the nature of social connectedness, and of the dimensions and methodological approaches that can and have been used in studying health, health care, and aging; 2) the range, strengths and limitations of the HRS data on each approach; and 3) suggestions for potential directions to increase the utility of data collected and further research contributions from the HRS. While no tabular listing of items relevant to social connectedness is presented, the sets of items that tap this notion are referenced throughout. Overall, the HRS represents one of, if not the most impressive data sets regarding the ability to examine the influence of social connectedness on health, illness and health care. Given different theoretical and methodological traditions of social connectedness (e.g., the local or ego-centered perspective; social support perspective; social capital perspective; Pescosolido 2006a), the HRS either currently offers a way to tap into various views of social connectedness or holds the potential to do so. Specifically, the HRS includes four kinds of social connectedness data: socio-demographic proxies that represent a tie (e.g., marital status) with detailed data on the nature of the bond; social support batteries which offer respondent perceptions of the overall positive and negative aspects of sets of relationships; eco-centric tie data, which provide a list of names or roles that can provide support (i.e. latent ties); and networks of event response in which respondents list individuals who were called upon (e.g., activated ties) under certain conditions. Given the individually-based and national scope of the HRS, the collection of full or complete network data is not feasible at present. Four strategies could improve the collection and use of social connectedness data in the HRS. First, data collection sections that are explicit or implicit ego-centric name generators or activated ties lists could be expanded and refined to provide more complete data. Under the looping structure of the HRS, both the ego-centric and event response batteries can serve as a foundation for expanded network batteries. Second, given the increasing role of social media in contemporary American lives, the HRS section on the use of technology should be reviewed and expanded to tap into virtual ties. Third, locator data designed to improve follow-up of the HRS samples can form the basis of a network roster and for analyses of the dynamics of ties and its influence on health and health care. Fourth, while it is not possible to go back and recapture data about social connectedness, a sub study which targets the named social convoy over a person s life (defined only as time in the HRS) would provide invaluable data that could not be collected from any other existing study. That is, while subject to a variety of criticism (e.g., telescoping effects), the ability to collect data on extent of turnover and the reasons for shifts in social connectedness would allow an analysis of the impact of social network dynamics in later life, potentially reveal key turning points in social network support, and offer targeted points of interventions for fostering the social connectedness that has, to date, been shown (in the HRS and other studies) to be so essential to health and well-being.
Keywords: Health Conditions and Status; Methodology

The State and Future of Blood-Based Biomarkers in the Health and Retirement Study - Thomas W McDade (Forum for Health Economics and Policy, 2011)
The Health and Retirement Study (HRS) is an important national resource for policy makers and investigators across a wide range of disciplines, and it is critical that the study collects the best information possible on the health status of its participants within the constraints of the survey design, and without compromising the integrity of the sample. Potential directions for the collection and analysis of biomarker data in future waves of HRS are discussed, with a primary focus on blood-based biomarkers. Advantages and disadvantages of various methods for collecting blood in the home are considered, with particular attention given to the strengths and weaknesses of dried blood spot (DBS) sampling. DBS sampling has been widely applied in recent biosocial surveys due to the low cost and burden associated with sample collection, but these benefits need to be weighed against challenges associated with quantification in the laboratory. Attention is also given to additional biomarkers that may be of relevance to HRS, and that would expand the survey s current focus on obesity and metabolic syndrome. Measures of inflammation, pathogen exposure, reproductive function, stress, and epigenetic modifications are suggested as potentially productive future directions for the study. In addition, the analysis concludes with the following recommendations for HRS: Continue to collect DBS samples, but consider alternatives; implement enhanced procedures for quality control; calibrate DBS results against plasma values, and invest in methods development.
Keywords: Health Conditions and Status; Methodology

Subjective Health Assessments And Active Labor Market Participation Of Older Men: Evidence From A Semiparametric Binary Choice Model With Nonadditive Correlated Individual-Specific Effects - Jürgen Maurer; Roger Klein; Francis Vella (The Review of Economics and Statistics, 2011)
We use panel data from the U.S. Health and Retirement Study, 1992-2002, to estimate the effect of self-assessed health limitations on the active labor market participation of older men. Self-assessments of health are likely to be endogenous to labor supply due to justification bias and individual-specific heterogeneity in subjective evaluations. We address both concerns. We propose a semiparametric binary choice procedure that incorporates nonadditive correlated individual-specific effects. Our estimation strategy identifies and estimates the average partial effects of health and functioning on labor market participation. The results indicate that poor health plays a major role in labor market exit decisions. PUBLICATION ABSTRACT
Keywords: Demographics; Employment and Labor Force; Health Conditions and Status; Methodology; Other

Temporary and Permanent Unit Non-Response in Follow-up Interviews of the Health and Retirement Study - Pierre-Carl Michaud; Arie Kapteyn; James P Smith; Arthur H.O. vanSoest (Longitudinal and Life Course Studies, 2011)
Keywords: Methodology

Time Use and Well-being, and Large Survey Studies - Dylan M Smith (Forum for Health Economics and Policy, 2011)
This paper reviews several methods for measuring how people spend their time, and how they feel during these different activities, and argues that some of these methods could be well suited for large scale longitudinal surveys. Because time use methods allow for the quantitative assessment of the dynamics of human experience, they provide opportunities to explore numerous research questions that cannot be readily answered with more traditional summary measures of well-being. In the last decade or two, techniques have become available that can capture the dynamics of time use and well-being in ways that also reduce methodological problems such as biased recall. The paper describes several such methods, with a discussion of how they are implemented, and a comparison of their relative strengths and weaknesses. In the final section, the paper describes how the addition of time use measures can enhance national surveys such as the Health and Retirement Study by a) opening new avenues of research, and b) clarifying previous findings from more traditional measures of well being.
Keywords: Methodology; Time Use

Updates to HRS Sample Weights - Mary Beth Ofstedal; David R Weir; Chen, K.T.; James Wagner (Institute for Social Research, University of Michigan, 2011)
Keywords: Methodology

What Explains Changes in Retirement Plans during the Great Recession? - Gopi Shah Goda; John B. Shoven; Sita Nataraj Slavov (The American Economic Review, 2011)
We examine changes in subjective probabilities regarding retirement between the 2006 and 2008 waves of the Health and Retirement Study. Using a first-difference approach to eliminate individual heterogeneity, we find that the steep drop in asset prices in 2008 increased the reported probability of working at age 62 during the Great Recession. Increasing unemployment at least partly attenuated this effect, but subjective probabilities of working did not respond to changes in housing markets. Older workers' probabilities of working were more sensitive to fluctuations in the stock market, but less responsive to changes in labor market conditions.
Keywords: Employment and Labor Force; Housing; Methodology; Public Policy; Retirement Planning and Satisfaction

Which Questions in the Health and Retirement Study are Used by Researchers? Evidence from Academic Journals, 2006-2009 - Jackson, Tina; Balduf, Mabel; Laura Yasaitis; Jonathan S Skinner (Forum for Health Economics and Policy, 2011)
Since 2002, the average number of questions asked per respondent in the Health and Retirement Study (HRS) has risen by 39 percent, from 413 to 581. Yet there is little or no understanding of which questions, or how many in total, should be included and more importantly, maintained in longitudinal surveys. In this paper, we propose a simple approach to assessing the value of survey questions: journal citation counts. A sample of journal articles and book chapters published in 2006-09 (N = 206) is used to document which questions, and categories of questions, were used most and least frequently. A disproportionate number of published articles used a relatively small number of questions regarding health, wealth, income, and employment. By contrast, several categories of questions were rarely used, and many specific questions were never used. This evidence-based approach to measuring the value of survey questions can have applications for other surveys beyond the HRS.
Keywords: Methodology

Accessibility of the residential environment: Its influence on the depressive symptoms of older adults - Guzzardo, Mariana T. (University of Connecticut, 2010)
As people age, a supportive and accessible environment becomes more salient in the face of declining functional capacity. Whereas past research supports a relationship between residential environment and well-being, few studies have focused on the specific relationship between the accessibility of the home and mental health. The purpose of the present study is to examine the influence of barrier-free/accessible features in the home on elderly individuals' depressive symptoms, when they experience difficulty with activities of daily living. The barrier-free/accessible features that are investigated include: ramps, railings, wheelchair modifications, grab bars, shower seats and call devices. This study uses data products distributed by the RAND Corporation, based on the 2006 wave of the Health and Retirement Study. The analytic procedures are divided into three parts. In the first place, descriptive analyses were conducted, including independent sample t -tests. These analyses served the purpose of examining differences between key groups within the sample (ethnic group comparisons, and comparisons between senior housing residents and non-senior housing residents). In the second place, hierarchical multiple regression analyses were conducted to examine the features of the home as predictors of depressive symptoms, after controlling for difficulty with ADLs, and various socio-demographic variables. In the third place, the main purpose of the present study was to test the influence of the residential environment on depressive symptoms through a structural regression (SR) model, using Structural Equation Modeling. The model contains functional impairment as a mediator, while age, income, education, gender, and living arrangement function as exogenous variables. Overall, results provide support for the hypothesized model. Findings suggest that accessible dimensions of the physical environment can contribute to psychological well-being by playing a compensatory or assistive role and meeting the individuals' functional needs.
Keywords: Consumption and Savings; Demographics; Health Conditions and Status; Healthcare; Methodology; Retirement Planning and Satisfaction

Are International Differences in Health Similar to International Differences in Life-Expectancy? - Eileen M. Crimmins; Krista Garcia; Jung K Kim (International Differences in Mortality at Older Ages: Dimensions and Sources, 2010)
The question addressed in this chapter is whether people in countries with relatively low life expectancy after age 50 have worse health than those in countries with longer life expectancy. We begin with a short discussion of the theoretical relationships between mortality and population health and the potential complexity of the link between measures of health and mortality. We then examine how indicators of health vary across countries and how closely differences in a set of health indicators correspond to differences in mortality across 10 countries. We note at the outset that most of the data we examine reflect analysis of cross-sectional differences in health; without comparable longitudinal data, there is little we can say about how the differences arose. The countries compared include Australia, Canada, Denmark, England, France, Italy, Japan, the Netherlands, Spain, and the United States.
Keywords: ELSA; Methodology; SHARE

Attrition and health in ageing studies: Evidence from ELSA and HRS - James Banks; Muriel, Alistair; James P Smith (RAND Working Paper, 2010)
In this paper we present results of an investigation into observable characteristics associated with attrition in ELSA and the HRS, with a particular focus on whether attrition is systematically related to health outcomes and socioeconomic status (SES). Investigating the links between health and SES is one of the primary goals of the ELSA and HRS, so attrition correlated with these outcomes is a critical concern. We explored some possible reasons for these differences. Survey maturity, mobility, respondent burden, interviewer quality, and differing sampling methods all fail to account for the gap. Differential respondent incentives may play some role, but the impact of respondent incentive is difficult to test. Apparently, cultural differences between the US and Europe population in agreeing to participate and remain in scientific surveys are a more likely explanation.
Keywords: Cross-National; Demographics; Healthcare; Methodology

Choices and consequences: Decisions on health, wealth, and employment - Levin, Victoria (Harvard University, 2010)
This collection of essays investigates the determinants of individual decisions pertaining to health, wealth, and employment, as well as the effects of these choices on welfare. The first essay examines the decision to take up prescription drug insurance in the context of the 2004/5 Russian benefit monetization reform. This essay uses a new set of questions included in a nationally-representative household survey to investigate the determinants of take-up and to explore its effects on beneficiaries' health outcomes and healthcare utilization. Regression analysis reveals that healthier people were less likely to choose the prescription drug insurance, which resulted in significant adverse selection. Propensity score and matching techniques suggest no significant declines in health for those opting out of the prescription drug insurance, and no evidence is found for substitution towards hospital care. The second essay focuses on the decision to prepare for one's demise by writing a will. This paper explores the relationship between will-holding and "death denial," or the inability to confront one's mortality. I propose the first operationalization of "death denial" in economic literature as the subjective self-assessment of 100% chance of survival to a target age, based on the questions in the Health and Retirement Study. Probit regressions reveal that death deniers are about 4-6% less likely to be will-holders. This finding supports the claim of psychological costs involved in estate planning, and could partly account for the observed underutilization of other intergenerational wealth transfers. The third essay considers the choice of search methods in the job search of postdoctoral scholars, and how this decision affects satisfaction, productivity, and turnover through the quality of the match between scholar and position. Using data on U.S. postdoctoral scholars from the Sigma Xi Scientific Research Society, we find suggestive evidence of weaker networks for foreign postdoctoral scholars, who more often resort to "impersonal" searches. The resulting difference in job match quality is related to differences in turnover, satisfaction, and productivity. We expect policies facilitating the job placement of foreign scholars to yield beneficial effects on the pace of innovation.
Keywords: Adult children; Employment and Labor Force; End of life decisions; Methodology; Other; Public Policy

Considering the impact of U.S. social policy retirement benefits on later life labor force participation - Ben Lennox Kail (The Florida State University, 2010)
As a life stage, retirement emerged out of the industrial revolution and the passage of the Social Security Act of 1935. Since the 1960s, however, several macrostructural changes have resulted in a much more varied landscape of later life labor force behavior. The research presented here extends the work of previous scholars on non-traditional paths to full labor force exit. Using data from the first eight waves of the Health and Retirement Study, the current research focuses on the role of retirement benefits from welfare policy and tax subsidized private retirement plans on transitions between labor force statuses in later life, using multinomial logistic regression in an Hierarchical Linear Modeling framework. Drawing on the hidden welfare state- and life course - perspectives yields several important findings. First, this study finds that welfare benefits allow individuals to reduce their work participation and fully exit the labor force, as well as to reduce the risk that they subsequently reverse their retirement. Because these benefits are nearly universal, they help decouple virtually all age eligible participants from work. Second, private benefits also help individuals to reduce their work, exit the labor force, and remain retired. However, because these benefits are limited to a select population they convey additional advantages to those beneficiaries. Third, the aforementioned macrostructural changes occur at different points within individuals' life courses and the results presented here suggest that this produces different patterns of labor force transitions across birth cohorts. Finally, using piecewise linear growth models, this study finds that, in addition to the actual welfare benefits individuals receive, becoming age eligible for public benefits also impacts later life labor force transitions. However, this influence is most noticeable among those who transition out of full time work, suggesting that public benefits are designed around a now parachronistic model of the life course.
Keywords: Demographics; Employment and Labor Force; Event History/Life Cycle; Methodology; Public Policy; Retirement Planning and Satisfaction

Do Older Adults Anticipate Relocating?: The Relationship Between Housing Relocation Expectations and Falls - Stoeckel, Kimberly J.; Frank Porell (The Journal of Applied Gerontology, 2010)
The relationship between the occurrence of falls and the expectations older adults have about making future residential moves is examined in this research. Data from the 2002 Health and Retirement Study (HRS) are used to analyze self-reported probabilities of moving among a nationally representative sample of noninstitutionalized adults aged 65 and older. The results show that falls were predictive of anticipation of housing relocation as indicated by more than 50 reported probability of moving within the next 2 years. The results suggest that consideration of housing relocation is greater among older adults who experience tangible events indicative of a trajectory of deteriorating health. Reprinted by permission of Sage Publications Inc., copyright The Southern Gerontological Society.
Keywords: Demographics; Health Conditions and Status; Housing; Methodology; Retirement Planning and Satisfaction

The effects of childbearing patterns on the timing of retirement - Chung, Hsiao-Yin (Gerontology, 2010)
The effects of childbearing patterns on the timing of men's and women's retirement were examined. The data for this study come from the Health and Retirement Study, waves 1-7: 1992, 1994, 1996, 1998, 2000, 2002, and 2004. A proportional hazard model (Cox regression) was chosen for this study. Two measures of retirement were considered: labor force exit and self-defined retirement. The results indicated that men with dependent children are more likely to postpone the timing of labor force exit and their self-definition as retired. At the same time, the study indicated that the presence (or absence) and timing of early childbearing experience has a long-term effect on the timing of retirement in later life. In particular, for both men and women, childbearing factors associated with a greater family burden in early life (e.g., parenthood and early childbearing) are related to a later labor force exit. The number of children, however, only affects the timing of women's labor force exit.
Keywords: Adult children; Employment and Labor Force; Methodology; Retirement Planning and Satisfaction

Effects of Immigration and Age on Health of Older People in the United States - Chizuko Wakabayashi (Journal of Applied Gerontology, 2010)
Following cumulative advantage/disadvantage theory and drawing longitudinal data from the 1996, 1998, 2000, 2002, 2004, and 2006 Health and Retirement Studies, this article examined the relationship between immigration experience and health transitions in late life among non-Hispanic White, non-Hispanic Black, and Mexicans in the United States. The results revealed that the timing of migration in the life course helped determine the ways in which individual health transitions would be associated with their aging process, and the pathways would be complex and vary based on the health outcomes and gender of the immigrants. For example, among women, the later-life immigrants would face most disadvantageous health trajectories as they aged with respect to activities of daily living limitations. The results suggested that the timing of U.S. immigration would affect the degree to which immigrants could take advantage of economic opportunities to accumulate financial resources that would benefit health later in life.
Keywords: Demographics; Health Conditions and Status; Healthcare; Methodology

Essays on Selection in Health Survey Data - Maksym Obrizan (Economics, 2010)
In this paper I consider the effects of sample selection in a study of stroke occurrence among Medicare-eligible Americans using the survey on Assets and HEAlth Dynamics among the Oldest Old (AHEAD). First of all, I apply the propensity score method based on the assumption of data missing at random and find no substantial effects of the sample selectivity, similar to Wolinsky et al. (2009). Then I employ a weaker assumption of incidental truncation and extend the Heckman's (1979) sample selection model to the case of a discrete outcome variable (whether a stroke occurred after the baseline). This constitutes the main methodological contribution of the current paper, with potential applications in health, labor and applied economics, where the outcome variable is discrete and selection takes place along multiple dimensions. The sample selection model with binary outcome(s) extends the multivariate probit setup in Chib and Greenberg (1998) to allow some of the responses to be missing. I also use Cholesky factorization of the variance matrix to simplify the Gibbs algorithm in Chib and Greenberg (1998). I do not find strong selection effects driven by the data in my application to the stroke equation. The main substantive contribution of the paper is that there is no evidence of selection in the AHEAD data based on either propensity score or sample selection model. Government shares in total output are characterized by significant variation across countries. In this paper I use a neoclassical growth model to show that in equilibrium government shares decline non-linearly in the price of government services relative to private consumption. I calibrate the model to the US economy and show that it generates government shares which closely match those from the Penn World Table. In addition, I provide empirical evidence showing that relative price of government consumption increases in income and that richer countries tend to have smaller governments if measured at international prices. The systematic relationships between factor productivities, output composition and economic development have not been explored in the literature.
Keywords: Employment and Labor Force; Health Conditions and Status; Healthcare; Income; Methodology; Other

Estimating Dynamic Discrete Choice Models with Hyperbolic Discounting, with an Application to Mammography Decisions - Fang, Hanming; Wang, Yang (NBER Working Paper, 2010)
We extend the semi-parametric estimation method for dynamic discrete choice models using Hotz and Miller's (1993) conditional choice probability (CCP) approach to the setting where individuals may have hyperbolic discounting time preferences and may be naive about their time inconsistency. We illustrate the proposed estimation method with an empirical application of adult women's decisions to undertake mammography to evaluate the importance of present bias and naivety in the under-utilization of this preventive health care. Our results show evidence for both present bias and naivety.
Keywords: Health Conditions and Status; Methodology

Estimating willingness to pay for medicare using a dynamic life-cycle model of demand for health insurance - Ahmed Khwaja (Journal of Econometrics, 2010)
Medicare is the largest health insurance program in the US. This paper uses a dynamic random utility model of demand for health insurance in a life-cycle human capital framework with endogenous production of health to calculate the individual willingness to pay (WTP) for Medicare. The model accounts for the feature that the demand for health insurance is derived through the demand for health, which is jointly determined with the production of health over the life-cycle. The WTP measure incorporates the effects of Medicare insurance on aggregate consumption through effects on medical expenditures and mortality, and consumption utility of health. The model is estimated using panel data from the Health and Retirement Study. The average WTP or change in lifetime expected utility resulting from delaying the age of eligibility to 67 is found to be 24,947 in 1991 dollars ( 39,435 in 2008 dollars). However, there is considerable variation in the WTP, e.g., in 1991 dollars the WTP of individuals who have less than a high school education and are white is 28,347 ( 44,810 in 2008 dollars), while the WTP of those with at least a college degree and who are neither white nor black is 15,584 ( 24,635 in 2008 dollars). More generally, the less educated have a higher WTP to avoid a policy change that delays availability of Medicare benefits. Additional model simulations imply that the primary benefits of Medicare are insurance against medical expenditures with relatively smaller benefits in terms of improved health status and longevity. Medicare also leads to large increases in medical utilization due to deferring of medical care prior to eligibility.
Keywords: Medicare/Medicaid/Health Insurance; Methodology; Net Worth and Assets; Other; Public Policy

Health and Access Effects of New Drugs: Combining Experimental and Non-Experimental Data - Pierre-Carl Michaud; Darius Lakdawalla; Dana P Goldman; Sood, Neeraj; Cong, Ze (2010)
We propose to combine clinical trial and estimates of behavioral responses in the population to quantify the value of new drug innovations when such values cannot be obtained by randomized experiments alone. New drugs are seen as having two distinct effects on patients. First, they can provide better outcomes for patients currently under treatment, due to better clinical efficacy. Second, they can also provide treatment access to more patients, perhaps by reducing side effects or expanding treatment. We compare these clinical and access effects using claims data, data on the arrival rate of new drugs, and the clinical trials literature on the effectiveness of these drugs. We find that the effect of new drug introductions on the number of patients treated accounts for a substantial majority of the value created by new drugs.
Keywords: Health Conditions and Status; Healthcare; Methodology; Other

Individuals' Uncertainty about Future Social Security Benefits and Portfolio Choice - Delavande, Adeline; Susann Rohwedder (Santa Monica, RAND Corporation Publications Department Working Papers, 2010)
Little is known about the degree to which individuals are uncertain about their future Social Security benefits, how this varies within the U.S. population, and whether this uncertainty influences financial decisions related to retirement planning. To illuminate these issues, the authors present empirical evidence from the Health and Retirement Study Internet Survey and document systematic variation in respondents' uncertainty about their future Social Security benefits by individual characteristics. They find that respondents with higher levels of uncertainty about future benefits hold a smaller share of their wealth in stocks.
Keywords: Consumption and Savings; End of life decisions; Expectations; Income; Methodology; Net Worth and Assets

Inference of Signs of Interaction Effects in Simultaneous Games with Incomplete Information, Second Version - Áureo de Paula; Tang, Xun (Penn Institute for Economic Research Working Paper, 2010)
This paper studies the inference of interaction effects, i.e., the impacts of players' actions on each other's payoffs, in discrete simultaneous games with incomplete information. We propose an easily implementable test for the signs of state-dependent interaction effects that does not require parametric specifications of players' payoffs, the distributions of their private signals or the equilibrium selection mechanism. The test relies on the commonly invoked assumption that players' private signals are independent conditional on observed states. The procedure is valid in the presence of multiple equilibria, and, as a by-product of our approach, we propose a formal test for multiple equilibria in the data-generating process. We provide Monte Carlo evidence of the test's good performance infinite samples. We also implement the test to infer the direction of interaction effects in couples' joint retirement decisions using data from the Health and Retirement Study.
Keywords: Methodology; Other; Retirement Planning and Satisfaction

A life-cycle analysis of retirement savings and portfolio choices: Optimal asset allocation and location with taxable and tax-deferred investment - Li, Zhe (Economics, 2010)
In this study, I analyze theoretically and empirically the optimal saving and investment decisions of the households in Defined Contribution (DC) pension accounts, and show that the pension characteristics play important roles in explaining the households' behavior. The first essay attempts to explain the observed asset allocation and location decisions for households making taxable and tax-deferred investment. I incorporate employer matching policies and other pension account characteristics into a life-cycle model of optimal intertemporal consumption and portfolio choice, which includes a taxable saving account and a tax-deferred retirement saving account. The model is estimated using data from the Surveys of Consumer Finances (1992 to 2007), and the structural parameters are recovered by the Method of Simulated Moments. After modeling the features of U.S. pension system, the predicted policy rules are able to explain the observed portfolio patterns of American households, who are more likely to hold equities in the tax-deferred pension account. The estimates and results show that employer matching policy induces higher proportion of total wealth held in the pension account, so investors tend to reduce equity holdings in the taxable account for precautionary saving purpose and boost equity investments in the tax-deferred account to maintain an optimal portfolio mix. I find that a 10 percentage point increase in the estimated employer matching rate makes investors reduce the average equity proportion in the taxable account by 22 percentage point and boost those holdings in the pension account by 10 percentage point. In contrast, since the employer stock match exposes the households to a riskier situation in the pension account than the cash match, it causes households voluntarily to hold less equity in that account, resulting in an average decrease of 4 percentage point in the equity ownership and 3 percentage point in the conditional equity proportion. Moreover, the policy experiment reveals that a deletion of Social Security taxes and payments makes the pension account the only source of retirement income, so households tend to put a higher proportion of savings in the tax-deferred account, and they are likely to invest conservatively and hold about 25 percent more of pension wealth in relatively safe assets. The second essay is about company stock investment in 401(k) plans. Previous studies on the determinants of company stock holdings focus on the past stock market performance of company stock, but ignore the characteristics of the retirement plans and individuals. In this study, using the data from Survey of Consumer Finances (SCF), I provide an empirical analysis of the factors that affect company stock holdings in 401(k) plans, by analyzing a broad list of company features, individual characteristics, and financial wealth information. My preferred estimates suggest that, different from general stocks which are sensitive to risk preference and total wealth, the decision of whether to hold company stock is more likely to be affected by the employer's characteristics and the availability of other investment opportunities. Individuals who work in larger companies and receive more employer matches in the retirement account are more likely to hold company stock in the retirement account, and they are less likely to hold company stocks when the wealth outside the pension account is large and they have other retirement accounts. In addition, I find that the company stock share in 401(k) account is decreasing with pension wealth and total net wealth, which indicates that less wealthy individuals are those who are more exposed to company stock risk. The third essay analyzes the impact of investment choice on savings in defined contribution pensions. The striking growth defined contribution (DC) pensions have vastly expanded the number of individuals with some discretion regarding their retirement savings. One of the factors that may affect saving decisions is investment choice: namely the ability of the participant to direct the investment of the assets in the pension account. In most studies, people who report that they have control over assets allocation in pension plans do not distinguish the assets between the participant contribution and the employer contribution, but it is common for the employer's contribution to be constrained-often to company stock. In this study, I use the Health and Retirement Study (HRS) to estimate the impacts of unconstrained and constrained investment choices on participant saving levels in DC Pensions. The estimates and results indicate that participants with investment choice contribute over 3 percentage points more of their earnings into the defined contribution plan than people without choice, and people constrained in their investment contribute about 3 percentage points less in their retirement saving account. In addition, I find that male and lower income participants tend to contribute more in a self-directed saving account.
Keywords: Consumption and Savings; Event History/Life Cycle; Methodology; Net Worth and Assets; Pensions; Retirement Planning and Satisfaction

Overview of HRS Public Data Files for Cross-sectional and Longitudinal Analysis - Servais, Marita (Institute for Social Research, University of Michigan, 2010)
This document provides an overview of HRS data products available to the public.
Keywords: Methodology

Prediction of disease status: A regressive model approach for repeated measures - M. Ataharul Islam; Rafiqul I Chowdhury (Statistical Methodology, 2010)
In this paper, regressive models are proposed for modeling a sequence of transitions in longitudinal data. These models are employed to predict the future status of the outcome variable of the individuals on the basis of their underlying background characteristics or risk factors. The estimation of parameters and also estimates of conditional and unconditional probabilities are shown for repeated measures. The goodness of fit tests are extended in this paper on the basis of the deviance and the Hosmer-Lemeshow procedures and generalized to repeated measures. In addition, to measure the suitability of the proposed models for predicting the disease status, we have extended the ROC curve approach to repeated measures. The procedure is shown for the conditional models for any order as well as for the unconditional model, to predict the outcome at the end of the study. The test procedures are also suggested. For testing the differences between areas under the ROC curves in subsequent follow-ups, two different test procedures are employed, one of which is based on permutation test. In this paper, an unconditional model is proposed on the basis of conditional models for the disease progression of depression among the elderly population in the USA on the basis of the Health and Retirement Survey data collected longitudinally. The illustration shows that the disease progression observed conditionally can be employed to predict the outcome and the role of selected variables and the previous outcomes can be utilized for predictive purposes. The results show that the percentage of correct predictions of a disease is quite high and the measures of sensitivity and specificity are also reasonably impressive. The extended measures of area under the ROC curve show that the models provide a reasonably good fit in terms of predicting the disease status during a long period of time. This procedure will have extensive applications in the field of longitudinal data analysis where the objective is to obtain estimates of unconditional probabilities on the basis of series of conditional transitional models.
Keywords: Health Conditions and Status; Methodology; Other; Risk Taking

A Quantile Estimation Approach to Identify Income and Age Variation in the Value of a Statistical Life - Mary F. Evans; Schaur, Georg (Journal of Environmental Economics and Management, 2010)
In theory, heterogeneity in individual characteristics translates into variation in the marginal willingness to pay for a mortality risk reduction. Two dimensions of heterogeneity, with respect to income and age, have recently received attention due to their policy relevance. We propose a quantile regression approach to simultaneously explore these two sources of heterogeneity and their interactions within the context of the hedonic wage model, the most common revealed preference approach for obtaining value of statistical life estimates. We illustrate the approach using data from the Health and Retirement Study (HRS). We find that the impact of age on the wage-risk tradeoff varies across the wage distribution. This result indicates important interactions between age and income heterogeneity. Thus, the conventional mean hedonic wage regression, even when the mean effect is allowed to vary with age, masks important heterogeneity.
Keywords: Health Conditions and Status; Income; Methodology

SSI eligibility and participation among the aged: A hazard model approach - Jin H. Kim (The University of Wisconsin - Madison, 2010)
This dissertation revisits the historic policy concern over nonparticipation in the Supplemental Security Income (SSI) program, and more specifically, the question of why take- up of SSI program benefits among the aged is perpetually lower than what theory proposes. The most contemporary research model suggests that from a static or cross-sectional perspective, the aged take-up decision is primarily determined by the financial situation of the eligible individuals (McGarry, 1995). Yet, extant studies have yet to establish a dynamic model of SSI participation that explicitly takes into account the changing circumstances of the elderly. For many elders, the period after age 65 is a time of rapid and considerable changes in the areas of income, health and functioning, as well as living situations. As such, this study extends the current literature by exploring the longitudinal processes leading to both SSI eligibility and eventual take-up of benefits among the aged. Methodologically, the research relies on event history analysis of data from the Health and Retirement Study spanning the years 1996-2006 to explain both the timing of transition to eligibility and participation status, as well as the role of life events on the aforementioned outcomes of interest. Life table analysis yields a cumulative, twelve-year take-up rate of ∼36% among those eligible, and a cumulative, twelve-year eligibility rate of ∼25% among those at risk. Meanwhile, hazard models reveal that changes in health and functioning over time in addition to changes in the expected benefit significantly influence the participation decision.
Keywords: Demographics; Expectations; Methodology; Other; Social Security

Three essays on cost, value, and consequences of health insurance - Keziah Cook (Economics, 2010)
In these three essays, I explore interactions between health insurance and other financial outcomes. Chapter 1 develops as model of cash wages and worker value of employer-sponsored health insurance (ESI), expanding standard economic models of compensating differentials by predicting that offsets in cash wages will differ among individuals. I examine new Medicare-eligibility of a worker's spouse--which lowers the value of ESI by improving the worker's non-employment insurance option--as a sudden change in worker value. Using a regression discontinuity approach in a sample of near elderly, full-time workers, I find that spousal Medicare eligibility leads to a raise of at least 6% if the spouse's only source of private insurance is through the worker's employer. Chapter 2 examines the financial consequences of illness for uninsured Americans using the Health and Retirement Study. We use triple difference median regressions on a sample of newly-ill/uninsured near elderly households matched to newly-ill/insured households to measure changes in non-housing assets. We also include a matched control group of households whose members are not ill. Controlling for the effects of insurance status and illness, we find that the median household with a newly-ill, uninsured individual suffers a statistically significant decline in household assets of between 30 and 50% relative to households with matched insured individuals. Newly-ill, insured individuals do not experience a decline in wealth. Chapter 3 shows predicted future availability of ESI affects the value of non-group health insurance and is a significant factor in the initial non-group purchase decision. I find individuals with a low probability of future ESI are more likely to purchase non-group insurance than similar individuals with a high probability of future ESI. Additionally, I interact state non-group insurance regulations with predicted future ESI and find that community rating in the non-group market increases the likelihood that workers with a low predicted probability of future ESI will purchase non-group insurance compared to workers with a higher predicted probability of future ESI.
Keywords: Insurance; Medicare/Medicaid/Health Insurance; Methodology; Other; Public Policy

Three essays on the economic decisions faced by elderly households - Wei Sun (Economics, 2010)
This dissertation contains three essays. Each considers an economic decision faced by elderly households. The cost of nursing home care represents a substantial financial risk for older households. Yet, only 10 percent purchase long-term care insurance (LTCI), with many relying on Medicaid. The first essay estimates a structural model of the LTCI purchase decision using Health and Retirement Study data. Estimates indicate that this population has a modest preference for higher quality care and thus Medicaid crowds out LTCI. In addition, housing wealth provides self-insurance against the cost of nursing home care, so that individuals who are "house-rich cash-poor" are less likely to purchase LTCI. I also evaluate public policies designed to stimulate the take-up of LTCI and reduce Medicaid spending. I find that a comprehensive 20 percent subsidy would increase take-up by 160 percent, but the resulting Medicaid savings would amount to only 22 percent of the subsidy cost. A targeted subsidy would be more likely to break even, but would have only a small effect on coverage. Full enforcement of Medicaid estate recovery programs would reduce Medicaid expenditure by 31 percent, but would have insignificant effect on LTCI coverage. The second essay investigates the impact of house prices fluctuations on the non-durable goods consumption decision of older households. House prices in the United States fluctuate over time with significant regional variation. Thus, understanding how these price movements affect households' consumption has important policy implications. Existing studies focus mostly on the working population, leaving the effect of older households, who could be either the largest beneficiaries or victims of house price fluctuations, unexamined. Using Health and Retirement Study data, I show that house price fluctuations significantly affect non-durable goods consumption of older households. Estimates indicate that both the wealth effect and a relaxed borrowing constraint increase consumption when house prices appreciate. In addition, I find that only unexpected changes in house prices lead to changes in consumption of non-credit constrained households, which is consistent with economic theory predictions. Finally, I provide evidence that older households usually fund the additional consumption by increasing mortgage debt, rather than by drawing down financial assets. The third essay evaluates the value of the additional longevity insurance acquired by delaying claiming social security benefit. Individuals can claim Social Security at any age from 62 to 70, although most claim at 62 or soon thereafter. Those who delay claiming receive increases that are approximately actuarially fair. I show that expected present value calculations substantially understate both the optimal claim age and the losses resulting from early claiming because they ignore the value of the additional longevity insurance acquired as a result of delay. Using numerical optimization techniques, I illustrate that for plausible preference parameters, the optimal age for non-liquidity constrained single individuals and married men to claim benefit is between 67 and 70. I calculate that Social Security Equivalent Income, the amount by which benefits payable at suboptimal ages must be increased so that a household is indifferent between claiming at those ages and the optimal combination of ages, can be as high as 19 percent.
Keywords: Healthcare; Methodology

Using generalized estimating equations to analyze alcohol consumption and job displacement among older workers - Patel, Nita (Biostatistics, 2010)
The objectives of this dissertation were to compare differences in alcohol consumption among the older workers (aged 51 to 61 years) who have experienced job displacement compared to those who remain continuously employed. Generalized estimating equations were used to model this relationship using longitudinal data from the Health and Retirement Study from 1992 to 2006. Approximately 39% of respondents had died during the study period. We analyzed four models. One model excluded data for deceased respondents. Another model retained data for deceased respondents. For the remaining two models, data was imputed using multiple imputation by chained equations. Data was imputed for only the predictors in one imputation, imputed for both the dependent variable and the predictors in the second imputation. All models were weighted and adjusted for key sociodemographic variables. The results of this study show that being continuously employed, compared to experiencing job displacement, has a protective effect on the onset of alcohol consumption. Older workers who were not displaced were less likely to report consuming alcohol compared to those who had been displaced. This finding remained statistical significant even after adjusting for key sociodemographic variables. Complete case analysis and observed sample models provided biased estimates (i.e. wider confidence intervals, smaller p values) compared to the two multiple imputation models. Our findings have important public health implications. Older workers are likely to have varied participation in the labor market. They are likely to be more experienced and hold senior or management positions, thereby earning higher wages. They may be at a higher risk of layoff during uncertain economic times, such as a recession. The effects of alcohol consumption among older individuals have been shown to be negative and particularly harmful, especially in terms of ethanol toxicity. Additional studies are needed to examine the health effects of late onset of drinking among older Americans.
Keywords: Employment and Labor Force; Health Conditions and Status; Methodology

Using Matched Survey and Administrative Data to Estimate Eligibility for the Medicare Part D Low-Income Subsidy Program - Erik Meijer; Lynn A Karoly; Pierre-Carl Michaud (Social Security Bulletin, 2010)
This article uses matched survey and administrative data to estimate, as of 2006, the size of the population eligible for the Low-Income Subsidy (LIS), which was designed to provide extra help with premiums, deductibles, and copayments for Medicare Part D beneficiaries with low income and limited assets. We employ individual-level data from the Survey of Income and Program Participation and the Health and Retirement Study to cover the potentially LIS-eligible noninstitutionalized and institutionalized populations of all ages. The survey data are matched to Social Security administrative data to improve on potentially error-ridden survey measures of income and program participation. Our baseline estimate, based on the matched data, is that about 12 million individuals were potentially eligible for the LIS as of 2006. A sensitivity analysis indicates that the use of administrative data has a relatively small effect on the estimates, but does suggest that measurement error is important to account for.
Keywords: Demographics; Income; Medicare/Medicaid/Health Insurance; Methodology; Public Policy

Using Matched Survey and Administrative Data to Estimate Eligibility for the Medicare Part D Low Income Subsidy Program - Erik Meijer; Lynn A Karoly; Pierre-Carl Michaud (RAND Working Paper, 2010)
The 2003 Medicare Prescription Drug Improvement and Modernization Act added a new prescription drug benefit to the Medicare program known as Part D (prescription drug coverage), as well as the Low-Income Subsidy (LIS) program to provide extra help with premiums, deductibles, and copayments for Medicare Part D beneficiaries with low income and limited assets. In this paper, the authors report on the use of matched survey and administrative data to estimate the size of the LIS-eligible population as of 2006. In particular, they employ individual-level data from the Survey of Income and Program Participation (SIPP) and the Health and Retirement Study (HRS) to cover the potentially LIS-eligible noninstitutionalized and institutionalized populations of all ages. The survey data are matched to Social Security Administration (SSA) administrative data to improve on potentially error-ridden survey measures of income components (e.g., earnings and beneficiary payments from Supplemental Security Income and Old Age, Survivors, and Disability Insurance) and program participation (e.g., participation in Medicare or a Medicaid/Medicare Savings program). The administrative data include the Master Beneficiary Record/Payment History Update System, the Master Earnings File, and the Supplemental Security Record. The survey data are the source of information on asset components, as well as the income components (e.g., private pensions) and individual characteristics (e.g., health status) not covered in the administrative data. Their baseline estimate, based on the matched data, is that about 12 million individuals were potentially eligible for the LIS as of 2006. A sensitivity analysis indicates that the use of administrative data has a relatively small effect on the estimates but does suggest that measurement error is important to account for. The estimate of the size of the LIS-eligible population is more sensitive to the relative weight they place on the two survey data sources, rather than the choice of methods we apply to either data source.
Keywords: Healthcare; Medicare/Medicaid/Health Insurance; Methodology

Validating Diabetes Disease Status in Claims and Survey Data. Proceedings of the 2010 International Methodology Symposium: The Interplay among Censuses, Surveys and Administrative Data - Joseph W Sakshaug; David R Weir; Lauren Hersch Nicholas (Ottawa, 2010)
Keywords: Health Conditions and Status; Methodology

The Wage Process of Older Workers - Maria Casanova (UCLA, 2010)
Because most studies of wage profiles and wage dynamics focus on individuals in their prime working years, little is known about the wage processes of workers approaching retirement. Do wages of older workers decline with age? Do older workers face more or less wage risk than their younger counterparts? This paper answers both questions using information on wages of older men and women from the Health and Retirement Study. First, we show that there is no statistical support for a decline of wages with age. The decreasing wage-age profile observed in cross-sectional data is a result of both compositional effects and negative selection. We show that there is considerable heterogeneity in the relative importance of these two motives across gender, education groups, and pension types. Second, we find that the degree of wage risk is lower for older male workers than for younger ones. For older female workers, the degree of wage risk is lower than it is for men. We do not know of any study of wage risk for younger women to compare to our results. From a methodological perspective, we show the importance of controlling for selection into retirement based on unobservable worker characteristics in order to obtain consistent estimates of wage processes of older workers.
Keywords: Employment and Labor Force; Methodology

Why Do Life Insurance Policyholders Lapse? The Roles of Income, Health and Bequest Motive Shocks - Fang, Hanming; Kung, Edward (New Haven, Yale University, 2010)
We present an empirical dynamic discrete choice model of life insurance decisions designed to bypass data limitations where researchers only observe whether an individual has made a new life insurance decision but but do not observe the actual policy choice or the choice set from which the policy is selected. The model also incorporates serially correlated unobservable state variables, for which we provide ample evidence that they are required to explain some key features in the data. We empirically implement the model using the limited life insurance holding information from the Health and Retirement Study (HRS) data. We deal with serially correlated unobserved state variables using posterior distributions of the unobservables simulated from Sequential Monte Carlo (SMC) methods. Counterfactual simulations using the estimates of our model suggest that a large fraction of life insurance lapsations are driven by i.i.d choice specific shocks, particularly when policyholders are relatively young. But as the remaining policyholders get older, the role of such i.i.d. shocks gets less important, and more of their lapsations are driven either by income, health or bequest motive shocks. Income and health shocks are relatively more important than bequest motive shocks in explaining lapsations when policyholders are young, but as they age, the bequest motive shocks play a more important role.
Keywords: Insurance; Methodology

Adaptive Testing of the Number Series Test Using Standard Approaches and a New Classification and Regression Tree Approach - John J McArdle (The Woodcock Munoz Research Foundation Journal, 2009)
Keywords: Methodology

Aging, Demographics and Memory Study (ADAMS): Sample Design, Weighting and Analysis for ADAMS - Steven G Heeringa; Gwenith G Fisher; Michael D Hurd; Kenneth M. Langa; Mary Beth Ofstedal; Brenda L Plassman; Rogers, Willard; David R Weir (Institute for Social Research, University of Michigan, 2009)
This technical report describes the sample design, design-based weighting and analysis procedures for the Aging, Demographics and Memory Study (ADAMS), a national study that recruited Health and Retirement Study (HRS) panel members to undergo a psychometric evaluation and clinical assessment visit. Langa et al. (2005) describe the general design and methods for the ADAMS including relevant background on the HRS longitudinal sample. This document provides additional detail on the sample design for the ADAMS including a description of survey sample selection, sample attrition and nonresponse, population weights, design-based variance estimation and related topics of importance to analysts of the ADAMS data.
Keywords: Health Conditions and Status; Methodology

Childlessness, Parenthood, and Depressive Symptoms Among Middle-Aged and Older Adults - Regina M. Bures; Koropeckyj-Cox, Tanya; Loree, Michael (Journal of Family Issues, 2009)
Prior research has examined whether parenthood is associated with higher levels of well-being among older adults, but definitions of parental status have varied. The authors examine links between parental status and depressive symptoms among older adults, comparing biological and social definitions of parenthood. The study finds few differences between biological and social parenthood but substantial variation in the relationship between parental status and depressive symptoms by gender and marital status. Biologically and socially childless adults had the lowest predicted levels of depression across all marital status groups. Widowed men averaged higher levels of depression than other men. For women, the highest predicted levels of depressive symptoms were observed among never-married biological parents and formerly married women who had outlived their children. Increased sampling of less common parental subgroups and diverse kinship relations to allow for more precise classifications and the consideration of joint marital parental statuses in future research.
Keywords: Adult children; Health Conditions and Status; Methodology

Consumption Response to Expected Future Income - Pounder, Laurie (International Finance Discussion Papers, 2009)
This paper shows empirical evidence in favor of forward-looking household consumption that consumption today depends directly on household-specific ex-ante expectations of future income. This analysis is unique in using a direct consumption measure combined with an exante household-specific measure of expected future income, constructed from detailed survey and administrative data on Social Security, pensions, and retirement plans. Households with high expected future income spend more today than households that have lower future income but identical current income and net worth. Omitting household-specific future income can cause mis-estimation of key consumption questions. Furthermore, when all three resources for consumption (current income, net worth, and future income) are accounted for, the average propensity to spend out of current income is similar to predictions of optimal consumption under uncertainty in a dynamic stochastic model, although the propensities to spend out of accumulated net worth and expected future income are notably lower in the data than the optimal model. Finally, these data also provide evidence on the effect of risk on consumption while controlling for all three resources. Households with high measured risk aversion consume less out of future income. All households, on average, consume more out of the more predictable sources of future income, such as future Social Security benefits.
Keywords: Consumption and Savings; Methodology

Contemporary Challenges of Longitudinal Measurement Using HRS Data - John J McArdle (The Sage Handbook of Measurement, 2009)
Keywords: Methodology

Documentation and Benchmarking of Health Insurance Measures in the Health and Retirement Study - Helen G Levy; Italo Gutierrez (Institute for Social Research, University of Michigan, 2009)
The Health and Retirement Study (HRS) has asked respondents about their health insurance coverage since the study began in 1992. The study has asked about public and private coverage, including detailed information on the source of coverage. These data can be used to paint a comprehensive picture of insurance coverage among the elderly and near-elderly from 1992 to the present. This documentation provides an overview of the health insurance measures in the HRS and benchmarks HRS estimates of health insurance for 1996 through 2006 to data from the Medical Expenditure Panel Study (MEPS). For selected outcomes, the data are also benchmarked to data from the National Health Interview Survey (NHIS) for 1997 through 2006.
Keywords: Medicare/Medicaid/Health Insurance; Methodology

The Effect of Body Weight on Mortality: Different countries and age groups - Yeom, Jihye (University of Southern California, 2009)
The goals of this dissertation were to examine differences in Body mass index (BMI) distribution among Japanese older adults, American older adults, and the U.S. middle-aged; to investigate which factors predict being underweight, overweight or obese among Japanese older adults and American older adults and how weight is associated with chronic diseases and ADL functioning difficulties; to determine how BMI is associated with all-cause mortality in Japanese older adults and the U.S. middle-aged and older adults; to investigate how different levels of BMI are related to all cause mortality and mortality from specific-causes considering the role of biomarkers indicating physiological risk, nutrition, and health behaviors. I found that Japanese older adults (the Nihon University Japanese Longitudinal Study of Aging) have a lower weight distribution with less dispersion than both American middle-aged (the Health and Retirement Study) and older adults (the Longitudinal Study on Aging). Second, education and income did not have an effect on BMI for older men in both countries. However, as years of education increased, both American and Japanese older women are less likely to be overweight. Also, it is interesting that underweight men and women are more likely to have ADL difficulties in the U.S. Third, for total Japanese older adults, being underweight has greater risk of death than being normal weight. For total American older adults, being overweight was associated with a reduced likelihood of dying although most of the indicators of poor health and behaviors are related to being overweight or obese. For American middle-aged persons, overweight or obese people are less likely to die than normal weight. Last, I found that overweight people had significantly higher levels of risk in many biomarkers than normal weight people (the Third National Health and Nutrition Examination Interview Survey). However, underweight people have significantly worse nutritional status and health behaviors than normal weight people. Underweight people who are 65 years and older have an increased hazard of death from all causes and an increased odds of death from cardiovascular disease than normal weight people.
Keywords: Cross-National; Health Conditions and Status; Methodology

Effects of Health Status on the Decision to Retire with Corrections for Measurement Error - Hyun, Kyung-Rae (Economics, 2009)
Many studies on the relationship between labor supply and health status generally do not illustrate a unanimous agreement on the usage of subjective and objective health due to the difficulty in employing the right measures to obtain the precise and up-to-date information on the health status of subjects in question. Thereby, to resolve this quandary, we propose two models; the first model addresses how a researcher could obtain more appropriate estimate in health measure with measurement error; the other model examines whether probabilities questions within and across waves could potentially result in another measurement error. In the first model allowing to justification bias, we found the health and financial compensation' lower and upper bounds for labor force exit and in views of bounds concept, health status plays a larger role in labor force exit than financial compensation. In the second model, we found that measurement error from survey effect has an impact on the survival probability along with the measurement errors from an inherent errors-in-variable bias by using two methods: the former employing the averaged survival probabilities and the latter incorporating the instrumental variables.
Keywords: Employment and Labor Force; Health Conditions and Status; Methodology

The Elasticity of Intertemporal Substitution: New Evidence from 401(k) Participation - Gary V. Engelhardt; Kumar, Anil (Economics Letters, 2009)
A key parameter in economics is the elasticity of intertemporal substitution (EIS), which measures the extent to which consumers shift total expenditures across time in response to changes in the effective rate of return. In contrast to the previous literature, which primarily has relied on Euler equation methods and generated a wide range of estimates, we show how a life-cycle-consistent econometric specification of employee 401(k) participation along with plausibly exogenous variation in rates of return due to employer matching contributions can be used to generate new estimates of the EIS. Because firms often cap the generosity of the match, employer matching generates non-linearities in household budget sets. We draw on non-linear budget-set estimation methods rooted in the public economics literature, and using detailed administrative contribution, earnings, and pension-plan data for a sample of 401(k)-eligible households from the Health and Retirement Study, we estimate the EIS to be 0.74 in our richest specification, with a 95 confidence interval that ranges from 0.37 to 1.21.
Keywords: Consumption and Savings; Methodology; Pensions

Essays in labor, health, and environmental economics - Ferris, Ann E. (University of Michigan, 2009)
The first essay examines the labor demand response of the Pacific Northwest timber industry to an environmental regulation that drastically reduced timber harvest in the region in the 1990s: protecting the northern spotted owl under the Endangered Species Act. I construct county-level measures of the local intensity of owl protection, using data on 7 million acres of federal forestland set aside as critical habitat. Difference-in-differences estimates indicate a 26 percent decline in timber employment from 1990 to 2000, approximately 17,600 timber jobs, and a 2 percent decline in timber earnings per worker. Owl-protected areas vary in size; the marginal effect of an additional protected acre on timber employment is a decline of 0.09 percent. I find mixed evidence of spillover effects. Using the Canadian province of British Columbia, a regional comparison finds a smaller loss of timber employment in the Pacific Northwest: 7,700 jobs. Taken together, these results indicate that Northern Spotted Owl protection plausibly led to a small loss of timber earnings per worker and employment. The second essay describes how parents' health is related to children's human capital accumulation and educational attainment. Using data from the Health and Retirement Study, we find evidence that children with unhealthy parents attain less education than similar children with health parents. Controlling for family assets and other background characteristics, daughters are significantly less likely to complete as many years of education as sons if their mother experiences a decline in health. The third essay describes the long-term association of poor parental health on children's labor force outcomes in adulthood. To describe this long-term association empirically we use two representative, longitudinal studies with detailed information on parents' health and children's labor force status: the Panel Study of Income Dynamics and the Health and Retirement Study. We show that adults, ages 18 to 29, whose parents reported being in poor health were less likely to be working ten years later, compared to similar young adults with healthier parents.
Keywords: Employment and Labor Force; Health Conditions and Status; Methodology; Other

Estimation and Tests for a Longitudinal Regression Model Based on the Markov Chain - M. Ataharul Islam; Khalaf S. Sultan; Rafiqul I Chowdhury (Statistical Methodology, 2009)
In this paper, the dependence of transition probabilities on covariates and a test procedure for covariate dependent Markov models are examined. The nonparametric test for the role of waiting time proposed by Jones and Crowley M. Jones, J. Crowley, Nonparametric tests of the Markov model for survival data Biometrika 79 (3) (1992) 513522 has been extended here to transitions and reverse transitions. The limitation of the Jones and Crowley method is that it does not take account of other covariates that might have association with the probabilities of transition. A simple test procedure is proposed that can be employed for testing: (i) the significance of association between covariates and transition probabilities, and (ii) the impact of waiting time on the transition probabilities. The procedure is illustrated using panel data on hospitalization of the elderly population in the USA from the Health and Retirement Survey (HRS).
Keywords: Methodology

Healthy Minds in Healthy Bodies: An International Comparison of Education-Related Inequality in Physical Health among Older Adults - Jurges, Hendrik (Scottish Journal of Political Economy, 2009)
We study education-related inequality in the physical health of older adults across 11 European countries and the United States. Combining the data from Health and Retirement Study 2002, the English Longitudinal Study of Ageing 2002 and the Survey of Health, Ageing and Retirement in Europe 2004, our results suggest that education is strongly correlated with health both across and within countries. Education-related inequality in health is larger in Mediterranean and Anglo-Saxon countries than in western European countries. We find no evidence of a trade-off between health levels and equity in health. Education-related inequality in health is hardly driven by income or wealth effects (except in the United States), and differences in health behaviours (smoking) by education level contribute little to health differences across education groups. Copyright (c) 2009 The Author. Journal compilation (c) 2009 Scottish Economic Society.
Keywords: Cross-National; Demographics; Health Conditions and Status; Methodology

How Do Pensions Affect Household Wealth Accumulation? - David M. Blau (2009)
Empirical analysis of the effects of pensions on saving behavior is usually based on a highly stylized version of the life cycle model, with a fixed retirement age, a perfect capital market, no uncertainty, and no institutional constraints on pensions. The model predicts one-for-one crowd out of household wealth by pension wealth over the life cycle. Empirical estimates of crowd out are usually much closer to zero, and it is not well understood whether such estimates are accurate indications of the true magnitude of crowd out or whether the strong assumptions imposed in the analysis result in severe misspecification. In this paper, I specify a richer life cycle model in which several of the key restrictions of the simple model are relaxed. The effects of pensions on household wealth are analyzed by solving and simulating the model. The compensating variation associated with pensions is treated as a measure of crowd out. The simulated data are then used to estimate regressions like those typically found in the literature. Preliminary results indicate that regression estimates of the effects of pensions on wealth accumulation estimated under the assumptions of the typical stylized life cycle model are quite misleading when those assumptions do not hold. Specifically, the extent of crowd out is substantially underestimated in the regression approach. This finding may help explain the common although not universal empirical finding of small crowd out.
Keywords: Consumption and Savings; Methodology; Pensions; Public Policy

Integrating Retirement Models - Alan L Gustman; Thomas L. Steinmeier (NBER Working Paper, 2009)
This paper advances the specification and estimation of models of retirement and saving in two earner families. The complications introduced by the interaction of retirement decisions by husbands and wives have led researchers to adopt a number of simplifications to increase the feasibility of estimating family retirement models. Our model relaxes these restrictions. It includes the extended choice set created when each spouse makes an independent retirement decision. It also includes the full range of complexity found in dynamic-stochastic models of retirement decision making, so far analyzed only in the context of single earner households. Retirement outcomes include full retirement, partial retirement and full-time work. Reverse flows from states of lesser to greater work are also included. The preference structure incorporates heterogeneity in time preference, varying taste parameters for full-time and part-time work, and the possibility of changes in preferences after retirement. The opportunity set reflects the full range of nonlinearities created by pensions and Social Security. Financial returns are stochastic. Exogenous shocks such as layoffs are also included. Estimation is based on data from the Health and Retirement Study. The solution method is based on backward induction. We show that this method is superior to a method based on a Nash equilibrium, providing plausible behavioral predictions when Nash equilibrium criteria fall silent. In contrast to some recent studies, the findings suggest the flow of wives into the labor force in the last few decades has probably reduced the amount of husbands work. The model also provides plausible responses to various policies. For example, we find that any effort to promote opportunities for partial retirement as a means to increase overall work is likely to be unsuccessful as any induced decline in full retirements is offset by a decrease in full-time work.
Keywords: Adult children; Methodology; Retirement Planning and Satisfaction

Keeping in Contact with Mobile Sample Members - Mick P. Couper; Mary Beth Ofstedal (Methodology of Longitudinal Surveys, 2009)
In this chapter, we first offer an overview of the location problem, as distinct from other sources of panel attrition or nonresponse. We then offer a framework for understanding the location propensity to guide fieldwork strategies and identify likely sources of bias. Then we briefly describe two cases studies, examining the extent of the location problem and correlates of (non)location. We end with a brief discussion of the changing role of technology in facilitating or impeding the ability to locate sample persons who have moved or changed contact information, and offer some thoughts for research and practice.
Keywords: Methodology

Markov Models with Covariate Dependence for Repeated Measures - M. Ataharul Islam; Rafiqul I Chowdhury; Huda, Shahariar (Nova Science Publishers, 2009)
During the recent past, there has been a great deal of interst in solving problems of repeated measures data employing the Markov chain models. Most of the researchers and users of such techniques are only transition probabilities of various orders to show relationships among various states. However, in the recent past, there are attempts to include covariates in order to analyse the transition probabilities. Due to lack of a book on this topic, it is difficult for the researchers, students, and other users to have a thorough understanding in applying the methods based on sound knowledge. In addition, there is a lack of suitable software to handle repeated measures for Markov model applications. The main purpose of the book is to provide a theoretical base to the readers who will be willing to use these techniques for real life situations as well as for those who intend to continue advanced research in this field. This book provides a comprehensive discussion and theoretical details of the techniques in this field along with their estimation and test procedures, application of the techniques to real life problems, and the computer programs for using the techniques.
Keywords: Methodology

The mediating effects of the sense of control on the financial well-being of older adults - Karen A. Zurlo (University of Pennsylvania, 2009)
Statement of the problem. The financial well-being of the older adult population has improved over the past few decades, but the outlook for future generations is not positive. As government and employers become less accountable for the provision of retirement income, adults are required to take greater responsibility for their financial circumstances as they age, yet they often have neither the skills nor ability to exercise this control. By not exercising adequate control over their different aspects of their lives, adults may be exposed to financial risk in retirement. Methods. A cross-sectional, quantitative analysis using survey data from two components of the Health and Retirement Study (HRS), the HRS Rand Data files and the Psychosocial Leave-Behind Participant Lifestyle Questionnaire, was conducted. These surveys were administered in 2006 to a sample of 7,549 adults over the age of 50 and merged to conduct this analysis. Statistical analyses used multi-stage statistical modeling to test the mediating effects of the general sense of control and domain-specific levels of control, also known as control beliefs, on the relationship between the general attributes of older adults and their financial well-being. Financial well-being was measured as financial satisfaction and wealth. Results. The control beliefs of older adults significantly influence the size and magnitudes of the linkages between their demographic attributes and financial outcomes. Control beliefs boosted explained variance in financial satisfaction by over 70 percent and they increased explained variance in wealth by 4.5 percent. The mediation analyses were consistent with these results. Conclusion. Control beliefs are more strongly influential over older adults' sense of financial satisfaction than on their actual wealth levels. Accordingly, interventions that influence peoples' sense of control may enhance their felt well-being but will be less influential on levels of wealth. This study can be considered the first of its kind to use the psychological construct of sense of control as a mediating factor on the relationship between the attributes of older adults and self-assessed financial satisfaction as well as actual wealth outcomes. In this way we contribute to the newly developing research stream evaluating the determinants of self-reported happiness.
Keywords: Demographics; Methodology; Net Worth and Assets; Other; Retirement Planning and Satisfaction

Mode and Context Effects in Measuring Household Assets - Arthur H.O. vanSoest; Arie Kapteyn (RAND Corporation Publications Department Working Papers: 668, 2009)
Differences in answers in Internet and traditional surveys can be due to selection, mode, or context effects. The authors exploit unique experimental data to analyze mode and context effects controlling for arbitrary selection. The Health and Retirement Study (HRS) surveys a random sample of the US 50 population, with CAPI or CATI core interviews once every two years. In 2003 and 2005, random samples were drawn from HRS respondents in 2002 and 2004 willing and able to participate in an Internet interview. Comparing core and Internet survey answers of the same people, the authors analyze mode and context effects, controlling for selection. They focus on household assets, for which mode effects in Internet surveys have rarely been studied. They find some large differences between the first Internet survey and the other three surveys which they interpret as a context and question wording effect rather than a pure mode effect.
Keywords: Demographics; Methodology; Net Worth and Assets

Mode and Context Effects of Measuring Household Assets - Arthur H.O. vanSoest; Arie Kapteyn (Tilburg University, Center for Economic Research, Discussion Paper 2009-14, 2009)
Differences in answers in Internet and traditional surveys can be due to selection, mode, or context effects. We exploit unique experimental data to analyze mode and context effects controlling for arbitrary selection. The Health and Retirement Study (HRS) surveys a random sample of the US 50 population, with CAPI or CATI core interviews once every two years. In 2003 and 2005, random samples were drawn from HRS respondents in 2002 and 2004 willing and able to participate in an Internet interview. Comparing core and Internet survey answers of the same people, we analyze mode and context effects, controlling for selection. We focus on household assets, for which mode effects in Internet surveys have rarely been studied. We find some large differences between the first Internet survey and the other three surveys which we interpret as a context and question wording effect rather than a pure mode effect.
Keywords: Methodology; Net Worth and Assets

Portfolio Choice in Retirement: Health Risk and the Demand for Annuities, Housing and Risky Assets - Yogo, Motohiro (Center for Retirement Research at Boston College Working Papers, 2009)
This paper develops a consumption and portfolio-choice model of a retiree who allocates wealth among four assets: a riskless bond, a risky asset, a real annuity, and housing. Unlike previous studies that treat health expenditures as exogenous negative income shocks, this paper builds on the Grossman model to endogenize health expenditures as investments in health. I calibrate the model to explain the joint evolution of health status and the composition of wealth for retirees, aged 65 to 96, in the Health and Retirement Study. I use the calibrated model to assess the welfare gains of an actuarially fair annuity market. The welfare gain is less than 1 of wealth for the median-health retiree at age 65, and the welfare gain is about 10 of wealth for the healthiest.
Keywords: Health Conditions and Status; Methodology; Net Worth and Assets

Poverty Transitions for the Elderly - Lee, Youngae (The Ohio State University, 2009)
The purpose of this study is to examine the likelihood of poverty transition and the effects of different events on poor elderly. This study is important because the aging population has grown rapidly, and elderly poverty involves many complex relationships across an individual's life span. The contributions of this study are to improve the understanding of elderly poverty and to provide considerable policy implications for elderly demographic changes in the future. The data for this study are from the years 1992-2006 of the Health and Retirement Study (HRS) and the sample consists of 30,405 elderly individuals from eight waves. To examine the incidence and dynamics of elderly poverty, poverty-rate decomposition and the poverty exit (re-entry) hazard rate based on Kaplan-Meier product-limit estimates are used. Entry into and exit from elderly poverty models are separately used to estimate the conditional relationship between poverty transition and multiple trigger events as well as various covariates using the discrete-time hazard model. These multivariate techniques show a more realistic picture of elderly poverty transition in terms of providing a preliminary explanation of the unobserved heterogeneity of the elderly poverty. The major findings are: (1) the poverty rates for the HRS data fluctuated considerably during the 1990s, but the rates have had little turnover and have been relatively stable over time during the 2000s; (2) in terms of poverty entry and exit rates, the exit rate was decreased during the 1990s, but the rate was increased during the 2000s while the entry rate fell somewhat during the 1990s and rose somewhat during the 2000s; (3) the poverty rate for the HRS cohort individuals in a given year by cross-sectional data is relatively low, and the duration of the poverty spell is also relatively short (a fifth of the HRS cohort individuals had at least one poverty spell); (4) as the length of the poverty spell increased, the probability of poverty exit decreased; (5) as the non-poverty duration increases, the poverty re-entry rates are constant at around 10 percent; (6) retirement and a negative change in health condition both have significant effects on elderly poverty entry, while retirement, increase in total wealth, and becoming insured from any government health program all have significant effects on elderly poverty exit; and (7) life history variables, such as total years of work and length of marriage have significant effects on both elderly poverty entry and exit. Results from the hazard rates (exit and re-entry rate) imply that a person who falls into poverty during his or her elderly years is highly likely to remain poor because the exit probabilities fall as the length of the poverty spell increases. In addition, the results of constant re-entry rates infer that the elderly population is exposed to the risk of falling to an income that puts them below the poverty line. Results from multivariate analysis suggest that retirement has an important role in elderly poverty transition and a negative change in health condition also has positive impact on elderly poverty entry. Thus, effective income support programs and social policies for the elderly help to prevent elderly individuals from becoming poor.
Keywords: Healthcare; Methodology

Preretirement Planning and Well-Being in Later Life: A Prospective Study - Jack H Noone; Christine Stephens; Fiona M. Alpass (Research on Aging, 2009)
Cross-sectional and retrospective research has identified a reliable relationship between preretirement planning and later-life well-being. Although it seems intuitive that retirement planning leads to more positive retirement outcomes, limited longitudinal analysis has confirmed the directionality of this relationship or clarified its complexities. The Health and Retirement Study, a prospective survey of American workers and retirees from 1992 to the present, can help illuminate this relationship. Data signifying the preretirement activities of employed individuals from the 1992 wave were compared with their postretirement ratings of retirement satisfaction and subjective physical and emotional health in 2004. An ordinal regression analysis indicated that those who had discussed retirement with their spouses and had retirement superannuation or savings plans in 1992 reported greater well-being in 2004 (controlling for health status, the reason for retirement, and income in 1992). These results confirm the importance of preretirement preparation and provide a rationale for developing more comprehensive, theory-driven measures of retirement planning.
Keywords: Methodology; Retirement Planning and Satisfaction

The Rise in Obesity Across the Atlantic: An economic perspective - Brunello, Giorgio; Pierre-Carl Michaud; Anna Sanz-de-Galdeano (Economic Policy, 2009)
We provide comparable evidence on the patterns and trends in obesity across the Atlantic and analyse whether there are economic rationales for public intervention to control obesity. We take into account equity issues as well as efficiency considerations, which are organized around three categories of market failures: productive inefficiencies, lack of information or rationality and health insurance externalities. We also calculate the long term financial consequences of current US and European obesity trends, and conclude with a brief review of current policies to reduce and prevent excessive body weight both in Europe and the US.
Keywords: Cross-National; Health Conditions and Status; Medicare/Medicaid/Health Insurance; Methodology; Public Policy

Selection Bias in Web Surveys and the Use of Propensity Scores - Matthias Schonlau; Arthur H.O. vanSoest; Arie Kapteyn; Mick P. Couper (Sociological Methods and Research, 2009)
Web surveys have several advantages compared to more traditional surveys with in-person interviews, telephone interviews, or mail surveys. Their most obvious potential drawback is that they may not be representative of the population of interest because the sub-population with access to Internet is quite specific. This paper investigates propensity scores as a method for dealing with selection bias in web surveys. The authors' main example has an unusually rich sampling design, where the Internet sample is drawn from an existing much larger probability sample that is representative of the US 50 population and their spouses (the Health and Retirement Study). They use this to estimate propensity scores and to construct weights based on the propensity scores to correct for selectivity. They investigate whether propensity weights constructed on the basis of a relatively small set of variables are sufficient to correct the distribution of other variables so that these distributions become representative of the population. If this is the case, information about these other variables could be collected over the Internet only. Using a backward stepwise regression they find that at a minimum all demographic variables are needed to construct the weights. The propensity adjustment works well for many but not all variables investigated. For example, they find that correcting on the basis of socio-economic status by using education level and personal income is not enough to get a representative estimate of stock ownership. This casts some doubt on the common procedure to use a few basic variables to blindly correct for selectivity in convenience samples drawn over the Internet. Alternatives include providing non-Internet users with access to the Web or conducting web surveys in the context of mixed mode surveys.
Keywords: Methodology

Sin Taxes: Do Heterogeneous Responses Undercut Their Value? - Padmaja Ayyagari; Deb, Partha; Jason M. Fletcher; William T Gallo; Jody L Sindelar (NBER Working Paper, 2009)
This paper estimates the price elasticity of demand for alcohol using Health and Retirement Survey data. To account for unobserved heterogeneity in price responsiveness, we use finite mixture models. We recover two latent groups, one is significantly responsive to price but the other is unresponsive. Differences between these two groups can be explained in part by the behavioral factors of risk aversion, financial planning horizon, forward looking and locus of control. These results have policy implications. Only a subgroup responds significantly to price. Importantly, the unresponsive group drinks more heavily, suggesting that a higher price could fail to curb drinking by those most likely to cause negative externalities. In contrast, those least likely to impose costs on others are more responsive, thus suffering greater deadweight loss yet with less prevention of negative externalities.
Keywords: Health Conditions and Status; Methodology; Public Policy

Stock Market Expectations and Portfolio Choice of American Households - Kezdi, Gabor; Robert J. Willis (University of Michigan, 2009)
This paper measures heterogeneity in the stock market expectations of households using survey answers to probability questions. We address survey measurement error in an explicit way and develop a joint model of the effect of expectations on portfolio choice on the one hand and survey answers on the other hand. The model is consistent with documented features of measurement error. We show substantial heterogeneity and that heterogeneity in expectations predicts heterogeneity in stockholding. We show that a general tendency to be optimistic is related to optimism about stock returns and in turn increases stockholding, while a general tendency to be uncertain is strongly related to uncertainty about stock market returns and in turn decreases stockholding. We estimate the level of risk tolerance that links subjective beliefs to stockholding to be moderate. We also show that a significant part of stockholding differences among demographic groups is explained by differences in their expectations.
Keywords: Expectations; Methodology; Net Worth and Assets; Risk Taking

Understanding the Economic Consequences of Shifting Trends in Population Health - Dana P Goldman; Darius Lakdawalla; Pierre-Carl Michaud; Yuhui Zheng; Adam Gailey (NBER Working Paper, 2009)
The public economic burden of shifting trends in population health remains uncertain. Sustained increases in obesity, diabetes, and other diseases could reduce life expectancy - with a concomitant decrease in the public-sector's annuity burden - but these savings may be offset by worsening functional status, which increases health care spending, reduces labor supply, and increases public assistance. Using a microsimulation approach, we quantify the competing public-finance consequences of shifting trends in population health for medical care costs, labor supply, earnings, wealth, tax revenues, and government expenditures (including Social Security and income assistance). Together, the reduction in smoking and the rise in obesity have increased net public-sector liabilities by $430bn, or approximately 4% of the current debt burden. Larger effects are observed for specific public programs: annual spending is 10% higher in the Medicaid program, and 7% higher for Medicare.
Keywords: Employment and Labor Force; Expectations; Health Conditions and Status; Healthcare; Methodology; Public Policy

Ageing in the U.S.: The Health and Retirement Study - Robert J. Willis (Social Protection in and Ageing World (International Series on Social Security), 2008)
In this paper, I attempt to describe from both historical and analytical standpoints how and why the HRS began and how and why it has evolved into an interdisciplinary and international scientific project of major significance both for basic science and for public policy.The spread ofthe HRSmodel internationally has not been the result of top-down agreements among governments. Rather, in analogy with open source software such as Linux, the HRS design and content provides researchers with a platform that can be used as a template to develop surveys in their own countries to address scientific and policy questions of both local and general significance. Each of the international studies has found it in its self-interest to be as comparable as possible to the HRS and to one another because, by being comparable, each country can use data from other countries as natural experiments to explore the implications of alternative policies. American researchers, for example, are interested in the implications of alternative forms of financing and delivering health care that have been developed in England and continental Europe. Were data available, American health insurance researchers would be especially interested in Canada.
Keywords: Methodology

Childlessness and Psychological Well-Being Across the Life Course as Manifested in Significant Life Events - Chang, Echo Win-Hu (University of Southern California, 2008)
The childless population in the United States is growing fast, accounting for approximately one fifth of population aged 65 and older. The combination of longevity, marital status changes, and childlessness has led to the projection that about 25% of the population aged 70 to 85 in 2030 will not have a living spouse or a living child. Surprisingly, there is relatively little documentation about the lives of childless elders. Childless people have been conspicuously ignored in social sciences, even in very pertinent fields such as adult development, aging, the life course, and the family. Among previous studies, two common shortcomings make results on childlessness and old-age well-being inconclusive: (a) treating childlessness as a static status and not considering possible changes in its meaning and impact felt in significant life events, and (b) focusing on negative aspect of childlessness at the exclusion of possible positive rewards. This dissertation added contextual variables and measured both negative and positive affects of psychological well-being. It adopts stress process model as a framework to study the effects of childlessness on psychological well-being in the events of caregiving in middle age, retirement in young-old age, and disability in advanced old age. This dissertation uses data from Health and Retirement Study. The findings indicate that childlessness by itself does not pose a negative threat to psychological well-being. The lack of a negative effect of childlessness on psychological well-being does not mean that children are not beneficial to parents. Rather, it suggests that taking the "deviant" path of childlessness, whether voluntarily or not, does not necessarily render childless persons at a greater disadvantage than parents in old age. However, one natural outcome of childlessness is the lack of biological grandchildren the benefits associated with grandparenthood. In this dissertation, grandchildren are found to have a positive influence on grandparents', and in particular grandfathers', transitions to retirement. The effects of childlessness were teased out from the impact of marital status. Possible interaction of gender, parental status, and marital status were tested. Childlessness and singlehood interacts in some cases. Childlessness poses different implications for men and women.
Keywords: Adult children; Health Conditions and Status; Healthcare; Methodology

Comparison between SHARE, ELSA, and HRS - Fernandes, M.; Erik Meijer; Gema Zamarro (First Results from the Survey of Health, Ageing and Retirement in Europe (2004-2007): Starting the longitudinal dimension, 2008)
Keywords: ELSA; Employment and Labor Force; Health Conditions and Status; Income; Methodology; SHARE

Data sources, Later Life: Health and Retirement Study (HRS) - Mary Beth Ofstedal (Encyclopedia of the Life Course and Human Development, 2008)
This reference is an entry in Volume 3 of the Encyclopedia of the Life Course and Human Development; it discusses the Health and Retirement Study as a data source for research on the Later Life stage of the life course.
Keywords: Methodology

Divergent Pathways: Racial/ethnic inequalities in wealth and health trajectories - Tyson H Brown (The University of North Carolina at Chapel Hill, 2008)
Extensive empirical evidence documents racial/ethnic disparities in both wealth and health: compared to Whites, Hispanics and Blacks have considerably less wealth and worse health. However, it remains unclear why racial/ethnic inequalities in wealth and health emerge, and whether these inequalities decrease, remain stable, or increase with age. This dissertation aims to fill these gaps in the literature by drawing on life course perspectives and methods to investigate racial/ethnic differences in wealth and health trajectories (i.e., long-term patterns of intra-individual change and stability in wealth and health with age) and how social disadvantage contributes to racial/ethnic wealth and health disparities. The first empirical chapter utilizes panel data from the National Longitudinal Study of Youth (NLSY), a nationally representative survey, and growth curve models to examine racial/ethnic differences in wealth trajectories between ages 21 and 45. Findings reveal that relatively small wealth gaps between Whites, Blacks and Hispanics exist in their early 20s, but these initial inequalities are magnified with age. In the second substantive chapter, data from the Health and Retirement Study (HRS), a nationally representative, longitudinal dataset is used to examine whether racial/ethnic wealth gaps narrow, remain stable, or widen between during the years leading up to retirement (ages 51 and 73). Results show that Whites experience more rapid rates of wealth accumulation than their minority counterparts during middle and later life, resulting in accelerating wealth disparities with age, consistent with a process of cumulative disadvantage. At age 73, the average White household has a net worth of approximately $122,000, whereas both Hispanic and Black household have less than $5,000. Substantial racial/ethnic disparities in wealth trajectories persist after controlling for group differences in life course capital suggesting that other factors such as racial/ethnic differences in portfolio composition, financial transfers, and exposure to discrimination may contribute to wealth disparities. The third substantive chapter uses HRS data to examine racial/ethnic differences in health trajectories. Results indicate that there are dramatic racial/ethnic disparities in both the levels and rates of change in health. Overall, findings from this study show that racial/ethnic inequalities result in divergent aging experiences for Black, Hispanic, and White Americans.
Keywords: Demographics; Methodology; Women and Minorities

Documentation of Health Behaviors and Risk Factors Measured in the Health and Retirement Study (HRS/AHEAD) - Kristi Rahrig Jenkins; Mary Beth Ofstedal; David R Weir (Institute for Social Research, University of Michigan, 2008)
The two most important negative behaviors for population health are smoking, which is declining over time, and obesity, which is on the rise. Recognizing the important role of health behaviors and risk factors with respect to issues of key importance to the HRS (health, employment, wealth, timing of retirement), the original designers of the HRS incorporated a set of core measures of health behaviors at the outset. These measures have been expanded over time. The health behaviors and risk factors that are covered in the HRS include: Cigarette smoking (current and past behavior); Alcohol consumption (current behavior and past drinking problems); Body mass index (derived from self-reports of height and weight); Exercise (current level); Preventive health screenings. This report is organized as follows. Section II provides an inventory of the measures of health behaviors and risk factors that are covered in HRS, noting additions and changes that have occurred across waves. Special methodological issues that must be considered when using these data are covered in Section III. Section IV (and corresponding Tables 2-28) presents prevalence estimates and frequency counts for each of the health behavior and risk factor measures over time. Lastly, Section V addresses data quality by comparing HRS prevalence estimates with those from other surveys, reviewing results from some of the studies that have used HRS data to study health behaviors and risk factors, and investigating the level of missing data for these measures.
Keywords: Health Conditions and Status; Methodology

Documentation of Physical Measures, Anthropometrics and Blood Pressure in the Health and Retirement Study - Eileen M. Crimmins; Heidi M Guyer; Kenneth M. Langa; Mary Beth Ofstedal; Robert B Wallace; David R Weir (Institute for Social Research, University of Michigan, 2008)
The assessment of physical performance is an important component of the evaluation of functioning of older persons. The HRS has employed a set of standardized assessments of lung function, grip strength, balance, and walking speed. In addition, HRS collected measures of blood pressure, height, weight, and waist circumference. In 2006, HRS included the following measurements, administered in this order: Blood pressure; Lung function; Hand grip strength; Balance tests; Timed walk; Height; Weight; Waist circumference. This report describes the following for each of the measures listed above: Rationale and key citations; Sample description; Measure description; Equipment; Protocol description; Special instructions
Keywords: Health Conditions and Status; Healthcare; Methodology

Essays on Reforming Health Care and Public Transfer Programs - Jung, Juergen (Indiana University, 2008)
My dissertation is focused on the effects of re-distributional policies with an emphasis on health care reform. In the first essay I analyze whether a consumer driven health care plan like the newly established Health Savings Accounts (HSAs) can reduce health care expenditures in the United States and increase the fraction of the population with health insurance. My results indicate that HSAs can decrease total health expenditures by up to 3% of GDP but can also increase the number of uninsured individuals by almost 5%. Furthermore, HSAs decrease the aggregate level of health capital and therefore decrease output. In the second essay I construct subjective health expectations curves and empirically evaluate its components using data from the Health and Retirement Study. I find that (i) subjective health expectations do contain additional information that is not incorporated in subjective mortality expectations and (ii) that the rational expectations assumption cannot be rejected for subjective health expectations. In the third essay I investigate whether a redistribution program that targets older individuals can "dominate" a redistribution program that targets younger individuals in terms of output and some measure of welfare. I find that late redistribution can dominate early redistribution in terms of welfare if the program is kept moderate in size by using the possibility of targeting the transfers. Late redistribution does not dominate early redistribution in terms of output. Better targeting of low income households cannot offset savings distortions.
Keywords: Methodology

Essays on Retirement and the Residential Choice of the Elderly - Kazi, Paula Mehboob (Michigan State University, 2008)
The dissertation consists of three chapters concerning the well being of the older adult population in the United States. All three essays use data from the Health and Retirement Study (HRS), a longitudinal survey on health, retirement, and aging. The first chapter studies the relationship between retirement and time transfers within the family. We use cross-sectional variation in the need for caregiving to assess whether caregiving affects the retirement decision. For instance, parents' inability to take care of certain tasks for themselves, or accumulated and new health problems of spouses could lead to a demand for care from working individuals. We do not find evidence that potential parental care-need accelerates retirement transitions. Also, it does not seem that people retire early to provide care for sick spouses. However, post-retirement health insurance coverage is important in early retirement, in that when people have access to such coverage, they retire sooner if a family member happens to be in ill health. The second chapter assesses the potential usefulness of subjective expectation information in micro data by documenting the relationship between moving expectations and subsequent moving realizations among the United States population ages sixty-five and older. We find that the subjective probabilities of moving are very important in predicting future moving, even once demographic information known to be associated with the propensity to move is added to the analysis. Motivated by the observed relationship between the reported subjective probabilities and actual moving propensities, we hypothesize that when people are asked for a subjective probability they report the true probability conditional on available information, plus some random noise. We look at the proposed model's implications regarding which population groups are better at predicting future residential moving. However, we fail to substantiate the hypothesis, and therefore, cannot conclusively identify individual characteristics associated with better forecasting. The third chapter examines the long contested issue of whether the elderly draw down their housing wealth during retirement. In examining whether housing wealth declines during retirement, we emphasize exploring heterogeneity across population groups in housing wealth adjustments. Our analysis demonstrates that for non-mover retirees there is no systematic decline in housing equity. But for retiree-movers there is a decline in the median housing equity starting at age 71, and a decline in the mean housing equity from age 76. We find evidence of significant heterogeneity in housing equity adjustments at retirement. Nearly a quarter of the retiree-movers report that they are moving to downsize, and they do. Those with low non-housing wealth and with low income reduce housing equity significantly more than their respective counterparts. Retiree-movers experiencing widowing or divorce reduce housing equity substantially more than those without similar experience. Our findings are, in fact, largely consistent with the existing evidence in the literature regarding downsizing in later life. This study does not disprove or bolster either side of the debate on the role of housing wealth in financing retirement needs. But it highlights that the choice of emphasis regarding which side of the debate holds is often reliant on how one chooses to interpret what is in the data.
Keywords: Methodology

Evaluating the role of Social Security in providing annuity insurance - Hosseini, Roozbeh (University of Minnesota, 2008)
In this dissertation I study the usefulness of social security in providing annuity insurance when there is adverse selection in the annuity market. In Chapter 1 I study a two period economy where altruistic consumers have uncertain lifetime and are privately informed about their survival probabilities. Consumers buy insurance by participating in insurance pools. In this environment competitive equilibrium with life and annuity insurance exists despite the presence of adverse selection. This environment has three key features: (1) In any equilibrium there is at most one insurance market where trade occurs. (2) Increase in social security tax and benefits leads to increase in price of annuity and crowds out trade activities in annuity market. (3) In this environment efficient allocations are independent of private information and can be optimally implemented using simple tax-transfer instruments. Under optimal policy both annuity and life insurance markets are endogenously closed. I extend the model to a multi-period dynamic environment in Chapter 2. I calculate the welfare cost of adverse selection in the annuity market using a life cycle model in which individuals have private information about their mortality. I calibrate the model to the current U.S. social security replacement ratio, fraction of annuitized wealth and mortality heterogeneity in the Health and Retirement Study. My findings are as follows. First, in the absence of social security, individuals (on average) maintain about the same fraction of annuitized wealth as they do in the presence of social security, despite the fact that prices in the market are actuarially unfair. As a result, the welfare loss of abolishing social security is only 0.12 percent (in terms of consumption). Second, there is an ex ante gain of 0.51 percent from implementing the ex ante efficient allocations, which comes from redistributing resources from high mortality types to low mortality types. Individuals with high mortality (who will die soon and do not have demand for longevity insurance) incur large welfare losses from mandatory participation. These losses offset the benefits of providing insurance to low mortality types, leaving the overall ex ante welfare gain small.
Keywords: Methodology

First and Higher Order Transition Models with Covariate Dependence - M. Ataharul Islam; Rafiqul I Chowdhury (Progress in Applied Mathematical Modeling, 2008)
The covariate dependent Markov models can be employed in various fields of research for analyzing time series or repeated measures data. This paper highlights the covariate dependent Markov models for the first and higher orders. The first order covariate dependent Markov model developed by Muenz and Rubinstein (1985) is reviewed and then second and higher order models for binary sequence are developed along with their estimation and test procedures based on Islam and Chowdhury (2006). The models for more than two outcomes are also shown. A general procedure based on the Chapman-Kolmogorov equations is proposed here in order to take account of the transitions at unequal intervals. A simple test procedure is suggested here to determine the order of the underlying Markov models. The proposed methods are illustrated with the Health and Retirement Survey data from the USA on the mobility difficulty of the elderly population. The results indicate the utility of the transitional models for first or higher orders of underlying transitions with binary or multiple outcomes.
Keywords: Demographics; Methodology

Income Data for Policy Analysis: A Comparative Assessment of Eight Surveys: Final Report - Czajka, John L.; Denmead, Gabrielle (Office of the Assistant Secretary for Planning and Evaluation, 2008)
Income is a critical variable in policy analysis, and because of this, most federal household surveys collect at least some data on income. Yet income is exceedingly difficult to measure well in a household survey. Income questions produce some of the highest item nonresponse rates recorded in surveys, and comparisons of survey estimates with benchmarks developed from administrative records provide evidence of significant under-reporting for many sources. Mathematica Policy Research, Inc. (MPR) and its subcontractor, Denmead Services & Consulting, have conducted a comprehensive and systematic assessment of the income data and its utility for policy-related analyses in eight major surveys: the Survey of Income and Program Participation (SIPP); the Annual Social and Economic Supplement to the Current Population Survey (CPS); the American Community Survey (ACS); the Household Component of the Medical Expenditure Panel Survey (MEPS); the National Health Interview Survey (NHIS); the Medicare Current Beneficiary Survey Cost and Use files (MCBS); the Health and Retirement Study (HRS); and the Panel Study of Income Dynamics (PSID). The assessment included both descriptive and empirical components. The descriptive component compiled extensive information on survey design and methodology in addition to the measurement of income and poverty and presented these data in a side-by-side format. The empirical component generated comparative tabulations of the distribution of income and poverty status for a range of personal characteristics for a common universe, income concept, and family definition, to the extent that this was feasible. Additional analysis focused on the implications of specific design choices. [416 PDF pages]
Keywords: Methodology; Public Policy

Kinship status and life course transitions as determinants of financial assistance to adult children - R Corey Remle (Sociology, 2008)
This dissertation contributes to the literature on intergenerational transfers by examining the dynamics of financial assistance provided by midlife parents to their adult children across the life course. This dissertation also examines whether the cumulative advantage hypothesis stretches across generational lines during co-occurring life course experiences so that financial transfers convey additional advantages to adult children. I use panel data from four waves of the Health and Retirement Study (1992, 1994, 1996 and 1998) to provide a broad picture of the process of financial assistance to younger adults within extended families. I constructed within-family trajectories of assistance to demonstrate that financial transfers are more common than previously estimated. Over 60% of all midlife-parent households gave $500 or more at least once and many parents gave multiple transfers and/or gave transfers to several adult children during a seven-year period. In an examination of kinship structures that differentiates between paternal children and maternal children within blended families, I use nonlinear logistic regression models to show that the decreased likelihood that fathers provided financial assistance to children from a previous marriage accounted solely for the reduction in transfers that all stepchildren received compared to biological children. Multilevel regression models demonstrate that transfer amounts are also influenced by kinship structures and parental resources. Additional analyses show adult child life course transitions related to schooling and coresidence were influential for parents' transfer behaviors while other life course transitions related to work, marriage, home ownership and the addition of a grandchild to the family were not influential. The number of life course transitions experienced by adult children during later waves significantly increased the likelihood of transfer receipt. However, the diversification of experiences over time made it difficult to pinpoint specific life course transitions relevant to financial assistance from parents. The strong impact of previous transfers upon the likelihood that adult children would receive transfers at later waves shows that patterns of repeated transfers were common for many intergenerational families. I argue that future research should analyze the impact of parental wealth on transfers and should explicitly examine parents' motives for giving money to adult children.
Keywords: Adult children; Health Conditions and Status; Healthcare; Methodology

Measurement Error in Earnings Data in the Health and Retirement Study - Bricker, Jesse; Gary V. Engelhardt (Journal of Economic and Social Measurement, 2008)
We provide new evidence on the extent of measurement error in respondent-reported earnings data by exploiting detailed W-2 records matched to older workers in the Health and Retirement Study (HRS). Our empirical findings are qualitatively consistent with the findings of previous studies. Mean measurement error in the 1991 HRS earnings data for men is somewhat larger than what has been found in other validation studies, but is still modest, averaging about 0.059 log points, approximately 5.9 percent, or 1,500. For women in 1991, it is 0.067 log points, approximately 6.7 percent, or 916. We find a negative correlation between the measurement error and the true value of earnings as measured by the W-2 records, which indicates the presence of non-classical measurement error. For men and women, this error shows little correlation with a standard set of cross-sectional earnings determinants. The one exception is that the measurement error rises with reported education. The bias on the OLS parameter estimate of the impact of having a college degree or higher (relative to a high school drop-out) from using the respondent-reported rather than the W-2 earnings is positive and estimated to be 0.071 log points, or roughly a bias of 7 percent.
Keywords: Methodology; Social Security

Modeling aging processes: Social activities, partner influence, and individual well-being - Hao, Yanni (The University of Chicago, 2008)
The past decade has witnessed a growing interest in longitudinal studies of aging. The perspective of cumulative advantage/adversity was employed to explain health disparities in later life. In terms of methodology, recent advances in the statistical theory of growth curve models have enabled important breakthroughs in the study of correlates of change. Moreover, moving beyond single-trajectory growth curve analysis, a combination of the longitudinal model for individual change and the cross-sectional model for matched pairs makes it possible to estimate dual aging trajectories of marital dyads. Hence, this dissertation focuses on effects from social activities and partner influences that affect aging. Using the Health and Retirement Study (HRS) and the Asset and Health Dynamics among the Oldest Old (AHEAD) data, I conduct three studies in this dissertation. In first two studies, I perform growth curve analyses to examine how activities such as volunteering, helping and late-life employment influence aging trajectories for mid-old aged and older adults. In the third study, I extend growth curve models into family and marriage research to estimate dual aging trajectories for marital dyads and to examine cross-partner interactive processes. The results suggest that social activity and marital context do influence aging processes after midlife. Findings also confirm the existence of selection mechanisms that may drive healthy individuals into activity and similar individuals into a marital relationship. In total, causal relations between activities and partner influence and the effects on later aging trajectories are established. Moreover, these studies predict that, to the extent that the changes accumulate, the above mechanisms will keep shaping older adults' health trajectories over time. This suggests a mutually reinforcing cumulative process of selection and causal mechanisms.
Keywords: Healthcare; Methodology

A Parsimonious Choquet Model of Subjective Life Expectancy - Ludwig, Alexander; Zimper, Alexander (Center for Retirement Research at Boston College Working Papers, 2008)
This paper develops and estimates a closed-form model of Bayesian learning of subjective survival beliefs within the framework of Choquet decision theory. Data from the Health and Retirement Study (HRS) indicate that, on average, young respondents underestimate their true survival probability whereas old respondents overestimate their survival probability. Such subjective beliefs violate the rational expectations paradigm and are also not in line with the predictions of the rational Bayesian learning paradigm which implies convergence of subjective to underlying 'objective' probabilities. Based on the assumption of non-additive beliefs, we therefore introduce a model of Bayesian learning which combines rational learning with the possibility that the interpretation of new information is prone to psychological attitudes. We estimate the parameters of our theoretical model by pooling the HRS data. Despite a parsimonious parametrization we find that our Choquet model results in a remarkable fit to the average subjective beliefs expressed in the data.
Keywords: Expectations; Methodology

Partial Identification of Probability Distributions with Misclassified Data - Molinari, Francesca (Journal of Econometrics, 2008)
This paper addresses the problem of data errors in discrete variables. When data errors occur, the observed variable is a misclassified version of the variable of interest, whose distribution is not identified. Inferential problems caused by data errors have been conceptualized through convolution and mixture models. This paper introduces the direct misclassification approach. The approach is based on the observation that in the presence of classification errors, the relation between the distribution of the 'true' but unobservable variable and its misclassified representation is given by a linear system of simultaneous equations, in which the coefficient matrix is the matrix of misclassification probabilities. Formalizing the problem in these terms allows one to incorporate any prior information into the analysis through sets of restrictions on the matrix of misclassification probabilities. Such information can have strong identifying power. The direct misclassification approach fully exploits it to derive identification regions for any real functional of the distribution of interest. A method for estimating the identification regions and construct their confidence sets is given, and illustrated with an empirical analysis of the distribution of pension plan types using data from the Health and Retirement Study.
Keywords: Methodology; Net Worth and Assets

Preparation for Retirement, Financial Literacy and Cognitive Resources - Delavande, Adeline; Susann Rohwedder; Robert J. Willis (Michigan Retirement Research Center Research Working Paper, 2008)
Traditional economic models assume that individuals have full information and act perfectly rationally. However, we show that there is considerable variation in financial literacy in the population and propose modeling the acquisition of financial knowledge in a human capital production framework. The model makes several predictions, notably with respect to portfolio choice. For example, it helps explain household non-participation in the stock market for some fraction of the population, and it provides guidance about the share of risky assets to hold for other types of households. Estimation of the human capital production function for financial knowledge on data from the Cognitive Economics Survey yields results that are consistent with important features of the model
Keywords: Methodology; Net Worth and Assets

Tax policy, housing markets, and elderly homeowners - Shan, Hui (Economics, 2008)
This dissertation consists of three essays studying the impact of tax policy on housing markets and elderly homeowners. Chapter One examines the potential lock-in effect of capital gains taxation on home sales, using the Taxpayer Relief Act of 1997 (TRA97) as a policy instrument. Before 1997, homeowners were subject to capital gains taxation when they sold their houses unless they purchased replacement homes of equal or greater value. Since 1997, homeowners can exclude $500,000 of capital gains when they sell their houses. Using zip-code level housing price indices and sales data from 1982 to 2006 on single-family houses in 16 affluent towns within the Boston metropolitan area, I find that TRA97 reversed the lock-in effect for houses with low and moderate capital gains. However, the semiannual home sale rate of houses with capital gains above $500,000 declined after TRA97, suggesting that TRA97 generated an unintended lock-in effect for houses with capital gains over the maximum exclusion amount. Chapter Two studies the relationship between property taxes and elderly mobility. This is the first study using an instrumental variable approach to address the endogeneity problem associated with property taxes in analyzing elderly mobility. Using household-level panel data from the Health and Retirement Study (HRS) and a newly-collected dataset on state-provided property tax relief programs, I find evidence suggesting that higher property taxes raise mobility rates among elderly homeowners. Eligibility for relief programs lowers mobility rates, and the impact of these programs appears to vary with program types, program generosity, and implementation strategy. Chapter Three investigates the effect of property taxes on elderly homeowners labor supply decisions, using similar data and empirical strategy employed in Chapter Two. I examine both the extensive margin--whether elderly homeowners' delay retirement or reenter the labor force in the face of rising property taxes, and the intensive margin--whether elderly homeowners work longer hours when property taxes increase. I find little evidence that property taxes have a significant impact on elderly labor supply. (Copies available exclusively from MIT Libraries, Rm. 14-0551, Cambridge, MA 02139-4307. Ph. 617-253-5668; Fax 617-253-1690.)
Keywords: Healthcare; Methodology; Public Policy

Topics in the economics of health and aging - Noam Y Kirson (Harvard University, 2008)
The following three essays contain examinations of several topics in the economics of health and aging. While the subject matter of each essay is quite distinct, all three share a strong empirical focus, and attempt to shed light on issues at the intersection of family, society, economics and health. The first essay examines the effects of women's labor force participation on health, primarily the health of their employed spouses. A wide array of data sources is used do demonstrate that among married couples, men whose spouses work suffer from a range of adverse health outcomes, compared to men whose spouses are homemakers. The results strongly suggest that dual-earning households are subjected to high levels of chronic stress, leading to poorer health outcomes. Statistical identification constrains the analysis to the health of men alone. The second essay shares some of the data sources used in the first, though shifts the focus to a much broader question. I conduct a cross-country comparison of health outcomes across five developed nations, to examine their performance on a range of chronic conditions. Importantly, this comparison overcomes many challenges in the existing literature by relying primarily on objectively measured health, rather than self-reported data. The comparison yields a surprising result: though considerably more obese, Americans display remarkably low levels of hypertension and total cholesterol. Treatment patterns can account for much of the difference, suggesting that the American healthcare system might be better at screening and treating these conditions, contrary to common belief. Finally, in the third essay I address a topic more closely associated with aging than health per se. In it, I examine whether a strategic bequest motive can account for apparent sub-optimal tax planning of older households with respect to estate taxes. I develop a theoretical model incorporating both strategic exchange and tax considerations among altruistic parents, leading to an outcome consistent with the literature on suboptimal estate tax behavior. I then turn to test the model's predictions using data from the Health and Retirement Study, and find evidence consistent with a strategic bequest motive among households more likely to face the estate tax.
Keywords: Healthcare; Methodology; Public Policy

Who Values the Social Security Annuity? New evidence on the annuity puzzle - Brown, Jeffrey R.; Casey, Marcus D.; Olivia S. Mitchell (NBER Working Paper, 2008)
We examine individuals' self-reported willingness to exchange part of their Social Security inflation-indexed annuity benefit for an immediate lump-sum payment, using an experimental module in the 2004 Health and Retirement Study. Our first finding is that nearly three out of five respondents favor the lump-sum payment if it were approximately actuarially fair, a finding that casts doubt on several leading explanations for why more people do not annuitize. Second, there is some modest price sensitivity and evidence consistent with adverse selection; in particular, people in better health and having more optimistic longevity expectations are more likely to choose the annuity. Third, after controlling on education, more financially literate individuals prefer the annuity. Fourth, people anticipating future Social Security benefit reductions are more likely to choose the lump-sum, suggesting that political risk matters. Other factors such as sex, marital status, income, wealth, or the presence of children are not associated with respondents' relative preferences for the annuity versus the lump-sum.
Keywords: Methodology; Net Worth and Assets; Pensions; Social Security

The Correlates of Cognitive and Metacognitive Stability and Change in the First Five Waves of the Health and Retirement Study (1992-2000) - Robnett, Regula H. (University of Massachusetts, Boston, 2007)
This dissertation explores the correlates of cognition and metacognition over the first five waves of the longitudinal Health and Retirement Study (HRS) out of the University of Michigan. The HRS is a national data base primarily concerned with health and retirement issues of those who were aged 51 to 61 in 1992. A new wave was completed every two years. Using multinomial logistic regression analyses various sociodemographic, health, lifestyle, and baseline, early-wave cognitive functioning variables were viewed as potential predictors of later-wave cognitive functioning four or eight years later and for trajectories of memory performance over the five waves. Several of the demographic and former cognitive functioning variables tended to be robust predictors of future cognitive functioning. Exerting a consistently negative influence were being male, an increase in depression symptoms, and self-reported Instrumental Activities of Daily Living impairments (specifically map-reading). Positive influences were exerted by being in the white racial group, higher educational levels, self-perceived better health, and higher baseline memory, analogies, and vocabulary scores. The current project lays the foundation for future exploration of the correlates of cognitive impairment, including dementia, as this population group heads into their seventh decade.
Keywords: Health Conditions and Status; Methodology

Disease prevalence and survey design effects: A response to Weir and Smith - Sven E. Wilson; Benjamin L. Howell (Social Science and Medicine, 2007)
Evidence provided by Weir and Smith, particularly the findings from the National Health and Nutrition Examination Survey (NHANES), leads us to conclude that an increase in arthritis prevalence during the 1990s in the United States is probable, but the trend is likely overstated in the Health and Retirement Study (HRS). We show that a mistake in our earlier method does not change substantively our previous conclusion that survey duration effects are occurring in the HRS, a finding that is also supported by a variety of regression models (including that of Weir and Smith). Furthermore, very little evidence exists for an upward trend among self-reporters in the National Health Interview Survey (NHIS), and less than 25 of the increase in the HRS over the 1990s can be attributed to increases in obesity.
Keywords: Health Conditions and Status; Methodology

Elastic Powers: The Integration of Biomarkers into the Health and Retirement Study - David R Weir (Bio-Social Surveys: Current insight and future promise, 2007)
Keywords: Methodology

Enhancing the Quality of Data on the Measurement of Income and Wealth - Juster, F. Thomas; Cao, Honggao; Mick P. Couper; Daniel H. Hill; Michael D Hurd; Joseph P. Lupton; Michael M. Perry; James P Smith (Michigan Retirement and Disability Research Center Research Paper, 2007)
Over the last decade or so, a substantial effort has gone into the design of a series of methodological investigations aimed at enhancing the quality of survey data on income and wealth. These investigations have largely been conducted at the Survey Research Center at the University of Michigan, and have mainly involved two longitudinal surveys: the Health and Retirement Study (HRS), with a first wave beginning in 1992 and continued thereafter every other year through 2004; and the Assets and Health Dynamics Among the Oldest Old (AHEAD) Study, begun in 1993 and continued in 1995 and 1998, then in every other year through 2004. Surveys for the year 2006 are currently in the field. This paper provides an overview of the main studies and summarizes what has been learned so far. The studies include; a paper by Juster and Smith (Improving the Quality of Economic Data: Lessons from the HRS and AHEAD, JASA, 1997); a paper by Juster, Cao, Perry and Couper (The Effect of Unfolding Brackets on the Quality of Wealth Data in HRS, MRRC Working Paper, WP 2006-113, January 2006); a paper by Hurd, Juster and Smith (Enhancing the Quality of Data on Income: Recent Innovations from the HRS, Journal of Human Resources, Summer 2003); a paper by Juster, Lupton and Cao (Ensuring Time-Series Consistency in Estimates of Income and Wealth, MRRC Working Paper, WP 2002-030, July 2002); a paper by Cao and Juster (Correcting Second-Home Equity in HRS/AHEAD: MRRC Working Paper WP 2004-081, June 2004); and a paper by Rohwedder, Haider and Hurd (RAND Working Paper, 2004).
Keywords: Income; Methodology; Net Worth and Assets

Future Social Security Entitlements and the Retirement Decision - Courtney Coile; Gruber, Jonathan (Review of Economics and Statistics, 2007)
A critical question for Social Security policy is how program incentives affect retirement behavior. We use the Health and Retirement Survey (HRS) to examine the impact of Social Security incentives on male retirement. We implement forward-looking models whereby individuals consider the incentives to work in all future years. We find that forwardlooking incentive measures for Social Security are significant determinants of retirement. We also find that private pension incentives have roughly similar effects. Our findings suggest that Social Security policies that increase the incentives to work at older ages can significantly reduce the labor force exit rate of older workers.
Keywords: Employment and Labor Force; Methodology; Public Policy; Retirement Planning and Satisfaction; Social Security

Imperfect Knowledge of Pension Plan Type - Alan L Gustman; Thomas L. Steinmeier; N. Tabatabai (NBER Working Paper, 2007)
This paper investigates the reasons for discrepancies between the pension plan type reported by respondents to the Health and Retirement Study (HRS) and pension plan type obtained from documents produced by their employers, called Summary Plan Descriptions (SPDs). The analysis suggests the discrepancies are sizable and are mainly due to misreports by respondents. Discrepancies between respondent and firm reports of plan type are first documented for different years and from different data sources. Changes over time in respondent and firm reports are analyzed for those who say their plans did not change. Plan type from payroll data produced by Watson Wyatt, a pension consulting company, is examined and compared to respondent reports for employees covered by Watson Wyatt plans. The Watson Wyatt payroll data report plan type without error, and yet we find the patterns of discrepancies between respondent and firm provided data are the same as for the HRS employer and respondent data. We also explore other evidence gathered by the HRS in the course of interviews and various experiments. Our findings that errors are mainly the result of misreporting by respondents, together with findings from experiments, suggest a number of changes in survey design that can help to reduce reporting error. They also suggest that models of retirement and saving behavior should allow for imperfect knowledge by decision makers.
Keywords: Methodology; Pensions

Living Rationally Under the Volcano? An Empirical Analysis of Heavy Drinking and Smoking - Arcidiacono, Peter; Sieg, Holger; Frank A Sloan (International Economic Review, 2007)
This study investigates whether models of forward-looking behavior explain the observed patterns of heavy drinking and smoking of men in late middle age in the Health and Retirement Study better than myopic models. We develop and estimate a sequence of nested models that differ by their degree of forward-looking behavior. Our empirical findings suggest that forward looking models fit the data better than myopic models. These models also dominate other behavioral models based on out-of-sample predictions using data of men aged 70 and over. Myopic models predict rates of smoking for old individuals, which are significantly larger than those found in the data on elderly men.
Keywords: Health Conditions and Status; Methodology; Risk Taking

Noncoverage and Nonresponse in an Internet Survey - Mick P. Couper; Arie Kapteyn; Matthias Schonlau; Joachim Winter (Social Science Research, 2007)
We explore the correlates of noncoverage and nonresponse in an Internet survey conducted as part of the Health and Retirement Study (HRS), a panel study of persons 50 years old and older in the US. About 30 of HRS respondents indicated they used the Internet. Of these, 73 expressed willingness to do a Web survey. A subset of this group was subsequently sent a mailed invitation to participate in a Web survey and 78 completed the survey. Using multivariate models, we Wnd signiWcant demographic, Wnancial, and health-related diVerences in access, consistent with other research. There are fewer diVerences in willingness (given access) and response (given willingness). However, disparities in health and socio-economic status persist after controlling for demographic diVerences in coverage and response. Weighting on demographics alone is thus unlikely to yield a representative sample in such surveys. Noncoverage (lack of access to the Internet) appears to be of greater concern than nonresponse (unwillingness to participate given access) for representation in Internet surveys of this age group.
Keywords: Methodology

Three Essays on Health Insurance and Health Care Consumption - Liu, Fei (Indiana University, 2007)
The first essay of this dissertation aims to study the decision to enroll in supplementary insurance plans for the Medicare elderly. It also examines the impact of insurance status on several health care utilization measures. The insurance decision and utilization can be influenced by common unobserved attributes, such as attitude toward risks. Therefore, I model medical utilization and insurance choices jointly with a latent factor specification in order to control for unobserved heterogeneity. The estimation method is maximum simulated likelihood. This chapter analyzes a five-wave panel data set derived from the Health and Retirement Study. The empirical results indicate a significant positive relation between supplementary insurance and nights spent in a nursing home, nursing home admission frequency, and hospital admission frequency. The evidence of selection on unobservables is modest. The results also show that supplementary insurance has a negative impact on number of doctor visits in clinics, a measure which excludes doctor contacts made in a hospital or nursing home. In addition, the number of doctor visits exhibits high positive correlation with unobserved heterogeneity. The second essay studies the impact of various supplementary insurance plans on medical expenditures of the Medicare elderly, with a focus on total out-of-pocket expenditure on all kinds of medical services used and out-of-pocket expenditure on prescription drugs. I use quantile regression method and finite mixture models to account for heterogeneity in medical consumption. The empirical results demonstrate the distinct impact of different supplementary insurance plans on health care expenditures. Employer-sponsored supplementary plans have a significant negative impact on total out-of-pocket, and out-of-pocket drug expenditure, relative to individually purchased plans; HMO plans decrease out-of-pocket expenditure significantly relative to other private plans. Quantile regressions show mild variation in the impact of supplementary insurance choices across quantiles. The results from finite mixture models support the hypothesis which assumes the existence of two latent subpopulations. That is, the impact of insurance choice is quite different in the heavy users group and the light users group. The third essay investigates the switching behavior of non-elderly enrollees in U.S. managed care plans. Treatment effect analysis is used to examine the disaggregated expenditures of plan switchers and plan stayers prior to their decision to switch or stay. Propensity score matching methods are used to estimate the average treatment effects on the treated. The results, which are based on a national representative data set from the Medical Expenditure Panel Survey, indicate that switchers (from HMO to non-HMO) spend more on hospitalization. The other type of switchers (from non-HMO to HMO) spends less on prescribed medicine and office-based physician visits. The findings suggest that the non-HMO private managed care plans provide better coverage on hospitalization, office-based physician visits and prescribed medicine than the HMO plans.
Keywords: Health Conditions and Status; Healthcare; Medicare/Medicaid/Health Insurance; Methodology

What Level of Alcohol Consumption Is Hazardous for Older People? Functioning and Mortality in U.S. and English National Cohorts - Iain A Lang; Jack M. Guralnik; Robert B Wallace; David Meltzer (Journal of the American Geriatrics Society, 2007)
OBJECTIVES: To estimate disability plus mortality risks in older people according to level of alcohol intake. DESIGN: Two population-based cohort studies. SETTING: The Health and Retirement Study (United States) and the English Longitudinal Study of Aging (England). PARTICIPANTS: Thirteen thousand three hundred thirtythree individuals aged 65 and older followed for 4 to 5 years. MEASUREMENTS: Difficulties with activities of daily living (ADLs), instrumental activities of daily living (IADLs), poor cognitive function, and mortality. RESULTS: One-tenth (10.8 ) of U.S. men, 28.6 of English men, 2.9 of U.S. women, and 10.3 of English women drank more than the U.S. National Institute on Alcohol Abuse and Alcoholism recommended limit for people aged 65 and older. Odds ratios (ORs) of disability, or disability plus mortality, in subjects drinking an average of more than one to two drinks per day were similar to ORs in subjects drinking an average of more than none to one drink per day. For example, those drinking more than one to two drinks per day at baseline had an OR of 1.0 (95 confidence interval (CI)50.8 1.2) for ADL problems, 0.7 (95 CI50.6 1.0) for IADL problems, and 0.8 (95 CI5 0.6 1.1) for poor cognitive function. Findings were robust across alternative models. The shape of the relationship between alcohol consumption and risk of disability was similar in men and women. CONCLUSION: Functioning and mortality outcomes in older people with alcohol intakes above U.S. recommended levels for the old but within recommendations for younger adults are not poor. More empirical evidence of net benefit is needed to support screening and intervention efforts in community-living older people with no specific contraindications who drink more than one to two drinks per day.
Keywords: Cross-National; Health Conditions and Status; Methodology

Consumption and Economic Well-Being at Older Ages: Income- and Consumption-Based Poverty Measures in the HRS - Michael D Hurd; Susann Rohwedder (RAND Working Paper, 2006)
According to economic theory, well-being or utility depends on consumption. However, at the household level, total consumption is rarely well measured because its collection requires a great deal of survey time. As a result income has been widely used to assess well-being and poverty rates. Yet, because households can use wealth to consume more than income, so an income-based measure of well-being could yield misleading results for many households. We use data from the Health and Retirement Study to find income-based poverty rates which we compare with poverty rates as measured in the Current Population Survey. We use HRS consumption data to calculate a consumption-based poverty rate and study the relationship between income-based and consumption-based poverty measures. We find that a poverty rate based on consumption is lower than an income-based poverty rate. Particularly noteworthy is the much lower rate among the oldest single persons such as widows. The explanation for the difference is the ability to consume out of wealth.
Keywords: Consumption and Savings; Health Conditions and Status; Income; Methodology

Development and Validation of a Prognostic Index for 4-year Mortality in Older Adults - Sei J. Lee; Lindquist, Karla; Mark Segal; Kenneth E Covinsky (Journal of the American Medical Association, 2006)
Context: Both comorbid conditions and functional measures predict mortality in older adults, but few prognostic indexes combine both classes of predictors. Combining easily obtained measures into an accurate predictive model could be useful to clinicians advising patients, as well as policy makers and epidemiologists interested in risk adjustment. . Objective To develop and validate a prognostic index for 4-year mortality using information that can be obtained from patient report. . Design, Setting, and Participants Using the 1998 wave of the Health and Retirement Study (HRS), a population-based study of community-dwelling US adults older than 50 years, we developed the prognostic index from 11 701 individuals and validated the index with 8009. Individuals were asked about their demographic characteristics, whether they had specific diseases, and whether they had difficulty with a series of functional measures. We identified variables independently associated with mortality and weighted the variables to create a risk index. Main Outcome Measure Death by December 31, 2002. Results: The overall response rate was 81 . During the 4-year follow-up, there were 1361 deaths (12 ) in the development cohort and 1072 deaths (13 ) in the validation cohort. Twelve independent predictors of mortality were identified: 2 demographic variables (age: 60-64 years, 1 point; 65-69 years, 2 points; 70-74 years, 3 points; 75-79 years, 4 points; 80-84 years, 5 points, 85 years, 7 points and male sex, 2 points), 6 comorbid conditions (diabetes, 1 point; cancer, 2 points; lung disease, 2 points; heart failure, 2 points; current tobacco use, 2 points; and body mass index 25, 1 point), and difficulty with 4 functional variables (bathing, 2 points; walking several blocks, 2 points; managing money, 2 points, and pushing large objects, 1 point. Scores on the risk index were strongly associated with 4-year mortality in the validation cohort, with 0 to 5 points predicting a less than 4 risk, 6 to 9 points predicting a 15 risk, 10 to 13 points predicting a 42 risk, and 14 or more points predicting a 64 risk. The risk index showed excellent discrimination with a c statistic of 0.84 in the development cohort and 0.82 in the validation cohort. Conclusion: This prognostic index, incorporating age, sex, self-reported comorbid conditions, and functional measures, accurately stratifies community-dwelling older adults into groups at varying risk of mortality.
Keywords: Demographics; Health Conditions and Status; Healthcare; Methodology

Disease and Disadvantage in the United States and in England - James Banks; Michael Marmot; Oldfield, Zoë; James P Smith (Journal of the American Medical Association, 2006)
Context The United States spends considerably more money on health care than the United Kingdom, but whether that translates to better health outcomes is unknown. Objective To assess the relative heath status of older individuals in England and the United States, especially how their health status varies by important indicators of socioeconomic position. Design, Setting, and Participants We analyzed representative samples of residents aged 55 to 64 years from both countries using 2002 data from the US Health and Retirement Survey (n=4386) and the English Longitudinal Study of Aging (n=3681), which were designed to have directly comparable measures of health, income, and education. This analysis is supplemented by samples of those aged 40 to 70 years from the 1999-2002 waves of National Health and Nutrition Examination Survey (n=2097) and the 2003 wave of the Health Survey for England (n=5526). These surveys contain extensive and comparable biological disease markers on respondents, which are used to determine whether differential propensities to report illness can explain these health differences. To ensure that health differences are not solely due to health issues in the black or Latino populations in the United States, the analysis is limited to non-Hispanic whites in both countries. Main Outcome Measure Self-reported prevalence rates of several chronic diseases related to diabetes and heart disease, adjusted for age and health behavior risk factors, were compared between the 2 countries and across education and income classes within each country. Results The US population in late middle age is less healthy than the equivalent British population for diabetes, hypertension, heart disease, myocardial infarction, stroke, lung disease, and cancer. Within each country, there exists a pronounced negative socioeconomic status (SES) gradient with self-reported disease so that health disparities are largest at the bottom of the education or income variants of the SES hierarchy. This conclusion is generally robust to control for a standard set of behavioral risk factors, including smoking, overweight, obesity, and alcohol drinking, which explain very little of these health differences. These differences between countries or across SES groups within each country are not due to biases in self-reported disease because biological markers of disease exhibit exactly the same patterns. To illustrate, among those aged 55 to 64 years, diabetes prevalence is twice as high in the United States and only one fifth of this difference can be explained by a common set of risk factors. Similarly, among middleaged adults, mean levels of C-reactive protein are 20 higher in the United States compared with England and mean high-density lipoprotein cholesterol levels are 14 lower. These differences are not solely driven by the bottom of the SES distribution. In many diseases, the top of the SES distribution is less healthy in the United States as well. Conclusion Based on self-reported illnesses and biological markers of disease, US residents are much less healthy than their English counterparts and these differences exist at all points of the SES distribution.
Keywords: Cross-National; Health Conditions and Status; Methodology

The Effect of Unfolding Brackets on the Quality of Wealth Data in HRS - Juster, F. Thomas; Cao, Honggao; Michael M. Perry; Mick P. Couper (The University of Michigan, Michigan Retirement Research Center, 2006)
A characteristic feature of survey data on household wealth is the high incidence of missing data roughly one in three respondents who report owning an asset are unable or unwilling to provide an estimate of the exact amount of their holding. A partial solution to that problem is to devise a series of questions that put the respondent s holdings into a quantitative range (less than x, more than x, or what?). These quantitative ranges are called unfolding brackets, and they represent a survey innovation that aims to improve the quality of wealth data by substituting range data for completely missing data. In this paper, we examine the effect of unfolding brackets on the quality of HRS wealth data. Special attention is given to the impact of unfolding bracket entry points on the distribution of asset holdings in HRS 1998. Although there is a small positive relationship between mean asset holdings and entry point, there are many cases where that relationship does not hold. In general, our conclusion is that entry point bias problems are not a major concern in the evaluation of quality in the 1998 HRS wealth data.
Keywords: Methodology; Net Worth and Assets

Effects of Attrition and Non-Response in the Health and Retirement Study - Arie Kapteyn; Pierre-Carl Michaud; James P Smith; Arthur H.O. vanSoest (IZA Discussion Paper Series, 2006)
We study the effect of attrition and other forms of non-response on the representativity over time of the Health and Retirement Study (HRS) sample born 1931-1941; the sample was initially drawn in 1992. Although some baseline characteristics of respondents do appear correlated with non-response over time, the 2002 sample of respondents does not appear to suffer significantly from selection on observables, except for race and ethnicity; for these two observables, longitudinal weights based on the Current Population Survey (CPS) can be used and are provided with the data set. We attribute this lack of selection to the fact that attritors who differ most eventually come back to the survey in waves prior to 2002. Although this allows cross-sections to remain fairly representative in later waves, it suggests that longitudinal analysis should use the unbalanced sample rather than the balanced sample of those interviewed in all waves. Individuals who attrit but who are recruited back into the survey are very different from those who are permanent attritors to the HRS. Finally, we investigate the selective nature of the decision of respondents to grant HRS permission to access their Social Security records and of the non-response introduced by employers of pension policyholders not providing HRS with worker's Summary Plan Descriptions. We find that subsamples for which such information is available are selective on a number of dimensions, such as education and other socioeconomic status (SES) outcomes.
Keywords: Methodology

Health Insurance Coverage and the Risk of Decline in Overall Health and Death Among the Near Elderly, 1992-2002 - David W. Baker; Joseph J Sudano; Durazo-Arvizu, Ramon; Joseph Feinglass; Whitney P. Witt; Jason A. Thompson (Medical Care, 2006)
Background: Although individuals' health insurance coverage changes frequently, previous analyses have not accounted for changes in insurance coverage over time. . Objective: We sought to determine the independent association between lack of insurance and the risk of a decline in self-reported overall health and death from 1992 to 2002, accounting for changes in self-reported overall health and insurance coverage. .Methods: We analyzed data from the Health and Retirement study, a prospective cohort study of a national sample of community-dwelling adults age 51-61 years old at baseline. Major decline in self-reported overall health and mortality was determined at 2-year intervals. . Results: People who were uninsured at baseline had a 35 (95 confidence interval CI 12-62 ) higher risk-adjusted mortality from 1992 to 2002 compared with those with private insurance. However, when we analyzed outcomes over 2-year intervals, individuals who were uninsured at the start of each interval were more likely to have a major decline in their overall health (pooled adjusted relative risk 1.43, 95 CI 1.28-1.63), but they were equally likely to die (pooled adjusted relative risk 0.96, 95 CI 0.73-1.27). Of the 1512 people who were uninsured at baseline, 220 (14.6 ) died; of those who died, only 70 (31.8 ) were still uninsured at the HRS inter-view prior to death. Conclusions: Death does not appear to be a short-term consequence of being uninsured. Instead, higher long-term mortality among the uninsured results from erosion in this population's health status over time and the attendant higher mortality associated with this. Most deaths among the uninsured occur after individuals have gained either public or private health insurance.
Keywords: Health Conditions and Status; Healthcare; Medicare/Medicaid/Health Insurance; Methodology; Other

His and Her Marriage Today: The impact of wives' employment on husbands' later mid-life health - Kristen W Springer (The University of Wisconsin - Madison, 2006)
Marriage is a highly gendered institution with expectations, norms, and resources organized through gender relations. The short-lived, though idealized, 1950s' notion of the "male breadwinner" solidified men's power in marriage through economic contributions from paid employment. However, the last several decades have witnessed an explosion of wives entering the labor market, all but demolishing the reality of the male breadwinner. This dissertation situates itself in this historical context to explore how wives' employment affects husbands' health. By combining gender literature on the breadwinner role with health inequalities literature, this dissertation utilizes feminist theories to contextualize men's health while at the same time using health as a heuristic to examine gender inequality and gender relations in marriage. I analyze longitudinal data on married couples from the Health and Retirement Study (HRS) to find strong evidence that a wife's employment impacts a husband's health only when he fails to achieve the normative prescription of the family breadwinner---supporting what I've termed the changing gendered-norms model. I found no support for the predominant sociological explanation that a wife's employment harms a husband's health because it limits her time available for caregiving. The starving hearts model which posits ill health effects of the social and financial burden associated with breadwinning also failed to explain the relationship between wives' employment and husbands' health. Further exploration of mechanisms driving the changing gendered-norms model did not support standard marital relations explanations including the economic resource mechanism and the marital dissatisfaction mechanism. In other words, husbands' health is not harmed because high earning wives exercise power in marital decisions nor is husbands' health harmed because economically dependent husbands are dissatisfied with their marriages. Rather, the results indicate that a husband's economic dependency adversely impacts his health through a masculinity threat resulting from having a primary breadwinning wife. These results underscore that gender inequality and ideological norms that privilege men are the sources of husbands' ill health associated with wives' employment. Social policies designed to dismantle the male breadwinner ideology and support combining home with work could improve women's social status while enhancing men's health.
Keywords: Adult children; Demographics; Health Conditions and Status; Methodology; Women and Minorities

Moral Hazard, Adverse Selection and Health Expenditures: A semiparametric analysis - Bajari, Patrick; Hong, Han; Ahmed Khwaja (Cambridge, MA, National Bureau of Economic Research, 2006)
Theoretical models predict asymmetric information in health insurance markets may generate inefficient outcomes due to adverse selection and moral hazard. However, previous empirical research has found it difficult to disentangle adverse selection from moral hazard in health care. We empirically study this question by using data from the Health and Retirement Study to estimate a structural model of the demand for health insurance and medical care. Using a two-step semi-parametric estimation strategy we find significant evidence of moral hazard, but not of adverse selection.
Keywords: Medicare/Medicaid/Health Insurance; Methodology

A New National Retirement Risk Index - Alicia H. Munnell; Anthony Webb; Delorme, Luke (Center for Retirement Research at Boston College, 2006)
Americans weaned on post-war affluence have come to expect an extended period of leisure at the end of their work life. And, indeed, the majority of today s retirees are able to afford a decent retirement. However, this group is living in a golden age that will fade as Baby Boomers and Generation Xers reach traditional retirement ages in the coming decades. This gloomy prediction reflects the trend towards longer retirements and likely declines in retirement incomes relative to pre-retirement earnings known as replacement rates. Because many Americans appear unaware of these disquieting trends, the Center for Retirement Research at Boston College has developed the National Retirement Risk Index. The Index measures the share of working-age households who are at risk of being unable to maintain their pre-retirement standard of living in retirement.
Keywords: Methodology; Public Policy; Retirement Planning and Satisfaction

Population Impact of Arthritis on Disability in Older Adults - Song, Jing; Rowland W Chang; Dorothy D Dunlop (Arthritis and Rheumatism, 2006)
Objective. Disability threatens the independence of older adults and has large economic and societal costs. This article examines the population impact of arthritis on disability incidence among older Americans. Methods. The present study used longitudinal data (1998 2000) from the Health and Retirement Study, a national probability sample of elderly Americans. Disability was defined by the inability to perform basic activities of daily living (ADL). A total of 7,758 participants ages 65 years with no ADL disability at baseline were included in the analyses. Multiple logistic regression was used to measure the impact of baseline arthritis (self reported) on incidence of subsequent ADL disability after controlling for baseline differences in demographics, health factors, health behaviors, and medical access. Results. Older adults who had baseline arthritis had a substantially higher incidence of ADL disability compared with those without arthritis (9.3 versus 4.5 ). The strong relationship of arthritis and ADL disability was partially explained by demographic, health, behavioral, and medical access factors. However, even after adjusting for all other risk factors, arthritis remained as an independent and significant predictor for developing ADL disability (adjusted odds ratio 1.5, 95 confidence interval 1.2 1.8). Almost 1 in every 4 new cases of ADL disability was due to arthritis (adjusted population attributable fraction: 23.7 ). Conclusion. The high frequency of incident ADL disability attributable to arthritis points to the importance of intervention programs that address the entire spectrum of health and functional problems in persons with arthritis to prevent disability.
Keywords: Disabilities; Health Conditions and Status; Methodology

Probabilistic Thinking and Early Social Security Claiming - Delavande, Adeline; Michael M. Perry; Robert J. Willis (The University of Michigan, Michigan Retirement Research Center, 2006)
This study analyzes the extent to which an individual.s survival expectations influence his or her decision to claim social security benefits at an early age. We find that subjective survival probabilities capture meaningful behavioral responses to incentives for early Social Security claiming when they are purged of measurement error using risk factors as instruments. Among people who are still working at age 62, those who expect to live longer are likely to delay claiming of Social Security benefits to a degree that is both statistically and economically significant.
Keywords: Methodology; Retirement Planning and Satisfaction; Social Security

State Fiscal Institutions and Empty-Nest Migration: Are Tiebout voters hobbled? - Martin P. Farnham; Purvi Sevak (Journal of Public Economics, 2006)
Using the Health and Retirement Study and a national panel of local fiscal data, we test a lifecycle model of Tiebout sorting. On average, cross-state, empty-nest movers-presumed to be out of fiscal equilibrium-experience large fiscal gains in the form of reduced exposure to local school spending and property taxes, while local empty-nest movers experience no fiscal adjustment. We find evidence that within-state fiscal adjustment is constrained by state institutions that limit local discretion. Empty-nest households moving within states with school finance equalization do not engage in Tiebout-consistent fiscal adjustment, while those moving within states lacking school finance equalization adjust substantially. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Demographics; Methodology; Public Policy

Three Essays in Public Economics - Wu, Binzhen (The University of Wisconsin - Madison, 2006)
The first essay uses the policy changes surrounding the 1992 Amendments to the Higher Education Act (HEA92) to examine the effects that the implicit financial-aid tax has on household saving behavior, particularly on portfolio choices. The empirical results show that the financial-aid tax does not significantly affect the total level of wealth. However, families significantly adjust their portfolio composition to avoid the tax. In addition, families seem to lack knowledge about financial-aid rules if they have not experienced with the financial-aid applications. Even if families know the rules, they do not change assets in response to the financial-aid tax if they face no imminent taxation. This second essay uses the policy changes surrounding the 1992 Amendments to the Higher Education Act (HEA92) to examine the reasons for which families have borrowed much more after the HEA92 increased the loan limits on subsidized and unsubsidized student loans. I find that the loan-limit changes do not significantly affect education investments. However, families significantly reduce some other financial instruments used to finance students' higher education, including loans from parents, parents' direct contributions, working while in school, and work-study aid. The third essay uses the Health and Retirement Study to study the effects of group health insurance on women's retirement decisions. I find the availability of alternative group health insurance, including retiree health insurance and spousal health insurance, significantly increases the retirement hazard and decreases retirement age for women. Married women are much more sensitive to the availability of spousal health insurance than to retiree health insurance. Medicare also has significant effect on women' retirement behavior.
Keywords: Consumption and Savings; Medicare/Medicaid/Health Insurance; Methodology; Net Worth and Assets

Three Essays on Health and Aging - Olsho, Lauren E.W. (The University of Wisconsin - Madison, 2006)
This dissertation consists of three essays exploring the interface between health, aging, and economic behavior. The first essay explores the influence of declining health on consumption behavior with age. I solve a life-cycle model treating health as a form of human capital, and predict substantial decreases in consumption after age 50 consistent with observed declines for individuals in the Health and Retirement Study, 1992-2002. When health and consumption are complements, decreasing health capital results in falling marginal utility of consumption with age. Thus rational agents will consume at higher levels when they are younger and healthier. Since lower wealth groups generally experience more rapid health deterioration, this model largely accounts for the divergence in life-cycle consumption patterns across asset quartiles in the United States. The second essay investigates the contribution of population aging to trends in chronic conditions in the United States in the past decade and a half. I apply direct standardization to data on high cholesterol, hypertension, and obesity from the National Health and Nutrition Examination Surveys to adjust for changes in the population distribution of age, sex, race/ethnicity, poverty-income ratio, and educational status. I find that the influence of population aging, while important, is often smaller in magnitude than the effects of population shifts in other sociodemographic variables. The third essay considers the impact of a training program for health care workers in the assisted-living industry. Using repeated cross-section data on direct care workers in Wisconsin assisted-living facilities collected prior to and following the advent of the Worker Education Training and Assistance Program, and licensing data obtained from the Wisconsin Department of Health and Human Services, I investigate the effects of training on the wages of program participants and on quality of care in participating facilities, using a difference-in-differences framework with propensity scoring to control for the fact that the decision to participate in the WETA program was non-random. Worker wages increased marginally after training, but the quality of care decreased. Anecdotal evidence suggests that participating workers were systematically promoted out of the direct-care positions in which they had the most influence on quality of care.
Keywords: Health Conditions and Status; Methodology

Activities of Daily Living and Cardiovascular Risk Factors' Impact on Cardiovascular Disease (CVD) and Cognitive Functioning: A three stage longitudinal model - Bozo, Ozlem (University of North Texas - Fort Worth, 2005)
The purpose of this study was to examine the longitudinal relationship of activities of daily living (ADL), cardiovascular risk factors, and cardiovascular diseases, to predict the future cognitive functioning of older Americans who are between the ages of 51 and 61 at the time of initial assessment. Three waves of the Health and Retirement Study (HRS) database between the years of 1992 and 2002 were examined with path analysis. The longitudinal hypotheses of the study were that 1) ADLs would positively predict future cognitive functioning, 2) ADLs would negatively predict future cardiovascular risk factors, 3) ADLs would negatively predict future cardiovascular diseases, 4) cardiovascular risk factors would positively predict cardiovascular diseases, 5) cardiovascular risk factors would negatively predict future cognitive functioning, 6) cardiovascular disease would negatively predict future cognitive functioning, 7) cardiovascular risk factors would mediate the relationship between ADLs and cardiovascular disease, and 8) cardiovascular disease would mediate the relationship between cardiovascular risk factors and cognitive functioning. The results of the analyses indicate that there was no effect of cardiovascular disease on cognitive functioning; however, there were significant effects of cardiovascular risk factors on cognitive functioning that ranged between -.021 and -.145. Moreover, it was found that cardiovascular risk factors mediate the relationship between ADLs and cognitive functioning, while cardiovascular disease does not. These results suggest that addressing cardiovascular risk factors may be more important than addressing existing cardiovascular disease to protect future cognitive functioning. This shows the importance of primary/secondary prevention versus tertiary interventions.
Keywords: Health Conditions and Status; Methodology; Risk Taking

Are Traditional Retirements a Thing of the Past? New Evidence on Retirement Patterns and Bridge Jobs - Kevin E. Cahill; Michael D. Giandrea; Joseph F. Quinn (Washington, DC, U.S. Department of Labor, Bureau of Labor Statistics, 2005)
Purpose: This paper investigates whether permanent, one-time retirements are coming to an end just as the trend towards earlier and earlier retirements did nearly 20 years ago. We explore how common bridge jobs are among today s retirees, and how uncommon traditional retirements have become. Methods: Using data from the Health and Retirement Study (HRS), we explore the work histories and retirement patterns of a cohort of retirees aged 51 to 61 in 1992 over a ten-year time period in both a cross-sectional and longitudinal context. Bridge job determinants are examined using bivariate comparisons and a multinomial logistic regression model of the bridge job decision. Results: We find that one-half to two-thirds of the HRS respondents with full-time career jobs take on bridge jobs before exiting the labor force completely. We also find that bridge job behavior is most common among younger respondents, respondents without defined-benefit pension plans, and respondents at the lower- and upper-end of the wage distribution. Implications: The evidence suggests that changes in the retirement income landscape since the 1980s appear to be taking root. Going forward, traditional retirements will be the exception rather than the rule.
Keywords: Employment and Labor Force; Methodology; Retirement Planning and Satisfaction

Discussion of Li Gan, Michael Hurd and Daniel McFadden, Individual Subjective Survival Curves - Robert J. Willis (Analyses in the Economics of Aging, 2005)
Keywords: Expectations; Methodology

Do Panel Surveys Make People Sick? U.S. Arthritis Trends in the Health and Retirement Study - Sven E. Wilson; Benjamin L. Howell (Social Science and Medicine, 2005)
Researchers have long viewed large, longitudinal studies as essential for understanding chronic illness and generally superior to cross-sectional studies. In this study, we show that (1) age-specific arthritis prevalence in the longitudinal Health and Retirement Study (HRS) from the United States has risen sharply since its inception in 1992, and (2) this rise is almost surely spurious. In periods for which the data sets are comparable, we find no such increase in the crosssectional National Health Interview Survey (NHIS), the primary source for prevalence data of chronic conditions in the US. More important, the upward trend in the HRS is not internally consistent: even though prevalence in the HRS rises sharply between 1992 and 1996 for 55 56 year-olds, the prevalence for that age group plummets to its 1992 level among the new cohort added in 1998 and then rises rapidly again between 1998 and 2002. We discuss possible reasons for these discrepancies and demonstrate that they are not due to sample attrition in the HRS.
Keywords: Health Conditions and Status; Methodology

Documentation of Chronic Disease Measures in the Health and Retirement Study - Gwenith G Fisher; Jessica Faul; David R Weir; Robert B Wallace (Institute for Social Research, University of Michigan, 2005)
The focus of this report is on (1) self-rated overall health status and recent changes in overall health, (2) the presence of common chronic medical conditions and follow-up questions concerning treatments in all waves of the core HRS/AHEAD through 2002.
Keywords: Health Conditions and Status; Healthcare; Methodology

Documentation of Cognitive Functioning Measures in the Health and Retirement Study - Mary Beth Ofstedal; Gwenith G Fisher; A. Regula Herzog (Institute for Social Research, University of Michigan, 2005)
Keywords: Health Conditions and Status; Methodology

Enhancing the Quality of Data on Income and Wealth - Cao, Honggao; Daniel H. Hill; Juster, F. Thomas; Michael M. Perry (The University of Michigan, Michigan Retirement Research Center, 2005)
Over the last decade or so, a substantial effort has gone into the design of a series of methodological investigations aimed at enhancing the quality of survey data on income and wealth. These investigations have largely been conducted at the Survey Research Center at the University of Michigan, and have mainly involved two longitudinal surveys: the Health and Retirement Study (HRS), with a first wave beginning in 1992 and continued thereafter every other year through 2004; and the Assets and Health Dynamics Among the Oldest Old (AHEAD) Study, begun in 1993 and continued in 1995 and 1998, then in every other year through 2004. This provides and overview of the main studies and summarizes what has been learned about correcting longitudinal inconsistencies that arise.
Keywords: Income; Methodology; Net Worth and Assets

Essays in the Economics of Aging - Gottschalk, Lynn Marie (University of Illinois at Urbana-Champaign, 2005)
The three chapters of my dissertation consider various aspects of the economics of aging. Understanding the issues facing older people is important as the number of Americans over the age of 50 is growing and will continue to grow in the next decade. A particularly important issue among older workers is the rising divorce rates. Chapter One examines divorcee's retirement behavior and Chapter Two studies the effect of divorce on social service participation. Health insurance is also a major concern of older workers and Chapter Three examines the effect of Employer Provided Health Insurance (EPHI) on worker mobility. Divorce is particular concern, as the divorce rate increased 80% between 1980 and 2000 among people over the age of 50. This study uses a difference-in-difference strategy to determine the effect of divorce on retirement age in a sample of workers from the Health and Retirement Study(HRS). The results in Chapter One indicate male divorcees retire earlier and female divorcees delay retirement. For both men and women, remarriage eliminates divorce's effect. Additional results demonstrate that divorce's effect operates through both changes in household wealth and changes in preferences for leisure and retirement. Because divorce causes a decrease in household wealth, the increase in older divorcees may cause an increase in the number of older people relying on social services. Chapter Two uses data from the HRS to determine the effect of divorce on both eligibility and participation in Supplemental Security Income(SSI) and Medicaid. The results indicate that divorce greatly increases eligibility and participation in both programs. The final issue addressed in the paper is the reduction in job mobility caused by a person receiving health insurance through an employer. Previous studies have tried to determine whether EPHI reduces job mobility. However, these studies provide conflicting evidence on the significance and magnitude of job-lock. Chapter Three uses data from the HRS to show the degree to which omitted variable bias and misidentified workers effect job-lock measures and explain previous studies' differing results. With a full set of controls and controls for endogeneity, I find a mobility reduction of 20%.
Keywords: Adult children; Income; Medicare/Medicaid/Health Insurance; Methodology

Essays on Intergenerational Transfers in Older Families - Azuma, Misuzu (The University of Wisconsin - Madison, 2005)
In a series of three essays, I examine intergenerational transfers between elderly parents and their adult children. In the first chapter, I examine the extent to which informal care from family members substitutes for nursing home care. I build a model of families' care decisions for their elderly relatives. My model predicts that nursing home admission is postponed for elderly persons with greater access to informal care. It also predicts that elderly individuals with greater access to informal care enter nursing homes only after their care needs become more severe. To test the predictions of my model, I use data from the 1993-2000 waves of the Assets and Health Dynamics Among the Oldest Old (AHEAD) study. I find that elderly individuals who are married and have more daughters enter nursing homes significantly later. I also find that elderly individuals who are married and are living with their adult children before nursing home entry face significantly higher mortality risk subsequent to nursing home entry. In the second chapter, I examine whether the generosity of the public transfer program for low-income elderly persons, Supplemental Security Income (SSI), displaces private support from family members in the form of coresidence. I use data from the first wave of the AHEAD study. My findings indicate that a $1,000 increase in SSI annual benefits reduces the probability of coresidence by 0.41 percent, implying a small effect of the SSI program on coresidence for the low-income elderly individuals. In the third chapter, coauthor Professor Meta Brown and I examine the motives for holding a trust, using data from the 1995-2002 waves of the Health and Retirement Study. We argue that among households with living trusts, 83 percent of living trusts are created to avoid a probate. We find that few households that are subject to federal estate tax take advantage of living trusts to minimize the estate tax. We also find that among households with estate trusts, 70 percent of estate trusts are created to restrict consumption pattern of the surviving spouse and to guarantee that assets are transferred to their adult children.
Keywords: Adult children; Employment and Labor Force; Healthcare; Methodology

Estimating Age Change in List Recall in Asset and Health Dynamics of the Oldest Old: Attrition bias and missing data treatment - Robert F. Kennison; Elizabeth Zelinski (Psychology and Aging, 2005)
Average change in list recall was evaluated as a function of missing data treatment (Study 1) and dropout status (Study 2) over ages 70 to 105 in Asset and Health Dynamics of the Oldest-Old data. In Study 1 the authors compared results of full-information maximum likelihood (FIML) and the multiple imputation (MI) missing-data treatments with and without independent predictors of missingness. Results showed declines in all treatments, but declines were larger for FIML and MI treatments when predictors were included in the treatment of missing data, indicating that attrition bias was reduced. In Study 2, models that included dropout status had better fits and reduced random variance compared with models without dropout status. The authors conclude that change estimates are most accurate when independent predictors of missingness are included in the treatment of missing data with either MI or FIML and when dropout effects are modeled.
Keywords: Health Conditions and Status; Methodology

HRS 2001 HUMS College Tuition Imputations - Cao, Honggao; John C Henretta; Norgard, T.M.; Beth J Soldo; David R Weir (Institute for Social Research, University of Michigan, 2005)
HRS 2001 Off-Year Mail Survey on Human Capital Investment (HRS 2001 HUMS) collected important information on the education of HRS respondents children. Among other things, the survey asked a selected set of HRS respondents to provide information about whether a child attended a two- or four-year undergraduate college, the total number of years in college(s), his or her age when he or she last attended college, and the name of the college that he or she last attended. One way to use the information is to produce college tuition data associated with each child, which can then be linked in an integrated analysis of family transfer with other family transfer information collected in the HRS core survey. In this document we describe what we have done in imputing HRS 2001 HUMS college tuitions. The general idea is to link the children college attendance information in HRS 2001 HUMS with a college tuition database (CASPAR) created and administered by the National Science Foundation. For 2000 and 2001, college cost data are also taken from the NCES IPEDS online database.
Keywords: Consumption and Savings; Methodology; Net Worth and Assets

Identification of Probability Distributions with Misclassified Data - Molinari, Francesca (CAE Working Paper, 2005)
This paper addresses the problem of data errors in discrete variables. When data errors occur, the observed variable is a misclassified version of the variable of interest, whose distribution is not identified. For many years econometricians have conceptualized the problem through convolution and mixture models. This paper introduces the direct misclassification approach. The approach is based on the observation that in the presence of classification errors, the relation between the distribution of the true but unobservable variable and its misclassified representation is given by a linear system of simultaneous equations, in which the coe.cient matrix is the matrix of misclassification probabilities. Formalizing the problem in these terms allows one to incorporate any prior information - e.g., validation studies, economic theory, social and cognitive psychology, or knowledge of the circumstances under which the data have been collected - into the analysis through sets of restrictions on the matrix of misclassification probabilities. Such information can have strong identifying power; the direct misclassification approach fully exploits it to derive identification regions for any real functional of the distribution of interest. The method readily extends to drawing inference on parameters of the conditional distribution of an outcome variable when the conditioning variable is misclassified. It is easy to implement and often computationally tractable. A method for estimating the identification regions is given, and illustrated with an empirical analysis of the distribution of pension plan types using data from the Health and Retirement Study.
Keywords: Methodology

Institutions and Saving for Retirement: Comparing the United States, Italy, and the Netherlands - Arie Kapteyn; Panis, Constantijn (Analyses in the Economics of Aging, 2005)
This paper analyzes retirement saving and portfolio choice in the United States, Italy, and the Netherlands. In addition to relying on public retirement provisions, households prepare for retirement through tax-sheltered and after-tax savings. They may invest these funds in a wide variety of assets, including housing, stocks, bonds, savings accounts, and so on. These asset types differ in their risk, return, and liquidity characteristics as well as in their fiscal treatment. Economic theory postulates that housholds allocate their portfolios according to their risk aversion, time horizon, uncertain out-of-pocket medical expenditures, income risk, informal (family) risk-sharing arrangements, and more. While the literature has tested various parts of the theory, both testing and quantification of the theory are hampered by the fact that some of the major variables do not exhibit sufficient variation within a country to establish their relative importance for portfolio choice, or, more generally, for retirement saving and investment. This paper partially fills that gap by exploring three countries with widely varying institutional arrangements for retirement income.
Keywords: Consumption and Savings; Methodology

Integrating Biology into the Study of Health Disparities - Eileen M. Crimmins; Teresa Seeman (Aging, Health, and Public Policy: Demographic and Economic Perspectives, 2005)
Keywords: Methodology

Knowledge and Preference in Reporting Financial Information - Cao, Honggao; Daniel H. Hill (Michigan Retirement Research Center Publication, 2005)
This article models respondent behavior in a financial survey with a framework explicitly integrating a respondent s knowledge of and willingness to reveal his or her financial status. Whether a respondent provides a valid answer, a don t know , or a refusal to a financial question depends on the interaction of his or her financial knowledge and preferences regarding revealing the knowledge. Using asset response and nonresponse data from the Health and Retirement Study (2000), we found that knowledge and preferences play interrelated roles in reporting financial information, that a respondent s age, gender, education, and race and ethnicity are important predictors of respondent behavior, and that race and ethnicity affect a respondent behavior only via their influence on preferences, while gender only via its influence on knowledge. We also found strong heterogeneity in respondents financial knowledge and their willingness to reveal the knowledge.
Keywords: Methodology

The Social Security Early Entitlement Age In A Structural Model of Retirement and Wealth - Alan L Gustman; Thomas L. Steinmeier (Journal of Public Economics, 2005)
A structural life cycle model of retirement and wealth attributes retirement peaks at both ages 62 and 65 to Social Security rules and wide heterogeneity in time preferences. Those with high discount rates often retire at 62. They have few assets and heavily value lost benefits from working after 62, largely ignoring potential increases in later benefits. Declining actuarial adjustments beginning at 65 induce those with low discount rates to retire at 65. Raising the Social Security early entitlement age to 64 induces 5 of the population to delay retiring, shifting the retirement spike from 62 to 64.
Keywords: Methodology; Net Worth and Assets

Survey Design and Methodology in the Health and Retirement Study and the Wisconsin Longitudinal Study - Hauser, Robert M.; Robert J. Willis (Aging, Health and Public Policy: Demographic and Economic Perspectives, 2005)
Large-scale data collection has become the kernel of the growth of knowledge in the social sciences. Nowhere is this more evident than in research in the demography of aging and the life course, where scientific progress has been stimulated and sustained by complementary longitudinal studies of aging populations. In this chapter, we review the history, organization, and design of two of these public resources, the Wisconsin Longitudinal Study (WLS) and the Health and Retirement Study (HRS). Recent innovations in each of these studies hold promise for major advances in knowledge about the demography, economics, sociology, and epidemiology of aging. The stories of the WLS and HRS highlight important clues about the creation of systems of continuing surveys to inform science and public policy.
Keywords: Methodology

Using a Structural Retirement Model to Simulate the Effect of Changes to the OASDI and Medicare Programs - John Bound; Todd R. Stinebrickner; Timothy A Waidmann (Michigan Retirement Research Center Publication, 2005)
In this paper, we specify a dynamic programming model that addresses the interplay among health, financial resources, and the labor market behavior of men in the later part of their working lives. Unlike previous work which has typically used self reported health of disability status as a proxy for health status, we model health as a latent variable, using self reported disability status as an indicator of this latent construct. Our model is explicitly designed to account for the possibility that the reporting of disability may be endogenous to the labor market behavior we are studying. The model is estimated using data from the Health and Retirement Study. We compare results based on our model to results based on models that treat in the typical way, and find large differences in the estimated effect of health on behavior. While estimates based on our model suggest that health has a large impact on behavior, the estimates suggest a substantially smaller role for health than we find when using standard techniques. We use our model to simulate the impact on behavior of raising the normal retirement age, eliminating early retirement altogether, eliminating the Social Security Disability Insurance program and introducing universal health insurance.
Keywords: Employment and Labor Force; Health Conditions and Status; Methodology

Work Disability is a Pain in the , Especially in England, The Netherlands, and the United States - James Banks; Arie Kapteyn; James P Smith; Arthur H.O. vanSoest (RAND Labor and Population Program, 2005)
This paper investigates the role of pain in determining self-reported work disability in the U.S., the U.K. and The Netherlands. Even if identical questions are asked, cross-country differences in reported work disability remain substantial. In the U.S. and the Netherlands, respondent evaluations of work limitations of hypothetical persons described in pain vignettes are used to identify the extent to which differences in self-reports between countries or socio-economic groups are due to systematic variation in the response scales.
Keywords: Disabilities; Methodology

Adjust for Selection Bias in Web Surveys with Propensity Scores: The case of the Health and Retirement Study - Matthias Schonlau; Arthur H.O. vanSoest; Mick P. Couper; Arie Kapteyn; Joachim Winter (Proceedings of the American Statistical Association, 2004)
Many web surveys allow respondents to self select into the survey. Making inference about the population from a self-selected survey is very difficult. We analyzed data from the Health and Retirement Study (HRS) respondents of the 2002 wave as well as supplementary information about which subset of HRS respondents also responded to an additional web survey (web responders). The HRS is a longitudinal study of health, retirement and aging. The target population of the HRS includes all adults in the contiguous United States, aged 51 and over, who reside in households. We investigated whether it is possible to adjust for selection bias using propensity scores. We found that it is possible to make inferences for financial assets based on data from web responders only. However, making inferences about home values was not possible based on data from the web responders only.
Keywords: Methodology

Black-White Mental and Physical Well-Being Following Divorce - Avellar, Sarah A. (University of Michigan, 2004)
Despite the consistent link between divorce and deleterious mental and physical health outcomes, racial variations have been relatively neglected. With divergent socioeconomic statuses, rates of divorce, and other stressors, African-Americans and whites are likely to experience divorce in very different contexts. Racial differences in health outcomes after divorce are often the result of particular constraints and resources, and thus reveal the functioning of social arrangements. I address this issue in three separate but related chapters. In Chapter II, I use five waves of the Health and Retirement Study (HRS) to examine racial differences in divorce outcomes among older people. Today's midlife and elderly cohorts are probably the first to contain a substantial number of divorcees. I model self-rated health, limitations in activities of daily living, other physical limitations, and mortality for 1) the overall sample and 2) a transitioners sample, comprised of respondents who divorce or separate between waves. The results indicate that in the overall sample, divorce affects blacks and whites similarly and negatively, though this is largely accounted for by an individual's wealth. In the transitioners sample, divorce is associated with an improvement in health status, though only for white respondents. In Chapter III, I establish whether the health gap between the divorced and married exists for both blacks and whites. I model self-rated health and depressive symptoms with both waves of the National Survey of Families and Households (NSFH), for a nationally representative sample of all ages. In addition to longitudinal data, I improve on past research by employing multiple estimations of the health gap: ordinary least squares, fixed-effects, and matching models. The results suggest that both blacks and whites experience an increase in depressive symptoms after divorce, but the results for self-rated health are inconsistent and weak. The last analytic chapter, Chapter IV, is an examination of whether other factors can account for the heightened depressive symptoms associated with divorce. Again using the NSFH, I include sociodemographic, psychological, social, and relationship variables in OLS models. For both blacks and whites, the heightened distress can be accounted for by employment, worries about income, and having moved.
Keywords: Adult children; Demographics; Health Conditions and Status; Healthcare; Methodology

Development and Validation of a Functional Morbidity Index to Predict Mortality in Community-Dwelling Elders - Carey, Elise C.; Louise C Walter; Lindquist, Karla; Kenneth E Covinsky (Journal of General Internal Medicine, 2004)
OBJECTIVE: Functional measures have a great appeal for prognostic instruments because they are associated with mortality, they represent the end-impact of disease on the patient, and information about them can be obtained directly from the patient. However, there are no prognostic indices that have been developed for community-dwelling elders based primarily on functional measures. Our objective in this study was to develop and validate a prognostic index for 2-year mortality in community-dwelling elders, based on self-reported functional status, age, and gender. DESIGN: Population-based cohort study from 1993 to 1995. SETTING: Community-dwelling elders within the United States. PARTICIPANTS: Subjects, age 70 and over (N= 7,393), from the Asset and Health Dynamics Among the Oldest Old study. We developed the index in 4,516 participants (mean age 78, 84 white, 61 female), and validated it in 2,877 different participants (mean age 78, 73 white, 61 female). MAIN OUTCOME MEASURES: Prediction of 2-year mortality using risk factors such as activities of daily living, instrumental activities of daily living, additional measures of physical function, age, and gender. RESULTS: Overall mortality was 10 in the development cohort and 12 in the validation cohort. In the development cohort, 6 independent predictors of mortality were identified and weighted, using logistic regression models, to create a point scale: male gender, 2 points; age (76 to 80, 1 point; 80, 2 points); dependence in bathing, 1 point; dependence in shopping, 2 points; difficulty walking several blocks, 2 points; and difficulty pulling or pushing heavy objects, 1 point. We calculated risk scores for each patient by adding the points of each independent risk factor present. In the development cohort, 2-year mortality was 3 in the lowest risk group (0 to 2 points), 11 in the middle risk group (3 to 6 points), and 34 in the highest risk group ( 7 points). In the validation cohort, 2-year mortality was 5 in the lowest risk group, 12 in the middle risk group, and 36 in the highest risk group. The c-statistics for the point system were 0.76 and 0.74 in the development and validation cohorts, respectively. CONCLUSIONS: This prognostic index, which relies solely on self-reported functional status, age, and gender, provides a simple and accurate method of stratifying communitydwelling elders into groups at varying risk of mortality.
Keywords: Health Conditions and Status; Methodology

Documentation of Physical Functioning Measures in the Health and Retirement Study and the Asset and Health Dynamics Among the Oldest Old Study - Stephanie J. Fonda; A. Regula Herzog (The University of Michigan, 2004)
This document is part of a series of working papers on health-related measures in the Health and Retirement Study (HRS) and the Asset and Health Dynamics Among the Oldest-Old (AHEAD) study. The series currently contains papers on cognitive function, affective function, and physical function, the latter of which is the focus of this document. The purpose of this document is to aid prospective analysts in the appropriate use of the physical functioning data. To do so, this document provides an inventory of the physical functioning measures included in the survey interviews, describes the formats and origins of these measures, discusses their reliability, validity, and change over time and several options for working with the evolution of the questions, and provides SAS code for recoding the variables and creating simple summary measures.
Keywords: Health Conditions and Status; Healthcare; Methodology

The Effect of Social Security on Retirement in the United States - Courtney Coile; Gruber, Jonathan (Social Security Programs and Retirement Around the World, 2004)
Keywords: Methodology; Retirement Planning and Satisfaction

The Effects of Mortgage Debt on Assets and Total Resources among Near-Retirement Households - Palmer, Lance (Utah State University, 2004)
This study investigated the long-term relation between household leverage through the use of mortgages, and changes in household wealth using the theoretical framework of the life cycle income hypothesis. This study used the 1992 through 2002 waves of the Health and Retirement Study. The characteristics of leveraged and unleveraged households were compared. The relation between household leverage and changes in assets and total resources over the period was modeled using robust regression analysis. Retained or incurred mortgage debt during the study period, relative to not having mortgage debt, had a consistent negative effect on changes in assets and total resources. However, for high-income and more risk-tolerant households, mortgage debt was beneficial and enhanced increases in assets and total resources. Implications for consumers, financial professionals, educators, and tax policymakers were drawn from the results of the study.
Keywords: Housing; Methodology; Net Worth and Assets

An Elementary Cookbook of Data Management using HRS Data with SPSS, SAS and Stata Examples - Servais, Marita (Institute for Social Research, University of Michigan, 2004)
This document is designed to provide new users with an overview of HRS data structures, focussing on within-wave and cross-wave merges. Examples are provided for SAS, Stata, and SPSS.
Keywords: Methodology

Examining the Effect of Welfare Reform on the Economic Well-Being of the Elderly - Eun-Young Choi (University of Missouri - Columbia, 2004)
This study examines the impact of passage of the 1996 Personal Responsibility and Work Opportunity Reconciliation Act (commonly referred to as the Welfare Reform Act) on the economic well-being of the elderly. Longitudinal data from the 1994 and 1998 waves of the Health and Retirement Study were used to examine change in participation of several public welfare programs. Change in respondents' participation in SSI, Food Stamps, and Medicaid between pre- and post-Welfare Reform years were examined using the one-way chi-square test. Multivariate analysis was conducted to analyze the factors associated with moving into poverty and with leaving welfare, SSI, Food Stamps and Medicaid. Results indicate that elderly tended to leave Food Stamps and Medicaid after Welfare Reform but there was not enough evidence to say that this result is a direct result of Welfare Reform. Results of logistic analysis of leaving Food Stamps and Medicaid indicate, not surprisingly, income and job status were statistically significant factors in leaving these welfare programs.
Keywords: Demographics; Employment and Labor Force; Healthcare; Methodology; Women and Minorities

How Alternative Definitions of Retirement and Social Class Shape Conclusions about the Retired Population - Araiza, Isabel (Boston College, 2004)
The conceptualization and operationalization of retirement remains a challenge in retirement research. Those studies which have examined multiple conceptualizations of retirement often limit the investigation to two, three, or four definitions of retirement. These studies also produce contradictory results with respect to the degree of overlap among various definitions of retirement. Moreover, in the investigation of the relationship between predictor variables and the probability of retirement, push and pull factors (such as pension receipt and health) are often the focal point of the inquiry. While most studies include in their analysis a class measure as a control variable for the model, seldom is the relationship between social class and the probability of retirement the focal point of the investigation. This study employs data from the 1998 wave of the Health and Retirement Study to perform an extensive analysis of seven operationalizations of retirement and five operationalizations of social class to evaluate how the use of alternative definitions of retirement and social class shape conclusions drawn about the composition of the retired population. Analyses are performed for the entire sample selected for this study, as well as for Non-Hispanic White, Hispanic, and Non-Hispanic Black subgroups. The results of the analyses indicate that different operationalizations of retirement affect the characterization the retired population; moreover the use of different operationalizations of social class influences the perceptions of the socio-economic condition of the retired population. Despite socio-economic achievements, the findings suggest that initial inequalities associated with ascriptive traits like race and gender continue to constrain women and minorities' life course trajectories. While it is not possible to conduct a comprehensive examination of operationalizations of retirement in gerontological literature, this study includes operationalizations of retirement that acknowledge retirement as an event, an identity, and a process.
Keywords: Demographics; Healthcare; Methodology; Retirement Planning and Satisfaction; Women and Minorities

How Large is the Bias in Self-Reported Disability? - Hugo Benítez-Silva; Buchinsky, Moshe; Hiu-Man Chan; Sheidvasser, Sofia; Rust, John (Applied Econometrics, 2004)
A pervasive concern with the use of self-reported health and disability measures in behavioral models is that they are biased and endogenous. A commonly suggested explanation is that survey respondents exaggerate the severity of health problems and incidence of disabilities in order to rationalize labor force non-participation, application for disability benefits and/or receipt of those benefits. This paper re-examines this issue using a self-reported indicator of disability status from the Health and Retirement Survey. Using a bivariate probit model we test and are unable to reject the hypothesis that the self-reported disability measure is an exogenous explanatory variable in a model of individual's decision to apply for DI benefits or Social Security Administration's decision to award benefits. We further study a subsample of individuals who applied for Disability Insurance and Supplemental Security Income benefits from the Social Security Administration (SSA) for whom we can also observe SSA's award/deny decision. For this subsample we test and are unable to reject the hypothesis that self-reported disability is health and socio-economic characteristics similar to the information used by the SSA in making its award decisions. The unbiasedness restriction implies that these two variables have the same conditional probability distributions. Thus, our results indicate that disability applicant do not exaggerate their disability status at least in anonymous surveys such as the HRS. Indeed, our results are consistent with the hypothesis that disability applicants are aware of the criteria and decision rules that SSA uses in making awards and act as if they were applying these same criteria and rules when reporting their own disability status.
Keywords: Disabilities; Methodology; Social Security

Increases in Wealth Among the Elderly in the Early 1990s: How Much is Due to Survey Design? - Susann Rohwedder; Steven Haider; Michael D Hurd (NBER Working Paper, 2004)
The Asset and Health Dynamics Among the Oldest Old (AHEAD) study shows a large increase in reported total wealth between 1993 and 1995. Such an increase is not found in other US household surveys around that period. This paper examines one source of this difference. We find that in AHEAD 1993 ownership rates of stocks, CDs, bonds, and checking and saving accounts were underreported, resulting in under-measurement of wealth in 1993, and a substantial increase in wealth from 1993 to 1995. The explanation for the under-reporting is a combination of question sequence and wording in the AHEAD survey instrument.
Keywords: Methodology; Net Worth and Assets

A Longitudinal Look at the Predictors of Four Types of Retirement - Weymouth, Penny L. (Central Michigan University, 2004)
The general purpose of the study was to further the understanding of the retirement process. More specifically, the study investigated several personal and work-related predictors of individual retirement status that have received relatively little past examination. By gaining a better understanding of the retirement process, policy makers and organizational leaders can use this knowledge to make informed decisions affecting older workers, their organizations, and society in general. Public release data of the Health and Retirement Study (HRS)--a recent, large, representative, national panel study that focuses on the health, retirement, and aging of persons born between the years of 1931 and 1941--were analyzed. In-home, face-to-face interviews were conducted in 1992, with follow-up interviews conducted every two years by phone. From survey years 1992 through 2000, samples of working individuals over the age of 50 were used to examine nine hypotheses and four different operationalizations of retirement. The hypotheses involved the following predictor variables: gender, partner status, characteristics of one's partner (i.e., retirement status and health), number of dependents, obsolescence of job skills, "demanding" job characteristics, perceived age-related discrimination, work and retirement attitudes, and flexibility of organizational policies regarding older workers. Event history analysis using logistic regression was used to predict the dichotomous criterion variables, while linear mixed model analysis for repeated measures was used to predict the continuous dependent variable. After statistically controlling variables such as age, health, and finances, results indicated that gender, partner's retirement status, work and retirement attitudes, and organizational flexibility were each predictors of at least one type of retirement. In addition, the statistical interaction of gender with partner status predicted retirement defined in several ways. The study expanded what is known about retirement predictors by examining actual versus intended retirement behavior and increased the generalizability of past research by utilizing national panel data. The study also highlighted the importance of clearly defining retirement measures and explored the complete versus partial retirement typology. It was suggested that flexible work options may improve work and retirement attitudes by making the transition into retirement a gradual process, and may keep older employees in the work force longer.
Keywords: Health Conditions and Status; Healthcare; Methodology; Retirement Planning and Satisfaction

Predicting Nursing Home Admission: Estimates from a seven-year follow-up of a nationally representative sample of older Americans - Banaszak-Holl, Jane; A. Mark Fendrick; Norman L Foster; A. Regula Herzog; Mohammed U Kabeto; Kent, David; Walter L. Straus; Kenneth M. Langa (Alzheimer Disease and Associated Disorders, 2004)
This study determines whether prevalence and predictors of nursing home admission changed in the 1990s, during a period of dramatic changes in the service provision for and medical care of chronic impairments. Data from the 1993-2000 surveys of the Asset and Health Dynamics Among the Oldest Old (AHEAD) Study, a longitudinal and nationally representative sample, were used. Proportional hazard models were used to determine the effects of dementia, physical functioning, clinical conditions, and sociodemographics on the likelihood of nursing home admission. Of the 6,676 respondents, 17 were admitted to a nursing home. Models excluding functional impairment demonstrated significant effects of chronic medical conditions and dementia on the risk of institutionalization. After controlling for functional impairment, dementia still had significant and strong effects on institutionalization but clinical conditions did not, suggesting that the impact of dementia goes beyond its effect on physical functioning. Nursing home admissions did not decrease during the study period, and the impact of dementia on the risk of nursing home admission did not decrease. Interventions for individuals with dementia should impact the behavioral aspects of the condition and slow disease progression in addition to improving physical functioning.
Keywords: Demographics; Health Conditions and Status; Healthcare; Methodology

Retirement Transitions: The role of shocks to household resources - Kim, Sora (The Ohio State University, 2004)
The role of shocks to household resources in affecting retirement transitions among older employees was analyzed using data from the Health and Retirement Study (HRS). The transitions of reverse retirement and partial retirement were of particular interest. The objectives of the study were: 1) To explore how shocks, or unexpected changes to financial and human resources, affect retirement transitions, and 2) To explore the relative importance of shocks in making retirement transitions. The study sample consisted of 2,514 HRS respondents, born between 1926 and 1938, who changed employment status between 1998 and 2000 or between 2000 and 2002. A multinomial Logit model was used in order to make comparisons among the four retirement transition groups. The empirical model included institutional variables and demographic and environmental control variables. The results suggest that just as the paths to retirement are diverse and complex, so are their determinants. Shocks to financial resources had the largest effects on reverse retirement transitions. Shocks to human resources, including family structure and health, affected all retirement transitions. Institutional variables had the largest marginal effects on partial retirement. As expected, positive shocks to assets decreased the odds of reverse retirement, and negative income shocks had larger marginal effects on retirement transitions than positive income shocks. However, positive asset shocks had larger marginal effects on retirement transitions than negative asset shocks. The partial retirement group was distinguished from the reverse retirement group in terms of financial shock impacts; for members of the partial retirement group, rather than shocks to resources, institutional supports were key determinants. Fewer significant effects on the odds of partial retirement over traditional retirement were found, and the effects were smaller than those for reverse retirement and retirement from part-time employment in terms of their magnitudes. The loss of human resources was important across the transition groups, with greater impact of shock to marital status on women's labor force transitions compared to men's. To reduce shocks to household resources under uncertainty, retirement education should encompass information on asset allocation and financial risk. These topics may help workers more effectively plan for retirement.
Keywords: Health Conditions and Status; Healthcare; Methodology; Net Worth and Assets; Retirement Planning and Satisfaction

Review of: The smoking puzzle: Information, risk perception, and choice - Jahn K. Hakes (Journal of Economic Literature, 2004)
Keywords: Consumption and Savings; Health Conditions and Status; Healthcare; Methodology; Public Policy

Selection Correction and Sensitivity Analysis for Ordered Treatment Effect on Count Response - Lee, Myoung Jae (Journal of Applied Econometrics, 2004)
In estimating the effect of an ordered treatment on a count response y with an observational data where tau is self selected (not randomized), observed variables x and unobserved variables epsilon can be unbalanced across the control group (tau = 0) and the treatment groups (tau = 1, . . . , J). While the imbalance in x causes overt bias which can be removed by controlling for x, the imbalance in epsilon causes covert (hidden or selection) bias which cannot be easily removed. This paper makes three contributions. First, a proper counter factual causal framework for ordered treatment effect on count response is set up. Second, with no plausible instrument available for tau, a selection correction approach is proposed for the hidden bias. Third, a nonparametric sensitivity analysis is proposed where the treatment effect is nonparametrically estimated under no hidden bias first, and then a sensitivity analysis is conducted to see how sensitive the nonparametric estimate is to the assumption of no hidden bias. The analytic framework is applied to data from the Health and Retirement Study: the treatment is ordered exercise levels in five categories and the response is doctor office visits per year. The selection correction approach yields very large effects, which are however ruled out by the nonparametric sensitivity analysis. This finding suggests a good deal of caution in using selection correction approaches.
Keywords: Health Conditions and Status; Methodology

Social, Cultural, and Economic Capital, and Behavioral Investments in Health - Patrick M. Krueger (University of Colorado at Boulder, 2004)
I develop a health stratification perspective to examine whether differential access to social, cultural, and economic capital account for differences in individuals' abilities and proclivities to behaviorally invest in their health. I suggest that each form of capital derives from key social institutions. To test my theoretical framework, I use the 1998 and 2000 waves of the Health and Retirement Study (HRS) to examine changes in health behaviors over a two year period. The HRS provides a nationally representative sample of adults aged 51 and older and has detail on six key behaviors, including physical activity, smoking, binge drinking, preventive blood cholesterol tests, preventive cancer screening behaviors, and flu shot receipt. First, Chapter 4 examines the relationship between socioeconomic status (SES) and behavioral investments in health. I find that socioeconomic position is multidimensional and indicates people's locations in diverse institutions including the occupational hierarchy, education, employment, and the financial marketplace. Although much prior work assumes that diverse socioeconomic measures are indicators of a single underlying concept, I find that each dimension of SES has a unique association with various health behaviors. Second, Chapter 5 examines the relationship between employment, gender, and marital status. Prior research suggests that employment enhances the health of both men and women. Further, wives often have better health if their husbands work, but husbands typically have worse health if their wives work. I fail to find support for this relationship when examining health behaviors; thus prior theoretical work may not adequately explain various dimensions of health. Finally, Chapter 6 finds that marriage generally promotes healthier lifestyles among men and women. However, the quality of the marriage is important--those whose spouses have healthier lifestyles undertake healthier behaviors than those whose spouses have less healthy lifestyles. Further, prior work suggests that marriage benefits the health of men more than women. But I find that marriage benefits women more than men for some health behaviors. Thus, health research may be inadequate if it focuses on a limited number of health indicators.
Keywords: Adult children; Demographics; Health Conditions and Status; Methodology

Three Essays on the Effect of Taxes on Economic Behavior - Kumar, Anil (Syracuse University, 2004)
Estimation of the effect of tax and transfer policies on economic behavior is a central area of study in the fields of public finance and labor economics. By changing relative prices, policies affect the consumption/saving and labor/leisure choices of individuals and households. The direction and magnitude of such responses are key elements in the effort to measure the overall effect of taxes on economic behavior. The three essays in this dissertation examine two important areas of recent research: the effect of taxes on female labor supply and the effect of subsidies on saving behavior. In the first essay, I estimate female labor supply elasticities in the presence of taxes in a lifecycle-consistent framework, and then calculate the economic cost of taxation. I employ many of the most current econometric techniques to estimate panel data models with fixed effects in the presence of censoring and am able to estimate both intratemporal and intertemporal elasticities for female labor supply. Using data on a panel of married females from the Panel Study of Income Dynamics (PSID), female labor supply is found to be highly responsive to taxes, while intratemporal and intertemporal elasticities are estimated to be larger than 1. Blomquist and Newey (2002) have proposed a nonparametric estimator for labor supply functions, in the presence of nonlinear budget sets. In the second essay, I extend their nonparametric estimator to censored dependent variables, propose econometric strategies to empirically estimate the model, and estimate female labor supply elasticities taking into account the entire budget set using data from 1987 wave of PSID. I find evidence of an elastic response to taxation with the compensated wage elasticity estimated to be 1.19. In the last essay, Gary Engelhardt and I study the effect of employer matching on 401(k) saving using data from the 1992 wave of Health and Retirement Study (HRS). We derive a lifecycle-consistent theoretical model for 401(k) saving, and structurally estimate behavioral elasticities using unique administrative data on 401(k) plans by laying out the individual's complete budget set. We estimate that the elasticity of 401(k) contributions with respect to the match rate is 0.33.
Keywords: Consumption and Savings; Employment and Labor Force; Methodology; Public Policy; Women and Minorities

Disability and Employment: Reevaluating the Evidence in Light of Reporting Errors - Kreider, Brent; John V Pepper (Center for Retirement Research, 2003)
Long-standing debates about relationships between labor supply behavior and health status among persons nearing retirement age have centered largely on disagreements about the reliability of self-reported health indicators. In light of reporting errors in work capacity, this paper considers the problem of predicting how employment rates vary with disability status when true disability is unobserved. Rather than imposing the strong assumptions required to obtain point identification, we take a step back to evaluate what can be inferred under a variety of assumptions that are weaker but arguably more credible than those imposed in the existing literature. Although these assumptions do not identify the conditional employment rates except in special cases, nonparametric bounds for these parameters can be obtained. Using data from the Health and Retirement Study, we estimate a set of bounds that formalize the identifying power of a number of different assumptions that appear to have broad consensus in the literature. Our results suggest that models estimated under the assumption of fully accurate reporting lead to biased inferences. In particular, it appears that nonworkers tend to overreport disabilities.
Keywords: Employment and Labor Force; Health Conditions and Status; Methodology

The Effects of Bracketing in Wealth Estimation - Chand, Harish; Gan, Li (Review of Income and Wealth, 2003)
The use of bracketing in wealth surveys is sometimes criticized on the grounds that it will encourage respondents to substitute rough guesses for careful thought. In such a manner, the use of bracketing will crowd out more specic answers, creating the illusion of a reduction in nonresponse. This paper examines the patterns of wealth response in the first two waves of the Health and Retirement Study. On average, people do not appear to transition to bracketing. New tests of the breakeven level of crowding-out are suggested. Based on the explanatory power of the brackets, the degree of crowding-out which would be necessary to make the use of bracketing counterproductive appears to be much higher than plausible.
Keywords: Methodology; Public Policy

Enhancing the Quality of Data on Income: Recent Innovations from the HRS - Michael D Hurd; Juster, F. Thomas; James P Smith (Journal of Human Resources, 2003)
This paper evaluates two survey innovations introduced in the HRS that aimed to improve income measurement. The innovations are (1) the integration of questions for income and wealth and (2) matching the periodicity over which income questions are asked to the typical way such income is received. Both innovations had significant impacts in improving the quality of income reports. For example, the integration of income questions into the asset module produced in HRS an across-wave 63 percent increase in the amount of income derived from financial assets, real estate investments and farm and business equity. Similarly, asking respondents to answer using a time interval consistent with how income is received substantially improved the quality of reports on social security income. Fortunately, we also suggest ways that these innovations can be introduced into other major social science surveys.
Keywords: Income; Methodology

How Large Are the Classification Errors in the Social Security Disability Award Process? - Hugo Benítez-Silva; Buchinsky, Moshe; Rust, John (SUNY-Stony Brook, 2003)
This paper presents an audit of the multistage application and appeal process that the U.S. Social Security Administration (SSA) uses to determine eligibility for disability benefits of the Disability Insurance (DI) and Supplemental Security Income (SSI) programs. We study a subset of individuals from the Health and Retirement Survey (HRS) who applied for DI or SSI benefits between 1992 and 1996. We compare the SSA s ultimate award decision a (i.e., after allowing for all possible appeals) to the applicant s self-reported disability status d (recorded at the first HRS survey after their initial application for benefits). We use these data to estimate classification error rates under the hypothesis that applicants self-reported disability status d is the relevant measure of true disability and the SSA s ultimate award decision a is a noisy but unbiased indicator of d This truthful, accurate reporting hypothesis allows us to estimate the magnitude of classification errors in the SSA award process and obtain insights into the patterns of self-selection induced by varying delays and award probabilities at various levels of the application and appeal process. Overall we find that 22 of SSI/DI applicants who are ultimately awarded benefits are not disabled, and that 59 of applicants who were denied benefits are disabled. We construct a computerized disability screening rule using a subset of objective health indicators that the SSA uses in making award decisions that results in significantly lower classification error rates than does SSA s current award process. This suggests that there may be cheaper, faster, and more accurate ways to make disability determinations than the SSA s current disability award process. We also estimate classification errors under the assumption that both a and d are noisy but unbiased indicators of an (unobserved) underlying indicator of true disability, t . However, the estimated classification error rates remain virtually unchanged under this alternative hypothesis.
Keywords: Disabilities; Methodology; Social Security

Joint Labor Supply Dynamics of Older Couples - Pierre-Carl Michaud (IZA DP, 2003)
This paper studies the labour force participation dynamics of older couples in the United States. Longitudinal data from the five available waves of the Health and Retirement Study (HRS) is used to investigate if the dynamics introduced by considering both spouses behavior provide additional information in trying to fit observed participation sequences. The paper uses a bivariate dynamic binary choice model with unobserved heterogeneity and serial correlation to disentangle the many sources of dynamics and correlation in a couple s decision making. First, strong true state-dependence is found and results in a bunching of participation and non-participation sequences. Cross-spouse state-dependence is also found which points to indirect effects of social security and pension incentives through complementarity in leisure. Second, the Spouse Allowance program is found to have predicted effects on participation of the couple and these effects are statistically significant. A simulation exercise presents evidence that the elimination of the spouse allowance can raise participation of wives at age 62 by more than the decrease in participation of husbands at age 65.
Keywords: Adult children; Employment and Labor Force; Methodology; Retirement Planning and Satisfaction

Measuring Pension Wealth in the HRS: Employer and Self-Reports - Susann Rohwedder (RAND, 2003)
Keywords: Methodology; Net Worth and Assets

Parsing the Smoking Puzzle: Information, Risk Perception, and Choice - Frank A Sloan; Donald H. Taylor Jr.; V. Kerry Smith (Harvard University Press, 2003)
Examines how perceptions of the risks of smoking are updated as older individuals receive new personalized information and how risk perceptions affect smoking behavior. Highlights the potential for reducing cigarette consumption using a message about a smoker's quality of life at the end of life. Based on data collected in the Health and Retirement Study (HRS), a national panel survey conducted by the University of Michigan's Institute for Social Research on adults aged fifty one to sixty one in the baseline year of the survey (1992), and on information from focus group meetings and interviews with current or former smokers. Surveys government policy and industry advertising with regard to smoking over the past fifty to one hundred years and their effectiveness in influencing cigarette demand. Summarizes existing knowledge and HRS findings on the effects of smoking on mortality and morbidity. Focuses on the survey respondent's assessment of the probability that they will live to age seventy five; examines how well individuals predict their own survival; and explores how people use new information about their own health to update their longevity expectations. Presents new information on smoking cessation and relapse patterns in older adults, paying special attention to the impact of health shocks. Considers whether it is possible to design information messages that mimic the information conveyed to middle aged smokers by personal health shocks and investigates the factors that may make a message especially salient for smokers. Incorporates new findings into an economic analysis of the demand for cigarettes and evaluates the potential impact of a new information policy on daily cigarette consumption of smokers in the sixth and seventh decade of life. Presents policy implications. Sloan is at Duke University. Smith is at North Carolina State University. Taylor is at the Stanford Institute of Public Policy, Duke University. Index.
Keywords: Consumption and Savings; Health Conditions and Status; Healthcare; Methodology; Public Policy; Risk Taking

Planning and Saving for Retirement - Annamaria Lusardi (Dartmouth College, Dept. of Economics, 2003)
There are vast differences in wealth holdings, even among households in similar age groups. In addition, a large percentage of U.S. households arrive close to retirement with little or no wealth. While many explanations can be found to rationalize these facts, approximately thirty percent of households whose head is close to retirement have done little or no planning for retirement. Planning is shaped by the experience of other individuals: individuals learn to plan for retirement from older siblings. They also learn from the experience of old parents. In particular, unpleasant events, such as financial difficulties and health shocks at the end of life, provide incentives toward planning. In addition, planning affects wealth levels as well as portfolio choice. Individuals who plan are more likely to hold large amounts of wealth and to invest their wealth holdings in high return assets, such as stocks. Thus, planning plays an important role in explaining the saving behavior of many households.
Keywords: Methodology; Net Worth and Assets; Retirement Planning and Satisfaction

Retirement Income Data: Improvements Could Better Support Analysis of Future Retirees' Prospects - United States General Accounting Office (Washington, DC, U.S. General Accounting Office, 2003)
Future demographic trends include a doubling of the nation's retiree population and only modest labor force growth, leading to concerns about retirement income adequacy for future generations. Credible projections of the effects of policy proposals on federal spending and future retirees' income are necessary. Because adequate data is critical to the analysis of retirement income and wealth, GAO was asked to identify data improvements that experts say are a priority for the study of retirement income and wealth, as well as factors limiting efforts to obtain the needed information. Experts consulted by GAO cited priorities for improving retirement data that fit into two broad categories: (1) obtaining better data from employers on employee benefits and (2) obtaining better data by linking more individual and household surveys with administrative data (such as employer records, and Social Security earnings history records). Information from employers, such as documents describing the features of their pension plans, would enable analysts to forecast future retirement income of pension holders, based on the specific features of their pension plans and the likely distribution of pension income and wealth for different segments of the population. Linking individual and household surveys with administrative data creates new information, such as the demographic characteristics of employees whose pensions are affected by the formulas that employers use to calculate contributions or pension payments. Analysts attribute the shortcomings in retirement income data primarily to fragmentation of the responsibility for data collection and analysis, the burden of data collection on respondents, and confidentiality considerations that restrict access to these data. Fragmentation of responsibility occurs, in their view, because no single agency has a statutory mandate to collect or to analyze all the data needed to support a more comprehensive study of retirement income and wealth. With regard to respondent burden, some information on pension plans is no longer collected, in part, out of concern that it was an unnecessary burden on the firms having to submit it. Finally, certain kinds of data needed to make projections are not widely available to all analysts because of the confidentiality laws that authorize their collection.
Keywords: Methodology; Pensions; Retirement Planning and Satisfaction

Another Look at Aggregate Changes in Severe Cognitive Impairment: Further investigation into the cumulative effects of three survey design issues - Vicki A Freedman; Aykan, Hakan; Linda G Martin (The Journals of Gerontology Series B, 2002)
OBJECTIVES: This study explored whether previously reported declines in severe cognitive impairment were robust to cumulative effects of potentially confounding survey design issues. METHODS: Using the 1993 Asset and Health Dynamics of the Oldest Old study (n = 7,443) and 1998 Health and Retirement Survey (HRS; n = 7,624) the proportion of persons ages 70 and older with severe cognitive impairment was calculated under various assumptions about item nonresponse, differential loss to follow-up, and the size and composition of the nursing home population. Impairment was measured for self-respondents using a modified version of the Telephone Interview Cognitive Screen; for proxy respondents ratings of memory and judgment were used. Chi-square tests were adjusted to account for complex survey designs. RESULTS: Ignoring loss to follow-up, excluding nursing home residents, and assigning a low score to those refusing subscales yielded a statistically significant decline in severe cognitive impairment from 5.8 in 1993 to 3.8 in 1998, or an average annual decline of 6.9 . When cumulative effects of survey design issues were considered and design effects incorporated into statistical tests, statistically significant declines persisted, albeit at a reduced average annual rate, ranging from 2.5 to 6.9 per year. DISCUSSION: Previously reported improvements in severe cognitive impairment appear to be robust to a variety of specifications. Replication with future waves of the HRS and other data is warranted.
Keywords: Demographics; Health Conditions and Status; Healthcare; Methodology; Other

Couple Retirement Patterns and Retirement Age: A Comparison of Austria and the United States - Maximiliane E Szinovacz (International Journal of Sociology and Social Policy, 2002)
Keywords: Methodology; Retirement Planning and Satisfaction

Crediting Care, Citizenship or Marriage? Gender, Race, Class, and Social Security Reform - Herd, Pamela (Syracuse University, 2002)
This project addresses welfare state theoretical debates as to how benefits should be distributed to reduce gender, race, and class inequities. Should benefit eligibility be based on citizenship, care or marital status? Scholars concerned about class-based inequities are supportive of minimum benefits that reward citizenship, while scholars concerned with gender-based inequities are supportive of policies that either reward unpaid care through care credits or policies that soften the economic ramifications of marital dissolution such as improving benefits for divorced women. The reform debate over social security in the United States provides a useful case study of how benefit distribution impacts inequality. Over 20 years have passed since policy analysts first argued that social security benefits needed to be altered to better protect women. These benefits contain two flaws. First, they no longer represent the American family due to the rise in divorce rates, single parent families, and mothers working. Second, family benefits undermine the program's redistributive goals. But no project has attempted to quantitatively evaluate the impact of the three most popular sets of reforms proposed to improve family
Keywords: Adult children; Methodology; Public Policy; Women and Minorities

Crediting Care? Gender, Race, Class and Social Security Reform - Herd, Pamela (Syracuse University, 2002)
Keywords: Demographics; Methodology; Net Worth and Assets

Critique of Cognitive Measures in the Health and Retirement Study (HRS) and the Asset and Health Dynamics among the Oldest Old (AHEAD) Study - Margie E Lachman; Avron Spiro III (2002)
Keywords: Health Conditions and Status; Methodology

The Effects of Changing Social Security Administation's Early Entitlement Age and the Normal Retirement Age - Panis, Constantijn; Michael D Hurd; Loughran, David; Julie M Zissimopoulos; Steven Haider; Patricia A St Clair (Social Security Administration: Labor & Population Program, 2002)
The Old-Age and Survivors Insurance (OASI) program is projected to be unable to meet its obligations by approximately the year 2041. Many proposals that aim to restore solvency include provisions to accelerate the already legislated increase of the normal retirement age (NRA) or to increase it beyond the current target of 67 years; some proposals also suggest raising the early entitlement age (EEA) beyond 62 years. This document sheds light on the implications of EEA and/or NRA increases on the solvency of the OASI and DI programs. It does not discuss private accounts. The report starts with a characterization of workers who claim benefits at age 62 and a discussion of retirement planning. We then estimate formal models of retirement and DI application and simulate the financial consequences of EEA and/or NRA increases and other policy proposals. We conclude with an assessment of likely responses of employers to changes in Social Security policy. Most analyses in this report are based on the Health and Retirement Study (HRS), a survey of individuals in their 50s and 60s with very extensive information about work, financial resources including Social security and private pensions, and health.
Keywords: Methodology; Retirement Planning and Satisfaction; Test

Ensuring Time-Series Consistency in Estimates of Income from Wealth - Juster, F. Thomas; Joseph P. Lupton; Cao, Honggao (Ann Arbor, MI, The University of Michigan, Michigan Retirement Research Center, 2002)
Keywords: Income; Methodology; Net Worth and Assets

Gender and Ethnic/Racial Disparities in Health Care Utilization Among Older Adults - Dorothy D Dunlop; Larry M Manheim; Song, Jing; Rowland W Chang (The Journals of Gerontology: Social Sciences, 2002)
OBJECTIVE: We examine the role of economic access in gender and ethnic/racial disparities in the use of health services among older adults. METHODS: Data from the 1993-1995 study on the Asset of Health Dynamics Among the Oldest Old (AHEAD) were used to investigate differences in the 2-year use of health services by gender and among non-Hispanic White versus minority (Hispanic and African American) ethnic/racial groups. Analyses account for predisposing factors, health needs, and economic access. RESULTS: African American men had fewer physician contacts; minority and non-Hispanic White women used fewer hospital or outpatient surgery services; minority men used less outpatient surgery; and Hispanic women were less likely to use nursing home care, compared with non-Hispanic White men, controlling for predisposing factors and measures of need. Although economic access was related to some medical utilization, it had little effect on gender/ethnic disparities for services covered by Medicare. However, economic access accounted for minority disparities in dental care, which is not covered by Medicare. DISCUSSION: Medicare plays a significant role in providing older women and minorities access to medical services. Significant gender and ethnic/racial disparities in use of medical services covered by Medicare were not accounted for by economic access among older adults with similar levels of health needs. Other cultural and attitudinal factors merit investigation to explain these gender/ethnic disparities.
Keywords: Demographics; Health Conditions and Status; Healthcare; Methodology; Other; Women and Minorities

Guaranteed Income: SSI and the Well-Being of the Elderly Poor - Kathleen McGarry (The Distributional Aspects of Social Security and Social Security Reform, 2002)
It is a well known fact that over the past 40 years Social Security has made a major contribution to reducing the poverty levels of elderly persons. At the same time people are beginning to realize the decline in labor force participation of the near-elderly. This paper examines these two topics, as well as, the elderly population that is not being provided sufficient Social Security compensation. Within this context the authors discuss possible changes in Supplemental Security Income, the elimination of the asset test, increasing unearned income disregards, raising guarantees to the poverty line, using social security income, costs of changes, and the effects on poverty.
Keywords: Demographics; Methodology; Public Policy; Social Security

Job Search Behavior at the End of the Life Cycle - Hugo Benítez-Silva (Center for Retirement Research at Boston College Working Papers, 2002)
This paper presents one of the first formal dynamic models of job search by older individuals. It also presents an empirical analysis of job search behavior among this population using the Health and Retirement Study. Several factors currently compound to make the topic of this research an important one in the agenda of the Economics of Aging: ongoing demographic, epidemiological, socio-economic, technological, and labor market trends indicate that older Americans are more likely to be labor force participants beyond traditional retirement ages. Increasing longevity, improving health, strong labor market conditions, increasing labor supply flexibility stemming from an increase in part-time work and self-employment and the use of technological advances to promote second careers, and increasing labor force participation, make the study of search behavior at the end of the life cycle, in a formal theoretical and empirical model, an important contribution. Our findings show that older Americans actively search for new jobs, both on the job and when out of work, and that previous work attachment and health limitations are key to understanding the different job search behavior of employed and non-employed individuals, as well as males and females.
Keywords: Employment and Labor Force; Event History/Life Cycle; Methodology

Older Workers and their Selection of Partial and Full Retirement: Evidence from Health and Retirement Study - Kim, Haejeong (Purdue University, 2002)
The purpose was to investigate older workers' retirement transitions by examining factors associated with partial retirement and full retirement during a four-year period. The study used data from three waves of the Health and Retirement Study. The sample consisted of 3,268 primary respondents who were working full time in Wave 1. A conceptual model was developed based on the life-cycle retirement model, the lifecycle income hypothesis, disengagement theory, activity theory, continuity theory, lifecourse perspectives, role theory, and the findings of previous research on retirement behavior. Binary logit regression and multinomial logit regression analyses were employed for model estimation. Major findings from the multinomial logit using baseline predictors to examine partial and full retirement in Wave 3 are 1) unearned income, Individual Retirement Account and Keogh plans positively impact the likelihood of partial retirement versus full-time work, while the ownership of defined benefit plans and the ownership of defined contribution plans negatively impact partial retirement versus full-time work; 2) the number of chronic conditions positively impact the likelihood of partial retirement; 3) perceived age discrimination, age, male, and a college degree are positively associated with the likelihood of partial retirement; 4) the expected age of Social Security benefit receipt is negatively related to the likelihood of full retirement versus full time work, while the ownership of defined benefit plans, the ownership of both defined benefit and defined contribution plans, the ownership of IRA and Keogh plans, the ownership of health insurance after retirement are positively related to the likelihood of full retirement; 5) excellent and good health, and the meaning of work is more important are negatively associated with the likelihood of full retirement; and 6) age is positively associated with the likelihood of full retirement. The conflicting effects of pension plans on partial retirement and full retirement show that pension are a stimulus to encourage working although part-time, while pension plans are important as retirement incentives for the full retirement decision. Theoretical, empirical, and practical implications are presented based on the findings.
Keywords: Employment and Labor Force; Health Conditions and Status; Healthcare; Methodology; Retirement Planning and Satisfaction

The Predictive Validity of Subjective Probabilities of Survival - Michael D Hurd; Kathleen McGarry (The Economic Journal, 2002)
Although expectations, or more precisely subjective probability distributions, play a prominent role in models of decision making under uncertainty, we have had very little data on them. Based on panel data from the Health and Retirement Study, we study the evolution of subjective survival probabilities and their ability to predict actual mortality. In panel, respondents modify their survival probabilities in response to new information such as the onset of a new disease condition. Subjective survival probabilities predict actual survival: those who survived in the panel reported survival probabilities approximately 50 greater at baseline than those who died.
Keywords: Expectations; Methodology

Pre-Retirement Lump-Sum Pension Distributions and Retirement Income Security: Evidence from the Health and Retirement Study - Gary V. Engelhardt (National Tax Journal, 2002)
This paper uses the Health and Retirement Study to examine the extent of retirement wealth erosion from pre-retirement lump-sum pension distributions. There is little evidence that spent distributions have resulted in significant pension leakage. If spent distributions had been rolled over into a tax-qualified plan, they would have represented 5-11 percent of pension and Social Security wealth for the median household that spent a distribution. However, one-quarter of the households that spent distributions--which is 2.25 percent of all households age 51 to 61--could have increased retirement wealth by 25 percent or more had the distributions been rolled over.
Keywords: Methodology; Net Worth and Assets; Pensions

Research in Population Health - Jones, Nathan Reed (University of Pennsylvania, 2002)
This dissertation presents three chapters on population health and mortality risk using cause of death and underlying conditions data as well as longitudinal studies that include a wide spectrum of individual, household, and community variables. Although the three studies contained in this dissertation are not directly linked topically, they share a concern about the role of smaller components of a population to the mortality dynamics of the population as a whole. Each of the three papers builds on previous research to provide a level of detail or innovation in measurement to improve understanding of mortality dynamics and their effects on the population of interest. In the first chapter, I hold wealth rank in the poorest and richest global wealth quintiles constant over time to provide estimates of the deaths by primary cause group in 1970, 1990, and 2020. I also provide projections of deaths by cause for the richest and poorest countries in 2020 for twenty-one causes of death. The mortality structure among the poorest countries in the world continues to be dominated by infectious causes of death despite global estimates that suggest the epidemiologic transition has progressed to an advanced stage. The second chapter describes age-graded mortality risk for sub-groups of the U.S. population taking into account several demographic, economic, and health characteristics. Using data from different representative cohorts, I estimate age-specific relative risks of death associated with different health, socioeconomic, marital status, and behavioral characteristics to the mean risk of death. The third chapter describes a method for estimating variance in individual mortality risk based on observed characteristics using representative cohorts of the Health and Retirement Study (HRS). I compare distributions of predicted mortality risk to estimates of the degree of population-level heterogeneity in previous studies that have used parameterized frailty models for unobserved heterogeneity in mortality. Findings in this chapter show that the coefficient of variation for estimates of individual mortality risk decrease with age, thus suggesting that the inverse gaussian distribution may be more appropriate in frailty models than the gamma distribution, which implies a coefficient of variation that is constant with age.
Keywords: Demographics; Health Conditions and Status; Healthcare; Methodology

The Size and Composition of Wealth Holdings in the United States, Italy, and the Netherlands - Arie Kapteyn; Panis, Constantijn (RAND Unrestricted Draft, 2002)
This report analyzes retirement-saving behavior and portfolio choice in the United States, Italy, and the Netherlands. The authors test hypotheses on the implications of institutional differences for wealth accumulation and portfolio composition.
Keywords: Methodology; Net Worth and Assets

Size of Incentive Effects in a Longitudinal Study - Rogers, Willard (American Association for Public Research 2002, 2002)
This paper describes an experiment conducted as part of one wave of the Health and Retirement Study (HRS), which is a longitudinal survey of a nationally representative sample of persons who were born in 1947 or before. Interviews have been conducted biennially since 1992. The general practice, after wave 1, has been to include a check for $20 along with an advance letter sent to each sample member prior to their being contacted, by telephone or face-to-face, by an interviewer. The experiment consisted of changing the amount of the incentive check for randomly selected sample members, with the objective of examining the effect of incentive size in the response rate, on the amount of effort required to finalize the case, and the quality of the data obtained from respondents. In this paper, we examine the effects of the size of the incentive on the response rate on the immediate wave, and also briefly examine the effects on the number of calls.
Keywords: Healthcare; Methodology

Social Security, Pensions and the Savings and Retirement Behavior of Households - van der Klaauw, Wilbert; Wolpin, Kenneth I. (University of North Carolina at Chapel Hill, 2002)
In this paper we formulate and estimate an explicit sequential decision model of savings and work behavior of elderly individuals and couples. More specifcally, we develop a stochastic dynamic model of retirement behavior in which forward-looking individuals are making employment and savings decisions in a setting that accounts for uncertainty about future labor market opportunities, health insurance coverage, health status, survival, and the future generosity of the social security system. The choice environment is characterized by an incomplete health insurance market, the presence and characteristics of employer provided health insurance and private pension plans, the Social Security and Medicare insurance system, and a capital market which applies borrowing limits. The model is estimated using longitudinal data from the Health and Retirement Study. The estimates are used to evaluate the importance of potential earnings, health, social security benefits and employer provided health insurance coverage and pensions in explaining observed retirement behavior, and to simulate the impact of potential social security reforms on life cycle employment and savings behavior and on welfare.
Keywords: Consumption and Savings; Employment and Labor Force; Methodology

Who Expects to Continue Working After Age 62? The retirement plans of couples - Pienta, Amy M.; Mark D Hayward (The Journals of Gerontology: Social Sciences, 2002)
OBJECTIVES: This study examines the individual, spousal, and household characteristics associated with the retirement expectations of husbands and wives. METHODS: Using data from the 1992 Health and Retirement Study, subjective probabilities of working full-time after reaching age 62 and age 65 are used to measure retirement expectations. The retirement expectations of husbands and wives are modeled simultaneously using a joint-generalized least-squares approach. RESULTS: Within a marriage, retirement expectations are shaped by individual, spousal, and household characteristics. We observe some gender differences in cross-spousal influence with wives' retirement expectations being more influenced by husbands' resources and constraints than vice versa. Nonetheless, individual and household factors associated with retirement expectations are widely shared by husbands and wives. DISCUSSION: Husbands and wives both respond to individual and joint constraints and opportunities when planning for retirement. Findings support that there is considerable overlap in retirement planning of husbands and wives during early parts of the retirement decision-making process. However, inequity in cross-spousal influences is a defining characteristic of retirement decision making. Implications for both policy makers and practitioners are briefly discussed.
Keywords: Adult children; Demographics; Employment and Labor Force; Expectations; Health Conditions and Status; Healthcare; Methodology; Retirement Planning and Satisfaction; Risk Taking

Workers' Ignorance of Retirement Benefits - David J Ekerdt; Kyle J Hackney (The Gerontologist, 2002)
PURPOSE: This study considered the extent of workers' unfamiliarity with retirement benefits, a problem that could compromise informed retirement planning. DESIGN AND METHODS: Among workers in the 1992 Health and Retirement Study, we examined the frequency of don't know responses to question series about employer pensions, health insurance, and Social Security. RESULTS: Eligible workers readily offered responses about the shared, public details of pension plans, but knowledge about personal pension wealth was lacking for one third of persons in defined benefit plans and for one fifth of those in defined contribution plans. Among household financial respondents, 14 did not know about health insurance continuation after retirement, and 52 could not offer an expected Social Security amount. Such nonresponse was patterned by proximity to retirement and by social and occupational factors. IMPLICATIONS: More than a problem of missing data, these findings argue for a theoretical reconsideration of the role of financial knowledge in retirement behavior. Ignorance of benefits is probably less a problem of disclosure than of workers' inattention to available information.
Keywords: Demographics; Education; Medicare/Medicaid/Health Insurance; Methodology; Other; Pensions; Social Security

Worklife Determinants of Retirement Income Differentials Between Men and Women - Phillip B. Levine; Olivia S. Mitchell; John W R Phillips (Innovations in Financing Retirement, 2002)
Women enter retirement having spent fewer years in market, earned less over their lifetimes, and work in different jobs than men of the same age. This study examines whether these differences in work life experiences help explain why many women end with lower level of retirement income in old age. We use Health and Retirement Study (HRS), which provide information on labor market histories along with the ability to predict retirement income from employer pensions, social security benefits, and investment returns. We document differences in anticipated retirement income by sex that exist largely between non-married men and women. Multivariate models show that 85 percent of this retirement income gap can be attributed to differences in lifetime labor market earnings, years worked, and occupational segregation by sex. Our results suggest that as women's work life experiences become more congruent with men's over time, the gap in retirement income between men and women may shrink.
Keywords: Income; Methodology; Retirement Planning and Satisfaction; Women and Minorities

Aggregate Changes in Severe Cognitive Impairment Among Older Americans: 1993 and 1998 - Vicki A Freedman; Aykan, Hakan; Linda G Martin (The Journals of Gerontology: Social Sciences, 2001)
OBJECTIVES: This study explored whether improvements in cognitive functioning occurred during the 1990s among older Americans and investigated several possible explanations for such changes. METHODS: Using the 1993 Asset and Health Dynamics of the Oldest Old study (N = 7,443) and 1998 Health and Retirement Survey (N = 7,624), this study examined aggregate changes in the proportion of the noninstitutionalized population aged 70 and older with severe cognitive impairment. Impairment was measured for self-respondents using a modified version of the Telephone Interview Cognitive Screen; for proxy respondents, ratings of memory and judgment were used. Logistic regression was used to investigate potential explanations for aggregate changes. RESULTS: The percentage of older Americans with severe cognitive impairment declined from 6.1 in 1993 to 3.6 in 1998 (p .001). The decline was statistically significant among self-respondents but not among those with proxy interviews. Improvements between 1993 and 1998 were not explained by shifts in demographic and socioeconomic factors or by changes in the prevalence of stroke, vision, or hearing impairments. DISCUSSION: As a group, older persons, especially those well into their 80s, appear to have better cognitive functioning today than they did in the early 1990s.
Keywords: Demographics; Health Conditions and Status; Healthcare; Methodology

Antihypertensive Medication Use in Hispanic Adults: A comparison with Black adults and White adults - Joseph J Sudano; David W. Baker (Medical Care, 2001)
BACKGROUND. Variations in awareness, treatment, and control of hypertension among different racial/ethnic groups have been widely reported. It is unclear whether these differences are explained fully by differences in socioeconomic status, insurance coverage, health status, and health behaviors, or whether these differences indicate that racial/ethnic subgroups have unique barriers to hypertension control. OBJECTIVES. Determine whether there are significant differences between racial/ethnic groups in medication use for hypertension after adjusting for potentially confounding variables. RESEARCH DESIGN. Cross-sectional analysis of the 1992 Health and Retirement Study. SUBJECTS. 2450 non-Hispanic white, 939 non-Hispanic black, and 345 Hispanic participants, ages 51 to 61, reporting a history of hypertension. MEASURES. Self-reported current antihypertensive medication use. We used logistic regression to adjust for demographics, socioeconomic status, health status, insurance, and health risk behaviors. RESULTS. 63.6 of white adults, 72.6 of black adults, and 52.5 of Hispanic adults reported current medication use to control hypertension (P 0.001 across all three groups). In stratified analysis, the lower rate of use for Hispanic adults was consistent regardless of gender, insurance coverage, or health status. After controlling for all variables, the adjusted prevalence for Hispanic adults was 50.8 and 73.3 for black adults. CONCLUSIONS. The differences in antihypertensive medication use between white adults, black adults, and Hispanic adults, particularly the markedly lower rates among Hispanic adults, are not explained by differences in demographics, socioeconomic status, health insurance coverage, health status, or health risk behaviors. Alternative explanations for these results and areas for future research and intervention are explored.
Keywords: Demographics; Health Conditions and Status; Healthcare; Methodology; Risk Taking; Women and Minorities

Betwixt and Between: Targeting coverage reforms to those approaching Medicare - Dennis G. Shea; Pamela F. Short; M. Paige Powell (Health Affairs, 2001)
Recent Medicare buy-in proposals agree on setting eligibility at age sixty-two but disagree on linking eligibility to loss of employer insurance or ability to pay. We examine arguments for targeting incremental coverage for older Americans in these ways. While access to retiree health insurance is declining, we question whether targeting loss of employer insurance can address many older Americans' insurance problems. Furthermore, focusing on persons ages sixty-two to sixty-four misses a large group of persons in poor health with limited resources. Efforts to improve coverage for older Americans should consider trade-offs between defining eligibility by age versus ability to pay.
Keywords: Demographics; Health Conditions and Status; Healthcare; Income; Insurance; Medicare/Medicaid/Health Insurance; Methodology; Net Worth and Assets

Breast Cancer Survival, Work, and Earnings - Cathy J. Bradley; Bednarek, Heather; David Neumark (NBER Working Paper, 2001)
Relying on data from the Health and Retirement Study, we examine differences between breast cancer survivors and a non-cancer control group in employment, hours worked, wages, and earnings. Overall, breast cancer has a negative impact on the decision to work. However, among survivors who work, hours of work and, correspondingly, annual earnings are higher compared to women in the non-cancer control group. These findings suggest that while breast cancer has a negative effect on women's employment, breast cancer may not be debilitating for those who remain in the work force. We explore numerous possible biases underlying our estimates especially selection based on information in the Health and Retirement Study, and examine related evidence from supplemental data sources.
Keywords: Demographics; Employment and Labor Force; Health Conditions and Status; Healthcare; Medicare/Medicaid/Health Insurance; Methodology; Other; Retirement Planning and Satisfaction; Social Security; Women and Minorities

Depressive Symptomatology in Middle-aged and Older Married Couples: A dyadic analysis - Aloen L. Townsend; Baila Miller; Guo, S. (The Journals of Gerontology: Social Sciences, 2001)
OBJECTIVES: Depressive symptomatology has been frequently conceptualized as an individual matter, but social contextual models argue that symptom levels are likely to covary in close relationships. The present study investigated correlation between spouses' depressive symptomatology in middle-aged and older married couples, the influence of gender and race/ethnicity in predicting variability in symptom level, and the importance of individual-level covariates (education, health, and age) and couple-level covariates (household income and net worth). METHODS: Results were based on secondary analysis of Wave 1 interviews with White, Black, and Mexican American married couples (N = 5,423) from the Health and Retirement Study (HRS) and the Study of Asset and Health Dynamics Among the Oldest Old (AHEAD). Dyadic data from husbands and wives were analyzed with multilevel modeling. RESULTS: Husbands' and wives' depressive symptoms were moderately correlated, gender and race/ethnicity (and their interaction) predicted depressive symptoms, and both individual-level and couple-level characteristics were significant covariates. Similarities as well as differences are noted between the HRS and AHEAD results. DISCUSSION: Results highlight the importance of dyadic data and multilevel models for understanding depressive symptomatology in married couples. The influence of race/ethnicity merits greater attention in future research. Differences in findings between HRS and AHEAD suggest life-course, cohort, or methodological influences.
Keywords: Adult children; Demographics; Health Conditions and Status; Methodology

Eddies in the Stream: The Prevalence of Uncertain Plans for Retirement - David J Ekerdt; Kyle J Hackney; Karl Kosloski; S. DeViney (The Journals of Gerontology: Social Sciences, 2001)
OBJECTIVE: This study examined an assumption of retirement theory that typifies older workers as preretirees who are planfully engaged in paths toward retirement. METHODS: Using survey responses among workers in the 1992 and 1994 waves of the Health and Retirement Study, we described the prevalence of nonsubstantive answers to questions about the expected form and timing of retirement (e.g., don't know, haven't thought about it ). We tested explanations for this uncertainty as an artifact of the survey process, but also as an outcome of the opportunity structure for retirement planning. RESULTS: Survey procedure did generate some of these noncommittal responses. Depending on question type, approximately 10 to 40 of workers did not state when or how they would retire, and such responses were less prevalent across age and time. In addition, categorical uncertainty about form and timing was theoretically predictable in a framework that supposed that workers less subject to a socially attended life--at work or away--would be more undecided about the future. DISCUSSION: Uncertainty is an authentic, meaningful stance toward retirement that theory and research design should not ignore. Just as actual transitions to retirement can be ambiguous or blurred, the expectation of retirement, as well, can be untidy.
Keywords: Demographics; Employment and Labor Force; End of life decisions; Health Conditions and Status; Healthcare; Methodology; Other; Retirement Planning and Satisfaction; Time Use

Evaluation of Social Security reforms under alternative models of retirement and savings - Aguirregabiria, Victor (University of Western Ontario, 2001)
Keywords: Methodology; Social Security

Explaining the Role of Sex on Disability: A population-based study - Linda A. Wray; Caroline S Blaum (The Gerontologist, 2001)
PURPOSE: There is no clear consensus about how sex influences prevalent disability and through what mechanisms. We investigated whether sex had a direct independent effect on disability or whether sex had an interactive effect on the relationship between chronic diseases/conditions and disability, and whether these effects differed in middle-aged versus older adults. DESIGN AND METHODS: We used baseline data from two nationally representative health interview surveys, the Health and Retirement Study (HRS) and the Study of Asset and Health Dynamics Among the Oldest Old (AHEAD), and disability and covariate measures that were nearly identical in both surveys. Logistic regression models tested the contributions of diseases, impairments, and demographic and social characteristics on difficulties with prevalent activities of daily living (ADLs), mobility, and strength. RESULTS: Models demonstrated no direct sex effect for ADL disability in either age group after adjusting for key covariates. However, sex did exert an indirect effect on ADL disability in older adults via musculoskeletal conditions and depressive symptoms. In contrast, female sex remained strongly associated with mobility and strength disability in both age groups, net of covariates. Major interactions were also significant, including a female sex/body mass index (BMI) interaction for mobility difficulty and several sex-disease interactions for strength disability in the middle-aged group. IMPLICATIONS: The effect of sex on ADL difficulty is largely explained by social and health-related covariates in middle-aged and older adults. In contrast, the independent association of female sex with decreased strength and mobility in both groups cannot be explained by our models' social or health-related variables. In addition, the positive association of BMI with mobility difficulty is significantly worse for women than for men.
Keywords: Demographics; Disabilities; Health Conditions and Status; Methodology

HRS 1996 Imputations: Documentation - Cao, Honggao (Institute for Social Research, University of Michigan, 2001)
Keywords: Imputation; Methodology

The Impact of Involuntary Job Loss on Subsequent Alcohol Consumption by Older Workers: Findings from the Health and Retirement Survey - William T Gallo; Elizabeth H Bradley; Michele J. Siegel; Stanislav V Kasl (The Journals of Gerontology: Social Sciences, 2001)
OBJECTIVE: To estimate the effect of involuntary job loss on subsequent alcohol consumption by older workers in the United States. METHODS: Using longitudinal data from the 1992 and 1994 waves of the Health and Retirement Survey, the authors estimated multivariate models to assess the impact of involuntary job loss on subsequent alcohol use. Two outcomes were investigated: reported daily alcohol consumption and onset of drinking. The analysis sample included 207 workers who experienced involuntary job loss between survey dates and a comparison group of 2,866 continuously employed workers. RESULTS: After baseline alcohol consumption and a variety of socioeconomic and illness-related covariates were controlled, involuntary job loss was not associated (p .05) with number of daily drinks consumed at follow-up. However, among those who did not consume alcohol at baseline, individuals who suffered involuntary job loss were twice as likely as continuously employed individuals to start drinking by follow-up (OR = 2.01; CI = 1.06-3.80). The majority of those who began drinking at follow-up reported drinking less than 1 drink per day. DISCUSSION: The findings provide evidence of a significant relationship between job loss and subsequent alcohol use among baseline nondrinkers. However, the magnitude of the changes in drinking was quite modest.
Keywords: Demographics; Employment and Labor Force; Health Conditions and Status; Healthcare; Methodology; Other; Retirement Planning and Satisfaction; Risk Taking

Impute: A SAS Application System for Missing Value Imputations-With Special Reference to HRS Income/Assets - Cao, Honggao (Institute for Social Research, University of Michigan, 2001)
Survey questions that ask respondents to report amounts are often subject to high rates of missing data (Heeringa, Hill, and Howell, 1995; Hill, 1999; Juster and Smith, 1998). To avoid losing altogether valuable information from those who are unable or unwilling to provide answers to amount questions, more and more researchers rely on special questionnaire designs to collect bracket information, trying to infer exact amounts from the brackets collected. The work involving an inference of exact amount from bracket information may be called missing value imputation with brackets . When the bracket information is not available, it is reduced to a general type of imputation, called here missing value imputation without brackets . In this document, we describe a SAS application system, IMPUTE, designed for missing value imputation without brackets in general, and for inferring exact amount from bracket information in particular. To navigate our tour, and as a motivation for this project, we shall pay special attention to the Health and Retirement Study (HRS) income and assets imputations. Among many other advantages, the HRS income and asset data sets provide a good example for illustrating the uses of, and the limits to, the system.
Keywords: Income; Methodology; Net Worth and Assets

Income and Wealth Differentials of Late Middle-aged United States-born and Foreign-born Households in the United States: Implications for immigrant Social Security and retirement income - Rojanawon, Wichian (Boston College, 2001)
This study examines the economic resources and retirement outlook of older foreign-born individuals and their families in the United States. Past research indicates that immigrants experience some disadvantages compared to the U.S.-Born in the labor market due to migration and adjustment to a new culture as well as difficulty with the english language. Through the political economy and life course perspectives, stressing the importance of an individual's early experiences with the labor force, it is predicted that certain disadvantages will have an impact on retirement prospects as well as issues associated with old age. Nevertheless, there is a scarcity of research on the economic status of aging immigrants in the immigrant and retirement research, including the current research and discussion on social security reform. Research questions and hypotheses are addressed by using the Wave 1 of the Health and Retirement Study (HRS) and the HRS restricted data files. Findings from this study suggest that as a group, immigrants are likely to have low social security wealth and their income, assets and investment profiles are less than those of native-born counterparts are. Immigrants are also less likely to have employer-sponsored pensions and stock investment. If they do own stocks, the value of their holdings is likely to be much less. Recommendations for addressing policy, practice, and research efforts are presented with the goal of improving the economic conditions of aging immigrants who are at risk of poverty in old age.
Keywords: Demographics; Healthcare; Methodology; Other; Public Policy; Retirement Planning and Satisfaction

Inferring Disability Status from Corrupt Data - Kreider, Brent; John V Pepper (Iowa State University, Dept. of Economics, 2001)
We investigate what can be learned about the prevalence of work disability using self-reported assessments of work capacity. Although health status is widely recognized as a crucial determinant of labor supply behavior and participation in public transfer programs, there is a long-standing debate about the reliability of self-reported indicators. Anderson and Burkhauser (1985), in fact, labeled the appropriate use of health controls the major unsettled issue in the empirical literature on the labor supply of older workers, and the debate has only grown stronger over time. Rather than focus on assumptions required to obtain point identification, we take a step back to evaluate what can be inferred about disability rates under a variety of assumptions that are weaker but arguably more credible than those imposed in the existing literature. Extending the work on corrupt samples developed by Horowitz and Manski (1995), we develop a set of nonparametric bounds that, in the most basic setting, require only prior information restricting the fraction of persons who might misreport disability. These bounds inform the ongoing debate by effectively constraining the range of uncertainty regarding the effects of inaccurate reporting on inferences. The results clearly show that the strength of the conclusions one can draw depend directly on the strength of the assumptions one is willing to impose. Under minimal assumptions, the bounds are nearly uninformative. Tighter bounds can be obtained with additional assumptions. Under the assumption that the true disability rate is nondecreasing with age, our results imply that conventional participation models which presume valid self-reports may be misspecifed.
Keywords: Disabilities; Methodology

Lack of Health Insurance and Decline in Overall Health in Late Middle Age - David W. Baker; Joseph J Sudano; Jeffrey M. Albert; Elaine A Borawski; Avi Dor (New England Journal of Medicine, 2001)
BACKGROUND: The number of adults in their 50s and 60s in the United States who do not have health insurance is increasing. This group may be particularly vulnerable to the ill effects of being uninsured. METHODS: We conducted a prospective cohort study using files from the Health and Retirement Study, a national survey of adults who were 51 to 61 years old in 1992. We determined the risks of a major decline in overall health and of the development of new physical difficulties between 1992 and 1996 for participants who were continuously uninsured (uninsured in 1992 and in 1994), those who were intermittently uninsured (uninsured either in 1992 or in 1994), and those who were continuously insured. We used logistic regression to determine the independent effects of being uninsured on health outcomes after adjustment for base-line sociodemographic factors, preexisting medical conditions, and types of health-related behavior such as smoking and alcohol use. RESULTS: We analyzed data for 7577 participants. The 717 continuously uninsured participants and the 825 intermittently uninsured participants were more likely than the 6035 continuously insured participants to have a major decline in overall health between 1992 and 1996 (21.6 percent, 16.1 percent, and 8.3 percent of the three groups, respectively; P 0.001 for both comparisons). According to a multivariate analysis, the adjusted relative risk of a major decline in overall health was 1.63 (95 percent confidence interval, 1.26 to 2.08) for continuously uninsured participants and 1.41 (95 percent confidence interval, 1.11 to 1.78) for intermittently uninsured participants, as compared with continuously insured participants. A new difficulty in walking or climbing stairs was also more likely to develop in the continuously or intermittently uninsured participants than in the continuously insured participants (28.8 percent, 26.4 percent, and 17.1 percent of the three groups, respectively; P 0.001 for both comparisons). The adjusted relative risk of such a new physical difficulty was 1.23 (95 percent confidence interval, 1.02 to 1.47) for the continuously uninsured participants and 1.26 (95 percent confidence interval, 1.01 to 1.54) for the intermittently uninsured participants. CONCLUSIONS: The lack of health insurance is associated with an increased risk of a decline in overall health among adults 51 to 61 years old.
Keywords: Demographics; Health Conditions and Status; Medicare/Medicaid/Health Insurance; Methodology; Other

Longitudinal Changes in Net Worth by Household Income and Demographic Characteristics for the first three waves of HRS Data - Karen E. Lahey; Kim, Doseong (Financial Services Review, 2001)
The purpose of this study is to provide an initial examination of the first three waves of HRS in terms of non-housing net worth by gender, education, race, religion, income, and age. The longitudinal data that is available for a sample of those who are nearing retirement or in retirmenet allows a picture of their financial condition to be drawn. Statistical analysis indicates that there is a difference in non-housing net worth by demographic characteristics and material status for each wave of data.
Keywords: Adult children; Income; Methodology; Net Worth and Assets

Probability Limits: Are Subjective Assessments Adequately Accurate? - Bassett, William F.; Lumsdaine, Robin L. (Journal of Human Resources, 2001)
The Health and Retirement Study asks respondents their subjective probabilities about 12 future events. An individual's responses contain a common component that is unrelated to the true probability of the event in question. Use of the entire set of an individual's responses to control for this unobserved individual heterogeneity can improve the information content in responses regarding intergenerational transfer and labor force participation plans. Although there is little overall gain from renormalization, in samples where the respondent may not fully have understood the question adjusting the responses for heterogeneity leads to an improved ability to predict outcomes in later waves.
Keywords: End of life decisions; Methodology

Record Linkage and Privacy: Issues in Creating New Federal Research and Statistical Information - United States General Accounting Office (2001)
Keywords: Methodology

Reducing Panel Attrition: A Search for Effective Policy Instruments - Daniel H. Hill; Robert J. Willis (Journal of Human Resources, 2001)
In this paper we develop a theory of the survey response decision process and apply it to the analysis of field office policy measures in an attempt to see which of these are effective in reducing panel attrition. We use data from the Health and Retirement Study (HRS) to assess the effectiveness of 1) reducing the length of the interview and 2) assigning the same initial interviewer wave after wave. There is virtually no evidence in the data that interview length affects subsequent wave response. Assigning the same interviewer wave after wave, however, has a strong positive effect on response rates.
Keywords: Methodology

The Role of Micro-level Panel Data in Policy Research - R.V. Burkhauser; Smeeding, Timothy M. (Schmollers Jahrbuch: Zeitschrift fur Wirtschafts und Sozialwissenschaften/Journal of Applied Social Science Studies, 2001)
This paper focuses on the value of longitudinal micro-level data for policy centered research on behavioral and economic well-being. It provides examples of policy questions that can best be answered using such data and shows how they have been answered using data from four ongoing longitudinal panels--the BHPS (British Household Panel Study), the GSOEP (German Socio-Economic Panel), the HRS (Health and Retirement Study) and the PSID (Panel Study of Income Dynamics). Finally, it suggests a set of policy issues that can be considered using these data or from a national or a cross-national perspective.
Keywords: Consumption and Savings; Health Conditions and Status; Healthcare; Methodology; Public Policy; Retirement Planning and Satisfaction

Social Security: What is it good for? - Van Wesep, Edward P. (Michigan State University, 2001)
I develop three life cycle models that are designed to examine under what circumstances social security can improve the welfare of societies in the Pareto sense: can at least one person be made better off, without harming young and all old people are assumed to be identical. Rather, the focus is on intergenerational redistribution, which can occur three ways: (1) via private intergenerational transfers, (2) via private saving, and (3) via social security. Externalities play a prominent role in two of the models. In chapter 1, young people make private transfers to their parents, but the quantity of the total transfer from children to parents is not optimal because of an externality. Social security plays a Pigovian role in that model, setting up an incentive system designed to cause private behavior to yield the optimum result. In chapter 3, pay-as-you-go social security is revealed to be a system of intergenerational externalities. Because of this, there is avoidance of social security taxes by the young. This phenomenon of social security tax avoidance leads to a stricter welfare test for pay-as- you-go social security than the traditional Samuelsonian test. There are no externalities in chapter 2, since social security is treated there as an investment plan for workers: workers thus internalize all of the utility impacts of social security tax payments, just as they internalize the utility impacts of their private saving decisions. The welfare impact of social security in that model is a pure "moneysworth," or rate of return effect. The simplicity of the welfare criterion developed in the model of chapter 2 makes it possible to develop an empirical test of the welfare properties of the United States' Social Security system, using data from the Health and Retirement Study.
Keywords: Adult children; Demographics; Event History/Life Cycle; Methodology; Other; Public Policy

Stretching Social Surveys to Include Bioindicators: Possibilities for the Health and Retirement Study, Experience from The Taiwan Study of the Elderly - Weinstein, Maxine; Robert J. Willis (Cells and Surveys: Should Biological Measures Be Included in Social Research?, 2001)
Keywords: Methodology; Mortality

Surveys of the Life Course and Aging: Some Comparisons - Kuo, Hsiang-Hui Daphne; Park, Hyunjoon; Hauser, Taissa S.; Hauser, Robert M.; Marks, Nadine F. (University of Wisconsin-Madison, 2001)
In this paper, we introduce, compare, and evaluate the design and content of five major longitudinal studies of aging: the Wisconsin Longitudinal Study (WLS), Health and Retirement Survey (HRS), National Survey of Families and Households (NSFH), Americans' Changing Lives (ACL), and Midlife in the United States (MIDUS). We first compare population coverage, sampling design, response rate, observational duration, sources of relational and multi-level data, and links to public records. Overall, WLS, HRS, and NSFH excel in many respects. We also evaluate questions and measures in each study. In topical coverage, WLS and NSFH are the most complete. In question quality, WLS, HRS, and NSFH excel in several areas, while MIDUS and ACL stand out mainly in life event inventories, psychological measures and some health measures.
Keywords: Methodology

On The Use and Misuse of Socioeconomic Status: A Study of Mortality Among the Elderly - Donahue, Dennis (Population Association of America, 2001)
Abstract: Examined the effects of occupation on mortality among older adults, with an emphasis on how these effects relate to other measures of socioeconomic status (SES) such as income, wealth and assets, and education. Data were obtained from the Asset and Health Dynamics of the Oldest Old (AHEAD) survey on 7,441 adults aged 70 and older (mean age 77.48) in regard to 10 categories of occupations (including those who had never worked) and various measures of SES. Although the measures are crude, primary lifetime occupation was found to be as strong a predictor of mortality as traditional measures of SES. Further analysis of the effects of education found that although educational status is a significant predictor of mortality in simple hazard models, it acts fundamentally as a proxy for other SES measures. The results suggest that data availability and statistical convenience have led to the overuse of such measures as education as proxies for SES, to the detriment of more refined SES measures that are more directly proximate to individual differences in behavior, lifestyle, and financial resources.
Keywords: Demographics; Employment and Labor Force; Health Conditions and Status; Methodology

A Benefit of One's Own: Older Women's Entitlement to Social Security Retirement - Phillip B. Levine; Olivia S. Mitchell; John W R Phillips (Social Security Bulletin, 2000)
Using data from the Health and Retirement Study (HRS) and linked administrative records, we explore differences in old-age benefits between men and women attributable to differences in length of work life and pay. We find that most women are fully insured for Social Security purposes, but those who are not would have to work substantially more to become eligible. Among those who are eligible, additional work would translate into only slightly higher benefits.
Keywords: Consumption and Savings; Health Conditions and Status; Methodology; Retirement Planning and Satisfaction; Social Security; Women and Minorities

Data Watch: Research Data in Health Economics - Evans, William N.; Helen G Levy; Kosali I. Simon (Journal of Economic Perspectives, 2000)
This paper describes what data are available, what questions can be addressed by, and how one can gain access to data sets of interest to economists. The HRS and AHEAD are written up under the 'Longitudinal and Household Surveys of Health Status and Health Care Use' section of the paper. The paper summarizes both studies, explains their longitudinal nature, and describes the data used. The HRS and AHEAD represent an incredibly rich source of information on the health and economic behavior of individuals nearing retirement.
Keywords: Methodology

Employer Provided Pension Data in the NLS Mature Women's Survey and in the Health and Retirement Study - Alan L Gustman; Thomas L. Steinmeier (Research in Labor Economics, 2000)
Keywords: Consumption and Savings; Employment and Labor Force; Income; Methodology; Net Worth and Assets; Pensions; Retirement Planning and Satisfaction

Explaining Applications to the U.S. Disability System: A Semiparametric Approach - Kreider, Brent; Riphahn, Regina T. (Journal of Human Resources, 2000)
This study investigates the determinants of applications for U.S. disability benefits between, 1986 and 1993 using a semiparametric discrete factor procedure separately for men and women. Approximating a dynamic optimization model, the estimation accounts for a variety of potential biases that were unaddressed in prior studies. Our results indicate different responses of men and women to variations in policy measures. Past labor earnings and fringe benefits as well as benefit eligibility and benefit amounts clearly affect application behavior.
Keywords: Disabilities; Methodology; Pensions; Public Policy; Social Security

The Future of Age Integration in Unemployment - John C Henretta (The Gerontologist, 2000)
This article discusses the direction and implications of current and possible future trends in workplace age integration. The study used HRS respondents' attitudes towards work as a way of examining the possible supply of older workers. Overall, there are a number of underlying trends that will combine in the near future that will likely result in an increase of older persons remaining in the work force for longer. The shifting population age composition and the high education and ability levels of the cohorts born around 1950 are some of the trends that contribute to the increased demand for older workers. Other trends, such as changes in Social Security eligibility ages, the shift to DC pension plans, and the improving health of older cohorts, contribute to the increase in the supply of older workers. HRS data indicate that an overwhelming majority, 77 of men and 71 of women, say that they would like to continue some paid work when they retire. Evidence also suggests that since job flexibility among this cohort is limited, that either significant job changing from pre-retirement to postretirement jobs will be required, or significant job redesign must occur.
Keywords: Adult children; Demographics; Employment and Labor Force; Methodology; Other; Retirement Planning and Satisfaction; Social Security

A Health and Demographic Profile of Noninstitutionalized Older Americans Residing in Environments with Home Modifications. - Tabbarah, M.; Merril Silverstein; Teresa Seeman (Journal of Aging and Health, 2000)
OBJECTIVES. In this analysis the authors investigate the demographic characteristics, the health conditions/events, and the disabilities of community-dwelling Americans 70 years of age and older that are associated with residing in environments with specific home modifications. METHODS. Data from a large population-based study of the elderly are used to estimate logistic regression equations that reveal profiles of older individuals who are likely to have distinct home modifications. RESULTS. Having diseases such as diabetes and stroke, having experienced a hip fracture, a fall or a joint replacement, and having greater limitations with activities of daily living raise the likelihood of having home modifications. Low income, Hispanic, and African American elderly appear underrepresented among those with modifications. DISCUSSION. The authors conclude that specialized housing alternatives will be an increasingly important issue in the future as individuals aim to achieve and maintain the delicate balance between their functional ability and their living environment.
Keywords: Demographics; Disabilities; Health Conditions and Status; Healthcare; Housing; Methodology

The Health and Retirement Study Data Set - Unattributed (Social Security Bulletin, 2000)
This article provides a brief overview of the HRS. It comments on the valuable features and variables unique to the study and mentions the many publications that have been based on HRS data. The Health and Retirement Study (HRS) is a longitudinal study intended to provide data for researchers, policy analysts, and program planners who are making major policy decisions that affect retirement, health insurance, saving, and economic well-being. (taken from article abstract)
Keywords: Methodology

HRS 1998 Preliminary Imputations - Cao, Honggao (Institute for Social Research, University of Michigan, 2000)
Keywords: Imputation; Methodology

Microdata Panel Data and Public Policy: National and Cross-National Perspectives - R.V. Burkhauser; Smeeding, Timothy M. (Center for Policy Research Working Paper, 2000)
This paper focuses on the movement of data-based social policy analysis from a single country cross-sectional frame to a multicountry panel frame. It provides examples of policy insights this movement to panel data has permitted, both with respect to economic well-being and behavior-using data from the PSID (Panel Study of Income Dynamics), the BHPS (British Household Panel Study), the GSOEP (German Socio-Economic Panel), and the HRS (Health and Retirement Study). It also suggests fruitful areas for future panel data-based policy research.
Keywords: Methodology; Public Policy

Nonrandom Selection in the HRS Social Security Earnings Sample. - Steven Haider; Solon, Gary (Santa Monica, CA, RAND Corp., 2000)
The Health and Retirement Study (HRS), administered by the Institute for Social Research (ISR) at the University of Michigan, is a longitudinal survey of the population of U.S. households with at least one adult between the ages of 51 and 61 in 1992 (individuals born between 1931 and 1941). Wave 1 of the survey was carried out in 1992 with subsequent waves to be conducted every two years. In Wave 1, the HRS collected data on 12,652 respondents from 7,702 households. In accordance with an agreement with the Social Security Administration, HRS respondents were asked to grant ISR permission to obtain the respondents' earnings histories as reported to the Social Security Administration. Such data are extremely valuable because they provide unusually accurate administrative earnings histories over an unusually long period, 1951- 1991, and these data can be used in conjunction with the wealth of survey information collected in the HRS itself. Because of the highly confidential nature of the data, the earnings histories are not part of the FIRS public release data sets; rather, the Social Security earnings data are provided only through special permission from the HRS.
Keywords: Methodology; Social Security

Obesity, Disease, and Functional Limitation in Later Life - Christine L Himes (Demography, 2000)
Little is known about the effects of obesity late in life. Using data from the Longitudinal Study of Aging and the Assets and Health Dynamics of the Oldest Old Survey, this study finds an increased prevalence of obesity, over time, among those 70 and older. Obesity is related most strongly to limitations in activities of daily living (ADLs) for women and to activities related to mobility. One ADL, eating, has a negative association to obesity. Obesity is associated with an increased prevalence of arthritis, diabetes, and hypertension. These results are cross-sectional and are based on self-reports of height and weight; they must be interpreted cautiously.
Keywords: Demographics; Health Conditions and Status; Methodology; Other

Pension Wealth at Midlife: Comparing Self-Reports with Provider Data - Richard W. Johnson; Sambamoorthi, Usha; Crystal, Stephen (Review of Income and Wealth, 2000)
This paper evaluates the accuracy of estimates of pension wealth based on self-reports by comparing them to estimates based on provider data. Using data from the Health and Retirement Study, we found that few workers are well informed about their future pension benefits. Self-reports were often incomplete and typically varied widely from those based on information from providers. In defined benefit (DB) plans, discrepancies were greatest for workers who had limited education, earned low wages, and did not expect to retire soon. Differences in median pension wealth were smaller at the aggregate level than the individual level, because individual differences tended to offset each other when aggregated. Provider data appear better than self-reports for DB plans, but not for defined contribution (DC) plans. Where both are available, the best method of computing pension wealth may be to estimate DB wealth from provider data and to estimate DC wealth from self -reports.
Keywords: Employment and Labor Force; Methodology; Net Worth and Assets; Pensions; Retirement Planning and Satisfaction

Private Long-term Care Insurance and the Asset Protection Motive - Jennifer M Mellor (The Gerontologist, 2000)
This research examined the role of assets in the decision to purchase insurance for long-term care using survey data from the Asset and Health Dynamics Among the Oldest Old (AHEAD) study. Previous research suggests that assets matter, but the size and direction of the effect varies. An important issue regarding the role of assets has not been explored adequately--whether the effect of assets differs between less wealthy and very wealthy individuals. A methodology to control for this type of variation is employed in this analysis. Results suggest that increases in assets have the greatest influence on the probability that less wealthy individuals own long-term care insurance, and have a negligible impact on the wealthy. This has important implications for policies designed to increase long-term care insurance ownership.
Keywords: Demographics; End of life decisions; Healthcare; Medicare/Medicaid/Health Insurance; Methodology; Net Worth and Assets

Prospects for Widow Poverty - David R Weir; Robert J. Willis (Forecasting retirement needs and retirement wealth., 2000)
Keywords: Consumption and Savings; Methodology; Net Worth and Assets; Retirement Planning and Satisfaction

The Road Ahead - Wheelan, Charles J. (The Economist, 2000)
This article provides a brief overview of the HRS. It mentions the study's history and funding, and then goes on to discuss its accomplishments and major findings.
Keywords: Methodology

Scaling the Semantics of Satisfaction - Hazelrigg, Lawrence E.; Melissa A. Hardy (Social Indicators Research, 2000)
Self-assessed satisfaction is typically measured on an ordinal scale of verbal categories. Here, data from the 1992 Wave 1 of the US Health and Retirement Study (N = 12,654 respondents) are used to investigate whether the boundaries that persons implicitly set between contiguous categories are uniformly set across persons and/or across domains of satisfaction, or are variably sensitive to status characteristics and/or to domain. Analysis demonstrates systematic variations and sensitivities in the semantics of satisfaction. This semantic elasticity affects other estimates in models of self-assessed satisfaction. 3 Tables, 3 Figures, 43 References. Adapted from the source document
Keywords: Methodology; Retirement Planning and Satisfaction

Studies on the Relationship Between the Elderly and Public Policies - Harris, Amy Lenae (University of Maryland, College Park, 2000)
A number of important demographic phenomena--rising life expectancy, the post-war baby boom, and the subsequent baby bust--will have dramatic effects on the age distribution of the U.S. population well into the next century. In particular, the American population is aging. This dissertation looks at the relationships between two very different public policies and the aging population. The first relationship is a possible intergenerational conflict over public education spending at the local level. Previous research by Poterba (1997) shows a negative effect from aging on public education spending at the state level. Using school district data, the second chapter shows that at the local level the elderly also have a negative and statistically significant effect on per-pupil education spending; however, the district-level results are much smaller than previous state-level results. Several pieces of evidence are then presented to bolster my results which indicate that the elderly are much less likely to support increased spending at the state level than at the local level. The second relationship is the interaction between elderly retirement behavior and the largest federal public spending program, Social Security. To project the aging population's future claims for Social Security benefits, it is crucial to have a reliable model of retirement behavior which incorporates the incentives of the Social Security system. A promising model of retirement is the Stock and Wise (1990a) option-value model. Their structural retirement model predicts retirement behavior based on the forward-looking incentives created by social security and pensions. However, they estimated their model using an unrepresentative sample of 1,500 salesmen working for one large firm. The third chapter tests whether the Stock and Wise option-value model can be applied to a more representative sample of males from the Health and Retirement Study. When the option-value model is applied to the HRS sample, the model fails to yield economically meaningful parameters. My results suggest that additional work is needed to accurately model and project future retirement behavior of the growing elderly population.
Keywords: Demographics; Employment and Labor Force; Methodology; Other; Public Policy; Retirement Planning and Satisfaction

Why Polls Are Fickle - Charles F Manski (The New York Times, 2000)
Keywords: Methodology

Worker Well-being - Solomon W. Polachek (New York and Tokyo, 2000)
Fourteen papers address issues relevant to worker well-being. Papers discuss technology, unemployment, and inflation; the incidence of overschooling and underschooling and its effect on earnings in the United States and Hong Kong; whether higher returns to college education encourage college enrollments; whether compulsory school attendance laws alone explain the association between quarter of birth and earnings; motivation and labor market outcomes; career hierarchy in dual-earner families; whether gender matters for job mobility in 1990s Britain; how to measure relative quality of life from a cross-migration regression and an application to Canadian Provinces; employer -provided pension data in the National Longitudinal Survey of Mature Women and in the Health and Retirement Study; a test of E. Lazear's mandatory retirement model; the effectiveness of public works programs in Eastern Germany as measured by their effects on individual future reemployment probabilities in regular jobs; lessons about the labor supply implications of universal health coverage from a study of individuals receiving insurance through their spouses' employers; dimensions of the wage-unemployment relationship in the Nordic countries; and the extent and consequences of downward nominal wage rigidity. Polachek is in the Department of Economics at the State University of New York, Binghamton. No index.
Keywords: Employment and Labor Force; Methodology; Time Use

Anchoring and Acquiescence Bias in Measuring Assets in Household Surveys - Michael D Hurd (Journal of Risk and Uncertainty, 1999)
Cognitive psychology has identified and studied extensively a number of cognitive anomalies that may be important for the assessment of the economic status of individuals and households. In particular the use of brackets to elicit information about income and assets in surveys of households can interact with acquiescence bias and anchoring to cause bias in the estimates of the distributions of income and assets. This paper uses data from the Health and Retirement Study and the Asset and Health Dynamics Study to find that, as predicted by psychology, bracketing can produce bias in population estimates of assets.
Keywords: Methodology

Approaches for Estimating Noncompliance: Examples From Federal Taxation in the United States - Feinstein, Jonathan S. (The Economic Journal, 1999)
Keywords: Methodology

The Association of Influenza Vaccine Receipt with Health and Economic Expectations among Elders: The AHEAD Study - Robert B Wallace; Nichols, Sara; Michael D Hurd (Wealth, work, and health: Innovations in measurement in the social sciences: Essays in honor of F. Thomas Juster, 1999)
Keywords: Consumption and Savings; Expectations; Health Conditions and Status; Methodology

Changing Pensions in Cross-Section and Panel Data: Analysis with Employer Provided Plan Descriptions - Alan L Gustman; Thomas L. Steinmeier (Proceedings, National Tax Association, 1999)
This study analyzes changes in the value of defined benefit (DB) pension plans over time. It uses summary plan descriptions provided by the employers of respondents to the Survey of Consumer Finances (SCF) in 1983 and in 1989, applying them to similar earnings histories. Pension changes between 1990 and 1995 are also analyzed, using employer plan descriptions for large firms published by the Watson Wyatt Company. Substantial changes are found in pension values and pension accruals between the two SCF cross-sections. For example, the median value of DB plans at age 55 is 40 percent higher in 1989 than in 1983. Also, early retirement age falls over the time period. Because there are important changes in the composition of the pensions in each cross-section, those who are covered by the same plan in both years experience smaller changes than are suggested by comparing cross-section data from two different time periods. Nevertheless, those who are continuously covered by the same pension also experience important pension changes over the period. For example, a fifth of those continuously covered by a defined benefit plan experiences a substantial change in early retirement date and early retirement benefits. In addition, subgroups of continuously covered workers experience pension changes in opposite directions. These changes will have a substantial influence on retirement behavior, but are dampened when comparing the differences over time in the means and medians of plan features and plan values. Using the data from Watson Wyatt on the pensions offered by thirty-nine of the fifty largest companies, we also find similar evidence of important changes over the period 1990 to 1995. Again a sizable minority of firms experience very large changes in their plans. These findings suggest that changes in successive cross-sections of pensions will exaggerate the changes in continuing plans. Nevertheless, substantial errors will be introduced into retirement studies if pension incentives and pension values are estimated from a single cross-section under the assumption that pension plans remain stable over time.
Keywords: Methodology; Pensions

Characteristics of Individuals with Integrated Pensions - Bender, Keith A. (Social Security Bulletin, 1999)
This paper examines the characteristics of individuals covered under integrated pension plans by comparing them with people covered by non-integrated plans and those with no pesion coverage. Females, whites, non-union members, and those workers with less than a postgraduate education are more likely to be covered under integrated pensions. Higher earnings or having a defined benefit pension plan are also strong predictors for having an integrated pension plan. When region and industry type are considered, reults show that workers in the Pacific region and in manufacturing are more likely to be covered by integrated pensions.
Keywords: Demographics; Employment and Labor Force; Methodology; Net Worth and Assets

Cognitive Performance Measures in Survey Research on Older Adults - A. Regula Herzog; Willard L Rodgers (Cognition, Aging, and Self Reports, 1999)
Many researchers wonder whether cognitive ability decreases in the elderly and surveys of the elderly tend to include tests of cognitive ability that allow survey administrators to reject certain peoples responses or adjust the weight given to responses based on the respondents cognitive ability. The author s discuss cognitive tests used in the AHEAD Study, methodological issues of such tests, and the validity of cognitive measures in these tests. After a great deal of testing they conclude that the survey measures for cognition in the two studies are valid. They also present a number of methodological problems within cognitive tests and ways to resolve such problems.
Keywords: Health Conditions and Status; Methodology

Employer Provided Pension Data in the NLS Mature Women's Survey and in the Health and Retirement Study - Alan L Gustman; Thomas L. Steinmeier (National Bureau of Economics Research, 1999)
We compute pension wealth from employer provided pension plan descriptions matched to respondent surveys to the National Longitudinal Survey of Mature Women (NLS-MW) and the Health and Retirement Study (HRS). These calculations provide detailed information on the level and distribution of pension wealth and a variety of incentives from pensions. Differences between the pensions of men and women are largely explained by differences in earnings. However, there also are differences in the shapes of the pension accrual profiles of defined benefit plans that are likely to reflect tenure of women. Pension coverage is lower in the NLS-MW than in the HRS. As a result, wealth is lower in the NLS-MW than in the HRS. But the difference in coverage is not due to the effects of pension matching. Pension values for covered respondents are similar between the NLS-MW and HRS surveys. Systematic differences between the surveys in the rate at which pensions were matched do not have a major effect on findings as to the levels and distributions of pension wealth between the surveys.
Keywords: Consumption and Savings; Employment and Labor Force; Income; Methodology; Net Worth and Assets; Pensions; Retirement Planning and Satisfaction

Essays in Applied Microeconometrics - Robert R. Weathers II (Syracuse University, 1999)
This dissertation consists of three essays in applied microeconometrics. In the first essay, I use retrospective data from the Health and Retirement Study (HRS) together with matching state level data on SSDI allowance rates and individual level Social Security administrative record data on the generosity of SSDI benefits to examine how the Social Security Disability Insurance program affects a person's work behavior following the onset of a disability. A hazard model that allows for both measured and unmeasured heterogeneity is used to estimate the relative importance of policy variables--employer accommodation as well as the relative value and likelihood of acceptance onto the SSDI program--on the timing of SSDI application following the onset of a disability. The results show that employer accommodation significantly slows a worker's application for SSDI benefits while easier access to SSDI benefits and more generous SSDI benefits increase the speed of application following the onset of a health condition. In the second essay, I develop three approaches that may be used to obtain consistent estimates of the structural parameters in the fixed effects ordered logit model. The first approach uses the adjacent categories form of the ordered logit along with the conditional logit and minimum distance estimator to obtain estimates of the structural parameters. In a second step, the Generalized Method of Moments (GMM) is used to estimate the sum of the limit parameters and the fixed effects, and finally the limits are estimated based on the means of the sums. The other approaches interpret fixed effects as random effects. The second approach specifies the fixed effects as omitted variables that raise the variance of the disturbance and bias the logit estimates. A generated regressor is created to allow the bias to be corrected. The third approach generalizes a new method of estimation for the fixed effects logit model to the ordered logit. Specification tests are extended to these estimators and a Monte Carlo experiment is constructed to test the small sample properties of the estimator. The third essay uses data from the Panel Study of Income Dynamics (PSID) to examine how experience with entrepreneurship--defined as persons who are self-employed--has affected an individual's place in the earnings distribution. The strategy is to follow individuals' positions in the income distribution over time, and to see how their mobility was affected by involvement with entrepreneurship. The results show that for low-income individuals there is some merit to the notion that the self-employed moved ahead in the earnings distribution relative to those who remained wage earners. On the other hand, for those at the upper end of the earnings distribution, those who became self-employed often advanced less in the earnings distribution than their wage and salary counterparts.
Keywords: Demographics; Disabilities; Employment and Labor Force; Methodology; Social Security

Formation of Trusts and Spend Down to Medicaid - Donald H. Taylor Jr.; Frank A Sloan; Edward C Norton (The Journals of Gerontology: Social Sciences, 1999)
OBJECTIVE: To identify the proportion of community-dwelling elderly persons (70 ) who could affect their eligibility for Medicaid financing of a nursing home stay through the use of a trust and to quantify the prevalence and predictors of trusts. METHODS: State-specific Medicaid eligibility regulations were used to determine eligibility and to identify those who could affect the same through the use of trusts. Multivariate logistic regression was used to identify correlates of having a trust. Wave 1 of the Assets and Health Dynamics of the Oldest Old (AHEAD) data base was used. RESULTS: Four in 10 elderly community dwellers could potentially qualify for Medicaid by using a trust; however, less than 10 had a trust. On average, wealthier persons had trusts. Avoidance of probate and controlling assets after death appear to be stronger motivations for trust creation among the elderly than achieving Medicaid spend down. DISCUSSION: The use of trusts was not common, and motives other than spend down were more important for those with trusts. Our results suggest little need for policy efforts to limit the use of trusts to achieve spend down.
Keywords: Adult children; Demographics; Health Conditions and Status; Healthcare; Medicare/Medicaid/Health Insurance; Methodology; Net Worth and Assets

Inheritances and Bequests - James P Smith (Wealth, work, and health: Innovations in measurement in the social sciences: Essays in honor of F. Thomas Juster, 1999)
Keywords: Adult children; Consumption and Savings; Methodology

Intergenerational Transfers: Blood, Marriage, and Gender Effects on Household Decisions - Beth J Soldo; Douglas A. Wolf; John C Henretta (Wealth, work, and health: Innovations in measurement in the social sciences: Essays in honor of F. Thomas Juster., 1999)
Keywords: Adult children; Consumption and Savings; Demographics; Event History/Life Cycle; Methodology

Lifetime Earnings, Saving Choices, and Wealth at Retirement - Steven F Venti; David A Wise (Wealth, work, and health: Innovations in measurement in the social sciences: Essays in honor of F. Thomas Juster, 1999)
Keywords: Consumption and Savings; Event History/Life Cycle; Methodology; Net Worth and Assets; Retirement Planning and Satisfaction

Nonparametric Modeling of the Anchoring Effect in an Unfolding Bracket Design - Vazquez Alvarez, Rosalia; Melenberg, Bertrand; Arthur H.O. vanSoest (Tilburg, NE, Tilburg University, Center for Economic Research Discussion Paper, 1999)
Household surveys are often plagued by item non-response on economic variables of interest like income, savings or the amount of wealth. Manski (1989,1994, 1995) shows how, in the presence of such non-response, bounds on conditional quantiles of the variable of interest can be derived, allowing for any type of non-random response behavior. Including follow up categorical questions in the form of unfolding brackets for initial item non-respondents, is an effective way to reduce complete item non-response. Recent evidence, however, suggests that such design is vulnerable to a psychometric bias known as the anchoring effect. In this paper, we extend the approach by Manski to take account of the information provided by the bracket respondents. We derive bounds which do and do not allow for the anchoring effect. These bounds are applied to earnings in the 1996 wave of the Health and Retirement Survey (HRS). The results show that the categorical questions can be useful to increase precision of the bounds, even if anchoring is allowed for.
Keywords: Methodology

Panel Attrition Bias in Health-Event Models - Daniel H. Hill (University of Michigan Institute for Social Resear, 1999)
Keywords: Methodology

Scale Simplification of Expectations for Survival: Cognitive Ability and the Quality of Survey Responses - Robert F. Belli; A. Regula Herzog; Van Hoewyk, John (Cognitive Technology, 1999)
This paper examines how data quality (specifically data that uses response scales designed to measure event probability) is affected by the cognitive ability of respondents and whether or not respondents provide a simplification process. Cognitive ability does have an affect on how respondents answer survey questions that use a high number of response options. Evidence of satisficing and providing simplification responses does show up in respondents with lower cognitive abilities, but the bunching phenomenon (due to satisficing) appears to have only limited effects on the data quality. Regardless of this limited effect, the results suggest ways of improving the quality of survey questions that use many response options. Better data quality will result when questioning leads respondents with higher cognitive abilities to maximize the number of response options while leading lower able respondents to deal with a reduced set of response options. The unfolded bracket technique is an example of such a method.
Keywords: Expectations; Health Conditions and Status; Methodology

The Several Cultures of Research on Subjective Expectations - Dominitz, Jeff; Charles F Manski (Wealth, Work and Health: Innovations in Measurement in the Social Sciences, 1999)
Keywords: Expectations; Methodology

The Size Distribution of Wealth in the United States: A Comparison Among Recent Household Surveys - Wolff, Edward (Wealth, Work and Health: Innovations in Measurement in the Social Sciences, 1999)
Keywords: Income; Methodology

Social Security, Pensions, and the Retirement Decisions of Individuals and Couples - Courtney Coile (Massachusetts Institute of Technology, 1999)
This thesis presents three empirical studies of Social Security, private pensions, and retirement decisions. Chapter 2 is a study of the retirement decisions of women and couples. Motivated by the fact that the typical household is a dual-worker family, this chapter addresses three issues. The first is the effect of retirement incentives from Social Security and pensions on women's retirement behavior. The second is the spillover effects of incentives on the retirement behavior of spouses. The third is the joint retirement decision-making of couples. Using the Health and Retirement Study (HRS), the retirement incentives from Social Security and pensions are calculated and reduced form models of the impact of each spouse's incentives on their own and spouse's retirement decisions are estimated, as well as two-stage models using incentives as instruments for retirement behavior. The principal findings are that women are as responsive to their own retirement incentives as men and that women's incentives have large spillover effects on men's behavior, while men's incentives do not. The latter result is attributed to asymmetric complementarities of leisure. Chapter 3, joint with Jonathan Gruber, examines the retirement decisions of men. This chapter also uses the HRS to compute retirement incentives and aims to overcome a lack of attention in previous work to dynamic incentives, to the separate effect of Social Security and pensions, to the identification of retirement impacts, and to data deficiencies. Forward-looking incentive measures are found to be more important in explaining behavior and policy simulations suggest that incentive effects may be large. Chapter 4, joint with Peter Diamond, Jonathan Gruber, and Alain Jousten, examines Social Security benefit claiming behavior. The key findings are that delays are optimal in a wide variety of cases, that a non-trivial share of early retirees delays at least one year, and that delays are consistent with cross-sectional predictions.
Keywords: Employment and Labor Force; Methodology; Retirement Planning and Satisfaction

Theory Confronts Data: How the HRS is Shaped by the Economics of Aging and How the Economics of Aging Will be Shaped by the HRS - Robert J. Willis (Labour Economics, 1999)
This paper describes the evolution of the HRS from its origins in 1992 to its current design as a longitudinal 'steady state' sample of older Americans which is representative of the U.S. population over age 50. It discusses the conceptual framework of the survey as well as the broad theoretical concepts that lead to its content and design. The paper concludes with a description of some recent findings that use the HRS data; in particular the positive correlation between health and wealth.
Keywords: Health Conditions and Status; Methodology; Net Worth and Assets

Unfolding Bracket Method in the Measurement of Expenditures and Wealth - Daniel H. Hill (Wealth, Work, and Health: Innovations in Measurement in the Social Sciences: Essays in honor of F. Thomas Juster., 1999)
Keywords: Consumption and Savings; Methodology; Net Worth and Assets

Wealth, Work, and Health: Innovations in Measurement in the Social Sciences: Essays in honor of F. Thomas Juster - James P Smith; Robert J. Willis (University of Michigan Press, 1999)
Twelve papers, presented at a December 1996 conference at the Institute for Social Research (ISR), celebrating the career of F. Thomas Juster and his retirement from the University of Michigan and the ISR, focus on survey measurement and analysis of survey data in the social sciences. Papers discuss the several cultures of research on subjective expectations; measuring investment in young children with time diaries; the unfolding bracket method in the measurement of expenditures and wealth; lifetime earnings, saving choices, and wealth at retirement; inheritances and bequests; pension and social security wealth in the Health and Retirement Study; the size distribution of wealth in the United States as measured by recent household surveys; a cross -national comparison of health, work, and economic well-being of older workers aged fifty-one to sixty-one using the U.S. and Dutch data sets; labor market transitions and whether subjective probabilities of working have predictive power for actual retirement; the impact of education and heart attack on smoking cessation among middle-aged adults; the association of influenza vaccine receipt with health and economic expectations among elders; and co -residence between married adult children and their elderly unmarried mothers. Contributors include economists. Smith is at the RAND Corporation. Willis is at the University of Michigan and the Institute for Social Research. No index.
Keywords: Consumption and Savings; Health Conditions and Status; Income; Methodology; Retirement Planning and Satisfaction

Anchoring Effects in the HRS: Experimental and Nonexperimental Evidence - Michael D Hurd (The National Bureau of Economic Research, 1998)
The Health and Retirement Study (HRS) and a number of other major household surveys use unfolding brackets to reduce item nonresponse. However, the initial entry point into a bracketing sequence is likely to act as an anchor or point of reference to the respondent. For example, when the initial entry point is high the distribution will be shifted to the right, leading one to believe that holdings of the particular asset are greater than they truly are. This paper analyzes some experimental data on housing value from HRS wave 3 for anchoring effects. The paper also compares the distributions of assets in HRS waves 1 and 2 for evidence about any anchoring effects that may have been caused by changes in the entry points between the waves. Both the experimental data on housing values and the nonexperimental data from HRS waves 1 and 2 on assets show anchoring effects.
Keywords: Health Conditions and Status; Healthcare; Methodology; Retirement Planning and Satisfaction

Caring for the Elderly: The Role of Adult Children - Kathleen McGarry (Inquiries in the economics of aging, 1998)
Keywords: Adult children; Consumption and Savings; Demographics; Healthcare; Methodology

Consumption and Saving Balances of the Elderly: Experimental Evidence on Survey Response Bias - Michael D Hurd; Daniel McFadden; Chand, Harish; Gan, Li; Merrill, Angela; Michael Ewing Roberts (Frontiers in the Economics of Aging, 1998)
A prerequisite for understanding the economic behavior of the elderly, and the impacts of public policy on their health and well-being, is accurate data on key economic variables such as income, consumption, and assets, as well as on expectations regarding future economic and demographic events such as major health costs, disabilities, and death. Standard practice is to elicit such information in economic surveys, relying on respondents’ statements regarding the variables in question. Economists are generally aware that stated responses are noisy. Item nonresponse is a common problem, and carefully done surveys are designed to minimize it. Well-designed analyses of economic survey data are careful about detecting implausible outliers, imputing missing values, and correcting for selection caused by dropping missing observations. Circumstances are recognized that tend to produce systematic biases in response, such as telescoping in recall of past events that arises from the psychophysical perception of time intervals, or overstatement of charitable contributions that arises from the incentive to project a positive self-image. Nevertheless, economic studies are often too sanguine about the reliability of subjects’ statements regarding objective economic data.
Keywords: Consumption and Savings; Methodology

The Effects of Bracketing and Anchoring on Measurement in the Health and Retirement Study - Michael D Hurd; Willard L Rodgers (University of Michigan, Institute for Social Research, 1998)
Keywords: Methodology

The Empirical Validity of the HRS Medical Expenditure Data: A Model to Account for Different Reference Periods - Daniel H. Hill; Mathiowetz, Nancy A. (University of Michigan Institute for Social Research, 1998)
Keywords: Medicare/Medicaid/Health Insurance; Methodology

The Impact of Education and Heart Attack on Smoking Cessation Among Middle-aged Adults - Linda A. Wray; A. Regula Herzog; Robert J. Willis; Robert B Wallace (Journal of Health and Social Behavior, 1998)
Considerable evidence supports the premise that higher levels of education lead to enhanced health, including protective health behaviors. This paper focuses on how education affects one health behavior known to lead to enhanced health: the cessation of smoking. In particular, the authors examine the extent to which education influences the decision by middle-aged adults to quit smoking following a heart attack, a potentially life-threatening health event. We first hypothesize that middle-aged adults with more formal education will stop smoking more readily than people with less formal education following the experience of a heart attack. Second, we ask what other factors might underlie and explain that hypothesized effect. Using longitudinal data, the authors track changes in individual smoking behaviors after a heart attack among preretirement-age Americans. We control for documented correlates of smoking and heart attack plus other factors associated with education, heart attack, and smoking that may also influence whether a person quits smoking. In addition to confirming evidence on the education-health association as well as the documented connection between heart attack and smoking cessation, this study provides a surprising twist on those links: Our results show that the move to quit smoking following the experience of a heart attack among middle-aged adults is significantly and dramatically moderated by their level of educational attainment.
Keywords: Demographics; Health Conditions and Status; Methodology

International Models for Pension Reform - Olivia S. Mitchell (University of Pennsylvania, 1998)
Keywords: Methodology; Pensions; Public Policy

Late Life Job Displacement - Kenneth A. Couch (The Gerontologist, 1998)
Data from the 1992 wave of the Health and Retirement Study are used to examine the incidence of job displacement among workers ages 51 through 60. The average displaced worker experiences a loss in earnings of 39 . Households which contain a displaced worker have incomes 24 lower than the household of an average worker. Little of these lost earnings are replaced through pension income. The rate of health insurance coverage is 16 lower among displaced workers. As with other labor market outcomes, non-Whites on average are the most economically vulnerable following displacement.
Keywords: Demographics; Employment and Labor Force; Health Conditions and Status; Income; Medicare/Medicaid/Health Insurance; Methodology; Other; Pensions

Married Women's Retirement Expectations: Do Pensions and Social Security Matter? - Honig, Marjorie (American Economic Review, 1998)
Keywords: Methodology; Pensions; Retirement Planning and Satisfaction; Social Security; Women and Minorities

The Microeconomics of the Retirement Decision in the United States - Joseph F. Quinn; R.V. Burkhauser; Kevin E. Cahill; Robert R. Weathers II (1998)
Keywords: Methodology; Retirement Planning and Satisfaction

The Multidimensional Configuration of Functional Disability: Patterning by Age, Sex, Race, and Health Status - Lamb, V.L.; Faust, K. (University of South Carolina, Dept. of Sociology, 1998)
Keywords: Disabilities; Methodology

Older Parents' Expectations of Moving Closer to Their Children. - Merril Silverstein; Angelelli, J.J. (The Journals of Gerontology: Social Sciences, 1998)
Research shows that older parents engage in return migration in older to live closer to children from whom they receive care. However, less is known about how characteristics of adult children influence this process. Data for this analysis are from 5,382 older parents participating in the 1993/4 AHEAD national survey of adults aged 70 years old and older. Findings demonstrate that elderly parents who expect to move closer to adult children tend to be older, female, and have at least one child who is better-off financially than they are. Living alone magnifies the effect of poor self-rated health on expecting to move closer to a child. Random effects modeling of children's characteristics reveals that parents are more likely to expect to move closer to a daughter than to a son. Greater parental functional impairment was found to further depress the selection of sons. Overall, the findings suggest that older parents expect to move closer to adult children out of need and tend to select a target child with greater potential to provide support.
Keywords: Adult children; Demographics; Health Conditions and Status; Housing; Income; Methodology

Predictors of Onset Of and Recovery From Mobility Difficulty Among Adults Aged 51-61 Years - Daniel O. Clark; Timothy E. Stump; Frederic D Wolinsky (American Journal of Epidemiology, 1998)
Relative to information on activities of daily living, information regarding the onset of and recovery from mobility difficulty has been limited. Drawing upon data gathered from 6,376 self-respondents aged 51-61 years at baseline (1992) who were successfully reinterviewed in 1994 as part of the Health and Retirement Survey, the authors were able to build upon and add to knowledge gained from previous studies of the onset of and recovery from mobility difficulty. Hierarchical logistic regression was used to separate the direct and indirect effects of predictors of mobility difficulty onset and recovery at 2-year follow-up. To separate direct and indirect effects, the authors categorized various predictors as being related to sociodemographic factors, economic factors, health behavior, chronic disease, or physical impairment, and the categories were sequentially incorporated into a series of equations. The order in which the predictors were incorporated into the equations followed from a theoretical model of the disability process. In this study of mobility difficulty, the strongest direct predictors of recovery were having little baseline difficulty and the absence of diabetes mellitus, lung disease, and frequent pain. The strongest direct predictors of onset were female sex, less education, low net worth, lack of private health insurance, obesity, and frequent pain. Few indirect predictors for either onset or recovery were identified. Predictors of recovery were few and differed from predictors of onset. Further efforts are needed to identify modifiable predictors among females, persons with few economic resources, and those with frequent pain.
Keywords: Demographics; Disabilities; Health Conditions and Status; Methodology; Other; Risk Taking

Privatizing Social Security: First Round Effects of a Generic Voluntary Privatized U.S. Social Security System - Alan L Gustman; Olivia S. Mitchell; Thomas L. Steinmeier (Privatizing Social Security, 1998)
Keywords: Methodology; Public Policy; Social Security

Adverse Selection, Bequests, Crowding Out, and Private Demand for Insurance: Evidence from the Long-Term Care Insurance Market - Frank A Sloan; Edward C Norton (Journal of Risk and Uncertainty, 1997)
Adverse selection, moral hazard and crowding out by public insurance have all been proposed as theoretical reasons for why the market for private long -term care insurance has been slow to evolve in the U.S. Using national samples of the elderly and near elderly, this study investigates which is most important. The data contain direct measures of risk aversion, expectations of future nursing home use and living to old age, and the bequest motive. For both groups, we find evidence of adverse selection, and, for the elderly, crowding out of private long-term care insurance by Medicaid. However, we do not find that demand for such insurance is motivated either by bequest or exchange motives.
Keywords: Consumption and Savings; Demographics; Health Conditions and Status; Healthcare; Insurance; Methodology

Asset and Health Dynamics Among the Oldest Old: An overview of the AHEAD Study - Beth J Soldo; Michael D Hurd; Willard L Rodgers; Robert B Wallace (The Journals of Gerontology, Series B: Psychological Sciences and Social Sciences, 1997)
This article contains background information on the study of Asset and Health Dynamics Among the Oldest Old (AHEAD), a prospective panel survey of persons born in 1923 or earlier who were residing in the community at the time of the 1993 baseline. Interviews were sought with both spouses in married households, and an overall total of 8,222 were completed. We review the interdisciplinary scientific issues that motivated the study, describe the fundamental design decisions that structured AHEAD, and summarize the content in the core and experimental modules. The study provides unusually detailed data on cognition, family structure and transfers, and assets. Data are presented on sample selections, response rates, and oversamples of minority groups. Basic descriptive data on the demographic, health, and socioeconomic attributes of respondents also are presented. Plans for future waves of AHEAD are described, including a next-of-kin interview for decreased respondents.
Keywords: Adult children; Demographics; Health Conditions and Status; Healthcare; Income; Methodology; Net Worth and Assets

Building Better Retirement Income Models - Bone, Christopher M.; Olivia S. Mitchell (North American Actuarial Journal, 1997)
There is a strong and immediate need to collect more data and to construct better retirement income policy models. In the very near future, changes must be made to the U.S. retirement policy. These changes and the policy itself will only be effective if it is based on strong retirement models. The article describes recent efforts and developments that may interest those concerned with retirement issues. The HRS is praised for its ability to obtain the necessary information on older workers that has for so long been missing from the field of retirement research.
Keywords: Methodology; Retirement Planning and Satisfaction

Data Markets and the Production of Surveys - Philipson, Tomas (Review of Economic Studies, 1997)
The production of data, and the functioning of the market for observations, are universal concerns to all fields of positive economics. Economists, however, have typically placed greater emphasis on systematically analyzing the consumption of data than on considering its production. In the production of data through surveys, an important input market is that of labor, in which a demander trades observations with the supplying sample members. This paper analyses optimal monopsony compensation in such data markets, the important relationship it bears to estimation using the data that are obtained, and the statistical effects of implicit public wage regulations that are present in US markets for observations.
Keywords: Employment and Labor Force; Methodology

Distribution and Association of Chronic Disease and Mobility Difficulty Across Four Body Mass Index Categories of African-American Women - Daniel O. Clark; Mungai, S.M. (American Journal of Epidemiology, 1997)
A majority of African-American women over the age of 50 are obese, have at least one chronic disease, and experience mobility difficulty. Using self-reported data from the 1992 Health and Retirement Study of 1,150 African-American women aged 30-70 years, this report first compares chronic disease prevalence and severity, pain, sensory deficits, and mobility difficulty across four categories of body mass index and, second, investigates whether body mass index affects the association of chronic disease with mobility difficulty. Body mass index was categorized as low, medium, high, and severe, being equal to 19-24 (20 ), 25-29 (38 ), 30-34 (24 ), and 35 or over (18 ), respectively. There were few differences when comparing the medium category with either the low or high category. Those in the severe body mass index category, however, reported significantly more frequent and severe hypertension, diabetes, cancer, heart disease, arthritis, pain, sensory deficits, and mobility difficulty than did those in the medium body mass index category. Obesity did not appear to affect the association between chronic disease and mobility difficulty. The relatively high rates of mobility difficulty observed among the severe body mass index group appear to be more likely a result of relatively high chronic disease prevalence and severity than to a disproportionate impact of these on mobility.
Keywords: Demographics; Health Conditions and Status; Methodology; Other

Improving the Quality of Economic Data: Lessons from the HRS and AHEAD - Juster, F. Thomas; James P Smith (Journal of the American Statistical Association, 1997)
Missing data are an increasingly important problem in economic surveys, especially when trying to measure household wealth. However, some relatively simple new survey methods such as follow-up brackets appear to appreciably improve the quality of household economic data. Brackets represent partial responses to asset questions and apparently significantly reduce item nonresponse. Brackets also provide a remedy to deal with nonignorable nonresponse bias, a critical problem with economic survey data.
Keywords: Methodology

Imputation of Multivariate Data on Household Net Worth - Steven G Heeringa; Roderick J.A. Little; Trivellore E. Raghunathan (Proceedings of the American Statistical Association, 1997)
This paper analyzes the various methods involved in the imputation of multivariate data. The paper investigates methods of imputing amounts for bracketed net worth variables; empirically compares the distributional properties of data imputed by the alternative methods; and estimates the imputation variance that each method adds to the completed data set.
Keywords: Methodology; Net Worth and Assets

Older Couples: An Examination of Health and Retirement within the Context of the Family - Pienta, Amy M. (Penn State University Population Research Institute, 1997)
This paper illustrates the ways in which health experiences of one's spouse effects retirement choices of other persons in the family. To understand the consequences of health problems on one's spouse the researchers devise a theoretical model and use data from the first (1992) and second (1994) waves of the Health and Retirement Study. A longitudinal study was necessary in order to see changes across time and develop multilevel hazard models reflecting the labor force transitions due to changes in a spouses health. Poor health of ones spouse reduces the chance of a persons retiring at the time that one had initially anticipated. They also find that a person whose spouse is disabled is no more likely to become disabled themselves then one whose spouse is not disabled. The researchers were surprised to find that labor force reentry was not changed when a family member became ill or disabled.
Keywords: Adult children; Disabilities; Employment and Labor Force; Health Conditions and Status; Healthcare; Methodology

Pension and Social Security Wealth in the Health and Retirement Study - Alan L Gustman; Olivia S. Mitchell; Andrew A. Samwick; Thomas L. Steinmeier (National Bureau of Economic Research, 1997)
Together, pensions, social security and health insurance account for half of the wealth held by all households in the Health and Retirement Study (HRS), for 60 percent of total wealth of HRS households who are in the 45th to 55th wealth percentiles, and even for 48 percent of wealth for those in the 90th to 95th wealth percentiles. The HRS surveys households aged 51 to 61 in 1992, and obtains pension plan descriptions from respondents' employers. Pension accrual profiles, income and wealth distributions by type, wealth-income ratios and accrued wealth by pension status are also explored.
Keywords: Consumption and Savings; Income; Medicare/Medicaid/Health Insurance; Methodology; Net Worth and Assets; Pensions; Retirement Planning and Satisfaction; Social Security

Question Difficulty and Respondents' Cognitive Ability: The Impact on Data Quality - Barbel Knauper; Robert F. Belli; Daniel H. Hill; A. Regula Herzog (Journal of Official Statistics, 1997)
Older respondents lower in cognitive ability are more affected by question difficulty than older respondents higher in cognitive ability. Respondents lower in cognitive ability gave more DK responses to difficult than to easy questions, while the differences between the difficult and easy questions were not as apparent for respondents with higher cognitive abilities. This effect may result in biased survey findings because responses to difficult questions from respondents with lower cognitive ability would be underrepresented.
Keywords: Health Conditions and Status; Medicare/Medicaid/Health Insurance; Methodology

The Role of Conditioning Information in Reports of Subjective Phenomena - Dominitz, Jeff (California Institute of Technology, 1997)
Reports of subjective phenomena are inherently subject to some uncertainty on the part of the respondent. The existence of uncertainty is obvious when the reports are of subjective expectations about prospective outcomes. In other cases, it is not so clear. Sometimes respondents are asked to make hypothetical choices, in which case uncertainty remains unless all relevant elements of the hypothetical scenario are specified. More generally, whenever concepts are loosely defined, be they prospective outcomes, hypothetical scenarios, or other relevant aspects of the question, uncertainty about the appropriate response will remain. This paper considers the interaction between this uncertainty and the text and context of the survey question. Three types of questions are discussed -- questions eliciting unconditional expectations, conditional expectations, and hypothetical choices. In each case, it is difficult to convey to respondents the types of information on which they should and should not condition. When respondents use information in a way that differs from the researcher s assumptions, the researcher may infer that respondents are deficient in some way (e.g., do not provide coherent probability assessments or do not have consistent preference orderings).
Keywords: Expectations; Methodology

Selection of Children to Provide Care: The effect of earlier parental transfers - John C Henretta; Martha S. Hill; Li, Wei; Beth J Soldo; Douglas A. Wolf (The Journals of Gerontology, Series B: Psychological Sciences and Social Sciences, 1997)
We use the first wave of data from the Asset and Health Dynamics Among the Oldest Old (AHEAD) study to examine the effects of past parent-to-child financial transfers on selection of a child to provide assistance with basic personal care for unmarried parents. We estimate a fixed-effects conditional logit model and find a positive and significant association between past financial transfers and a child's current helping behavior. The coefficient of past financial transfers is in the direction hypothesized, and its magnitude is 80 as large as that of gender, a well-documented powerful predictor of parental caregiving. There appears to be substantial evidence that earlier parent-to-child financial gifts play a role in determining which child in the family will provide assistance.
Keywords: Adult children; Demographics; Health Conditions and Status; Healthcare; Income; Methodology; Other

Socioeconomic Status and Racial and Ethnic Differences in Functional Status Associated with Chronic Diseases - Raynard Kington; James P Smith (American Journal of Public Health, 1997)
OBJECTIVES: This study examined the relationships between wealth and income and selected racial and ethnic differences in health. METHODS: Cross-sectional data on a national sample of 9744 men and women aged 51 through 61 from the 1992 Health and Retirement Survey were analyzed to examine the association between socioeconomic status and racial and ethnic differences in functional status among those with hypertension, diabetes, a heart condition, and arthritis. RESULTS: Compared with Whites, African Americans report higher rates of hypertension, diabetes, and arthritis, while Hispanics report higher rates of hypertension and diabetes and a lower rate of heart conditions. Accounting for differences in education, income, and wealth had little effect on these prevalence differences. In general, among those with chronic diseases, African Americans and Hispanics reported worse function than Whites. This disadvantage was eliminated in every case by controlling for socioeconomic status. CONCLUSIONS: While socioeconomic status, including wealth, accounts for much of the difference in functional status associated with these chronic diseases. It plays a relatively small role in explaining differences in the prevalence of chronic disease, possibly reflecting different causal pathways.
Keywords: Demographics; Health Conditions and Status; Income; Methodology; Other; Retirement Planning and Satisfaction; Women and Minorities

The Structure of Health Status among Hispanic, African American, and White Older Adults - Timothy E. Stump; Daniel O. Clark; Johnson, R.J.; Frederic D Wolinsky (The Journals of Gerontology, Series B: Psychological Sciences and Social Sciences, 1997)
Activities of daily living (ADLs), instrumental ADLs, and disability markers have traditionally been the most common indicators of functional status. The study on Asset and Health Dynamics Among the Oldest Old (AHEAD) is used to replicate a five-dimensional measurement model composed of these observable indicators among the older adult self-respondents. The items available to measure upper body disability were found wanting, but the lower body disability, and the basic, household, and advanced ADL constructs were confirmed. Analyses of the measurement model separately among subgroups of women, men, Hispanics, Mexican Americans, African Americans, and Whites found no meaningful differences. Two structural models linking the lower body disability, and the basic, household, and advanced ADL constructs to perceived health and depression were also replicated among the older adult self-respondents, as well as separately among African Americans and among Whites. These models reaffirmed the dominant role of lower body disability on the everyday activities of older adults, and on their perceived health and depression.
Keywords: Demographics; Disabilities; Health Conditions and Status; Methodology; Women and Minorities

Alcohol and Occupational Injuries among Older Workers - Zwerling, Craig; Nancy L. Sprince; Robert B Wallace; Charles S. Davis; Paul S. Whitten; Steven G Heeringa (Accident Analysis and Prevention, 1996)
Keywords: Demographics; Employment and Labor Force; Health Conditions and Status; Methodology; Risk Taking

Applications to the U.S. Disability Program: A Semiparametric Approach - Kreider, Brent; Riphahn, Regina T. (Center for Economic Policy Research, 1996)
This study investigates the determinants of applications for US disability benefits between 1986 and 1993 using a semiparametric discrete factor procedure. Approximating a dynamic optimization model, the estimation carefully accounts for a variety of potential biases that weren’t addressed in previous studies. Our results indicate vast differences in the responses of men and women to variations in policy measures. Past labour earnings and fringe benefits as well as benefit eligibility and benefit amounts clearly affect application behaviour.
Keywords: Disabilities; Methodology; Pensions

A 'Big Science' Survey for the Social Sciences - Roush, Wade (Science, 1996)
Keywords: Methodology

A Comparison of Subjective Expectations Elicitation Methods in the HRS, PSID, and SEE - Dominitz, Jeff (University of Michigan, 1996)
This paper examines subjective expectations data collected by three different (United States) national surveys which utilize varying methods of subjective probability elicitation. The results of the analysis contribute to the accumulating body of evidence that researchers who wish to obtain direct reports of an individual's expectations can and should elicit subjective probabilities rather than adopt more traditional survey methods for eliciting expectations. Using the Health and Retirement Study wave 2 survey data to build on previous findings validating the wave 1 expectations data, I find that reported expectations are stable over time, despite what appears to be a substantial change in the question format. Analysis of subjective probability data collected in the Panel Study of Income Dynamics and the Survey of Economic Expectations reveals that data quality may be further enhanced by revising the questions asked of survey respondents.
Keywords: Expectations; Methodology

Comparisons of Two Sampling Frames for Surveys of the Oldest Old - Willard L Rodgers (Health Survey Research Methods, 1996)
Keywords: Methodology

Construction of the Earnings and Benefits File (EBF) for Use With the Health and Retirement Survey - Olivia S. Mitchell; Olson, Jan; Thomas L. Steinmeier (National Bureau of Economic Research, 1996)
Analysts using the Health and Retirement Survey (HRS) often require information on earnings, labor market attachment, and social security benefits in order to better understand the factors affecting retirement and well-being at older ages. To this end, several derived variables were constructed and documented in the Earnings and Benefits File (EBF) described here. The EBF provides a set of summary earnings, employment, and social security wealth measures for a subset of HRS respondents in Wave 1 of the survey, for whom administration records are available. The EBF, a restricted data file, is available from the University of Michigan's Institute for Social Research for matching only with versions of the HRS containing geographic detail no finer than the Census Division level. Interested users should contact hrsquest umich.edu by email for further information on access to the data.
Keywords: Employment and Labor Force; Income; Methodology; Social Security

Construction of the Earnings and Benefits File (EBF) for Use with the Health and Retirement Study - Olivia S. Mitchell; Olson, Jan; Thomas L. Steinmeier (University of Pennsylvania, 1996)
Analysts using the Health and Retirement Survey (HRS) often require information on earnings, labor market attachment, and social security benefits in order to better understand the factors affecting retirement and well-being at older ages. To this end, several derived variables were constructed and documented in the Earnings and Benefits File (EBF) described here. The EBF provides a set of summary earnings, employment, and social security wealth measures for a subset of HRS respondents in Wave 1 of the survey, for whom administrative records are available. The EBF, a restricted data file, is available from the University of Michigan's Institute for Social Research for matching only with versions of the HRS containing geographic detail no finer than the Census Division level. Interested users should contact hrsquest@umich.edu by email for further information on access to the data.
Keywords: Methodology; Social Security

Estimating a Cardinal Attribute from Ordered Categorical Responses Subject to Noise - Miles S Kimball; Matthew D. Shapiro (1996)
Estimating a Cardinal Attribute from Ordered Categorical Responses Subject to Noise This paper presents an estimate of the distribution of relative risk tolerance---a preference parameter quantifying individuals' behavior toward risk. The estimate is based on a new survey question about gambles over lifetime income. The preference parameter is treated as a latent variable subject to error; responses to the survey are modeled as depending on whether this latent variable falls within certain bounds. In contrast to the standard discrete choice model, the latent variable and the bounds have a cardinal interpretation. Moreover, for a subset of survey respondents, the survey questions are answered twice. This structure allows identification of the mean and variance of the preference parameter and the variance of the noise.
Keywords: Methodology; Risk Taking

The Health and Retirement Study: The New Retirement Survey - Olson, Janice A. (Social Security Bulletin, 1996)
This paper provides an introduction to the HRS, describes the support that the Social Security Administration is providing, and comments on some of the features that make it especially valuable to SSA. Early results and references to the growing body of research on the study are also provided.
Keywords: Methodology

Household Saving: Micro Theories and Micro Facts - Browning, Martin; Annamaria Lusardi (Journal of Economic Literature, 1996)
In this article the main goal is to uncover what causes households to save currency in any form, liquid or not. The authors begin with the eight postulates on saving of John Maynard Keyenes and add a ninth reason to accumulate deposits to buy houses, cars, and other durables. From this they try to link facts about household saving with the microeconomic theories regarding household saving. Their over-arching assumption is that rational forward looking people will not want expenditure or the marginal utility of their expenditure to be greater at one time than at any other time. Various microeconomic saving theories are discussed and the authors make arguments toward what is realistic in the models and where the models deviate from the real world, as well as, how the models differ from one another. Statistical information from the HRS, AHEAD, RHS studies are used as facts that are explained by, or linked to, concepts of the various models. This data thus explains who saves, but not why. The theories described at the beginning of the paper and the statistical information presented are then used in a sort of case study on the declining savings rate over the two decades of the 1970s and 1980s. The conclusion is that the Standard Model of saving is the most flexible and helpful in understanding saving and consumption. The Certainty-Equivalence Model is very strong, but leaves out the important postulate of saving in order to have enough resources in the case of an unforeseen economic downturn or shock. It is the author s belief that the only alternatives to the standard model are behavioral models, but behavioral models may be harder to test. Attempting to link standard model predictions with behavioral models may enable economists to learn more about cross-section variation among ages with regard to savings.
Keywords: Consumption and Savings; Methodology

Profiling Plans for Retirement - David J Ekerdt; Stanley DeViney; Karl Kosloski (The Journals of Gerontology: Series B, 1996)
Actual decision making for retirement is largely inaccessible to investigation, yet research can focus on plans as a window into the preretirement process. This article proposes a construct that profiles five generic types of retirement plans, including plans to retire completely, change jobs, never retire, and uncertainty about retirement. The heuristic value of the construct lies in its recognition of the heterogeneity of retirement intentions. The five plan types were operationalized among workers aged 51-61 in the 1992 Health and Retirement Study. Convergent validity was demonstrated by comparisons to analogous survey questions. Construct validity was shown by predictable relationships between intentions and elements of workers' opportunity structure. The retirement-plans construct can serve as the foundation for a taxonomy of specific retirement plans (e.g., about timing, employment), to organize research on stability and change in retirement intentions, and characterize the path dependence of eventual retirement behavior.
Keywords: Adult children; Demographics; Employment and Labor Force; End of life decisions; Health Conditions and Status; Methodology; Other; Retirement Planning and Satisfaction

Race Differences in Labor Force Attachment and Disability Status - John Bound; Michael Schoenbaum; Timothy A Waidmann (The Gerontologist, 1996)
We used the first wave of the Health and Retirement Survey to study the effect of health on the labor force activity of black and white men and women in their 50s. The evidence we present confirms the notion that health is an extremely important determinant of early labor force exit. Our estimates suggest that health differences between blacks and whites can account for most of the racial gap in labor force attachment for men. For women, when participation rates are comparable, our estimates imply that black women would be substantially more likely to work than white women were it not for the marked health differences. We also found for both men and women that poor health has a substantially larger effect on labor force behavior for blacks. The evidence suggests that these differences result from black/white differences in access to the resources necessary to retire.
Keywords: Demographics; Disabilities; Employment and Labor Force; Health Conditions and Status; Methodology; Other; Women and Minorities

Gender, Disabilities, and Employment in the Health and Retirement Study - Loprest, Pamela; Rupp, Kalman; Sandell, Steven H. (Journal of Human Resources, 1995)
This paper examines disabilities of older women and men and analyzes gender differences in the effect of disabilities on labor force participation using information on men and women aged 51-61 from the early release of the first wave of the Health and Retirement Survey. Our results demonstrate the importance of using multiple measures of disabilities (we use work limitations, functional limitations, and specific health impairments) to document gender differences and understand the connections between disabilities and work. We find that men and women have different rates of disability, and that both men and women working in occupations with greater physical requirements exhibit higher rates of disabilities than other workers. We also find that measures of functional limitations and health impairments both have significant negative effects on labor force participation. The effects of disabilities on labor force participation are larger for men and single women than for married women.
Keywords: Consumption and Savings; Demographics; Employment and Labor Force; Health Conditions and Status; Methodology; Women and Minorities

Introduction: Special Issue on the Health and Retirement Survey: Data Quality and Early Results - R.V. Burkhauser; Paul J. Gertler (Journal of Human Resources, 1995)
Keywords: Methodology

Musculoskeletal Conditions and Employment - Yelin, Edward (Arthritis Care and Research, 1995)
OBJECTIVE: To describe the prevalence, incidence, and correlates of work disability among persons with musculoskeletal conditions. METHODS: Literature review and analysis of the Health and Retirement Survey, a national, probability sample of community-based adults ages 51-61. RESULTS: Clinical samples of persons with RA report work disability rates of 51 to 60 . Community-based studies of persons with a broad range of musculoskeletal conditions find work disability rates of 38 to 71 , depending on the mix of symptoms and particular sampling strategy. Persons with musculoskeletal conditions and comorbidity are particularly prone to work loss, with three-quarters leaving work prior to the normal age of retirement. In multivariate models, after adjusting for demographic and functional characteristics, persons with musculoskeletal conditions actually are more likely to work than those without. CONCLUSIONS: Persons with musculoskeletal conditions have high rates of work disability, but given their level of impairment, are more likely to work than persons without musculoskeletal conditions.
Keywords: Demographics; Disabilities; Employment and Labor Force; Health Conditions and Status; Methodology

An Overview of the Health and Retirement Study - Juster, F. Thomas; Richard M. Suzman (Journal of Human Resources, 1995)
This paper examines the scientific, public policy, and organizational background out of which the Health and Retirement Study emerged. It describes the evolution of the major parameters of the survey and the unique planning structure designed to ensure that the substantive insights of the research community were fully reflected in the content of the database, highlights key survey innovations contained in the HRS, and provides a preliminary assessment of the quality of the data as reflected by sample size, sample composition, response rate, and survey content. The paper also describes the several types of administrative data that are expected to be added to the HRS data: earnings and benefits from Social Security files, and health insurance and pension data from the employers of survey respondents.
Keywords: Demographics; Healthcare; Methodology; Retirement Planning and Satisfaction

Overview of the Health Measures in the Health and Retirement Survey - Robert B Wallace; A. Regula Herzog (The Journal of Human Resources, 1995)
This report discusses the conceptual and logistical issues that lead to the items and instruments used to measure health and function status in Wave 1 of the Health and Retirement Study (HRS). Health status was conceptualized as multidimensional, and included selected major symptoms, diseases and conditions, global self-assessment of health, physical and cognitive functional status, the utilization of health services and selected elements of emotional health. In addition, two physiologic measures were obtained on a sample basis: grip strength and pulmonary maximum expiratory flow rate. Prevalence rates for major conditions and functional states are presented. Correlational analyses generally demonstrated a high rate of convergent, discriminant and construct validity. These findings should assist those intending to analyze HRS data in terms of the focus and utility of the measures employed.
Keywords: Consumption and Savings; Health Conditions and Status; Healthcare; Methodology

Racial and Ethnic Differences in Wealth in the Health and Retirement Study - James P Smith (Journal of Human Resources, 1995)
This paper examines wealth data in the Health and Retirement Study (HRS). In comparison with asset data in other major surveys, the quality of HRS asset data is high. Missing asset data does remain a problem, however, to which future HRS analysts must remain sensitive. Evidence is presented showing that it is no accident that asset data are missing, and solutions for imputing missing data are developed. Finally, racial and ethnic wealth disparities are large. These minority wealth disparities are due in part to differential inheritances and desired bequests as inequities perpetuate themselves across generations; the disparities are also due to lower minority incomes, poorer health, and an excessively narrow definition of wealth that excludes Social Security and employer pensions.
Keywords: Demographics; Income; Methodology; Net Worth and Assets; Women and Minorities

Technical Description of the Asset and Health Dynamics Among the Oldest Old (AHEAD) Study Sample Design - Steven G Heeringa (Institute for Social Research, University of Michigan, 1995)
Describes the sample design, sampling procedures, and sample outcomes for Wave 1 of the Study of Aging and Health Dynamics (AHEAD). The document is divided into eight sections. The introduction describes the purpose and organization of the AHEAD study. Sections 2, 3, and 4 provide an overview and a detailed description of the AHEAD dual-frame probability sample design. The fifth and sixth sections describe the AHEAD Wave 1 sample control procedures and sample outcomes. Sections 7 and 8 contain descriptions of the construction and use of the analysis weights and the codes and procedures for computation of sampling errors for the AHEAD Wave 1 data.
Keywords: Methodology

Technical Description of the Health and Retirement Study Sample Design - Steven G Heeringa; Connor, Judith (Institute for Social Research, University of Michigan, 1995)
This technical memorandum describes the sample design, sampling procedures, and sample outcomes for Wave 1 of the Health and Retirement Study (HRS). This document is divided into six sections. The introduction describes the purpose and organization of the HRS. Sections 2 and 3 provide an overview and a detailed description of the multi-stage area probability sample design. The fourth section reports the HRS Wave 1 sample outcomes -- a comparison of the expected versus observed occupancy, eligibility, and response rates. Sections 5 and 6 contain descriptions of the construction and use of the analysis weights and the codes and procedures for computation of sampling errors for the HRS data.
Keywords: Methodology

Unfolding Brackets for Reducing Item Nonresponse in Economic Surveys - Steven G Heeringa (1995)
This paper describes and analyzes a new survey methodology for reducing item non-response on financial measures. This unfolding bracket method is systematic and applicable in both face-to-face and telephone surveys. The proportion of missing observations for financial variables in national surveys is often in the 20-25 range and in some cases is as high as a third. With the unfolding bracket method the proportion of completely missing data can be cut by two-thirds. Furthermore, with appropriately chosen bracket breakpoints, the amount of the variance in the underlying measure recovered is quite high. We propose and demonstrate one method for choosing the breakpoints which employs the Downhill Simplex algorithm to maximize their exploratory value. Additionally, use of a Box-Cox transform of the actual data in conjunction with this algorithm, can result in breakpoints which are effective in explaining most of the underlying variance in both actual values and their log transforms. Since each of these metrics is appropriate for some uses this compromise is quite useful in meeting the needs of a wide variety of potential users. Finally, we investigate the effects of bracketing on the empirical validity of survey data. While we do find lower empirical validity for data from individuals exposed to brackets early in the survey instrument, this appears to be the result of self-selection rather than a direct effect of exposure to the methodology.
Keywords: Methodology

Unfolding Brackets for Reducing Item Non-Response in Economic Surveys - Steven G Heeringa; Daniel H. Hill; Howell, David A. (University of Michigan, 1995)
This paper describes and analyzes a new survey methodology for reducing item non-response on financial measures. This unfolding bracket method is systematic and applicable in both face-to-face and telephone surveys. The proportion of missing observations for financial variables in national surveys is often in the 20-25 range and in some cases is as high as a third. With the unfolding bracket method the proportion of completely missing data can be cut by two-thirds. Furthermore, with appropriately chosen bracket breakpoints, the amount of the variance in the underlying measure recovered is quite high. We propose and demonstrate one method for choosing the breakpoints which employs the Downhill Simplex algorithm to maximize their exploratory value. Additionally, use of a Box-Cox transform of the actual data in conjunction with this algorithm, can result in breakpoints which are effective in explaining most of the underlying variance in both actual values and their log transforms. Since each of these metrics is appropriate for some uses this compromise is quite useful in meeting the needs of a wide variety of potential users. Finally, we investigate the effects of bracketing on the empirical validity of survey data. While we do find lower empirical validity for data from individuals exposed to brackets early in the survey instrument, this appears to be the result of self-selection rather than a direct effect of exposure to the methodology.
Keywords: Methodology

How Does Pension Coverage Affect Household Saving. Final Report - Sabelhaus, J. (Washington, DC, Urban Institute, 1994)
This paper analyzes the extent to which substitution between pension coverage and household-level saving occurs at the micro level. Data from the beta release of the Health and Retirement Study (HRS) which covered people age 51 to 61 in 1992 is used. The results are mixed. Although there appears to be some substitution between household saving and pension coverage in the top half of the income distribution, the level differences in accumulated wealth seem to fall short of complete offset. Evidence that household wealth accumulation does not vary significantly by type of pension coverage is also found. The paper explores various explanations for why the pension offset is missing or incomplete.
Keywords: Adult children; Consumption and Savings; Employment and Labor Force; Income; Methodology; Pensions; Retirement Planning and Satisfaction

Problems of Housing the Elderly in the United States and Japan - Daniel McFadden; David A Wise (Aging in the United States and Japan, 1994)
Keywords: Housing; Methodology

Transfer Behavior: Measurement and the Redistribution of Resources within the Family - Kathleen McGarry; Robert F. Schoeni (NBER, 1994)
Keywords: Adult children; Methodology

Evaluation of Subjective Probability Distributions in the HRS - Michael D Hurd; Kathleen McGarry (National Bureau of Economic Research, 1993)
In the Health and Retirement Survey respondents were asked about the chances they would live to 75 or to 85, and the chances they would work after age 62 or 65. We analyze the responses to determine if they behave like probabilities, if their averages are close to average probabilities in the population, and if they have correlations with other variables that are similar to correlations with actual outcomes. We find that generally they do behave like probabilities and they do aggregate. Most remarkable, however, is that they covary with other variables in the same way actual outcomes vary with the variables. For example, smokers give lower probabilities of living to 75 than nonsmokers. We conclude that these measures of subjective probabilities have great potential use in models of intertemporal decision making under uncertainty.
Keywords: Consumption and Savings; Health Conditions and Status; Methodology

Evaluation of the HRS and RHS from a Decision-Theoretic Perspective - Rust, John (University of Michigan, 1993)
This paper has 3 objectives: 1) it presents a structural econometric DP model of retirement behavior that requires extensive datasets such as RHS and HRS, 2) it evaluates the pros and cons of the overall survey design of the RHS and HRS from the standpoint of a person interested in estimating a DP model, and 3) it provides a comparative data analysis of key variables in the RHS and HRS. The results of the data analysis indicate that relative to the RHS male primary respondents work less, have substantially higher total family income (but not much higher labor income) and are significantly more likely to apply for Social Security early retirement benefits at age 62. Part of the reason why total family income has increased much more than labor income of male primary respondents is due to increased labor force participation on the part of the spouse. Levels of education and home ownership are significantly higher in the HRS, and the housing continues to remain the predominant component of family net worth.
Keywords: Methodology

Intergenerational Transfers: Economic, Demographic, and Social Perspectives - Beth J Soldo; Martha S. Hill (Annual Review of Gerontology and Geriatrics: Focus on Kinship, Aging, and Social Change, 1993)
Intergenerational transfers can be studied from an economic, social gerontological, or social-psychological perspective. This chapter describes a variety of the social science theories and reviews related empirical research relevant to the major types of intergenerational transfers: a) flows of assistance from parents to children and grandchildren, b) flows of assistance from middle-aged children to elderly parents, c) coresidence of parents and children. While there seems to be remarkable consensus about the factors affecting the probability of exchange, because the various disciplines have focused on different aspects of exchange behavior at different points in the life cycle, the evidence in support of competing theories is not consistent. The chapter then focuses on the upcoming availability of the HRS and AHEAD studies as potentially providing the data necessary to capturing all of the relevant dimensions of transfer behaviors that have been missing for all disciplines.
Keywords: Adult children; Healthcare; Methodology

Respondent Rules and the Quality of Net Worth Data in the HRS - Daniel H. Hill (University of Michigan, 1993)
The HRS uses an informed selection procedure in choosing with spouse to ask about the household's assets and debts. This is more expensive than presumptive selection which has been commonly employed in past surveys. This paper evaluates the quality of the resulting net worth data in terms of the exactness of the reports. A trivariate ordered probit model is developed and estimated. This model controls for the self-selectivity of both the gender and proxy interview status of the net-worth respondent. The results suggest that the informed selection procedure does indeed result in lower item non-response and less reliance on approximation strategies than would a presumptive husband R1 respondent rule.
Keywords: Methodology; Net Worth and Assets